3. Summer School "Toleranzmanagement" und 28. Symposium "Design for X" - Wartzack, Sandro; Schleich, Benjamin (WiGeP News, 2018)
Erfolgreiche Veranstaltungen im Doppelpack: bereits zum dritten Mal trafen sich an der FAU Erlangen- Nürnberg zahlreiche Vertreter aus Lehre, Forschung und Industrie zur Summer School "Toleranzmanagement" sowie über 50 Teilnehmer aus Industrie und Forschung zum 28. Symposium "Design for X"<br

A business model canvas for idecide - how to design a new decision making app - Luft, Thomas; Lamé, Guillaume; Ponn, Josef; Le Cardinal, Julie; Wartzack, Sandro (DS 84: Proceedings of the DESIGN 2016 14th International Design Conference, 2016)
As products become increasingly complex, product developers have to make decisions effectively and efficiently. Therefore, the long term goal of the SIG DM is to develop an iDecide App. This app should support developers in complex decision making situations during the development process. The aim of this paper is to describe possible business models for an iDecide App with the Business Model Canvas. Some business models and one industrial case study for an iDecide App are described. This should initiate an in-depth discussion on a detailed business model for an iDecide App.
Keywords: decision making; computer-aided decision making process; business model canvas; app; innovation process

A Case Study on Established and New Approaches for Optimized Laminate Design - Völkl, Harald; Franz, Michael; Wartzack, Sandro (ECCM18 - 18th European Conference on Composite Materials, 2018)
Optimized laminate design, although crucial for high-quality lightweight parts, still remains a challenge for engineers. The high number of mutually dependent parameters requires expert skills – and really good designs can only be obtained when load paths are considered appropriately, which is frequently missed out on when simply replacing isotropic material by quasi-isotropic laminate. Therefore, both commercial software solutions and approaches from research have been put forward to support engineers at finding adequate layups. In this paper, using a bike rocker arm demonstrator, a lightweight benchmark under displacement constraint is conducted with the goal of reducing mass using three approaches: OptiStruct (Altair), mfkCODE (from research) and a combination of a specific topology optimization algorithm for transversely isotropic materials and mfkCODE. The resulting conceptual designs are discussed both quantitatively and qualitatively.
Keywords: Laminate Design; Carbon Fiber Reinforced Plastics; Topology Optimization; Lightweight Design; Benchmark

Accelerating sampling-based tolerance–cost optimization by adaptive surrogate models - Roth, Martin; Freitag, Stephan; Franz, Michael; Götz, Stefan; Wartzack, Sandro (Engineering Optimization, 2024)
High numbers of function evaluations are inevitable to guarantee the reliability and optimality of sampling-based tolerance–cost optimization. Despite using different countermeasures to increase its efficiency, unreasonably long computation times and unreliable results currently hinder its profitable application. Motivated to overcome this shortcoming, this article presents a novel strategy harmonizing metaheuristic optimization and surrogate modelling. It is based on the idea of adaptive surrogate model-based optimization substituting the tolerance analysis subroutine with a surrogate model, which is iteratively re-modelled with intermediate optimization results to improve its accuracy continuously in potential optima regions. On the one hand, a directed intensification of promising solutions and, on the other hand, an accelerated exploration of the search space is achieved. Optimization studies prove its positive effect on overall efficiency, where a case study with multiple nonlinear assembly response functions and geometrical tolerances serves as a use cas
Keywords: Tolerance–cost optimization; Tolerance allocation; Sampling-based tolerance analysis; Surrogate modelling; Metaheuristic optimization

A classification system for secondary design features for the use within sheet-bulk metal forming - Breitsprecher, Thilo; Wartzack, Sandro (Proceedings of the 19th International Conference on Engineering Design, 2013)
Estimating the potential of new emerging manufacturing technologies for the area of engineering design is crucial for the establishment of these processes in the industry sector. An example for such a new technology is sheet-bulk metal forming (SBMF): New parts can be designed due to the higher design freedom for design engineers and the possibility to integrate more functions by using more functional elements per part. Furthermore it is of high interest if this emerging technology can be used to substitute established manufacturing processes and produce parts with a higher functional density with less process steps and more robust processes. In this paper a new classification system is presented that enables the design engineer to classify parts with primary and especially secondary design features. On the one hand the classification system can be used to identify parts for which the established manufacturing process may be substituted by SBMF. On the other hand potential for new innovative solutions can be revealed.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.aclass
Keywords: Design for x; Feature classification; Information management; New product development; Sheet-bulk metal forming

A Comparative Study on Tolerance Analysis Approaches - Schleich, Benjamin; Anwer, Nabil; Zhu, Z.; Qiao, L.; Mathieu, Luc; Wartzack, Sandro (Proceedings of the International Symposium on Robust Design - ISoRD14, 2014)
Robust product designs are characterized by their insensitivity to disturbances and noise, such as geometric part deviations, which are inevitably observed on every manufactured workpiece. These observed deviations are covered by the axioms of manufacturing imprecision and measurement uncertainty, which convey the concepts of variability and uncertainty as fundamental aspects of robust design. In order to ensure the product function though the presence of these geometric part deviations without building physical artefacts, tolerance simulations are employed in the context of computer-aided tolerancing. Motivated by the shortcomings of existing tools, the concept of Skin Model Shapes has been developed as a novel paradigm for the computer-aided tolerance analysis. This paper presents a comparative study on the standard procedure for the tolerance analysis employing proprietary CAT tools and the tolerance simulation based on Skin Model Shapes. For this purpose, two exemplary study cases are highlighted. Based on the comparisons, general remarks on the use of CAT tools in the context of tolerance analysis and robust design are derived.
Keywords: Computer-Aided Tolerancing; Skin Model; Tolerance Simulation

A Comprehensive Framework for Skin Model Simulation - Schleich, Benjamin; Walter, Michael; Wartzack, Sandro; Anwer, Nabil; Mathieu, Luc (ASME 2012 11th Biennial Conference on Engineering Systems Design and Analysis, Volume 3: Advanced Composite Materials and Processing; Robotics; Information Management and PLM; Design Engineering, 2012)
The need for geometrical variations management is an important issue in design, manufacturing and all other phases of product development. Two main axioms cover geometrical variations, namely the axiom of manufacturing imprecision and the axiom of measurement uncertainty. Therefore, this paper reviews common models for the description of non-ideal geometry (shape with geometric deviations) and shows how the random field theory can be applied to create more realistic skin models (a model which comprises these geometric deviations). Furthermore, methods to estimate and to express the underlying random field from a sample population are shown. These can be used to create and simulate random shapes considering systematic and random deviations observed through measurement or gathered from manufacturing process simulations. The proposed approach incorporates given information from manufacturing process simulations or prototypes. Based on these information, skin model samples are created which can represent the "realistic" part in assembly simulations or other geometrical analyses. This can help to identify the optimal tolerance sets within every stage of the product development process. The efficiency of the introduced approaches is shown in a case study.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.acompr
Keywords: Geometric deviations; GPS; Random fields; Skin model simulation

A computational design approach for composite structures at the early embodiment design stage - Klein, Daniel; Malezki, Waldemar; Wartzack, Sandro (NAFEMS World Congress 2015, 21. - 24. Juni, San Diego, USA, NAFEMS World Congress, 2015)
The design of composite structures is a big challenge because a lot of different and mutually dependent parameters like the fiber orientation, the stacking sequence or the layer thicknesses have to be defined. Additionally, even small deviations of these parameters from the ideal can significantly reduce the mechanical properties of the composite part which makes the design of composite parts particularly challenging. Therefore, it is essential to use novel simulation tools and computational methods as soon as possible in the design process. However, many existing software tools are based on a sequence of complex optimization algorithms or are highly restricted, and therefore, not suitable for the early embodiment design of composite parts. Within the intended paper a novel simulation based design approach will be presented which offers a high freedom in design and is based on simple engineering considerations. The design approach can be divided into four different steps: Step 1: Modified Multi-Layer CAIO Method Step 2: Cluster-algorithm Step 3: Defining the stacking sequence Step 4: Compute layer thicknesses In the first step of the design approach the so called Modified Multi-Layer CAIO method is used to compute the ideal fiber orientations and stresses for each load case in an iterative process. As input for this method a FE model for each load case with an arbitrary number of layers and fiber orientation is created and each model is solved separately. For each model the mean stress directions are computed and the elemental fiber orientations in the FE models are oriented in direction of the maximum mean stresses. These modified models are solved again and the process is repeated as long as there is a significant change in the mean stresses. Based on the results of the Modified Multi-Layer CAIO, the number of layers for each finite element as well as the needed fiber orientations can be computed. However, since every element can have a different fiber orientation and number of layers, the computed laminate structure is not manufacturable. For this reason, a cluster algorithm is needed (step 2) to find areas with equal fiber orientation and, therefore, areas where patches could be placed. The basic principle of the cluster algorithm is to choose a first layer of an arbitrary starting element and compare the fiber orientations of this layer to all layers in the neighboring elements. If the comparison of the fiber orientations is positive the neighboring layer is added to the first cluster. For this grown cluster again all the neighboring elements are checked and the comparison process repeats until no new layer can be added to the existing cluster. In this case a new starting element is chosen and the procedure starts again to form a new cluster.  In the end, the clusters are highlighted and a possible patch structure is shown which helps product developers to define a first laminate. However, the ideal stacking sequence as well as the thickness of each layer is still unknown at this stage. Therefore, steps three and four have to follow. In step three the stacking sequence is defined with the help of the stresses which were computed in step 1. The fiber orientations of the patches are compared to the mean stresses in each of the arbitrary layers and a value for the overlapping is computed in each position. The stacking sequence with the highest overall overlapping value is chosen. In the last step (step 4), a FE model is created with the computed stacking sequence and the thicknesses are defined with a simple genetic algorithm.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.acompu
Keywords: Composites; Leichtbau; Simulation

A concept and prototype for a new app to support collaborative and multi-criteria decision making in product development - Luft, Thomas; Rupprecht, Simon; Wartzack, Sandro (DS 87-1 Proceedings of the 21st International Conference on Engineering Design (ICED17), Vol. 1: Resource-Sensitive Design, Design Research Applications and Case Studies, 2017)
As products become increasingly complex, product developers have to make decisions effectively and efficiently. Therefore, the long term goal of the authors is the development of a new app to support collaborative and multi-criteria decision making in product development. For this, the basic requirements of such a new app are presented. Based on this, the methodological concept and procedure are briefly explained. Afterwards, a first prototype of the app with the core functionalities and the user interface is presented. Finally, this prototype is applied and evaluated by an example. In the future, the authors aim to improve the concept and to integrate further functionalities by implementing the presented concept as a real smartphone app.
Keywords: Decision making; Evaluation; Collaborative design; Decision-making app; Design management

A concept for a novel hybrid augmented reality computer workstation for virtual product development - Harlan, Jakob; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
Extended reality user interfaces for engineering design often suffer from gaps in the user’s workflow. Usually, the user must at least put on hardware, but often also data preparation is needed. This research aims to close these gaps by proposing a setup fusing desktop and immersive user experience into a hybrid augmented reality computer workstation. Here the user can decide for each operation what modality is best suited, using the strengths of both interfaces while avoiding their drawbacks. In this paper, a concept for such a hybrid computer workstation is developed using the morphological matrix method. Different solutions for the main features, holographic stereo display, spatial interaction, and the software architecture, are discussed and a reasoned combination is proposed as a feasible concept.<br
Keywords: CAD; Augmented Reality; Product Design; Morphological Matrix; Computer workstation

A concept for FE plausibility checks in structural mechanics - Sprügel, Tobias; Hallmann, Martin; Wartzack, Sandro (Summary of Proceedings, 2015)
The finite element method is, alongside with CAD, one of the most efficient tools for optimizing the quality of engineering tasks (Klein 2010). Furthermore, the currently available FE software is getting more and more user friendly. However, especially less experienced users - such as designers - perform more and more FE simulations but do not have the knowledge of experienced computation engineers. Often these users do not have a complete overview of the performance of currently used simulation and calculation tools for securing product and also manufacturing process characteristics. However it is highly essential to optimize the quality and minimize the costs of a technical design as early as possible during the product development process. Therefore, these users need to be assisted when performing simulation tasks. This can be achieved by an integrated plausibility check in the postprocessing of the FE software. When an existing FE result data set is checked for plausibility further steps towards a better assistance for part time users can be taken. Such as an error assistant for implausible results or a context-sensitive result visualization to help the user to understand the simulated results. The presented approach in this paper is part of the Bavarian Research Cooperation FORPRO² for efficient product and process development by knowledge based simulation. The aim of the Research Cooperation is to increase efficiency of virtual product and process development through the creation of an expert knowledge based simulation framework for property optimization and quality improvement of new products. The expected result is to provide the necessary situational simulation knowledge as a function of decisive factors such as the phase in the development process, the manufacturing processes employed, and the company's individual circumstances. Within the Research Cooperation an FEA-assistance system with an integrated plausibility check is developed. In this paper an approach for plausibility checks applicable for different standard components with mathematical meta-models is presented. At first the terms plausibility, verification and validation are distinguished. Then different meta-models and their requirements and possibilities for evaluating the quality are shown. The paper closes with an exemplary application – a piston pin of a combustion engine, for which a plausibility check with different mathematical meta-models is demonstrated.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.aconce
Keywords: plausibility checks; FEM; structural mechanics; meta-models; RSM; ANN

A Concept for Physiological User Description in the Context of Dual User Integration - Schröppel, Tina; Diepold, Theresia; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
In order to ensure the user's acceptance towards a product, the user has to be captured with all his facets and requirements. In this context, many user-centred design methods only focus on single aspects such as subjective expectation or ergonomic product design. Correlations and connections or a common consideration of several user parameters are often neglected, even if this can provide useful information for improving the design of products. Dual user integration tries to close this gap to a certain extent and considers the user's subjective expectation in combination with their physiological capacities. An integral part of this approach is a target-oriented evaluation of the user. Currently available methods of physiological and subjective evaluation of the user are only partially applicable for dual user integration. Especially physiological measurement techniques are time-consuming and expensive. For this reason, this contribution presents a new concept for capturing and describing the physiological capacity of the user via semantic differentials. Thereby, motor functions, cognition and perception are considere
Keywords: User centred design; Design methods; Integrated product development; Dual user integration; Physiological user description

A concept for process-oriented interdisciplinary tolerance management considering production-specific deviations - Heling, Björn; Oberleiter, Thomas; Rohrmoser, Andreas; Kiener, Christoph; Schleich, Benjamin; Hagenah, Hinnerk; Merklein, Marion; Willner, Kai; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)

A Concept for the Consideration of Dimensional and Geometrical Deviations in the Evaluation of the Internal Clearance of Roller Bearings - Aschenbrenner, Alexander; Wartzack, Sandro (Procedia CIRP, 2016)
Internal clearance is a functional key characteristic of bearings. The bearing clearance can be evaluated using rigid body movements of the inner ring. Due to the deviations of dimension and roundness the contact areas between the bearing components cannot be predicted. Hence contact detection is necessary. For this purpose the herein presented concept is based on a raytrace algorithm. The concept can be used for the simulation of the bearing clearance for deviated bearing components. This enables the evaluation of the influence of dimensional and form deviations on the bearing clearanc
Keywords: tolerance simulation; bearing clearance; dimensional deviation; deviation of roundness; contact detection

A Concept Towards Automated Reconstruction of Topology Optimized Structures Using Medial Axis Skeletons - Mayer, Johannes; Wartzack, Sandro (Proceedings of the Munich Symposium on Lightweight Design 2020, 2021)
Through continuous topology optimization the design within modern product development of structural loaded components can be enhanced by using maximized lightweight potential. At the same time the product development pro-cess is accelerated due to a reduced number of design cycles. Because topology optimization yields an optimized material distribution, the designer is not re-quired anymore to iteratively work out the principal geometric shape. How-ever, optimized material distribution itself neither follows design rules, nor does it pro-vide parametric relations within parts. Instead, a redesign has to be done in order to fulfill manufacturing requirements and to obtain a parametric CAD-model. This usually takes a lot of effort in time and expert knowledge. For the reason of a consistent development approach under assistance of com-puter aided methods, a concept is presented, that is demanded to solve the task of redesigning topology optimization results in parametric CAD-models in a semi-automated manner. To achieve this, medial axis skeletons are used for analyzing the geometric data of optimization results. In a second step, the skeletons are used for rebuilding parametric CAD-models. They are taken as references for common CAD-functionality whereby a parametric and history based modeling structure are generated.<br
Keywords: Topology Optimization; Medial Axis Skeleton; CAD

A CONCEPTUAL MODEL COMBINATION FOR THE UNIFICATION OF DESIGN AND TOLERANCING IN ROBUST DESIGN - Grauberger, Patric; Götz, Stefan; Schleich, Benjamin; Gwosch, Thomas; Matthiesen, Sven; Wartzack, Sandro (Proceedings of the Design Society: DESIGN Conference, 2020)
In design engineering, the early consideration of tolerance chains contributes to robust design. For this, a link of design and tolerancing domains is essential. This paper presents a combination of the graph-based tolerancing approach and the Contact and Channel approach to link these domains. The combined approach is applied at a coinage machine. Here it provides detailed insights into state-dependent relations of embodiment and functions, which can improve robustness evaluation of the concept. This approach shows a possibility to bridge the gap between design and tolerancing domains.<br
Keywords: Engineering design; Modelling; Tolerance representation and management; Robust design

A contact model to simulate human–artifact interaction based on force optimization: implementation and application to the analysis of a training machine - Krüger, Daniel; Wartzack, Sandro (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Musculoskeletal multibody models are increasingly used to analyze and optimize physical interactions between humans and technical artifacts. Since interaction is conveyed by contact between the human body and the artifact, a computationally robust modeling approach for frictional contact forces is a crucial aspect. In this contribution, we propose a parametric contact model and formulate an associated force optimization problem to simultaneously estimate unknown muscle and contact forces in an inverse dynamic manner from a prescribed motion trajectory. Unlike existing work, we consider both the static and the kinetic regime of Coulomb’s friction law. The approach is applied to the analysis of a leg extension training machine with the objective to reduce the stress on the tibiofemoral joint. The uncertainty of the simulation results due to a tunable parameter of the contact model is of particular interest.
Keywords: musculoskeletal simulation; contact modeling; optimization; device design

A Co-Simulation Model Integrating a Musculoskeletal Human Model with Exoskeleton and Power Tool Model - Molz, Carla; Scherb, David; Löffelmann, Christopher; Sänger, Johannes; Yao, Zhejun; Lindenmann, Andreas; Matthiesen, Sven; Weidner, Robert; Wartzack, Sandro; Miehling, Jörg (Applied Sciences, 2024)
Working at and above head height with a power tool represents a common activity in craft and assembly applications. To assist and protect the user from overload and injuries in these situations, the development and use of application-specific support systems, such as exoskeletons and power tools, have greatly increased in recent years. Thus, the integration of aspects of the user-centered product development of support systems in the early phases of product development process has high potentials. A common approach to integrate the user early in the product development process is the use of musculoskeletal human models, which allow the evaluation of effects on the human body. This could also be applicable in the mentioned use case to enable the evaluation of the interactions for the user. Therefore, a co-simulation model for virtual modelling and simulating human–machine interactions is presented. The co-simulation model is made up of a musculoskeletal human model and the models of the technical systems (exoskeleton and power tool). By applying the co-simulation model, the impact of technical systems on the human body can be taken into account to derive design alternatives for the technical system due to the requirements of the user. The paper describes the design of the co-simulation model and particularly, the interaction of the submodels. The evaluation of the co-simulation model is carried out with the help of a subject study for the selected use case working at and above head height. The results show plausible results for the muscle loads considering the support by an exoskeleton. Furthermore, the comparison of simulated results to measured muscle activations via surface electromyography shows a good agreement. Thus, the co-simulation model passes the test for functionality and seems to be applicable for the derivation of design alternatives of technical systems regarding the user needs. In future, the co-simulation model will be further validated with a higher number of subjects and to implement design alterations in the technical systems.<br
Keywords: human–machine interaction; biomechanics; support systems; exoskeleton; product development; user-centered design; musculoskeletal human model

Acquisition of design-relevant knowledge within the development of sheet-bulk metal forming - Röhner, Sebastian; Breitsprecher, Thilo; Wartzack, Sandro (Proceedings of the 18th International Conference on Engineering Design 2011 (ICED11), 2011)
The increasing requirements on technical products represent a growing challenge for the manufacturing engineering. This challenge will be met by the development of a new manufacturing technology called sheet-bulk metal forming. For the early consideration of the full potential of sheetbulk metal forming in a design process, a design engineer has to know the process limitations as soon as possible. Hence, the objective has to be to acquire design-relevant knowledge already in the early phases of process development and to maintain this knowledge simultaneously to the further development of the process. These are the declared aims of the self-learning engineering assistance system that will carry out the acquisition and maintenance of knowledge owing to its self-learning aspect. In this article, within an evaluation of knowledge acquisition methodologies, data mining was identified as a possibility for the realization of the self-learning aptitude. The potential of data mining was shown by its application on simulation data to acquire design-relevant knowledge. Copyright © 2002-2012 The Design Society. All rights reserved.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.acquis
Keywords: Data Mining; Knowledge Acquisition; Sheet-Bulk Metal Forming

Acquisition of heuristic knowledge for the prediction of the frictional behavior of surface structures created by self-excited tool vibrations - Breitsprecher, Thilo; Hense, R.; Hauer, Franz; Wartzack, Sandro; Biermann, Dirk; Willner, Kai (Key Engineering Materials, 2012)
The selective control of the frictional behavior (tailored friction) in metal forming processes is of high importance with regard to technical and economic aspects. This applies especially for the sheet-bulk-metal forming process. Milling with intentionally invoked regenerative tool vibrations can be applied in order to generate structured surfaces with tailored friction properties on the forming tool. These structures affect the formation of lubrication pockets during the forming process which determine the local frictional properties exceedingly. The full potential of this emerging technology can, however, only be revealed if the heuristic and design-relevant knowledge is acquired and provided to the tool-designer already in the early phases of process development. One thing the tool-designer has to specify is the local frictional behavior on the tool surface. But, however, he does not know which milling parameters lead to the necessary surface structures because in most cases he has no expert knowledge in milling, tribology and forming tools. In this paper data mining is used to determine the frictional behavior based on these parameters. The potential of this method in the described context is revealed by the application on data derived from simulation results, both from milling simulations and contact simulations. The latter are performed by using a Halfspace model for rough surface contact. Both approaches for these simulations, the data mining process and the results are explained to the reader.© (2012) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.acquis
Keywords: Data mining; Halfspace model; Milling with vibrations; Self-learning system

Adapting FE-Meshes to real, 3D surface detected geometry data to improve FE-simulation results - Katona, Sebastian; Sprügel, Tobias; Koch, Michael; Wartzack, Sandro (Summary of Proceedings, 2015)
Today’s product development process is picking up the pace. To avoid performing complex and expensive testing including all iterations of the product development with a real prototype, various FE-simulations (finite element) for the functional validation of the desired characteristics are made. The discretization of a developed component and the use of the simulation conditions, like taking different non-linearities (i.e. material behavior, contact situations, large deflections etc.) into account, is a tremendous effort and is necessary to get precise and significant results. In general, every constructed component shows differences to its ideal geometry of the designed CAD-model (Computer Aided Design), i.e. due to deformations in the production process. Depending on the manufacturing process, random deviations and the component size, these differences can vary. In cutting processes the value is relatively small, but using forming (i.e. deep-drawing or bending) and casting techniques (i.e. die casting or injection molding) process-related effects like spring back and shrinkage or warpage occur and can trigger bigger deformations. Despite knowing the effects of deformations, due to the production process mentioned above, the product developer always uses the non-deformed design model of a CAD-system for the FEsimulation of a component. It seems rather doubtful that further refinement of simulation methods makes sense, if the real manufactured geometry of the component is not considered for in the simulation. For an efficient exploit of the potential of simulation methods, an approach has been developed which offers a geometry model for simulation based on the existing CAD-model but with integrated production deviations as soon as a first prototype is at hand. Thus, a functional validation of the real geometry can easily be performed. The approach in this article is to detect the occurring deformations of a near-series produced prototype with a high-resolution optical measuring instrument and to use that data for simulation purposes. The whole reverse engineering (RE) process including data preparation, complex surface reconstruction and furthermore a complete new simulation preprocessing is omitted due to lack of capacity. Therefore, the detected data (either point cloud or polygonal model) is used directly for the creation of an adapted FE mesh. The presented method describes an opportunity to automatically adapt existing FE-meshes, generated with the non-deformed CAD-model, to the deviated geometry caused by production. Thereby 3d surface scans and relevant algorithms are used. Therefore, the surface nodes are extracted from an ANSYS input file. A measurement of the deviation to the scanned model at each node position (point cloud or polygonal model) takes place by using a comparison point within the software PolyWorks. Afterwards a preload-step is defined, in which the deviation of every surface node is applied as a displacement. The mesh emerging from this preload-step with its new nodes coordinates is the basis for further simulations with real geometry. Herewith, a completely new input file with the new mesh and the identical content of the initial input file based on the ideal CAD-model (considering material definition, forces, boundary conditions etc.) is created. As a result, an FE-model with real geometry is available and can be used directly for a simulation without spending a lot of time on additional preprocessing. The advantage can be seen in the omission of a complex creation of a new model for simulating the real manufactured geometry. Comparative analysis between ideal and real geometry is simple, when using this approach in the product development process.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.adapti
Keywords: FEA (finite element analysis); preprocessing; simulation; 3D surface detection; RE (reverse engineering)

A data model for linking testbed and field test data - Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (32nd Symposium Design for X (DFX2021), 2021)
With the help of data-driven methods such as machine learning, the development of the current product generation can be supported and improved through the early use of data from previous products and product generations. For example, machine learning can be used to predict later product behaviour in field tests from testbed data. This can significantly shorten the development time and save expensive field tests. To implement this data provision for the development processes, uniform data models enable the use of data-driven methods and are of central importance. This paper presents a data model using the example of a testbed for electric vehicle transmissions. Here, potentials for a later data-driven prediction of the product behaviour in the field test for the optimisation of the existing development are shown
Keywords: Graph databases; machine learning; digital engineering

A discrete geometry approach for tolerance analysis of mechanism - Schleich, Benjamin; Wartzack, Sandro (Mechanism and Machine Theory, 2014)
Tolerance analysis aims at predicting the effects of inevitable geometric deviations on the quality and function of mechanical products and is therefore an import tool in the design and dimensioning of mechanism. Since geometric deviations have various sources, different simulation tools and computer-aided engineering applications must be applied to determine them. Most of these tools are based on a surface or volume discretization, which leads to a workpiece representation in discrete geometry. In this contribution, an approach for the tolerance analysis of mechanism employing these discrete geometry representations is proposed. It is based on the processing of non-ideal workpiece representatives and helps to incorporate results from different validation applications. The approach is applied to the tolerance analysis of spur gears by employing a Tooth Contact Analysis algorithm.
Keywords: Tolerance analysis; Tooth Contact Analysis; Discrete geometry

A function-oriented surface reconstruction framework for reverse engineering - Qie, Yifan; Bickel, Sebastian; Wartzack, Sandro; Schleich, Benjamin; Anwer, Nabil (CIRP Annals - Manufacturing Technology, 2021)
Reverse engineering can be considered as the methodological process of analyzing and reconstructing a digital model of a physical asset. It has gained considerable interest with the advent of sophisticated sensors and data processing technologies hence becoming an important enabler for the product digital twin. However, while existing approaches to reverse engineering focus on the mere geometric reconstruction, this paper presents a novel paradigm called function-oriented surface reconstruction, that is capable of reconstructing the underlying part and surface function and thus outperforms existing methods. The applicability of the presented method is demonstrated through a case study of a gearbox.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Data-driven design; Machine learning; Reverse engineering

A Generic Approach to Sensitivity Analysis in Geometric Variations Management - Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED 15) Vol 4: Design for X, Design to X, 2015)
Engineering design teams are increasingly required to consider sustainability in the design of products and related manufacturing and assembly processes. In this regard, the economic and ecological sustainability of products as well as their quality and cost is influenced by geometric part deviations, which are inevitably observed on every manufactured artefact. Thus, the management of geometric deviations along the product lifecycle is a key issue for companies to living up to modern innovation requirements. The aim of this paper is to provide an overview of tools for the tolerance analysis in different stages of geometric variations management and to propose a versatile approach for the sensitivity analysis applicable in these different stages. This approach is to support decision making in the geometric variations management during integrated product and process design.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.agener
Keywords: Robust Design; Tolerance Representation And Management; Decision Making

A haptic based Hybrid Mock-Up for mechanical products supporting human-centered design - Krüger, Daniel; Stockinger, Andreas; Wartzack, Sandro (Proceedings of the 18th International Conference on Engineering Design (ICED 11) Vol. 10, 2011)
The overall goal of the design process is to create products of good usability. A human-centered design process is characterized by a continuous involvement of the prospective user of the product. This also comprises user-based concept assessments and design optimizations. For this purpose in many cases it is necessary that the user is given the possibility to perceive the product emotionally. Thus the flexibility of digital mock-ups well established in digital engineering can't be used. Instead, physical prototypes are often indispensible. In this paper a Hybrid Mock-Up approach is presented that allows a physical interaction with virtual prototypes. The behavior of the product is simulated digitally whereas elements of the human-machine interface are emulated using a generic haptic device. The benefit of the approach is that for the user a realistic product perception is achieved without having to dispense with the advantages digital engineering offers: saving of costs and time due to a reduction of physical prototypes. The approach is illustrated in a case study of a crank driven car jack.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.ahapti
Keywords: Computer haptics; Design space exploration; Human-centered design; Hybrid mock-up

A Hierarchical Approach for the Verification and Validation of Tolerance Analysis Models - Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the ASME 2022 International Mechanical Engineering Congress and Exposition (IMECE2022), 2023)
Established tolerance analysis methods are capable of predicting the effects of geometrical part variations on the quality of products and hence virtually assuring their functionality. However, assumptions and simplifications are often made, which can lead to decisive uncertainties. To omit a significant effect of these uncertainties on the overall model and on the obtained results, both a virtual assessment of the model as well as an experimental validation are necessary. The current state of the art still lacks suitable methods and metrics to reliably evaluate the results of tolerance analyses. In addition, an approach is needed to investigate and evaluate the effects of uncertainties within the analysis model on the overall model. The aim of this contribution is therefore to derive statements about the suitability and significance of methods and metrics of verification and validation for evaluating simulation models and their feasibility in the context of tolerance analysis. First, general methods and metrics for the evaluation of simulation results are presented. Subsequently, the most promising ones are customized in an unifying approach. The statistical tolerance analysis of a 3-D-printed non-assembly mechanism in motion serves as an explanatory example for highlighting the procedure and the current challenges and constraints. Finally, the findings are critically discussed and as a result, statements about the further need for action are presented.<br
Keywords: Verification & Validation; Tolerance Analysis

A holistic decision making process for awarding development projects to external service providers - Bausewein, Natascha; Luft, Thomas; Thater, Gerald; Wartzack, Sandro (11. Gemeinsames Kolloquium Konstruktionstechnik 2013: Standortvorteil Methodik, 2013)
Particular challenges faced by the automotive industry are the increasing product variety and complexity caused by customer requirements in terms of individualization. The resulting large number of development projects can often not be realized in particular by small and medium enterprises due to staff shortages. In case of resource bottlenecks companies have the option to award projects to external service providers. The goal of the present paper is to define a holistic decision making process for awarding development projects because of staff shortages. For this purpose an appropriate and detailed process will be developed that standardizes the outsourcing procedures and provides methodological support for practical use. As a result, critical factors will be considered and consequently the success rate of awarding projects will be increased. Finally, the suitability of the proposed approach is validated in an industrial case study.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.aholis
Keywords: development service; awarding development projects; outsourcing; decision making; evaluation methods; methodologies for small and medium enterprises

AI4PD—Towards a Standardized Interconnection of Artificial Intelligence Methods with Product Development Processes - Gerschütz, Benjamin; Götz, Stefan; Wartzack, Sandro (Applied Sciences, 2023)
The transformation of virtual product development to Digital Engineering (DE) requires the successful integration of Digital Engineering or data-driven methods into existing product development processes. Those methods allow for the analysis and usage of existing data. However, missing knowledge about these methods, as well as their performance or limitations, is a major burden for their application, especially in small and medium-sized enterprises. In order to close this gap, this paper proposes the AI4PD ontology, linking product development processes (PD) and Digital Engineering methods (AI). This knowledge representation gives companies an overview of the available methods to support them in selecting a suitable solution for their problems. The representation of AI4PD is performed in Protégé using the W3C standard OWL syntax. The opportunities of AI4PD are shown by a use case of identifying a DE-Method for predicting manufacturing possibilities based on test data and CAD files. Furthermore, after possible problems in existing product development processes are identified, AI4PD covers the necessary knowledge for a successful method of identification and integration to transform virtual product development to Digital Engineerin
Keywords: ontology; digital engineering; artificial intelligence; product development; formalisation; knowledge reuse; knowledge representation

A Literature Review on the Development and Creation of Digital Twins, Cyber-Physical Systems, and Product-Service Systems - Fett, Michel; Wilking, Fabian; Götz, Stefan; Kirchner, Eckhard; Wartzack, Sandro (Sensors, 2023)
Digital Twins offer vast potential, yet many companies, particularly small and medium-sized enterprises, hesitate to implement them. This hesitation stems partly from the challenges posed by the interdisciplinary nature of creating Digital Twins. To address these challenges, this paper explores systematic approaches for the development and creation of Digital Twins, drawing on relevant methods and approaches presented in the literature. Conducting a systematic literature review, we delve into the development of Digital Twins while also considering analogous concepts, such as Cyber-Physical Systems and Product-Service Systems. The compiled literature is categorised into three main sections: holistic approaches, architecture, and models. Each category encompasses various subcategories, all of which are detailed in this paper. Through this comprehensive review, we discuss the findings and identify research gaps, shedding light on the current state of knowledge in the field of Digital Twin development. This paper aims to provide valuable insights for practitioners and researchers alike, guiding them in navigating the complexities associated with the implementation of Digital Twins.<br
Keywords: Digital Twin; Cyber-Physical System; development; review; methods

A Machine Learning-Based Approach for Quick Evaluation of Live Simulations in Embodiment Design - Sauer, Christopher; Gerschütz, Benjamin; Bernsdorf, Jörg; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
Supporting product developers in early design phases with Live-Simulation can enhance the quality of early product designs. Live-Simulation can also facilitate a democratization of simulation and puts away pressure from simulation experts. In this paper, a machine learning based quick evaluation tool is proposed to support product developers in interpreting Live-Simulation results. The proposed tool enables a quick evaluation of the Live-Simulation results and enables product developers to further enhance their simulations. The tool is shown within a use case in bike rocker switch design.<br
Keywords: data-driven design; simulation-based design; structural analysis; machine learning; live-simulation

A Method for Analyzing the Influence of Process and Design Parameters on the Build Time of Additively Manufactured Components - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
When using additive manufacturing processes, the choice of the numerous settings for the process and design parameters significantly influences the build and production time. To reduce the required build time, it is useful to adapt the parameters with the greatest influence. However, since the contribution of the individual parameters is not readily apparent, a sensible choice of process and design parameters can become a challenging task. Thus, the following article presents a method, that enables the product developer to determine the main contributors to the required build time of additively manufactured products. By using this sensitivity analysis method, the contributors of the individual parameters can be analyzed for a given parametrized CAD model with the help of an analysis-based build time estimation approach. The novelty of the contribution can be found in providing a method that allows studying both design and process parameters simultaneously, taking the machine to be used into account. The exemplary application of the presented method to a sample part manufactured by Fused Deposition Modeling demonstrates its benefits and applicabilit
Keywords: Additive Manufacturing; 3D printing; Design for Additive Manufacturing (DfAM); Sensitivity analysis; Analysis-based build time estimation

A Method for the Tolerance Analysis of Bearing Seats for Cylindrical Roller Bearings in respect to the Operating Clearance and the Fatigue Life - Aschenbrenner, Alexander; Wartzack, Sandro (DS 87-4 Proceedings of the 21st International Conference on Engineering Design (ICED 17), Vol 4: Design Methods and Tools, 2017)
Roller bearings are used in a vast variety of mechanical applications and are often highly stressed machine elements. Therefore the fatigue life of roller bearings can determine the reliability and service life of these mechanical systems. The fatigue life of a roller bearing is greatly affected by its operating clearance and the design of the adjacent components (namely shaft and housing). Especially the geometric dimensioning and tolerancing of the bearing seats can have great influence on the operating clearance and therefore the fatigue life of a roller bearing. In this article a method for the statistical tolerance analysis of the operating clearance of cylindrical roller bearings is presented. The method uses a discrete geometry representation coupled with contact detection algorithms for the determination of the operating clearance. The results are thereafter coupled with the calculation of the fatigue life. Statistical analysis of the results assists an engineering designer when choosing a robust design for the bearing seats.
Keywords: Tolerance representation and management; Robust design; Uncertainty; Cylindrical roller bearing

A methodical approach to model and map interconnected decision making situations and their consequences - Luft, Thomas; Schneider, Samuel; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), Vol. 4: Design for X, 27.-30. Juli 2015, Mailand, 2015, S. 11-20., 2015)
As products become more and more complex and have to be developed in less time, decision makers are facing the need to achieve good decisions efficiently. While some of the decision making processes are easy to undergo and their respective consequences can be identified with precision, other decision situations are characterized by complex steps and by consequences which are hard to predict. Therefore, the objective of this paper is to identify, analyze and evaluate conflicting decision making situations whose consequences are difficult to predict. The goal is to elaborate on a methodology in order to categorize and structure decision making situations and their respective consequences. This methodology is intended to support decision makers in evaluating decision making situations with regard to their interconnectivity and potential consequences. Future steps are the application of the overall methodology in a case study and its improvement due to the lessons learned.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.ametho
Keywords: Decision making; Decision making process; Decision consequences; Design methods; Process modelling

A methodology for the application of virtual evaluation methods within the design process of cold forged steel pinions - Rohrmoser, Andreas; Heling, Björn; Schleich, Benjamin; Kiener, Christoph; Hagenah, Hinnerk; Wartzack, Sandro; Merklein, Marion (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)

A model-based approach for early robustness evaluation – Combination of Contact and Channel Approach with tolerance graphs in SysML - Horber, Dennis; Li, Jiahang; Grauberger, Patric; Schleich, Benjamin; Matthiesen, Sven; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
Considering variations is essential for the development of robust products, but the applicability of existing robust design approaches in early stages is challenging due to the lack of product information and high levels of abstraction. To overcome this, a combined model is presented, which enables a holistic robustness evaluation in a linked approach. This approach uses the contact and channel approach to identify the relations between embodiment and functions as well as the robustness evaluation based on tolerance graphs. The combined model is implemented with the Systems Modeling Language (SysML) and applied to a coining machine use case. An initial assessment of the model combination and a proposal for a methodically supported workflow for the holistic robustness evaluation is give
Keywords: Robust Design; Variation Management; Contact and Channel Approach; SysML; Model-based Development

A Model-Based Approach for Integrated Variation Management - Horber, Dennis; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the ASME 2022 International Mechanical Engineering Congress and Exposition (IMECE2022), 2023)
Variation management is a responsible task for product developers, which have to balance the ever-increasing quality demands and cost pressures, while considering the product design as well as the manufacturing and assembly process. These aspects have a direct impact on its subsequent success in the market. Therefore, a large number of different activities of variation management are necessary. In this area, a wide variety of mostly document-centered methods support product developers, which have individual interfaces. Thus, it is currently not possible to map the entire variation management process in a single model. Especially with regard to the increasing availability of large amounts of data, the potential of an integrated variation management cannot be exploited efficiently. For this reason, this paper presents a novel model-based approach for the development of a combined system and tolerancing model. This model contains the processes and activities of integrated variation management and links them with further system models and the corresponding data. The presented approach is a superordinate model for variation management as well as its processes and provides the modeling of individual views of different stakeholders. In addition, process- and program-specific solutions can be integrated into the model, which enables a cross-linking of the data beyond their interfaces. In this paper, the approach is realized using the systems modeling language (SysML
Keywords: integrated variation management; model-based systems engineering; process modelling; change effects

A modified approach for simulating complex compound structures within early design steps - Gruber, Georg; Klein, Daniel; Wartzack, Sandro (8th European LS-DYNA Users Conference, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.amodif_7

A modified scratch test for the mechanical characterization of scratch resistance and adhesion of thin hard coatings on soft substrates - Sander, Thomas; Tremmel, Stephan; Wartzack, Sandro (Surface & Coatings Technology, 2011)
The scratch resistance of coatings and the adhesion between coating and substrate are usually determined in model experiments performed with sharp diamond indenters. These common methods as described for example in EN 1071-3 often fail for the combination of hard coatings on soft substrates due to very small critical loads or no detectable failure modes at all. Hence in the industry a lot of highly subjective and provisional test methods are used. On the one hand, quantitative comparability is difficult with common methods since defects already occur at very small loads for ductile and relative soft substrate materials like plastics. On the other hand, wear of the indenter in contact with hard coatings like pure diamond coatings requires its cost-intensive replacement.In this article a macroscopic tribological-mechanical test method is suggested which uses balls of hardened steel as indenters. A wide scope can be applied for both soft and hard coatings and different substrate materials. By variation of the ball-diameter, the normal contact force and the sliding speed different levels of stress and wear can be induced to analyze the tribological and mechanical behavior between body and counterpart as well as the interface of coating and substrate. To determine scratch resistance close to reality as usual scratch conditions on consumer products are better represented by a small ball than a sharp diamond indenter. Another benefit of the presented test method is the cost saving acquisition of the balls for indentation in very high quality as they are standard parts in the ball bearing industry. For every test on very hard coatings a new ball can be used with the possibility to detect the wear both on the base object and the counterpart. The occurring failure modes of coating and substrate also can be compared with comparatively easy numerical models to verify the results. Additionally to the test concept, first results of different coatings will be presented in this paper and compared with the results of common scratch tests.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KLMEFK.amodif_0
Keywords: Adhesion; Characterization; Critical load; Scratch resistance; Scratch test; Soft substrates

Amorphe Kohlenstoffschichten für die Blechmassivumformung - Wartzack, Sandro; Hetzner, Harald; Tremmel, Stephan (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.amorph_6

Amorphous Carbon Coatings for Locally Adjusted Tribological Properties in Sheet Bulk Metal Forming - Hetzner, Harald; Tremmel, Stephan; Wartzack, Sandro (Key Engineering Materials, 2012)
In sheet bulk metal forming, locally adapted friction properties of the contact tool/workpiece are an appropriate means for the targeted enhancement of the material flow, enabling an improved form filling and lowered forming forces. However, the implementation of desirable friction conditions is not trivial. And further, friction is inseparably linked to wear and damage of the contacting surfaces. This calls for a methodological approach in order to consider tribology as a whole already in the early phases of process layout, so that tribological measures which allow fulfilling the requirements concerning local friction and wear properties of the tool surfaces, can already be selected during the conceptual design of the forming tools. Thin tribological coatings are an effective way of improving the friction and wear properties of functional surfaces. Metalmodified amorphous carbon coatings, which are still rather new to the field of metal forming, allow tackling friction and wear simultaneously. Unlike many other types of amorphous carbon, they have the mechanical toughness to be used in sheet bulk metal forming, and at the same time their friction properties can be varied over wide ranges by proper choice of the deposition parameters. Based on concrete research results, the mechanical, structural and special tribological properties of tungstenmodified hydrogenated amorphous carbon coatings (a-C:H:W) are presented and discussed against the background of the tribological requirements of a typical sheet bulk metal forming process.© (2012) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.amorph
Keywords: a-C:H:W; Amorphous carbon coatings; DLC; Forming tool tribology; Sheet bulk metal forming

Amorphous carbon coatings for total knee arthroplasty – a knee simulator evaluation - Neusser, Kevin; Marian, Max; Bartz, Marcel; Wartzack, Sandro; Rothammer, Benedict (6th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2023)
The purpose of endoprosthetic joint replacement is to regain the functionality and allow patients to live a more mobile and pain-free life. Aseptic loosening of total knee arthroplasty (TKA) is a major cause of premature failure, with wear particles removed from the implant materials being largely responsible. Therefore, great efforts are being made to reduce the wear of polymer inlays by surface modifications. This study concentrates on the evaluation of the effectiveness of wear-reducing amorphous carbon coating systems on hard-on-soft pairings (metal-on-polymer). The biotribological behavior of the uncoated and coated TKA is investigated in a knee simulator according to ISO 14243. The articulation is lubricated with diluted bovine calf serum (BCS) at 37 °C mimicking in vivo boundary conditions and motion parameters. The wear is quantified by gravimetry after a total of 3.5 million cycles and the gravimetric wear of the polymeric tibial inlays are calculated in intervals of 500,000 cycles. This testing reveals the applicability of amorphous carbon (also known as diamond-like carbon (DLC)) coatings to the considered materials used for biomedical applications. The results represent an important milestone in demonstrating the potential of DLC coated contact partners for wear reduction in human joints, thus enabling more focused research and understanding in the development of biotribologically effective coating system

Amorphous Carbon Coatings for Total Knee Arthroplasty – a Knee Simulator Evaluation - Rothammer, Benedict; Neusser, Kevin; Bartz, Marcel; Wartzack, Sandro (24, 2024)

Amorphous Carbon Coatings for Total Knee Replacements—Part I: Deposition, Cytocompatibility, Chemical and Mechanical Properties - Rothammer, Benedict; Neusser, Kevin; Marian, Max; Bartz, Marcel; Krauß, Sebastian; Böhm, Thomas; Thiele, Simon; Merle, Benoit; Detsch, Rainer; Wartzack, Sandro (Polymers, 2021)
Diamond-like carbon (DLC) coatings have the potential to reduce implant wear and thus to contribute to avoiding premature failure and to increasing service life of total knee replacements (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While a detailed characterization of the tribological behavior is the subject of part II, part I focusses on the deposition of pure (a-C:H) and tungsten-doped hydrogen-containing amorphous carbon coatings (a-C:H:W) and the detailed characterization of their chemical, cytological, mechanical and adhesion behavior. The coatings are fabricated by physical vapor deposition (PVD) and display typical DLC morphology and composition – as verified by focused ion beam scanning electron microscopy and Raman spectroscopy. Their roughness is higher than that of the plain substrates. Initial screening with contact angle and surface tension as well as in vitro testing by indirect and direct application indicate favorable cytocompatibility. The DLC coatings feature excellent mechanical properties with a substantial enhancement of indentation hardness and elastic modulus ratios. The adhesion of the coatings as determined in modified scratch tests can be considered as sufficient for the use in TKAs.<br
Keywords: DLC coating; Biomedical applications; Biotribology; UHMWPE; CoCr; Ti64; Total knee arthroplasty; Cytocompatibility; Hardness; Adhesion

Amorphous Carbon Coatings for Total Knee Replacements—Part II: Tribological Behavior - Rothammer, Benedict; Marian, Max; Neusser, Kevin; Bartz, Marcel; Böhm, Thomas; Krauß, Sebastian; Schroeder, Stefan; Uhler, Maximilian; Thiele, Simon; Merle, Benoit; Kretzer, J. Philippe; Wartzack, Sandro (Polymers, 2021)
Diamond-like carbon coatings may decrease implant wear, therefore, they are helping to reduce aseptic loosening and increase service life of total knee arthroplasties (TKAs). This two-part study addresses the development of such coatings for ultrahigh molecular weight polyethylene (UHMWPE) tibial inlays as well as cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloy femoral components. While the deposition of a pure (a-C:H) and tungsten-doped hydrogen-containing amorphous carbon coating (a-C:H:W) as well as the detailed characterization of mechanical and adhesion properties were the subject of Part I, the tribological behavior is studied in Part II. Pin-on-disk tests are performed under artificial synovial fluid lubrication. Numerical elastohydrodynamic lubrication modeling is used to show the representability of contact conditions for TKAs and to assess the influence of coatings on lubrication conditions. The wear behavior is characterized by means of light and laser scanning microscopy, Raman spectroscopy, scanning electron microscopy and particle analyses. Although the coating leads to an increase in friction due to the considerably higher roughness, especially the UHMWPE wear is significantly reduced up to a factor of 49% (CoCr) and 77% (Ti64). Thereby, the coating shows continuous wear and no sudden failure or spallation of larger wear particles. This demonstrated the great potential of amorphous carbon coatings for knee replacements.
Keywords: DLC coating; Biomedical applications; Biotribology; UHMWPE; CoCr; Ti64; Total knee arthroplasty; Pin-on-disk; Friction; Wear

A Musculoskeletal Human Model-Based Approach for Evaluating Support Concepts of Exoskeletons for Selected Use Cases - Molz, Carla; Yao, Zhejun; Sänger, Johannes; Gwosch, Thomas; Weidner, Robert; Matthiesen, Sven; Wartzack, Sandro; Miehling, Jörg (Proceedings of the Design Society, 2022)
This paper presents an approach for evaluating exoskeleton support concepts through biomechanical analyses on a musculoskeletal human model. By simplifying the support forces of an exoskeleton as external forces, different support concepts can be biomechanically evaluated for the respective use case without concrete design specifications of the exoskeleton. This enables an estimation of the resulting relief and strain on the human body in the early stages of exoskeleton development. To present the approach, the use case of working at and above head height with a power tool is chosen.
Keywords: user-centred design; design optimisation; supportive technologies; musculoskeletal human model; exoskeleton

An adapted Method for Design Process Capturing to meet the challenges of digital product development - Gerschütz, Benjamin; Spießl, Bettina Vanessa Martina; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the International Conference on Engineering Design (ICED21), 2021)
n our modern, interconnected and globalized world, design is in motion, to adapt to new situations. But successful Design in Motion must be based on Processes in Motion. For a target-oriented adaptation of the processes to the new, challenging conditions, the as-is procedures must be captured and analysed. For this analysis, established capturing procedures from production or administration cannot be used due to some special features of design processes and workflows, which will be discussed in this contribution. To compensate for the weaknesses of existing methods, we propose an adapted method for holistic design process capturing. With the procedure, we want to enable an economic process analysis, which is crucial for small and medium-size companies in particular. To give an insight into the practical application of the method, we exemplarily analyse the process of a shaft construction and FEM-evaluation by two different employees. Based on this analysis and to verify the relevance of the presented approach, an evaluation with respect to the requirements is done. In our modern, interconnected and globalized world, design is in motion, to adapt to new situations. But successful Design in Motion must be based on Processes in Motion. For a target-oriented adaptation of the processes to the new, challenging conditions, the as-is procedures must be captured and analysed. For this analysis, established capturing procedures from production or administration cannot be used due to some special features of design processes and workflows, which will be discussed in this contribution. To compensate for the weaknesses of existing methods, we propose an adapted method for holistic design process capturing. With the procedure, we want to enable an economic process analysis, which is crucial for small and medium-size companies in particular. To give an insight into the practical application of the method, we exemplarily analyse the process of a shaft construction and FEM-evaluation by two different employees. Based on this analysis and to verify the relevance of the presented approach, an evaluation with respect to the requirements is don
Keywords: Process modelling; Organisation of product development; Digital/Digitised engineering value chanins

An advanced procedure model for property-based product development - Luft, Thomas; Krehmer, Hartmut; Wartzack, Sandro (DS 75-8: Proceedings of the 19th International Conference on Engineering Design (ICED13), 2013)
Increasing functionality, increasing individualization as well as the enormous complexity of modern products lead to steadily increasing challenges in the domain of product development. This causes a necessity of a novel approach for a purposeful guidance to lead developers through the process of product development. Therefore the objective of this work is to present an advanced procedure model for property-based product development which is showing effects of characteristics specifications based on a structured mapping of product properties. Due to its structure and the integration of a multitude of individual approaches that are developed within this paper, the presented procedure model provides product developers with a detailed guidance to the process of product development. Moreover, developers are supported not only in the field of preventative avoidance of unnecessary design iterations but also in in dealing with unavoidable iterations. By continuously monitoring the productâs degree of maturity information about the achievement of the required properties and about necessary changes can be deduced.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.anadva
Keywords: Design methodology; property-property-based product development; design process; process modeling; design management

Analyse anlagenspezifischer Fertigungseinflüsse auf die Genauigkeit FDM-gedruckter Bauteile - Hallmann, Martin; Kunz, David; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 29. DfX-Symposium, 2018)
Since the first successful integrations of additive manufacturing processes into industrial production, the achievable component qualities, such as geometric accuracy and surface quality, have improved significantly. Hence, such processes are often used for the manufacturing of directly usable components. Nevertheless, the deviations caused by the generative production principles are inevitably and strongly dependent on the respective machine. To address these aspects in the tolerance-driven design of additively manufactured components, a procedure for the acquisition of machine-specific component deviations is presented and applied to a revolute joint as an exampl
Keywords: Fused Deposition Modeling; Geometric Accuracy; Influences of production; Design of Experiment

Analyse der Betriebseigenschaften von losen Schmierringen und Ableitung von Gestaltungs- und Auslegungsrichtlinien - Müller, Matthias; Tremmel, Stephan; Weschta, Martin; Stangl, Thomas; Wartzack, Sandro (Wälzlagerkolloquium, 2015)

Analysis of hybrid structures: easy and efficient - Witzgall, Christian; Kellermeyer, Markus; Wartzack, Sandro (Adhesion Adhesives & Sealants, 2016)

Analysis of the effects of manufacturing-caused deviations and varying operation parameters on operation-depending deviations of systems in motion - Walter, Michael; Wartzack, Sandro (Proceedings of the 12th CIRP Conference on Computer Aided Tolerancing, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.analys

An approach for determining the influence of manufacturing process parameters on product quality characteristics - Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2020)
Scattering manufacturing process parameters affect the quality of manufactured products, because the product properties deviate from the nominal design. If the desired quality requirements are not met, individual part tolerances can be adjusted in such a way that the required reject rates are achieved. In this context, different methods can be used to determine the individual contributors and to quantify the influence of the individual part tolerances on the quality of the manufactured product. In all existing approaches, however, only geometric tolerances are considered but not the varying manufacturing process parameters that are responsible for the geometrical part deviations. To overcome this, in this article, a novel approach is presented that allows determining the influence of manufacturing process parameters on quality characteristics for systems in motion. The novel approach is also highlighted in a case study of an X-ray shutter. <br
Keywords: Tolerance Synthesis; Interdisciplinary process-oriented Tolerance Management; Sensitivity Analysis

An approach for semi-automatic redesign of mechatronic products by multidisciplinary optimisation - Walter, Leonie; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society: International Conference on Engineering Design, 2021)
Mechatronic products are widely spread today, but their development still is a challenge. In addition, with the trend of individualisation, not only one solution must be designed but multiple configurations are needed to fulfil customer-specific requirements. To reduce cost and development time, usually existing products are adapted for this purpose. Even though a lot of knowledge is already available through the previous product version, because of multiple disciplines that must be considered in mechatronic systems, even redesign processes are complex. To support the adaption of mechatronic products to changed requirements, an approach to systematically reuse the knowledge available from previous product versions is proposed in this contribution. Through multidisciplinary behaviour optimisation, the solution space is reduced to build an adapted product meeting the new requirements. The approach is explained in detail and illustrated with the example of an electric window regulator and the results are discussed thoroughl
Keywords: Mechatronics; Optimisation; Product modelling / models; Redesign

An Approach of a Knowledge-based Process to Integrate Real Geometry Models in Product Simulations - Katona, Sebastian; Koch, Michael; Wartzack, Sandro (Procedia CIRP, 2016)
Simulation driven product development is state of the art to insure that the desired characteristics in use behave as requested without performing a time-consuming testing using expensive prototypes. To achieve the aim of realistic and confidential results within this product simulations, a tremendous afford (i.e. when taking different non-linearities into account, like material behavior, contact situations, large deflections etc.) is necessary. Conflicting to this, the ideal CAD-model is always used for the analysis, despite knowing the effect, that every manufactured component shows differences to its ideal geometry. Within this paper an approach of a knowledge-based process to integrate real geometry data into product simulations is given. Furthermore, different methods for preparation of the simulation models are represented.
Keywords: Computer aided design (CAD); deformation; finite element method (FEM); geometry; knowledge-based system; process; simulation; strucural analysis

An Approach to the Sensitivity Analysis in Variation Simulations considering Form Deviations - Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, Volume 75, 2018)
In tolerance and variation simulations, sensitivity analyses are used to assess the influences of tolerance specifications and geometrical deviations on the assembly key characteristics and to support product and process developers in deriving more suitable tolerancing decisions and in optimizing manufacturing and assembly processes. However, established methods to the sensitivity analysis in the context of variation simulations disregard important statistical dependencies, which occur when considering form deviations. To overcome these shortcomings, an approach to the density-based sensitivity analysis in variation simulations considering form deviations based on Skin Model Shapes is presented. The method is highlighted and discussed employing a typical tolerance analysis case stud
Keywords: Sensitivity Analysis; Tolerance Analysis; Skin Model Shapes

An Approach to Transfer Biological Solutions Based on the Interaction of Mechanisms to Technical Products - Bartz, Marcel; Uttich, E.; Wanieck, K.; Bender, B.; Wartzack, Sandro (Proceedings of the Design Society, 2022)
Biological solutions are often used for developing technically innovative products in a biomimetic process. However, biological solutions do not always make it into a successful technical product, e.g. due to a lack of knowledge on the mechanisms of action. A new approach is presented for transferring biological solutions based on complex mechanisms of action. It is based on mathematical optimization methods and applied to the lightweight design of the musculoskeletal system. Finally, first technical implementations in the field of robotics, among others, will be presented.
Created from Fastlane, Scopus look-up
Keywords: biologically inspired design; biomimicry (biomimetics); lightweight design; topological optimisation

An efficient bionic topology optimization method for transversely isotropic materials - Völkl, Harald; Klein, Daniel; Franz, Michael; Wartzack, Sandro (Composite Structures, 2018)
Optimization specifically for fiber reinforced plastics (FRP) is becoming more and more important for creating high-quality composite structures. Yet, in spite of the increasing use of topology optimization (TO) within product development, specific TO methods for transversely isotropic materials like FRP are scarce in research and even more scarce in practical application. This is amongst other reasons caused by the challenge of simultaneous optimization of mutually dependent material distribution and fiber orientations, which poses an obstacle to established gradient-based optimization routines in terms of iterations (run time) and gradient formulation. Thus, based on bionic methods, an efficient, empirical optimization method is proposed to enable fast and FRP-suitable geometry propositions. Case studies show efficiency and effectiveness: the new approach offers very fast convergence; plus perceptible stiffness gains compared to established topology optimization for isotropic material
Keywords: Structural optimization Fiber-reinforced plastics Finite element analysis Bionics

A new approach to first tolerance evaluations in the conceptual design stage based on tolerance graphs - Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, Volume 75, 2018)
Tolerancing is commonly performed in late design stages, in which the product geometry is fully defined. However, this often leads to high manufacturing costs or expensive design changes. Therefore, motivated by the idea of frontloading, a new approach for first tolerance evaluations in conceptual design stages is developed, which enables a first tolerance specification and analysis based on the few geometry data available. Together with semantic information of the interface notations of adjacent parts, graphs including relevant geometry elements and tolerance information are generated. These graphs support designers with a first assessment of tolerance situations before the geometry is finally defined.<br
Keywords: Robust Design; Tolerance Graph; Early Design Stage

A New Design Method for Generating Surrogate Kinematic Truss Orthoses to support Pathological Gait Patterns in Human Model Simulations - Steck, Patrick; Scherb, David; Mayer, Johannes; Jäger, Michael; Miehling, Jörg; Völkl, Harald; Wartzack, Sandro (Proceedings of the Design Society, 2023)
With increasing life expectancy, the risk of diseases of the central nervous system, such as cancer,strokes, etc., also increases. Strokes often result in injury to the sciatic nerve, which is responsible forcontrolling the calf muscles (plantar and dorsal flexors). A so-called ankle joint orthosis (AFO) helps tosupport the pathological gait and to avoid foot drop during gait. Passive orthoses are of particularimportance for research, as they do not require additional incoming energy from outside to the orthoticsystem. However, current passive orthoses are often not personalized. On the one hand, because theyusually have only a temporary muscle-building function and, on the other hand, because the individualdesign process is computationally time consuming and thus expensive. This paper presents a possibilityto pre-dimension and pre-design passive orthoses fast and cost-efficiently by reducing the complexityof the model based on volume-optimized truss elements. Therefor a traditional high calculation intensivedesign procedure is compared with the complexity reduced model to show its effectiviness and thesimilarity of the results. Witl incoming energy from outside to the orthoticsystem. However, current passive orthoses are often not personalized. On the one hand, because theyusually have only a temporary muscle-building function and, on the other hand, because the individualdesign process is computationally time consuming and thus expensive. This paper presents a possibilityto pre-dimension and pre-design passive orthoses fast and cost-efficiently by reducing the complexityof the model based on volume-optimized truss elements. Therefor a traditional high calculation intensivedesign procedure is compared with the complexity reduced model to show its effectiviness and thesimilarity of the results. <br
Keywords: Orthoses; User centred design; Lightweight design; Truss optimization; Design methods

A new design process for anatomically enhanced osteosynthesis plates - Tkany, Luisa; Hofstätter, Bernhard; Petersik, Andreas; Miehling, Jörg; Wartzack, Sandro; Sesselmann, Stefan (Journal of Orthopaedic Research, 2019)

A new "knowledge-based engineering" guideline - Luft, Thomas; Roth, Daniel; Binz, Hansgeorg; Wartzack, Sandro (DS 87-6 Proceedings of the 21st International Conference on Engineering Design (ICED17), Vol. 6: Design Information and Knowledge, 2017)
It is necessary to enable product developers to use specific engineering knowledge in an efficient and fast way during the product development process. However, existing procedures supporting the development of products are not strictly convenient to meet this challenge. This is the reason why already in the 1980 various research approaches in the area of knowledge-based engineering (KBE) have been developed. Nevertheless, there is still no uniform and universally applicable description for the industrial environment, with which a KBE application can be implemented and operated. Therefore, the aim is empowering designers to use design-related knowledge in CAD-systems as a central engineering workbench. The main research question in this paper is: How to formulate a universally applicable procedure to conduct KBE-projects with all relevant roles as well as necessary instructions and recommendations regarding specific KBE-methods and -tools? By answering this question, this contribution offers insights in general adapted definitions and perspectives, a procedure for the implementation of KBE-projects, a classification of knowledge-based engineering and a first exemplary solution.
Keywords: Computer Aided Design (CAD); Computational design methods; Design informatics; Knowledge management; Product modelling

A New Method For Passive Ankle Foot Orthosis Design – Integration Of Musculoskeletal And Finite Element Simulation - Scherb, David; Steck, Patrick; Völkl, Harald; Wartzack, Sandro; Miehling, Jörg (Proceedings of the Design Society, 2023)
Motor disorders are diseases affecting the muscle function of the human body. A frequently occurring motor disorder affects the lower leg muscles resulting in a pathological gait called foot drop. Patients have a higher risk of stumbling and falling. The most common treatment is the use of a passive ankle-foot-orthosis (AFO). However, the compensation of foot drop is only limited due to the non possible support of all rotational directions of the ankle joint. Therefore, a newly developed concept for a passive AFO is currently in work. To ensure a best possible treatment of the patient, the provided support by the AFO and required support by the patient have to be in accordance. Thus, in this contribution a method is presented that integrates model order reduced finite element analysis for computing the provided support of the AFO and musculoskeletal human models for representing the patients' gait behaviour. With the method, the design of the force generating structures of the AFO can be realized regarding the patients' requirements. The presented method is further evaluated with a specific use case. The main focus lies here in the principal functionality of the method and the provision of valid results.<br
Keywords: User centred design; Design methods; Product modelling / models; Orthosis; Musculoskeletal human model

A New Projection Based Method for the Classification of Mechanical Components Using Convolutional Neural Networks - Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
Digital engineering is increasingly established in the industrial routine. Especially the application of machine learning on geometry data is a growing research issue. Driven by this, the paper presents a new method for the classification of mechanical components, which utilizes the projection of points onto a spherical detector surfaces to transfer the geometries into matrices. These matrices are then classified using deep learning networks. Different types of projection are examined, as are several deep learning models. Finally, a benchmark dataset is used to demonstrate the competitiveness.
Created from Fastlane, Scopus look-up
Keywords: artificial intelligence (AI); data mining; data-driven design; deep learning; part classification

Anforderungen an die Wissensakquisitionskomponente eines selbstlernenden Assistenzsystems - Röhner, Sebastian; Breitsprecher, Thilo; Wartzack, Sandro (8. Gemeinsames Kolloquium Konstruktionstechnik, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.anford

Anforderungen an technische Oberflächen und die Herausforderungen für den Produktentwickler - Sander, Thomas; Wartzack, Sandro (Beiträge zum 22. DfX-Symposium, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.anford

An indicator-based process monitoring cockpit for controlling and enhancing product development processes - an industrial case study - Luft, Thomas; Smoll, Simon; Wartzack, Sandro (Smart Product Engineering - Proceedings of the 23rd CIRP Design Conference, 2013)
The need for shorter development times, lower costs, and higher quality requires improving the performance of the product development process (PDP) continuously. Therefore the evaluation and monitoring of the product development performance is of great interest for companies wishing to increase their competitiveness. However, there are very few approaches for the performance measurement of the PDP. For this purpose, a process monitoring cockpit with the overall goal to enhance the PDP regarding time, costs, quality is presented. This approach for measuring and continuously improving the current state of a company’s PDP has been validated in an industrial case study.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.anindi
Keywords: product development process; evaluation methodology; knowledge management; decision making; continuous improvement; industrial case study

An optimized material representation for crashworthy lightweight structures within early design steps - Gruber, Georg; Wartzack, Sandro (Proceedings of the 16th International Conference on Industrial Engineering - Theory, Applications and Practice, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.anopti

A novel approach for the evaluation of composite suitability of lightweight structures at early design stages - Klein, Daniel; Witzgall, Christian; Wartzack, Sandro (International Design Conference - DESIGN, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.anovel

A novel approach to incorporating previous fatigue damage into a failure model for short-fibre reinforced plastics - Witzgall, Christian; Giolda, Jessica; Wartzack, Sandro (International Journal of Impact Engineering, 2022)
This paper describes how previous material damage due to cyclic loading can influence the failure properties of short-fibre reinforced thermoplastics under crash conditions. To enable these effects to be incorporated into numerical crash simulations, we present a mathematical failure model that takes fatigue damage into account. We perform an experimental study on the thermoplastic PBT GF30: We initially characterize the material under cyclic loading conditions. Subsequently, the behaviour of pre-damaged material specimens in highly dynamic loading experiments is compared to that of virgin specimens to determine the loss of strength due to fatigue damage. Based on the aforementioned experimental results, we develop, calibrate and implement an analytical model for use in the commercial software LS-DYNA.<br
Keywords: Short-fibre reinforced plastics; Crash simulation; Fatigue damage; Failure model

A Novel Approach to Simulating Realistic Exoskeleton Behavior in Response to Human Motion - Yao, Zhejun; Seyed Milad Mir, Latifi; Molz, Carla; Scherb, David; Löffelmann, Christopher; Sänger, Johannes; Miehling, Jörg; Wartzack, Sandro; Lindenmann, Andreas; Matthiesen, Sven; Weidner, Robert (Robotics, 2024)
Simulation models are a valuable tool for exoskeleton development, especially for system optimization and evaluation. It allows an assessment of the performance and effectiveness of exoskeletons even at an early stage of their development without physical realization. Due to the closed physical interaction between the exoskeleton and the user, accurate modeling of the human–exoskeleton interaction in defined scenarios is essential for exoskeleton simulations. This paper presents a novel approach to simulate exoskeleton motion in response to human motion and the interaction forces at the physical interfaces between the human and the exoskeleton. Our approach uses a multibody model of a shoulder exoskeleton in MATLAB R2021b and imports human motion via virtual markers from a digital human model to simulate human–exoskeleton interaction. To validate the human-motion-based approach, simulated exoskeleton motion and interaction forces are compared with experimental data from a previous lab study. The results demonstrate the feasibility of our approach to simulate human–exoskeleton interaction based on human motion. In addition, the approach is used to optimize the support profile of an exoskeleton, indicating its potential to assist exoskeleton development prior to physical prototyping.<br
Keywords: exoskeleton model; exoskeleton simulation; human–exoskeleton interaction; evaluation; optimization; human motion

A Novel Shape Retrieval Method for 3D Mechanical Components Based on Object Projection, Pre-Trained Deep Learning Models and Autoencoder - Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Computer-Aided Design, 2023)
The reuse of existing design models offers great potential in saving resources and generating an efficient workflow. In order to fully benefit from these advantages, it is necessary to develop methods that are able to retrieve mechanical engineering geometry from a query input. This paper aims to address this problem by presenting a method that focuses on the needs of product development to retrieve similar components by comparing the geometrical similarity of existing parts. Therefore, a method is described, which first converts surface meshes into point clouds, rotates them, and then transforms the results into matrices. These are subsequently passed to a pre-trained Deep Learning network to extract the feature vector. A similarity between different geometries is calculated and evaluated based on this vector. The procedure employs a new type of part alignment, especially developed for mechanical engineering geometries. The method is presented in detail and several parameters affecting the accuracy of the retrieval are discussed. This is followed by a critical comparison with other shape retrieval approaches through a mechanical engineering benchmark data set.
CRIS-Team Scopus Importer:2022-10-14
Keywords: 3D object retrieval; Autoencoder; Deep Learning; Part alignment; Projection method; Shape retrieval

An Overview and Classification of Tolerance Compensation Methods - Aschenbrenner, Alexander; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Technological advances as well as novel manufacturing and design paradigms, such as industry 4.0 and digitalization, offer new opportunities for innovative products. However, they also increase the product complexity and cause new challenges in the production process. Therefore, agile production approaches are crucial. Tolerance compensation provides more flexibility in the production process, as demands on dimensional accuracy of the components are reduced. As a result, tolerance compensation also offers the possibility of reducing production costs without compromising product quality. Nevertheless, tolerance compensation is often considered a reactive intervention to reduce the number of out-of-spec parts a posteriori instead of including it in the early stages of Geometrical Variations Management. The contribution tackles this issue by characterizing and categorizing different methods of tolerance compensation as well as providing design guidelines for the application of tolerance compensation methods. This enables design engineers to select a suitable tolerance compensation method for different application
Keywords: Tolerance Compensation; Robust Design; Tolerance representation and management; Uncertainty

Ansatz zur CAD-integrierten Rückführung von Konstruktionsgeometrie aus Formoptimierungsergebnissen - Stangl, Thomas; Wartzack, Sandro (Design for X. Beiträge zum 24. DfX-Symposium, 2013)
Today, the short product lifecycle is a main challenge to the product developer. This requires a high level of product maturity even in the virtual design stage. The consequence is a reduced time-to-market. Hence, the application of non-parametric shape optimization, especially the low setup-costs, robustness and high flexibility, is successfully established as a common standard. The common method for redesign of the adapted shape (triangulated surface data) in productive use is redesign by means of a CAD-system and visual interpretation. This procedure is susceptible to errors. Consequently, an efficient procedure is still lacking for seamless redesign of shape optimization results in a CAD System. This paper focuses on the development of a solution by presenting an approach and the basic structure of the associated design assistance system. By means of this application, it is possible for the product developer to integrate the complex shape changes of the optimization process in the original CAD model – even without any reverse engineering knowledge. The feature structure of the original model remains intact – and thus the intention and the knowledge of the product developer.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.ansatz
Keywords: Formoptimierung; CAD; Rückführung

Ansatz zur crashsicheren Auslegung von Leichtbaukonstruktionen unter besonderer Berücksichtigung der Fügestellen - Klein, Daniel; Wartzack, Sandro; Lindner, Christian (Design for X. Beiträge zum 23. DfX-Symposium, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.ansatz

Ansatz zur Ermittlung von Toleranz-Kosten-Kurven in der Serienproduktion - Brückner, Kai; Storch, Markus; Hallmann, Martin; Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2019)
Die Vergabe von Toleranzen dient der Erfüllung festgelegter Qualitätskriterien, beeinflusst jedoch zugleich wesentlich die Fertigungskosten. Um diesen Konflikt effizient zu lösen, hat sich die Methode der Toleranz-Kosten-Optimierung etabliert. Voraussetzung für eine realitätsnahe Toleranzfestlegung ist die Verfügbarkeit eines geeigneten Kostenmodells. Obgleich aus Literatur und Praxis zahlreiche Ansätze bekannt sind, eignen sich diese nur bedingt für die Serienfertigung. Um diese Lücke zu schließen, wird im Folgenden ein neuer Ansatz zur Ermittlung von Kostenkurven, welche unter anderem prozessfähigkeitsabhängige Messkosten als auch mehrere Prozessparameter berücksichtigt, vorgestellt. Das Beispiel eines Hochdruckeinspritzventils zeigt exemplarisch dessen Anwendung im industriellen Umfeld.</

ApOL-Application Oriented Workload Model for Digital Human Models for the Development of Human-Machine Systems - Sänger, Johannes; Wirth, Lukas; Yao, Zhejun; Scherb, David; Miehling, Jörg; Wartzack, Sandro; Weidner, Robert; Lindenmann, Andreas; Matthiesen, Sven (MDPI Machines, 2023)
Since musculoskeletal disorders are one of the most common work-related diseases for assemblers and machine operators, it is crucial to find new ways to alleviate the physical load on workers. Support systems such as exoskeletons or handheld power tools are promising technology to reduce the physical load on the humans. The development of such systems requires consideration of the interactions between human and technical systems. The physical relief effect of the exoskeleton can be demonstrated in experimental studies or by simulation with the digital human model (DHM). For the digital development of these support systems, an application-oriented representation of the workload is necessary. To facilitate digital development, an application-oriented workload model (ApOL model) of an overhead working task is presented. The ApOL model determines the load (forces, torques) onto the DHM during an overhead screw-in task using a cordless screwdriver, based on experimental data. The ApOL model is verified by comparing the simulated results to the calculated values from a mathematical model, using experimental data from three participants. The comparison demonstrates successful verification, with a maximum relative mean-absolute-error (rMAE) of the relevant load components at 11.4%. The presented ApOL model can be utilized to assess the impact of cordless screwdriver design on the human workload and facilitate a strain-based design approach for support systems e.g., exoskeletons.<br
Keywords: user-centered design; digital human model; virtual sensor; exoskeleton; cordless screwdriver

A posture prediction method for ergonomic assessment of user-product interactions while grasping using musculoskeletal human models - Hartmann, Carla; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
Using digital human models (DHMs) as the virtual representation of the human body enables the integration of ergonomic assessments in the product design process. Especially the use of DHMs in the early phases of product design can be decisive for competitive factors such as ergonomics or usability. Therefore, we present a method for automatic posture generation for grasping tasks using a musculoskeletal human model. This method enables ergonomic analyses without ergonomic knowledge of the product designer or subject tests. We implemented the presented method for a cylinder grasping scenario using the open source software OpenSim. Subsequently, we evaluated the implementation by means of a parameter stud
Keywords: Posture prediction; musculoskeletal simulation; digital human model

Application and validation of the matrix-based product description in a case study by using the software Loomeo - Luft, Thomas; Ewringmann, Niklas; Wartzack, Sandro (Proceedings of the 24th CIRP Design Conference 2014, Milano, Italy, 2014)
The main task of product developers is to meet the ever increasing demands on quality, cost and functionality of technical products by setting the appropriate characteristics in order to realize the product properties desired by the customer. The overall objective of the authors is to develop a suitable procedure model for property-based product development, which guides the developers purposefully through the development process. An essential part of this procedure model is the matrix-based product description, which is in the focus of this paper. The matrix-based product description is basically a so-called multi domain matrix. By using this matrix-based product description, dependencies between requirements, behaviors of the product and the product's properties and characteristics can be mapped and analyzed systematically during the product development process. Thereby, for example, the effects of characteristic changes on product properties become visible and traceable and also differential requirements are set into relationship with properties and characteristics of the product. However, it has been shown that the manual filling of the matrix-based product description is very time-consuming. Hence, a computer-aided support is indispensable. For this reason, the software Loomeo is used in this paper to investigate its potential for IT support for the matrixbased product description. The interaction of dependencies between characteristics, properties and the resulting behavior is demonstrated in this paper through the matrix-based product description using the example of a front wheel suspension of a car. Thus, the strengths and weaknesses as well as opportunities and risks of Loomeo regarding the suitability of the IT-based matrix-based product description can be determined. The findings from both the application as well as from the evaluation of the software are the basis for the improvement and extension of the matrixbased product description.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.applic
Keywords: case study; complexity management; design methodology; design structure matrix; Design synthesis and optimisation; Matrix-based product description; product-oriented process management

Application, evaluation and future research potential of the matrix and graph based product model - Luft, Thomas; Wartzack, Sandro (DS 84: Proceedings of the DESIGN 2016 14th International Design Conference, 2016)
The increasing individualization due to customer-specific requirements as well as the enormous complexity of modern products leads to steadily increasing challenges. To meet these challenges, the overall objective of the authors is to develop a computer aided matrix- and graphbased product modelling tool for the product-oriented process management. The aim of this paper is to give a short description of this methodological and conceptual approach and to apply and to evaluate it in order to show future research potential.
Keywords: design synthesis and optimisation; design methodology; product-oriented process management; matrix based product model; design structure matrix (DSM)

Application of reinforcement learning for the optimization of clinch joint characteristics - Zirngibl, Christoph; Dworschak, Fabian; Schleich, Benjamin; Wartzack, Sandro (Production Engineering, 2021)
Due to increasing challenges in the area of lightweight design, the demand for time- and cost-effective joining technologies is steadily rising. For this, cold-forming processes provide a fast and environmentally friendly alternative to common joining methods, such as welding. However, to ensure a sufficient applicability in combination with a high reliability of the joint connection, not only the selection of a best-fitting process, but also the suitable dimensioning of the individual joint is crucial. Therefore, few studies already investigated the systematic analysis of clinched joints usually focusing on the optimization of particular tool geometries against shear and tensile loading. This mainly involved the application of a meta-model assisted genetic algorithm to define a solution space including Pareto optima with all efficient allocations. However, if the investigation of new process configurations (e. g. changing materials) is necessary, the earlier generated meta-models often reach their limits which can lead to a significantly loss of estimation quality. Thus, it is mainly required to repeat the time-consuming and resource-intensive data sampling process in combination with the following identification of best-fitting meta-modeling algorithms. As a solution to this problem, the combination of Deep and Reinforcement Learning provides high potentials for the determination of optimal solutions without taking labeled input data into consideration. Therefore, the training of an Agent aims not only to predict quality-relevant joint characteristics, but also at learning a policy of how to obtain them. As a result, the parameters of the deep neural networks are adapted to represent the effects of varying tool configurations on the target variables. This provides the definition of a novel approach to analyze and optimize clinch joint characteristics for certain use-case scenarios.
CRIS-Team WoS Importer:2022-01-07

Approach and application to transfer heterogeneous simulation data from finite element analysis to neural networks - Sprügel, Tobias; Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Journal of Computational Design and Engineering, 2021)
The simulation of product behavior is a vital part of current virtual product development. It can be expected that soon there will be more product simulations due to the availability of easy-to-use finite element analysis software and computational power. Consequently, the amount of accessible new simulation data adds up to the already existing amount. However, even when using easy-to-use finite element software tools, errors can occur during the setup of finite element simulations, and users should be warned about certain mistakes by automatic algorithms. To use the vast amount of available finite element simulations for a data-driven finite element support tool, in this paper, a methodology will be presented to transform different finite element simulations to unified matrices. The procedure is based on the projection of nodes onto a detector sphere, which is converted into a matrix in the next step. The generated matrices represent the simulation and can be described as the DNA of a finite element simulation. They can be used as an input for any machine learning model, such as convolutional neural networks. The essential steps of preprocessing the data and an application with a large dataset are part of this contribution. The trained network can then be used for an automatic plausibility check for new simulations, based on the previous simulation data from the past. This can result in a tool for automatic plausibility checks and can be the backbone for a feedback system for less experienced user
Keywords: plausibility check; finite element simulation; spherical detector surface; deep neural network; convolutional neural network; simulation DNA

Approaches for the assembly simulation of skin model shapes - Schleich, Benjamin; Wartzack, Sandro (Computer-Aided Design, 2015)
Even though they are weakly noticed, geometric part deviations accompany our everyday life. These geometric deviations affect the assemblability and functional compliance of products, since small part variations accumulate through large-scale assemblies and lead to malfunction as well as decreased product reliability and safety. However, the consideration of part deviations in the virtual modelling of mechanical assemblies is an ongoing challenge in computer-aided tolerancing research. This is because the resulting assembly configurations for variant parts are far more complicated than for nominal assemblies. In this contribution, two approaches for the relative positioning of point based models are highlighted and adapted to the assembly simulation of Skin Model Shapes, which are specific workpiece representatives considering geometric deviations. The first approach employs constrained registration techniques to determine the position of variant parts in an assembly considering multiple assembly steps simultaneously, whereas the second utilizes the difference surface to solve the positioning problem sequentially. The application of these approaches to computer-aided tolerancing is demonstrated, though their applicability reaches various fields of industrial geometry.
Keywords: Computer-aided tolerancing; Skin model shapes; Relative positioning; Registration; Assembly simulation; Industrial geometry

Approach for the automated and data-based design of mechnical joints. - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2021)
As a result of the increasing challenges in the field of lightweight constructions, the demand for efficient joining technologies is continuously rising. For this purpose, cold forming processes offer an environmental friendly and fast alternative to established joining methods (e.g. welding). However, to ensure a high reliability, not only the selection of an appropriate procedure, but also the dimensioning of the individual joint is essential. While product designers can rely on a wide range of design principles for thermal processes, the dimensioning and evaluation of mechanical joining processes is mainly based on expert knowledge and a few experimental tests. Although few studies already investigated the numerical analysis of mechanical joints, an approach for the sustainable and consistent optimization of the strength and reliability of joining connections for varying use-cases is not available yet. Motivated by this lack, this paper presents an approach for the automated transfer of information within the process chain and the data-based analysis of mechanical joints by using clinching as an example. Therefore, the CRISP-DM reference model is used for the systematic data mining.<br

Approaching an ergonomic future: An affordance-based interaction concept for digital human models - Wolf, Alexander; Krüger, Daniel; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP Volume 84, 2019)
Digital human models offer great potential for the evaluation of physical human factors throughout all phases of product development. Unfortunately, digital human models lack a generic user-product interaction model to use them as universal and truly predictive CAE tools. In this contribution, we propose a concept for a generic and integrated interaction model based on the concept of affordances, the technology of CAD features and posture- and movement-prediction methods. Furthermore, we propose an affordance taxonomy, which shall enable a universal methodical description of interactions occurring during product us
Keywords: user-centered design; user-product interaction; digital human models; affordances; CAD features; human factors

A quality measure for comparing different feature deviations to perform sensitivity analysis in tolerancing - Ziegler, Philipp; Wartzack, Sandro (7th International Conference on Sensitivity Analysis of Model Output 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.aquali

A Quantitative Comparison of Tolerance Analysis Approaches for Rigid Mechanical Assemblies - Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, Volume 43, 2016)
Tolerance analysis is a key tool to predict the consequences of geometric variations on product quality. During the last decades, various approaches for the computer-aided tolerance analysis have been proposed, where each of them has specific advantages and disadvantages. In this contribution, three tolerance analysis approaches, namely tolerance stacks, vector loops, and the tolerance analysis based on the Small Displacement Torsor are quantitatively compared with the tolerance analysis based on Skin Model Shapes considering a typical case study. The novelty of the contribution lies in the profound assessment of these approaches and their results.
Keywords: Tolerance Analysis; Variation Simulation; Skin Model Shapes

A rapid CAE-based design method for modular hybrid truss structures - Walbrun, Simon; Witzgall, Christian; Wartzack, Sandro (Design Science, 2019)
The development of hybrid trusses made of carbon-fiber-reinforced plastic struts and aluminum knots is currently not standardized, and there is no overall method for the design, although it has been proven that mass reduction is feasible. This paper introduces a new method for computer-aided engineering based design of hybrid trusses using carbon-fiber-reinforced plastic struts and metal nodes based on a modular system. The method includes all design steps from topology optimization to computer-aided design model generation and offers support to the engineer. The method is discussed in theory. A case study is done with a beam-shaped truss. It shows that if the bisection optimization method is combined with further constraints, it is suitable for selecting the optimum struts from a modular system for the truss. The developed approach is a suitable method for designing hybrid trusses. The basis of the method has been developed and will be further detailed and extended.
CRIS-Team WoS Importer:2019-12-17

Architecture and realization of a selflearning engineering assistance system for the use within sheetbulk metal forming - Breitsprecher, Thilo; Wartzack, Sandro (Proceedings of the 9th Norddesign, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.archit

Architecture and realization of a self-learning engineering assistance system for the use within sheet-bulk metal forming - Breitsprecher, Thilo; Wartzack, Sandro (NordDesign 2012 - Proceedings of the 9th NordDesign Conference, 2012)
Substantial efforts have been taken in the past to integrate manufacturing related and design-relevant knowledge into the product development process. A common approach is to provide this knowledge to the designer by implementing a knowledge-based system (KBS), an expert system or, as it is referred to in this submission, an engineering assistance system. Keeping the knowledge base of this KBS up to date is a central issue and the necessary knowledge acquisition the bottleneck within the development and maintenance process of a KBS. This applies especially for KBS applications were the knowledge can be considered as dynamic, that is the design- and engineering-relevant knowledge changes within short periods of time. In this paper the emerging manufacturing technology sheet-bulk metal forming (SBMF) is taken as the background for the development and application of an engineering assistance system. To overcome the bottleneck of knowledge acquisition the architecture of the presented assistance system is equipped with a self-learning component, based on knowledge discovery in databases applications.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Engineering assistance system; Knowledge discovery in databases

A Review of Requirements and Approaches for Realistic Visual Perception in Virtual Reality - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
The amount of new virtual reality input and output devices being developed is enormous. Those peripherals offer novel opportunities and possibilities in the industrial context, especially in the product development process. Nevertheless, virtual reality has to face several problems, counteracting reliable use of the technology, especially in ergonomic and aesthetic assessments. In particular, the discrepancies in perception between the real world and virtual reality are of great importance. Therefore, we discuss these most important issues of current virtual reality technology and highlight approaches to solve them. First, we illustrate the use cases of VR in the product development process. In addition, we show which hardware is currently available for professional use and which issues exist with regard to visual perception and interaction. Derived from the depiction of a perfect virtual reality, we define the requirements to address visual perception and interaction. Subsequently we discuss approaches to solve the issues regarding visual perception and evaluate their suitability to enhance the use of virtual reality technology in engineering design.
Keywords: Virtual reality; Visualisation; Visual perception; Eye tracking; Conceptual design

A Semantic Annotation Pipeline towards the Generation of Knowledge Graphs in Tribology - Kügler, Patricia; Marian, Max; Dorsch, Rene; Schleich, Benjamin; Wartzack, Sandro (Lubricants, 2022)
Within the domain of tribology, enterprises and research institutions are constantly working on new concepts, materials, lubricants, or surface technologies for a wide range of applications. This is also reflected in the continuously growing number of publications, which in turn serve as guidance and benchmark for researchers and developers. However, those are almost impossible to keep up with due to their vast quantity and the associated complexity and diversity. Due to the lack of suited data and knowledge bases, knowledge acquisition and aggregation is still a manual process involving the time-consuming review of literature. Therefore, semantic annotation and natural language processing (NLP) techniques can decrease this manual effort by providing a semi-automatic support in knowledge acquisition. The generation of knowledge graphs from textual sources promises improved reuse and retrieval of information acquired from scientific literature in a structured way. Motivated by this, the contribution introduces a novel semantic annotation pipeline for generating knowledge graphs and streamline knowledge acquisition in the domain of tribology. The pipeline is built on BERT, a state-of-the-art language model and involves classic NLP tasks like information extraction, named entity recognition and question answering.<br
Keywords: tribology; tribo-testing; tribo-informatics; machine learning; artificial intelligence; semantic annotation; knowledge graph; natural language processing; tribAIn; BERT

A semantic web approach for structuring data-driven methods in the product development process - Gerschütz, Benjamin; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 32nd Symposium Design for X (DFX2021), 2021)
For the successful integration of data-driven methods in existing processes, it is first necessary to know these methods and their fields of application, potentials, and individual limits. This requires an easily accessible knowledge base. Depending on possible use cases and available data, this knowledge base should suggest methods that can lead to an optimization of the overall product development process. To prevent the knowledge base from being a rigid catalogue, it is essential to link it to the existing methods of the product development process. This contribution presents an approach based on the semantic web application Semantic MediaWiki, that ensures a connected representation of method knowledge and at the same time enables a link with use cases in the product development proces
Keywords: digital engineering; data-driven-method; design-process; semantic-web

A simplified approach towards integrating biomechanical simulations into engineering environments - Krüger, Daniel; Miehling, Jörg; Wartzack, Sandro (Proceedings of NordDesign 2012, the 9th NordDesign conference, 2012)
In human-centered design biomechanical simulations can be used to predict the characteristics of the interaction between the user and the product in order to optimize the design with respect to ergonomics. However since biomechanical modelling has its origin in medical applications the simulation procedure is not familiar to product designers yet. In this paper an approach towards the integration of an arbitrary biomechanical simulation system into the CAD/CAE engineering environment is proposed. The objective is to enable the analysis of user-product interaction in early design phases based on virtual prototypes. A major focus of this work is the fast acquisition of human body measures and motion sequences using an inexpensive depth imaging device originally designed for entertainment applications
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.asimpl
Keywords: biomechanics; simulation; human-centred design; ergonomics

A simplified simulation method for adhesively bonded hybrid structures - Witzgall, Christian; Wartzack, Sandro (International Conference on Impact Loading of Structures and Materials, 2016)

A Simulation-Based Design Approach For Endless-Fiber Reinforced Composite Structures - Klein, Daniel; Völkl, Harald; Wartzack, Sandro (Proceedings of the Seminar "Simulation of Composites - Ready for Industry 4.0", 2016)
The design of endless-fiber reinforced composites is a highly challenging task since the mechanical properties are highly anisotropic and several mutually dependent parameters have to be defined. Therefore product developers have to be supported through design approaches and methods to exploit the whole lightweight potential of this unique material. However, many existing design approaches and methods are restricted to simple geometries and load cases, cause high modelling and computation times or lead to an unstructured design process. For this reason a new design approach is introduced consisting of four consecutive steps. The advantages of this new approach are the resulting structured design process, the low modeling and computational effort and the applicability to arbitrary load cases. The single steps of the design approach as well as its possible results will be demonstrated with the help of the front wing connection of a race car.
Keywords: Leichtbau; Simulation; Konstruktion; Faserverbundwerkstoffe

A Software Tool for the Graph-Based Visualization of Complex Relations Between Product Properties and Characteristics - Luft, Thomas; Schuh, Patricia; Wartzack, Sandro (Research into Design for Communities, Volume 1 Proceedings of ICoRD 2017, 2017)
As products have to meet many different and contradictory requirements, product developers are facing major challenges. The fundamental prerequisite for developing successful products is to understand how desired product properties can be realized by setting appropriate product characteristics. The objective of this paper is to develop a software tool that supports product developers by visualizing the complex network of relations between properties and characteristics. This gives developers a better understanding of the many different relations in product models and can thus make more efficient and more targeted decisions.
Keywords: Design management; Design evaluation; Decision making; Product visualization; Complexity management

Assessment of the Suitability of Selected Linear Actuators for the Implementation of the Load-Adaptive Biological Principle of Redundant Motion Generation - Bartz, Marcel; Jüttner, Michael; Halmos, Fabian; Uhlich, Elias; Klein, Max; Drumm, Patricia; Dreßler, Erkan; Martin, Sina; Walter, Jonas; Franke, Jörg; Wartzack, Sandro (Biomimetics, 2024)
The load-adaptive behavior of the muscles in the human musculoskeletal system offers great potential for minimizing resource and energy requirements in many technical systems, especially in drive technology and robotics. However, the lack of knowledge about suitable technical linear actuators that can reproduce the load-adaptive behavior of biological muscles in technology is a major reason for the lack of successful implementation of this biological principle. In this paper, therefore, the different types of linear actuators are investigated. The focus is particularly on artificial muscles and rope pulls. The study is based on literature, on the one hand, and on two physical demonstrators in the form of articulated robots, on the other hand. The studies show that ropes are currently the best way to imitate the load-adaptive behavior of the biological model in technology. This is especially illustrated in the context of this paper by the discussion of different advantages and disadvantages of the technical linear actuators, where ropes, among other things, have a good mechanical and control behavior, which is very advantageous for use in an adaptive system. Finally, the next steps for future research are outlined to conclude how ropes can be used as linear actuators to transfer load-adaptive lightweight design into technical applications.<br
Keywords: load-adaptive systems; musculoskeletal lightweight design; lightweight design robotics; linear actuators; redundant motion generation; tension chording; cable-driven robotics; rope pulls; artificial muscles

Assistance system for automated and knowledge-based setup and evaluation of design-accompanying Finite Element Analyses - Kestel, Philipp; Sprügel, Tobias; Wartzack, Sandro (Automotive Simulation World Congress, 2016)
Due to growing demands for high functional integration, lightweight-design as well as shorter innovation cycles computer-based simulation techniques, such as FEA (Finite Element Analyses), has become an essential part in automotive development. However, an efficient use of FEA requires early application in the development process. Furthermore, extensive specialist knowledge is a crucial prerequisite to perform reliable simulations. Due to time constraints, design accompanying FEA are performed too rarely by experienced simulation engineers or, if they are applied by non-expert simulation users, are not sufficiently accurate. Thus, a knowledge-based FEA assistance system is presented, to provide the necessary expert knowledge as a function of decisive factors such as the phase in the development process, applied manufacturing processes and analyzed components. The assistance system automates the setup, interpretation and plausibility check of early applied simulations on the basis of the existing CAD (Computer Aided Design) working environment of design engineers, exemplarily implemented for steel construction and die-cast aluminum gear box housings.

A statistical method to identify main contributing tolerances in assemblability studies based on convex hull techniques - Ziegler, Philipp; Wartzack, Sandro (Proceedings of the 13th CIRP Conference on Computer Aided Tolerancing, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.astati

A SYSTEMATIC COLLECTION OF NATURAL INTERACTIONS FOR IMMERSIVE MODELING FROM BUILDING BLOCKS - Harlan, Jakob; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the International Conference on Engineering Design (ICED21), 2021)
The increased availability of affordable virtual reality hardware in the last years boosted research and development of such systems for many fields of application. While extended reality systems are well established for visualization of product data, immersive authoring tools that can create and modify that data are yet to see widespread productive use. Making use of building blocks, we see the possibility that such tools allow quick expression of spatial concepts, even for non-expert users. Optical hand-tracking technology allows the implementation of this immersive modeling using natural user interfaces. Here the users manipulated the virtual objects with their bare hands. In this work, we present a systematic collection of natural interactions suited for immersive building-block-based modeling systems. The interactions are conceptually described and categorized by the task they fulfi
Keywords: Virtual reality; Conceptual design; Computer Aided Design (CAD)

A transdisciplinary approach to model user-product interaction: how the collaboration between human sciences and engineering design could improve product development for physically impaired people - Krüger, Daniel; Miehling, Jörg; Wartzack, Sandro (International Workshop on the Future of Transdisciplinary Design, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.atrans

Ausarbeitungsleitfaden für Nutzerstudien zur Evaluation von XR-Interfaces in der Produktentwicklung - Harlan, Jakob; Schleich, Benjamin; Wartzack, Sandro (Entwerfen Entwickeln Erleben in Produktentwicklung und Design 2021, 2021)
Technologien der erweiterten Realität (extended reality, XR) finden im gesamten Produktentwicklungsprozess Anwendung. Insbesondere Systeme zur aktiven Erzeugung und Veränderung digitaler Produktdaten bieten noch viel Potential. Die Erforschung und Entwicklung dieser immersiven Interfaces beruht maßgeblich auf der Evaluation durch Nutzerstudien, denn nur so kann die Einsatztauglichkeit der Mensch-Maschine-Schnittstellen seriös beurteilt und verglichen werden. Bei der Konzeptionierung und Durchführung dieser Nutzerstudien gibt es viel zu beachten. In dieser Arbeit wird ein Leitfaden für das Design von Evaluationen von XR Interfaces für die Produktentwicklung präsentiert. Zu Beginn müssen die Fragestellungen festgelegt werden, welche die Studie beantworten soll. Ausgehend von die- sen müssen die zu testenden Versuchsbedingungen, die gestellten Aufgaben, die aufgenommen Metriken, die gewählten Probanden und der geplante Ablauf festgelegt werden. Zusätzlich zu der allgemeinen Darlegung wird das Vorgehen anhand eines Fallbeispiels an- gewandt. Die Gestaltung einer Nutzerstudie zur Evaluation der Usability und Eignung eines neuartigen Virtual Reality Interfaces zur natürlichen Gestaltung von Vorentwürfen wird vorgestellt.<br
Keywords: Virtuelle Realität; Erweiterte Realität; Nutzerstudie; Produktentwicklung; Mensch-Maschine-Schnittstelle

Auslegung eines CFK-Schubfelds über einen simulationsbasierten Ansatz - Völkl, Harald; Schemat, Markus; Weigert, Andreas; Wartzack, Sandro (ATZ - Automobiltechnische Zeitschrift, 2020)
Der Auslegungsprozess von CFK-Strukturen läuft häufig wenig strukturiert ab, ist geprägt von zahlreichen Iterationen und damit zeitaufwändig. Ein neu entwickelter, simulationsbasierter Ansatz kann durch sein strukturiertes Vorgehen helfen, die Auslegung effizienter zu gestalten. In einem Gemeinschaftsprojekt der BMW Group und dem Lehrstuhl für Konstruktionstechnik der Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU) wurde der neue Ansatz anhand eines Schubfeldes erprob

Auslegung und Gestaltung additiv gefertigter Bauteile - Wartzack, Sandro; Wittmann, Stefan; Stuppy, Julia; Tremmel, Stephan (Additive Fertigung, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.FT.FT-KLMEFK.ausleg

Auslegung von amorphen Kohlenstoffschichten für Knie-Totalendoprothesen - Wartzack, Sandro; Rothammer, Benedict; Marian, Max; Wolf, Alexander; Miehling, Jörg; Tremmel, Stephan (WiGeP News, 2019)

Auslegung von CFK-Strukturen – ein neuer Ansatz - Klein, Daniel; Kieser, Christoph; Wartzack, Sandro (Lightweight Design, 2016)
Die Auslegung von CFK-Strukturen ist ein oft unstrukturierter Prozess, der von zahlreichen Iterationen geprägt ist und ein hohes Maß an Erfahrung erfordert. Im Rahmen der Entwicklung einer Frontflügelanbindung in CFK-Sandwich-Bauweise wurde deshalb der neuentwickelte Ansatz mfkCODE angewendet, der eine strukturierte Auslegung beanspruchungsgerechter CFK-Bauteile erlaubt.
Keywords: Leichtbau; Faserverbundwerkstoffe; Simulation

Auswirkungen von passungsbedingten Deformationen auf das Radialspiel von Wälzlagerungen - Aschenbrenner, Alexander; Heling, Björn; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 2. Summer School - September 2015, 2015)
Keywords: Statistische Toleranzanalyse; Toleranz; Wälzlager; Radialspiel

Automated point-based tolerance analysis model creation for sheet metal parts - Litwa, Frank; Gottwald, M; Bohn, M; Klinger, J; Walter, Michael; Wartzack, Sandro; Vielhaber, M (Proceedings of the 13th CIRP Conference on Computer Aided Tolerancing, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.automa

Automotive Premium Quality Improvement by High-End-Visualization - Striegel, Serena; Schleich, Benjamin; Zielinski, Daniel; Wartzack, Sandro (ASME 2017 International Mechanical Engineering Congress and Exposition, Volume 2: Advanced Manufacturing, 2017)
Volatile markets, tough customer expectations, and short product life cycles are just some of the challenges the automotive industry has to deal with. In this context, important quality features are expressed as key product characteristics (KPC). The process of defining and reviewing such KPCs concerns each department of an automobile company. This paper presents a method for an intersubjective problem understanding of inter-divisional working groups and a common product KPC’s definition. The scientific contribution lies in the field of quality assessment for the premium-segment automotive industry, while the novelty can be found in providing the opportunity to take quality decisions based on variation simulations and on high-end-visualizations. The proposed method aims to realize and implement a higher premium quality standard and, at the same time, to reduce the number of physical prototypes, to shorten development times and to facilitate an intersubjective problem understanding. In relation to the developed method, an industrial application and its results are presented.
Keywords: Visualisation

A variational simulation framework for the analysis of load distribution and radial displacement of cylindrical roller bearings - Aschenbrenner, Alexander; Schleich, Benjamin; Tremmel, Stephan; Wartzack, Sandro (Mechanism and Machine Theory, 2020)
In many technical systems, rolling bearings are critical machine elements concerning accuracy and lifetime. Their load distribution and radial displacement are directly linked to the accuracy and the fatigue life of rolling bearings. However, load distribution and radial displacement form a complex interdependency. Geometric deviations further influence this mutual connection. Although there are several approaches to determine the load distribution and the radial displacement, most of them are either too simplistic, allowing only the consideration of dimensional deviations, or too sophisticated and therefore unsuitable for a statistical evaluation of geometric deviations. Hence, the main purpose of this contribution is to provide a method for the determination of load distribution and radial displacement of cylindrical roller bearings that allows the consideration of geometric deviations as well as statistical evaluation of these deviations. Moreover, applying the method to a use case shows, whether the consideration of geometric deviations in the determination of load distribution and radial displacement is reasonable. The novelty of the contribution is, therefore, the provision of a statistical variational simulation framework for the analysis of load distribution and radial displacement of rolling bearing
Keywords: Geometric variation simulation; Rolling bearing; Tolerance analysis; Load distribution; Radial deflection; Internal bearing clearance

A visualization methodology for evaluating parts made of short fiber reinforced thermoplastics regarding their lightweight potential - Gruber, Georg; Wartzack, Sandro; Kößler, Johannes (Proceedings of the 19th International Conference on Engineering Design, 2013)
Injection molded, short fiber reinforced thermoplastics are a promising lightweight material. However, the component design is getting complex with this type of material due to the process induced fiber orientation. To achieve substantial progress in lightweight design, the resulting anisotropic material properties have to be taken advantage of effectively. The most important correcting variables influencing the fiber orientation are the part's geometry and the gate design (position and type of gates). The goal of the present paper is introducing a new evaluation method, supporting the product developer at detecting the most appropriate geometry and gate layout. The basic idea behind the new approach is examining the deviations between the load path and the fiber orientation pattern. With the help of new quality criteria it can be rated to which extent load path and fiber orientation are in harmony. The methodology is implemented as a software tool, delivering a mean quality criterion per part as well as a contour plot enabling also the analysis of the local distribution of the focused quality criterion. The potential of the new approach is demonstrated within a brief case study.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.avisua
Keywords: Decision making; Lightweight design; Short fiber reinforced thermoplastics; Simulation; Visualization

Avoidance of unnecessary design iterations by monitoring the product´s degree of maturity - Krehmer, Hartmut; Meerkamm, Harald; Wartzack, Sandro (Proceedings of the 11th International Design Conference DESIGN 2010, 2010)
Increasing requirements as well as product development processes getting more and more complex cause an increased likelihood of unneccessary design iterations. So, developers need a framework to avoid unnecessary and time-consuming detours by assessing effects of each possible change. Aim of this contribution is to identify key factors for the avoidance of unnecessary iterations and to present approaches for coping these challenges. Furthermore a framework for the avoidance of unnecessary iterations based on a continuous monitoring the product's degree of maturity is introduced.
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.avoida
Keywords: Characteristics; Design iterations; Product's degree of maturity; Properties

Baukastensystem für CFK-Fachwerkstrukturen – Diskrete Optimierung der Strebenquerschnitte - Walbrun, Simon; Wartzack, Sandro (Design for X - Beiträge zum 30. DfX-Symposium, 2019)
Fiber-reinforced plastics have a high potential for lightweight structures due to their high specific strength and stiffness. A modular system enables a reduction of the manufacturing costs for trusses by standardizing the components. The subdivision of the truss struts into groups and the selection of the profiles for the strut groups can be done by optimization with a genetic algorithm and the initial population generation by the bisection method. The proposed method reduces the number of necessary iterations and improves the optimum in comparison to the previous descriptions
Keywords: Genetic algorithms; Initial population; Optimization; Self-adaptive member grouping

Berechnung beanspruchungsgerechter Faserorientierungen in CFK-Strukturen - Klein, Daniel; Caballero, Steffen; Wartzack, Sandro (ANSYS Conference & 31th CADFEM Users Meeting, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.berech
Keywords: Leichtbau; Composites; Simulation

Berechnung beanspruchungsgerechter Patch-Geometrien für die Auslegung von CFK-Strukturen in den frühen Phasen der Produktentwicklung - Klein, Daniel; Scheler, Kaja; Wartzack, Sandro (kunststoffe + SIMULATION 2014, 2014)
Keywords: Leichtbau; Composites

Berechnung und Analyse von Reibmoment- und Temperaturverlauf von Wälzlagern unter Drehzahl- und Lastkollektiven - Stahl, Thomas; Tremmel, Stephan; Wartzack, Sandro; Meerkamm, Harald (VDI-Fachtagung Gleit- und Wälzlagerungen 2011: Gestaltung, Berechnung, Einsatz (VDI-Berichte 2147), 2011)
Der Beitrag beschreibt einen Berechungsalgorithmus zur Ermittlung der Wälzlagerreibung unter Berücksichtigung von Drehzahl- und Lastkollektiven. Hierzu werden die grundlegenden Vorgänge der Wärmedissipation an einer Wälzlagerung und deren Zusammenhänge aufgezeigt, sowie Berechnungsmöglichkeiten der einzelnen Wärmeströme vorgestellt. Dabei wird auch die Einbauumgebung berücksichtigt, da die Wärmedissipation über Gehäuse, Welle, Fundament und weiteren damit in Kontakt stehenden Bauteilen die Temperatur im Lager maßgeblich beeinflusst. Anschließend werden die Ergebnisse dieser Berechnung mit den Messwerten der experimentellen Validierung gegenübergestellt. In diesem Zusammenhang wird gezeigt, wie sich unterschiedliche Kollektivausprägungen und Lagerparameter auf Reibung und Temperatur auswirken. Abschließend wird der „Bearing Friction Calculator“ vorgestellt. Ein Software-Werkzeug, das es dem Konstrukteur erlaubt, bereits in frühen Phasen des Produktentwicklungsprozesses die entstehende Reibung und Temperatur im Wälzlager unter Berücksichtung von Drehzahl- und Lastkollektiven zu ermitteln, um so eine optimierte Auslegung der Wälzlagerung durchführen zu können.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.berech
Keywords: Reibungsberechnung; Wärmeübertragung; Reibungsmessung; Kollektivparameter; Wälzlagerauslegung

Berücksichtigung der Schmierstoffhydrodynamik in der Käfigführung bei der Wälzlagerdynamiksimulation - Seiler, Katrin; Stadler, Marion; Tremmel, Stephan; Hahn, Bodo; Graf-Goller, Oliver; Wartzack, Sandro (SMK2014 Schweizer Maschinenelemente Kolloquium, 2014)
Bei Wälzlagern die zum Beispiel hohen Zentripetalbeschleunigungen ausgesetzt sind, kann die Reibung an den Käfigkontakten sehr stark zunehmen. Die Schmierstoffhydrodynamik in den Käfigkontakten ist in diesen Fällen in der Wälzlagermehrkörpersimulation zu berücksichtigen. Hierbei reicht es im Fall des Käfig/Außenring-Kontakts nicht aus, ausschließlich den hydrodynamischen Kontakt an den Käfigstirnringen zu berücksichtigen. Um die Käfigführung realistisch darstellen zu können, ist zusätzlich der Kontakt an den Käfigstegen, an denen ebenfalls hydrodynamische Effekte Einfluss haben, abzubilden. Der Beitrag stellt analytische Berechnungsmodelle für die Abbildung der Hydrodynamik an den Stegen im Käfig/Ring-Kontakt vor. Die Modelle beinhalten die Berechnung der Normalkraft, der Schmierstoffdämpfung und der Reibung aufgrund der Schmierstoffscherung. Die Berechnungsmodelle wurden in das Wälzlagermehrkörpersimulationsprogramm CABA3D implementiert und mit dem Gleitlagerberechnungsprogramm COMBROS abgeglichen. Anhand neuer Simulationsergebnisse wird im Beitrag der Einfluss der Hydrodynamik auf das Lagergesamtreibmoment und die Lagerkinematik dargestellt.
Keywords: Wälzlager; MKS; Tribologie; Hydrodynamik

Berücksichtigung von produktionsspezifischen Abweichungen im interdisziplinären Toleranzmanagement - Heling, Björn; Oberleiter, Thomas; Rohrmoser, Andreas; Kiener, Christoph; Schleich, Benjamin; Hagenah, Hinnerk; Merklein, Marion; Willner, Kai; Wartzack, Sandro (Industriekolloquium der Forschergruppe FOR 2271, 2019)
LFT Import::2019-08-05 (2353)

Berücksichtigung von Wechselwirkungen zwischen Abweichungen in der statistischen Toleranzanalyse - Walter, Michael; Sprügel, Tobias; Ziegler, Philipp; Wartzack, Sandro (Konstruktion, 2015)
Die Toleranzanalyse ermöglicht dem Konstrukteur die quantitative Beurteilung der Auswirkungen von Abweichungen auf Funktion und Ästhetik eines Produktes; unter anderem anhand der sogenannten Beitragsleister. Jedoch erlauben bisherige Methoden der Beitragsleister-Analyse lediglich die Berücksichtigung direkter Auswirkungen der Abweichungen; mögliche Wechselwirkungen zwischen Abweichungen und deren Auswirkungen bleiben somit unberücksichtigt. Dieser Beitrag widmet sich dem Einsatz der globalen Sensitivitätsanalyse zur Berechnung der Beitragsleister. Diese ermöglicht die Bestimmung der direkten Effekte der Abweichungen als auch deren indirekte Effekte aufgrund von Wechselwirkungen zwischen Abweichungen.
Keywords: Wechselwirkungen zwischen Abweichungen; Statistische Toleranzanalyse; varianzbasierte Sensitivitätsanalyse; Toleranz-Kosten-Kurven

Berücksichtigung zyklischer Materialdegradation in der crashsimulation kurzfaserverstärkter Thermoplaste - Witzgall, Christian; Huber, Martin; Wartzack, Sandro (Konstruktion, 2020)
Everything ages – including components made of short-fibre-reinforced plastic, which are frequently used in modern vehicle design. A thousand times repeated mechanical stress from service load cases leads to a degradation of the mechanical properties, which influences the crash behaviour of the structure. However, this effect is currently not taken into account in the assessment of crash safety due to the use of material data obtained from material samples in new condition. The present article therefore presents a method that allows the effects of this material degradation to be taken into account in numerical crash simulation – and thus an assessment of crash safety in various phases of life.

Beschichtete Kunststoffe für funktionsintegrierte Leichtbaulösungen - Sander, Thomas; Tremmel, Stephan; Wartzack, Sandro (Konstruktion, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.beschi

Besonderheiten bei der Auslegung und Gestaltung lasergesinterter Bauteile - Wartzack, Sandro; Drummer, Dietmar; Wittmann, Stefan; Stuppy, Julia; Rietzel, Dominik; Tremmel, Stephan; Kühnlein, Florian (RTejournal - Forum für Rapid Technologie, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KLMEFK.besond

Bestimmung und Berücksichtigung der Einzelpunktmessunsicherheit in virtuellen Toleranzanalysen - Heling, Björn; Müller, Andreas; Schleich, Benjamin; Hausotte, Tino; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)

Bewertung und Optimierung der Faserverbundeignung von Leichtbaustrukturen in den frühen Phasen der Produktentwicklung - Klein, Daniel; Witzgall, Christian; Wartzack, Sandro (NAFEMS Online-Magazin, 2014)
Die Auslegung von Produkten aus faserverstärktem Kunststoff (FVK) stellt an Produktentwick-ler besonders hohe Anforderungen, denn nur wenn es gelingt, die Fasern richtig zu belasten, kann das Leichtbaupotential von FVK ausgenutzt werden. Dabei ist es zwingend erforderlich, dass bereits in den frühen Phasen der Produktentwicklung das Bauteildesign kritisch in Bezug auf dessen Eignung für FVK hinterfragt wird. Eignet sich ein Bauteil aufgrund seiner Geometrie oder der Belastungsart nicht, kann dies selbst durch die beste Auslegung und Simulation nicht mehr ausgeglichen werden. In dem folgenden Beitrag wird ein erster Algorithmus vorgestellt, der es erlaubt, basierend auf einfachen FE-Simulationen mit isotropem Materialmodell, die Faserverbundeignung von Leichtbaustrukturen zu berechnen und zu visualisieren. Dazu werden über bewährte Theorien, wie etwa der klassischen Laminattheorie, Kriterien hergeleitet und diskutiert, die zusammen die Bewertung eines Bauteils zulassen. Ziel des Bewertungsalgorithmus ist es, zum einen eine Aussage über die generelle Eignung der Struktur für einen FVK zu geben und zum anderen auch Bereiche anzudeuten, die noch optimiert werden müssen. Am Ende des Beitrags wird gezeigt, dass so Verbesserungspotentiale abgeleitet werden können, die zu einer signifikanten Optimierung der Bauteileigenschaften führen. Es ist an dieser Stelle unbedingt zu erwähnen, dass das Hauptaugenmerk dieses Beitrags auf endlos-kohlefaserverstärktem Kunststoff (CFK) liegt. Weite Teile des Beitrags können aber direkt auf viele unterschiedliche FVK übertragen werden.
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.bewert

Biomechanical Digital Human Models: Chances and Challenges to Expand Ergonomic Evaluation - Peters, Markus; Quadrat, Eric; Nolte, Alexander; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro; Leidholdt, Wolfgang; Bauer, Sebastian; Fritzsche, Lars; Wischniewski, Sascha; et al. (Human Systems Engineering and Design, 2018)
Nowadays, ergonomic evaluation of work can be done using Digital Human Models (DHM). One advantage is to reduce the need for corrective measures by supporting a more prospective ergonomic work design. Although ergonomic models provide useful information for risk assessment, single working tasks with minor changes in work place design are difficult to evaluate. Instead, biomechanical models can analyze single movements or body postures, taking internal forces in muscles and joints into account. Therefore, the main goal of this work is to establish an interface between a biomechanical human model (AnyBody) and the “Editor for manual work activities” (ema) to enrich ergonomic evaluation with biomechanical parameters. First results demonstrate that the automatically generated movements of ema showed some specific deviations relative to the subjects’ movements in experimental conditions. Optimization of kinematic data in AnyBody is necessary to ensure more physiological movements which are highly valuable for ergonomic evaluatio
Keywords: Human factors; Digital Human Models; Ergonomics; Biomechanics; Anthropometry; Risk assessment

Biomechanischer Simulator zur prä-operativen Abschätzung und Optimierung der post-operativen Muskelfunktion am Beispiel der Revisionsendoprothetik des Hüftgelenks - Miehling, Jörg; Forst, Raimund; Wartzack, Sandro; Sesselmann, Stefan (Deutscher Kongress für Orthopädie und Unfallchirurgie - PO11 Beste klinische Abstracts, 2016)
Fragestellung: Die Anzahl der operierten Hüft- und Knie-Totalendoprothesen (TEP) in Deutschland steigt immer weiter an. Auch die Revisionsendoprothetik gewinnt immer mehr an Bedeutung. Dabei wird versucht, die gelenkanatomischen Parameter zu rekonstruieren. Biomechanische Parameter der Muskulatur finden in der präoperativen Planung kaum Berücksichtigung. Vor allem bei Revisionsimplantaten des Hüftgelenks können die ursprüngliche Gelenksgeometrie und defekte Muskelansätze aber häufig nicht rekonstruiert werden. Die Rehabilitation verlängert sich dadurch deutlich oder ist nicht mehr vollständig möglich. Daraus ergibt sich die Frage, ob und wie biomechanische Simulationen dazu beitragen können, den Operateur in der Planung zu unterstützen, sodass der Patient nach der OP geringstmöglich in seiner Lebensführung eingeschränkt ist. Methodik: Um den Einfluss der Implantatgeometrie sowie der anatomischen Gegebenheiten im Revisionsfall auf die Muskelfunktion abschätzen und optimieren zu können, wurde ein biomechanischer Simulator entwickelt. Das Muskel-Skelett-System des Menschen wird als durch Muskeln aktuiertes biomechanisches Mehrkörper-System nachgebildet. Die Gelenk- und Muskelgeometrie kann beliebig variiert werden. Beim vorgestellten Hüft-Simulator wird die Position des Trochanter major bezüglich des Drehzentrums sowie die Position der Hüftpfanne im Becken in kartesischen Koordinaten beschrieben. Aus der Trochanter-Position können CCD-Winkel, AT-Winkel, Offset und Beinlängendifferenz berechnet werden. Der Simulator kann nun den Einfluss der kinematischen Veränderungen durch das simulierte Kunstgelenk auf die Drehmomenterzeugung der einzelnen Muskelstränge in einer bestimmten Körperhaltung oder Bewegung berechnen. Defekte Muskeln oder Muskelanteile sind durch die Software ebenfalls simulierbar. Für die Hüftsimulation wurde der einbeinige Stand gewählt, da dieser der Standphase beim Gehen stark ähnelt. Ergebnisse und Schlussfolgerung: Die durchgeführten Simulationen zeigen, dass biomechanische Betrachtungen in die vorhandenen Tools zur Operationsplanung integriert werden sollten. Dem Operateur kann ein Werkzeug an die Hand gegeben werden, das ihn bezüglich der Biomechanik schon bei der Planung einer TEP unter Berücksichtigung der anatomischen Gegebenheiten sinnvolle Parameterbereiche erkennen lässt. Bereits kleine Veränderungen in der Positionierung der Implantate können dabei zu beträchtlichen Unterschieden in der Momenterzeugung durch die beteiligten Muskeln führen.
Keywords: Biomechanische Simulation; Muskelfunktion; Endoprothetik; Revision; Hüfte

Biotribological behavior of amorphous carbon coatings on Co28Cr6Mo alloy and UHMWPE - Neusser, Kevin; Rothammer, Benedict; Marian, Max; Bartz, Marcel; Wartzack, Sandro (4th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2021)
Endoprosthetic replacement of the joint intends to restore the functionality and to provide the patient with a pain-free and more mobile life. However, aseptic loosening of the total knee arthroplasty (TKA) is a major cause of early prosthesis failure and is multifactorial in etiology with wear debris removed from the implant materials being largely responsible. For this reason, a great effort is made to reduce polymeric inlay wear by applying tribologically effective surface modifications. Thus, this study concentrated on the effectiveness of wear-reducing amorphous carbon coating systems on the materials Co28Cr6Mo and UHMWPE. The tribological impact of the carbon coating systems can be particularly enhanced by a good adhesion to the substrate. Therefore, specific attention was also paid to the investigation of adhesion. The tribological behavior of the coated material pairings in comparison to the uncoated pairings was investigated utilizing a climate-controlled pin-on-disc tribometer in rotational sliding mode. The tribological behavior was studied under mixed lubrications conditions for a total number of 200 000 sliding cycles. Bovine serum, tempered to 37 °C, was used as a substitute synovial fluid. The wear rates were determined using light and laser scanning microscopy every 20 000 cycles. Thereby, various wear mechanisms were detected, which in turn affected the coefficient of friction. The strong wear traces on UHMWPE indicated abrasive and adhesive wear. Consequently, the present study showed the applicability of well-adhering coatings to the considered materials used for applications in medical technology and the potential for wear reduction. Furthermore, the tribological characteristics obtained serve as a basis for further development of the coating systems.<br

Biotribological behavior of amorphous carbon coatings on Co28Cr6Mo alloy and UHMWPE under boundary friction conditions in sliding contact - Neusser, Kevin; Rothammer, Benedict; Marian, Max; Bartz, Marcel; Wartzack, Sandro (62. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen., 2021)
Zusammenfassung: Nach einem Knie-Gelenkersatz wirkt sich Verschleiß infolge biotribologischer Vorgänge maßgeblich auf die Standzeit von Totalendoprothesen (TEP) aus. Aufgrund freigesetzter Abriebpartikel, insbesondere aus dem Kunststoff-Inlay der Tibia-Komponente, kommt es häufig zu Knochenabbaureaktion im periprothetischen Knochengewebe der Prothesenverankerung und somit zu einer aseptischen Lockerung. Ansätze hinsichtlich der Beschichtung artikulierender Oberflächen mit amorphen Kohlenstoffschichten (DLC) stellen Bemühungen dar, den Verschleißprozessen biokompatibel entgegenzuwirken. In diesem Beitrag wird die tribologische Wirksamkeit amorpher Kohlenstoffschichtsysteme in einem abstrahierten biotribologischen Versuch unter körpernahen Randbedingungen und Belastungskollektiven mittels eines Stift/Scheibe-Tribometers aufgezeigt. Abstract: Wear due to biotribological processes has a considerable influence on the service life of a total knee replacement. Released abrasion particles, especially from the polymeric inlay of the tibial component, may cause bone resorption in the periprosthetic bone tissue, leading to aseptic loosening. Introducing a tribologically effective diamond-like carbon (DLC) coating to the articulating surfaces represents an approach to prevent wear processes in a biocompatible manner. In this study, the tribological effectiveness of amorphous carbon coating systems is evaluated using an abstracted pin-on-disk experiment under near-body boundary conditions and load collectives.
Keywords: Total knee replacement; DLC coating; biotribology; wear; biocompatibility; UHMWPE; pin-on-disk

Biotribological behavior of MXene-UHMWPE composites - Marian, Max; Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Rosenkranz, Andreas (77th STLE Annual Meeting & Exhibition, 2023)
MXenes are a relatively new class of 2D transition metal carbides, nitridesand carbonitrides receiving increasing attention in tribologicalapplications due to their self-lubricating character. A prospectiveapplication of MXenes is their addition to UHMWPE with the overallpurpose to improve the biotribological behavior of polymericcomponents of load-bearing implants. Within this study, Ti3C2Tx-UHMWPE composites with varying MXene content were biotribologicallyanalyzed using pin-on-disk tribometer tests. Thereby, a friction reductionby up to 22% compared to pure UHMWPE was demonstrated. Thedetermined wear rates of the disks considerably decreased by up to 43%due to the addition of MXenes. Furthermore, the composite-disksreduced the wear rates of the tested CoCr-pins by up to 19%. Both the reduction of friction and wear underline the great potential of MXenes asa reinforcement phase in UHMWPE to improve the biotribologicalbehavior and service life of biomedical applicatio

Biotribological behavior of MXene-UHMWPE-composites for total knee arthroplasty - Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Marian, Max (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)
MXenes are a relatively new class of two-dimensional transition metal carbides, nitrides and carbonitrides experiencing increasing attention for tribological applications. Due to their multi-layer structure with relatively weak inter-layer bonding, a self-lubricating character is enabled. A possible, but not yet explored, application of MXenes is the addition to UHMWPE with the aim to improve the biotribological behavior of tibial inlays of total knee arthroplasties (TKA). Within this study, Ti3C2Tx-UHMWPE-composites with 0.5 wt.‑%, 1.0 wt.‑% and 2.0 wt.‑% MXenes were biotribologically tested using a pin-on-disk tribometer in oscillating sliding mode lubricated with diluted bovine calf serum at 37 °C. Thereby, a reduction of the coefficient of friction by up to 22 % compared to pure UHMWPE was demonstrated and the determined wear rates of the disks decreased considerably by 25 % (0.5 wt.‑% and 1.0 wt.‑%) and 43 % (2.0 wt.‑%). Furthermore, the composite-disks reduced the wear rates of the tested Co28Cr6Mo-pins by up to 19 %. Both the reduction of friction and wear show the great potential of MXenes as a reinforcement phase to UHMWPE to improve the biotribological behavior of tibial inlays and thus, increase the service life of TKA in the long-ter

Biotribological behavior of ta-C coatings for load-bearing implants - Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Weihnacht, Volker; Marian, Max (4th International Brazilian Conference on Tribology – TriBoBR 2023, 2023)
1. Introduction Amorphous/diamond-like carbon (DLC) coatings deposited on the articulating surfaces of total hip (THR) or total knee replacements (TKR) have the potential to enhance the overall biotribological behavior and longevity [1-2]. This requires excellent adhesion to soft and hard implant materials, biocompatibility as well as superior mechanical properties and wear resistance [3]. 2. Materials and Methods Medical grade Co28Cr6Mo (CoCr), Ti6Al4V (Ti64) and ultrahigh molecular weight polyethylene (UHMWPE) were studied as substrate materials. Tetrahedral amorphous carbon (ta-C) coatings were deposited by plasma-filtered pulsed laser-arc technique using a commercial PVD coating system. The surface topography, cytocompatibility as well as mechanical properties and adhesion of ta-C coatings were analyzed. The biotribological behavior was studied in pin-on-disk sliding experiments under substitute synovial fluid lubrication. The wear behavior was investigated through laser scanning microscopy (LSM), Raman spectroscopy as well as focused ion beam scanning electron microscopy (FIB-SEM). [4] 3. Results and discussion The ta-C coatings exhibited typical morphology and composition and featured higher roughness compared to the substrates. Contact angle measurement as well as indirect and direct cell testing suggested sufficient biocompatibility and suitability for biomedical applications. The ta-C coatings demonstrated excellent mechanical properties with improved hardness- to-elasticity ratio. The adhesion between the coatings and CoCr, Ti64, and UHMWPE substrates was excellent. Despite higher friction, the ta-C coatings significantly reduced wear on both contacting bodies. The intact coating effectively protected the UHMWPE disk from adhesive or abrasive wear. However, crack networks and near-surface fatigue were observed after prolonged testing. Particle analysis revealed minimal release of nanometer-sized particles compared to the reference groups. The biotribological behavior remained consistent over time. [4] Cracking and folding in the ta-C coating on UHMWPE substrates were attributed to the mismatch in thermal expansion coefficients between the coating and substrate materials, which led to varied expansion and shrinkage during temperature changes, along with the high intrinsic compressive stress typical of ta-C coatings. The compressive stress in the coating, combined with time-dependent plastic deformation of the PE substrate, resulted in fold formation, coating shearing, crack formation, and subduction. Furthermore, cyclic tribological stress exceeded the compressive stress resistance of the ta-C coating, leading to the formation and propagation of microcracks near the surface (near-surface fatigue). Anyways, the durability of the ta-C coating is expected to extend the service life of metallic and polymeric implant materials. [4] 4. References [1] B. Rothammer et al.: Amorphous Carbon Coatings for Total Knee Replacements—Part II: Tribological Behavior, Polymers, 13, 2021, 1880, DOI: 10.3390/polym13111880 [2] B. Rothammer, K. Neusser, M. Bartz, S. Wartzack, A. Schubert, M. Marian: Evaluation of the Wear-Resistance of DLC-Coated Hard-on-Soft Pairings for Biomedical Applications, Wear, 523, 2023, 204728, DOI: 10.1016/j.wear.2023.204728 [3] R. Shah et al.: Enhancing mechanical and biomedical properties of protheses - Surface and material design, Surfaces and Interfaces, 27, 2021, 101498, DOI: 10.1016/j.surfin.2021.101498 [4] B. Rothammer et al.: Wear mechanism of superhard tetrahedral amorphous carbon (ta-C) coatings for biomedical applications, Advanced Materials Interfaces, 2023, 2202370, DOI: 10.1002/admi.202202370

Biotribological screening of amorphous carbon coatings on hard-on-soft pairings for total knee arthroplasty - Neusser, Kevin; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Marian, Max (63. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen., 2022)
This screening reveals the applicability and biotribological effectiveness of amorphous carbon coating systems developed for hard-on-soft pairings in biomedical applications, such as total knee replacements, to potentially reduce implant wear and thus to prevent premature failure and extend the service lif

Biotribological screening of amorphous carbon coatings on hard-on-soft pairings for total knee arthroplasty - Neusser, Kevin; Rothammer, Benedict; Marian, Max; Bartz, Marcel; Wartzack, Sandro (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)
The purpose of endoprosthetic joint replacement is to regain the functionality and allow patients to live a more mobile and pain-free life. Aseptic loosening of total knee arthroplasty (TKA) is a major cause of premature failure, with wear particles removed from the implant materials being largely responsible. Therefore, great efforts are being made to reduce the wear of polymer inlays by surface modifications. This study concentrates on the screening of the effectiveness of wear-reducing amorphous carbon coating systems on hard-on-soft pairings (metal-on-polymer). The biotribological behavior of the uncoated and coated pairings is investigated using a climate- and stress-controlled rheometer supplemented with a tribo-cell in a polyethylene ball and three metallic pins configuration, lubricated with diluted bovine calf serum (BCS) at 37 °C, in oscillatory sliding mode. The frictional behavior is analyzed in-situ while the wear performance is characterized ex-situ using light microscopy and laser scanning microscopy. This screening reveals the applicability of amorphous carbon coatings to the considered materials used for biomedical applications. It demonstrates the potential for wear reduction and forms a basis to determine the most promising of the deposited diamond-like carbon (DLC) coatings, therefore allowing for more focused research in the development of tribologically effective coating system

CAD-based Tolerance Analysis in Preliminary Design Stages Enabling Early Tolerance Evaluation - Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the ASME IMECE 2018, 2018)
Associated with manufacturing and assembly processes, inevitable geometric deviations have a decisive influence on the function and quality of products. Therefore, their consideration and management are important tasks in product development. Moreover, to meet the demand for short development times, the front-loading of design processes is indispensable. This requires early tolerance analyses evaluating the effect of deviations in a design stage, where the product’s geometry has not yet been finally defined. Since such an early tolerance consideration allows quick and economic design changes seeking for robust designs, it is advisable that the design engineer, who is entirely familiar with the design, should take this step. For this purpose, this paper presents an easy-to-use CAD-based tolerance analysis method for skeleton models. The relevant part deviations are represented by varying geometric dimensions with externally driven family tables. The approach comprises the strength of vector-based methods but does not require an expensive set-up of tolerance analysis models. Particularly, the novelty of this method lies in the CAD-internal sampling-based tolerance analysis of simple geometries without the use of expensive CAT software. This enables designers to evaluate the effect of tolerances already at the preliminary design stage. Using a case study, the presented approach is compared with the conventional vector-based tolerance analysis. <br
Keywords: CAD-based tolerance analysis; early tolerance management; skeleton model

CAD-Gestaltmodellierung in VR für die frühe Entwurfsphase - Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2020)
Virtual Reality bietet neben der stereoskopischen Visualisierung zusätzlich die Möglichkeit der natürlichen Interaktion mit virtuellen Objekten ähnlich der Interaktion mit physischen Objekten in der Realität. Der nachfolgende Beitrag beschreibt eine auf Fingertracking basierende Methode, mit der die Gestalt eines frühen Entwurfs innerhalb einer virtuellen Umgebung in einer CAD-Anwendung synthetisiert werden kann.

Cascading Forgetting in Product Development - Challenges and Evaluation - Kügler, Patricia; Schon, Claudia; Schleich, Benjamin; Staab, Steffen; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Vast amounts of information and knowledge is produced and stored within product design projects. Especially for reuse and adaptation there exists no suitable method for product designers to handle this information overload. Due to this, the selection of relevant information in a specific development situation is time-consuming and inefficient. To tackle this issue, the novel approach Intentional Forgetting (IF) is applied for product design, which aims to support reuse and adaptation by reducing the vast amount of information to the relevant. Within this contribution an IF-operator called Cascading Forgetting is introduced and evaluated, which was implemented for forgetting related information elements in ontology knowledge bases. For the evaluation the development process of a test-rig for studying friction and wear behaviour of the cam/tappet contact in combustion engines is analysed. Due to the interdisciplinary task of the evaluation and the characteristics of semantic model, challenges are discussed. In conclusion, the focus of the evaluation is to consider how reliable the Cascading Forgetting works and how intuitive ontology-based representations appear to engineer
Keywords: Intentional Forgetting; Ontologies; Knowledge management; Semantic data processing

Case-Based-Reasoning zur Vorhersage von Produkteigenschaften - Gerschütz, Benjamin; Götz, Stefan; Hörmann, Matthias; Wartzack, Sandro (Artificial Intelligence und Machine Learning in der CAE-basierten Simulation, 2023)

CAx für Ingenieure - Eine praxisbezogene Einführung - Vajna, Sándor; Weber, Christian; Zeman, Klaus; Hehenberger, Peter; Gerhard, Detlef; Wartzack, Sandro (Springer Vieweg, 2018)
Dieses nun in der dritten Auflage erschienene Buch vermittelt die Grundlagen des systematischen Einsatzes von rechnerunterstützten Methoden, Vorgehensweisen und Werkzeugen in der Produktentstehung. Es bietet seinen Zielgruppen in knapper und übersichtlicher Form das Rüstzeug für die erfolgreiche Anwendung von CAx-Systemen. Vorgehensweisen und Beispiele basieren auf Erfahrungen in Industrie und Hochschulpraxis, wo sie ihre Effizienz bewiesen haben. Die 3. Auflage wurde gründlich überarbeitet, der Kreis der Autoren erweitert. So kamen nicht nur Aspekte unterschiedlicher Modellierungsarten, Mechatronik und Wissensverarbeitung hinzu, sondern auch Ausführungen zu Systembegriff und Modellaufbau (diese bilden die Basis für CAx-Anwendungen). Sie alle beeinflussen immer stärker die Fertigungstechnik und den modernen Fahrzeug-, Maschinen- und Anlagenbau und sie spannen den Bogen zur Systemtechnik. Neben dem aktuellen und zukünftigen Leistungsstand von CAx-Systemen wurden auch Richtlinien und Empfehlungen zum Stand der Technik berücksichtig
Keywords: Anlagenbau; Fertigung; Industrie; Ingenieur; Ingenieurwissenschaften; Lineare Optimierung; Maschine; Modellbildung; Planung; Praxis

Challenges and Potentials of Digital Twins and Industry 4.0 in Product Design and Production for High Performance Products - Wagner, Raphael; Schleich, Benjamin; Haefner, Benjamin; Kuhnle, Andreas; Wartzack, Sandro; Lanza, Gisela (Procedia CIRP Volume 84, 2019)
Digital twins offer great opportunities in various domains of the product engineering process. However, current approaches to the use of digital twins only focus on different separated disciplines. In contrast to that, it is expected that the holistic use of digital twin models in product development and production will dominate future product generations, because they allow to create high-performance products competitively. This paper explores important challenges and future potentials of digital twins and Industry 4.0 for the seamless integration of product specification and production. In this regard, approaches of linking digital twins to other domains open up new possibilities in tolerance allocation and production integration. Thereby, the most efficient product specifications in technical and economic terms are achieved for the manufacturer. In addition, the connectivity of Industry 4.0 broadens the scope and enables the evaluation of alternative approaches in production planning and control. Approaches at the organizational level, product functions with specifications beyond the technological limits and production control strategies (e.g. order dispatching) ensure high performance operations. Simulations with a digital production twin with integrated digital product twin allow early estimations even before the actual ramp-up of the product. The future challenge addressed in this paper is to define a consistent framework for the holistic use of digital twins in the entire product development process, which requires the integration of product designers and production planner concept
Keywords: Product development; Production planning; Information

Challenges in interaction modelling with digital human models – A systematic literature review of interaction modelling approaches - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Ergonomics, 2020)
Digital human models (DHM) allow for a proactive ergonomic assessment of products by applying different models describing the user-product interaction. In engineering design, DHM tools are currently not established as computer-aided ergonomics tools, since (among other reasons) the interaction models are either cumbersome to use, unstandardised, time-demanding or not trustworthy. To understand the challenges in interaction modelling, we conducted a systematic literature review with the aim of identification, classification and examination of existing interaction models. A schematic user–product interaction model for DHM is proposed, abstracting existing models and unifying the corresponding terminology. Additionally, nine general approaches to proactive interaction modelling were identified by classifying the reviewed interaction models. The approaches are discussed regarding their scope, limitations, strength and weaknesses. Ultimately, the literature review revealed that prevalent interaction models cannot be considered unconditionally suitable for engineering design since none of them offer a satisfactory combination of genuine proactivity and universal validity
Keywords: Computer-aided ergonomics; digital human models; interaction modelling; engineering design; posture and movement prediction

Challenges in the Design of Products for Elderly People - Paetzold, Kristin; Wartzack, Sandro; Miehling, Jörg (Proceedings of the 9th Workshop on Integrated Product Development, 2013)
In recent years, there were significant changes in our society related to age structures and this will have an appreciable effect in the coming years. This demographic change is accompanied by an aging society, a challenge for all areas of our life. The engineering sciences can offer solutions, which support less for fundamental change in the situation, but certainly can mitigate the effects of these changes on the society. Using technical systems, we are able to preserve the quality of life, so that e.g. life in a familiar home environment is possible without additional support even in old age. The development of technological systems for this group of users is challenging as the elderly not only have very complex but also very individual requirements for products. This is due to their life experiences, socialisation as well as their age-and disease-related restrictions. Challenges that arise for product development are presented in this paper. Furthermore the benefits and ongoing research of utilising computer technology to support the development of products for elderly people are outlined. To stay competitive these days the virtual product development is continually promoted but in the context of products for seniors especially the virtual assessment of user-product interfaces has the potential to reveal, analyse and optimise cause-effect relationships, possibly not observable neglecting these emerging digital technologies.
Keywords: Design for Elderly; User-Centred Design Methods; Digital Human Modelling; Biomechanics; Virtual Product Development

Challenges of Geometrical Variations Modelling in Virtual Product Realization - Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, Volume 60, 2017)
Geometrical variations are inevitably introduced during manufacturing and can thus be observed on every manufactured artefact. Although it is widely acknowledged that these part deviations distinctly affect the function and quality of mechanical assemblies, the majority of virtual product validation activities still rely on the modelling and analysis of the nominal product geometry without considering such geometrical part deviations. In order to overcome this shortcoming, the aim of this paper is to highlight the current status of geometrical variations modelling approaches for virtual product realization and to carve out future challenges in this domain. For this purpose, different geometry representation schemes, which are nowadays used during virtual product realization, are discussed. Furthermore, they are linked to the various virtual product realization activities and potentials for improvements for their use and exchange are highlighted. The novelty of the contribution can be found in the comprehensive review of approaches for geometrical variations modelling, their placement into a changing virtual product development landscape, and the exposition of elaborated challenges for future research in this domain.
Keywords: Geometrical Variations Management; Geometric Modelling; Skin Model Shapes

Coated polymers for low friction and wear of roller bearing cages in lightweight design - Sander, Thomas; Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro (ICMCTF 4th Anniversity, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.coated

Combination of Matrix-based and Graph-based Modeling for Product and Organizational Structures - Schweigert, Sebastian; Luft, Thomas; Wartzack, Sandro; Lindemann, Udo (Understand, Innovate, and Manage your Complex System! Proceedings of the 19th International DSM Conference, 2017)
As a consequence of volatile markets and agile development processes, products and organizational structures have become increasingly complex. Modeling and analyzing complex products and organizations via matrices and graphs are useful ways to handle this complexity. This paper combines approaches for modeling products and organizational structures with matrices on the one hand. On the other hand, graph-based methods for analyzing the dependencies within as well as between the product and organization domain are described. Combining these domains gives the possibility to improve the overall development process by minimizing iterations and by adjusting the organizational to the product structure.
Keywords: DSM; DMM; MDM; product modeling and analysis; organization modeling and analysis

Combining System Models and CAD for Change Scenario Management - Hick, Hannes; Schleich, Benjamin; Sanladerer, Stefan; Ryan, Karen; Trautner, Jessica; Piguet, Jean; Wilking, Fabian; Horber, Dennis; Faustmann, Clemens; Kranabitl, Philipp; Kollegger, Stefan; Bajzek, Matthias; et al. (33rd Annual INCOSE International Symposium, 2023)
In the development of complex mechatronic systems, interdisciplinary cooperation requires an exchange between stakeholders in order to ensure fulfillment of requirements and related functions. The cooperation of the stakeholders from different disciplines must be well coordinated to address systems changes. The system model as an essential aspect of model-based systems engineering, has to be linked to specific models of involved disciplines (mechanical, electrical/electronical and software) to enable a basis for automatic identification e.g., of affected subsystems and functions. This contribution discusses the potential of model linking from the perspective of change scenarios by considering published approaches to link system models and computer-aided design (CAD). A methodical approach on how descriptive system models can be used as base for computer-aided design is presented. This approach is analyzed by reviewing a use case for a design change scenario of an automotive eAxl
Keywords: MBSE

Comparative evaluation of WIMP and immersive natural finger interaction: a user study on CAD assembly modeling - Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Virtual Reality, 2021)
Virtual and augmented reality allows the utilization of natural user interfaces, such as realistic finger interaction, even for purposes that were previously dominated by the WIMP paradigm. This new form of interaction is particularly suitable for applications involving manipulation tasks in 3D space, such as CAD assembly modeling. The objective of this paper is to evaluate the suitability of natural interaction for CAD assembly modeling in virtual reality. An advantage of the natural interaction compared to the conventional operation by computer mouse would indicate development potential for user interfaces of current CAD applications. Our approach bases on two main elements. Firstly, a novel natural user interface for realistic finger interaction enables the user to interact with virtual objects similar to physical ones. Secondly, an algorithm automatically detects constraints between CAD components based solely on their geometry and spatial location. In order to prove the usability of the natural CAD assembly modeling approach in comparison with the assembly procedure in current WIMP operated CAD software, we present a comparative user study. Results show that the VR method including natural finger interaction significantly outperforms the desktop-based CAD application in terms of efficiency and ease of use.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Assembly modeling; Computer-aided design; Natural user interface; Virtual reality

Comparing CAD part models for geometrical similarity: A concept using machine learning algorithms - Bickel, Sebastian; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (CIRPe 2020 - 8th CIRP Global Web Conference -, 2020)
The efficient execution of process planning activities requires the knowledge from several distinct domains. However, in this context, a common issue is the existence of collective knowledge in the one domain with a lack of networked expertise with other domains. Motivated by this, the paper proposes an approach to support process planning by comparing the generated part design with older, validated products. The utilization of this earlier CAD part models has the potential to reduce development costs, shorten the production start-up time and improve the product quality. The new concept provides the manufacturing personnel with a method for comparing the newly designed part with a pool of validated models to identify the most similar one. Each previous CAD part model is linked with the necessary manufacturing information, so that the initial values for the manufacturing process are available without a time consuming testing phase. The method is divided in three main steps: the global similarity comparison, the segmentation of the part and the local similarity comparison. In the first step, the geometry is projected onto a sphere and then transformed to a matrix. Afterwards these matrices are compared and clustered into corresponding groups. In the following step, a Machine Learning algorithm segments the objects into specific, manufacturing relevant groups. In every cluster, the segmented geometries are again compared for similarity. The combination of the first and the second ranking results in a global similarity hierarchy for the newly designed part. In this paper, the entire procedure is shown with the example of sheet-bulk metal formed parts. This new manufacturing process particularly benefits from this method, as the amount of data is still limited and therefore little expert knowledge exists.<br
Keywords: "Digital Engineering; similarity; comparison; Machine Learning; data-driven" Abstract

Comparison of different methods for scrap rate estimation in sampling-based tolerance-cost-optimization - Hallmann, Martin; Schleich, Benjamin; Heling, Björn; Aschenbrenner, Alexander; Wartzack, Sandro (Procedia CIRP, Volume 75, 2018)
Tolerance-cost-optimizations help to find optimal tolerances for a given tolerance design, which achieve minimum total costs while satisfying the quality requirements. These requirements are commonly expressed as scrap rates in ppm-range. This paper presents several methods for the scrap rate estimation in sampling-based tolerance-cost-optimizations. Moreover, the proposed approaches are applied to a typical case study and compared in terms of their required computation time and the obtained optimization results. The novelty of the contribution can be found in comparing different scrap rate estimation techniques for sampling-based tolerance-cost-optimizations and giving recommendations to researchers as well as practitioner
Keywords: tolerance-cost-optimization; scrap rate; Latin-Hypercube-Sampling

Comparison of Different Sensitivity Analysis Methods in the Context of Dimensional Management - Heling, Björn; Oberleiter, Thomas; Schleich, Benjamin; Willner, Kai; Wartzack, Sandro (ASME 2017 International Mechanical Engineering Congress and Exposition, Volume 2: Advanced Manufacturing, 2017)
Although mass production parts look the same, every manufactured part is unique, at least on a closer inspection. The reason for this is that every manufactured part is inevitable subjected to different scattering influencing factors and variation in the manufacturing process, such as varying temperatures or tool wear. All these factors inevitably lead to parts, which deviate from their ideal shape. Products, which are built from these deviation-afflicted parts consequently show deviations from their ideal properties. To ensure that every single product nevertheless meets its technical requirements, it is necessary to specify the permitted deviations. Furthermore it is necessary to estimate the consequences of the permitted deviations, which is done via tolerance analysis. During this process the imperfect parts are assembled virtually and the effects of the geometric deviations can be calculated during a variation simulation. Since the tolerance analysis is to enable engineers to identify weak points in an early design stage it is important to know which contribution every single tolerance has on a certain quality-relevant characteristic, to restrict or increase the correct tolerances. In this paper two different approaches are shown and compared to represent the statistical behavior and the strongly connected sensitivity analyses. In particular a newly developed approach, which is based on fuzzy arithmetic, is compared to the established EFAST-method. The exemplary application of both methods and the comparison of the results are illustrated on a case stud

Comparison of maximum hip abductor torques from patient-specific multibody simulation models with isometric and isokinetic force measurements - Fleischmann, Christopher; Leher, Irina; Scherb, David; Kollerer, Marius; Miehling, Jörg; Wartzack, Sandro; Sesselmann, Stefan (Human Interaction & Emerging Technologies (IHIET 2023): Artificial Intelligence & Future Applications, 2023)
Muscuolskeletal simulations have become an important tool to simulate biomechanical properties. However, adaption of the models to patients or test persons is relevant in order to obtain realistic results (e.g. hip joint moments or muscle forces). It is particularly important to correctly reproduce the patient-specific maximum isometric muscle forces of the individual musculotendinous structures. The purpose of this work is to determine the extent to which gluteal muscle adaptation has an impact on the maximum hip joint moment during hip abduction.Based on MRI images volumes of the gluteal muscles were determined. These were used to calculate the muscles' maximum isometric force via the physiological cross-sectional area and the specific muscle tension. Since the values of the specific tension differ greatly in literature, several models were created. The models were investigated regarding their maximum hip joint moment and compared, first, to a marker-based scaled generic model and, second, to isokinetic and isometric force measurements using a dynamometer.It was shown that both, the models and the muscle strength measurements, show a maximum in the lower area of hip abduction and decrease sharply with increasing abduction. The models with a lower specific tension were much closer to the measured maximum hip torques. Higher values for the specific tension and the model without patient-specific information on the musculature were above the strength measurements. However, all models are clearly above the measurements with increasing abduction.It can be concluded that the gluteal muscles should be simulated with rather lower values of the specific tension.
Keywords: Biomechanics; Isometric Force; Isokinetic force; Muscle segmentation; patient-specific modelling

Complexity-reduced Simulation of Hybrid Adhesive Joints - Witzgall, Christian; Kellermeyer, Markus; Wartzack, Sandro (Grazer Symposium Virtuelles Fahrzeug, 2016)

Computational Geometry Reconstruction from 3D Topology Optimization Results: A New Parametric Approach by the Medial Axis - Mayer, Johannes; Wartzack, Sandro (Computer-Aided Design and Applications, 2023)
Topology Optimization (TO) is used to develop high strength, yet lightweight structural components. The geometry reconstruction from raw optimization results is a crucial task and especially challenging to do considering product development’s demand on parametrics. In this paper a new automated approach for computational reconstruction is presented that uses the Medial Axis for abstraction and inclusion of parametrics and features in the reconstruction. The presented method is both highly automated and at the same time offers optional geometry editing within the reconstruction itself. The steps of the method are (1) analysis of the TO result by the Voronoi computed Medial Axis Transform, (2) processing of the Medial Axis Transform into a decomposition, and (3) redesign thereon. Directly usable files of Computer-Aided Design (CAD) are generated. The concept is presented at real world case studies with focus on non-beam-like, structural component
Keywords: Topology Optimization; Computer-Aided Design; Computational Design; Geometry Reconstruction; Skeletonization; Medial Axis Transformation

Computation and Visualization of Patch Geometries for the Design of Carbon Fiber Reinforced Parts at Early Design Stages - Klein, Daniel; Scheler, Kaja; Wartzack, Sandro (Proceedings of the 24th CIRP Design Conference 2014, Milano, Italy, 2014)
The market for carbon fibers is forecast to experience a double-digit growth over the next years. The reason for this development can be found in the special characteristics of Carbon Fiber Reinforced Plastics (CFRP) like high stiffness and strength at very low weight which make this composite an ideal material for lightweight design. However, the design of parts made of CFRP is a tightrope walk between costs, mechanical characteristics and manufacturability for product developers. On the one hand, the mechanical properties are highly dependent on the ideal fiber orientation within the part and the unique material characteristics can only be exploited with a suitable fiber orientation, but on the other hand, the ideal fiber orientation is often not manufacturable or the required manufacturing technique is too expensive. Therefore, a novel algorithm to support product developers in finding a manufacturable fiber orientation or patch layout which is as close as possible to the ideal fiber orientation is introduced. This algorithm computes and highlights areas with constant fiber orientation (=cluster) based upon the ideal fiber alignment from the CAIO method. With the help of the visualization of the clusters, product developers can be supported in the decision for the best patch placement and geometry as well as in choosing the best manufacturing technique. It is important to point out that the algorithm is intended for endless fiber reinforced parts only.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.comput
Keywords: Early design stages; Endless fibre reinforced composites; Lightweight design

Computer Aided Ergonomics: Evaluation Study of a Interaction Model for Digital Human Models - Wolf, Alexander; Fackler, Konrad; Reulbach, Magnus; Wartzack, Sandro; Miehling, Jörg (Proceedings of the Design Society, 2022)
In user-centred design, digital human models hold the potential for proactive evaluations of ergonomics or discomfort in terms of a computer aided ergonomics tool. Therefore, models predicting human interaction behaviour, are necessary. In this contribution we present such a model as well as its initial evaluation. The evaluation is performed by applying the interaction model to a specific use case, conducting a comparison with an empirical subject study. The evaluation shows that similar and realistic human behaviour was predicted, which was consistent in terms of whole-body strai
Keywords: user-centred design; interaction design; digital human models; evaluation; computer-aided ergonomics

Computer Aided Ergonomics Through Parametric Biomechanical Simulation - Miehling, Jörg; Schuhhardt, Jürgen; Paulus-Rohmer, Florian; Wartzack, Sandro (ASME 2015 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, Volume 1B: 35th Computers and Information in Engineering Conference, 2015)
Computer aided ergonomics and particularly biomechanical simulations hold high potential for the implementation of the virtual product development paradigm in the field of human-centric design. Unfortunately, the relation between efforts to be invested to the insights gained by musculoskeletal simulations is still not sufficient for a widespread industrial application. This contribution shows how parametric biomechanical simulations can be used to gain specific indications on how interaction points of human-centric products are to be designed to meet the competencies of a given target user. This is demonstrated using cycling and rowing as two exemplary activities involving the entire human body. These activities are empirically well studied and electromyographic as well as force measurements are available. The comparison of the biomechanical simulations to the real-world scenario permits the validation of the proposed parametric approach as well as the applied models. This is a prerequisite for its application along the product engineering process.
Keywords: Computer-aided engineering; Simulation; Biomechanics; Ergonomics

Computer Aided Internal Optimisation (CAIO) method for fibre trajectory optimisation: A deep dive to enhance applicability - Völkl, Harald; Franz, Michael; Klein, Daniel; Wartzack, Sandro (Design Science, 2020)
The computer aided internal optimisation (CAIO) method produces an optimised fibre layout for parts made from fibre-reinforced plastics (FRP), starting from an initial shell geometry and a given load case. Its main principle is iterative reduction of shear stresses by aligning fibre main axes with principal normal stress trajectories. Previous contributions, ranging from CAIO’s introduction over testing to extensions towards multi-layer FRP laminates, highlighted its lightweight design potential. For its application to laminate design approaches, alterations have been proposed; however, questions remain open. These questions include which convergence criteria to use, how to handle ambiguous principle normal stress trajectories, influence of using multi-layer CAIO optimisation instead of the initial single-layer CAIO and how dire consequences of slightly deviating fibre orientations from the optimised trajectories are. These challenges are discussed in depth and guidelines are given. This paper is an enhanced version of a distinguished contribution at the first symposium ‘Lightweight Design in Product Development’, Zurich (June 14–15, 2018
Keywords: lightweight design; fibre trajectory optimisation; CAIO; fibre-reinforced plastics

Computer Aided Internal Optimization (CAIO) method for fiber trajectory optimization: enhancing applicability - Völkl, Harald; Franz, Michael; Wartzack, Sandro (1st Symposium for Lightweight Design and Product Development, 2018)
The bio-inspired Computer Aided Internal Optimization (CAIO) method optimizes fiber orientation of composite structures by minimizing shear stresses. Fiber directions are iteratively aligned with maximum principal normal stress trajectories (MPNST). Its effectiveness was exemplarily shown by Reuschel and Mattheck (1999) using a tension-loaded plate with two holes, doubling the strength of a specimen compared to an unidirectional design. Klein (2017) uses this method in a holistic approach to composite design – and points out, to find its way into practice more, the iterative method still leaves room for further research. This is especially the case in areas of non-unique MPNST. The extended abstract scrutinizes the behavior of the method in these areas and evaluates possible solutions<br

Concept and application of automatic part-recognition with artificial neural networks for FE simulations - Sprügel, Tobias; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), 2015)
Currently available finite element software is consequently getting more and more user-friendly, and simulation knowledge must be expanded to a growing pool of new and less-experienced users; for example designers. These users need to be assisted when performing simulation tasks. A promising way is to check the FE results for plausibility, but therefore, it is essential to know what kind of parts should be simulated and checked for plausibility. This paper presents a concept for the automatic recognition of standard parts within the FE software, using a predefined Artificial Neural Network (ANN). An existing approach is extended to deal with the issues of arbitrarily oriented parts in CAD (computer-aided design) assemblies of differing size in 3D space. Hence a Principal Component Analysis (PCA), and a spherical detector surface for FE nodes in spherical coordinates is used to gain input parameters for an ANN. In the paper, the concept and an application for certain standard components are demonstrated.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.concep
Keywords: Simulation; Design informatics; Artificial Neural Networks (ANN); part-recognition; FE simulation

Concept and implementation of a central knowledge framework for simulation knowledge - Kestel, Philipp; Sprügel, Tobias; Katona, Sebastian; Lehnhäuser, Thomas; Wartzack, Sandro (NAFEMS European Conference: Simulation Process and Data Management, 2015)
Due to increasing product- and process-requirements and shorter development periods the usage of numerical simulations has become an essential part of the product development process. This has led to expose simulation to not only the CAE experts but also to less experienced users such as designers. However, such users typically do not have the expertise to perform simulations from the ground up and need appropriate help systems.   Therefore, the aim of the Bavarian Research Cooperation FORPRO² for “Efficient Product and Process Development by Knowledge based Simulation” is to increase the efficiency of virtual product and process development. This is achieved by creating a simulation environment that allows corresponding users to automatically benefit from expert practices and knowledge. As a result, non-expert users can produce reliable results for virtually optimizing design parameters. This will allow shifting work load from the simulation engineer to the designer. As a consequence, the simulation process will become more agile and quick without compromising on quality of the simulation and the final product.   The goal of the simulation environment is to provide the necessary situational simulation knowledge as a function of decisive factors such as the phase in the development process, the manufacturing processes employed, and the company's individual circumstances. Considering such a wide range of factors, results in several challenges in the development of the simulation framework. Some of the challenges are associated with (manual or automatic) extraction processes of simulation knowledge from existing sources and the publication of the knowledge to the end user in an adequate manner.   The presentation will demonstrate the implementation of the central knowledge environment within the framework of a commercial SPDM system. Special emphasize will be laid on presenting an automatic acquisition of simulation knowledge from validated simulation reports by means of KDD-processes (Knowledge Discovery in Databases). The overall approach is demonstrated by considering the use case of performing a numerical FE simulation with real life geometry (including deviations caused by the manufacturing process) instead of ideal geometry from the CAD system (see image below for a the conceptual workflow for this use case).

Concept development for innovative products - a challenge for engineering design education - Luft, Thomas; Schleich, Benjamin; Wartzack, Sandro (DS 75-8: Proceedings of the 19th International Conference on Engineering Design (ICED13), 2013)
The complexity of new products steadily increases and therefore integrated engineering designers have to be skilled in various fields in order to develop innovative and successful products. This trend has to be considered in university education. Therefore, a new educational concept called âConcept Development for Innovative Productsâ (CIP) is proposed. In this subject the students are confronted with a vague task and are asked to develop and to present concepts for innovative products in teams of five. In this regard, CIP is a combination of three forms of teaching, which are presenting the working progress, discussing and lectures on demand. During mandatory working meetings the students have to present the project status to the supervisors and discuss the next steps with them. Furthermore, they can ask for lectures on specific engineering design methods which are presented using a comprehensive method catalog. The student feedback for CIP in the first semester was excellent and it is a very good enhancement for the curriculum. Consequently, the students are well prepared for a harmonic transition from university to their professional careers.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.concep_8
Keywords: Design education; conceptual design; design methods; teamwork

Concept for tolerance design in early design stages based on skeleton models - Ziegler, Philipp; Wartzack, Sandro (Proceedings of the 19th International Conference on Engineering Design, 2013)
A noticeable trend in mechanical industry is that the product lifecycle and within the product development phase shortens. One consequence is the necessity to perform product-analyses already in early design stages, even if the geometry of the product is only sketchy defined by skeleton models. For product functionality the dimensional and geometric variations of the product components play an important role, which are analyzed and limited by tolerancing. The lack of geometric information in the early design phase is challenging for tolerance analysis, but also offers chances by more flexibility of the product developer in changing the products geometry. Therefore, this paper presents the concept to perform tolerance design based on skeleton models.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.concep
Keywords: Computational design synthesis; Contributor analysis; Early design phases; Tolerance design

Concept of a Modular and System Model Driven Digital Twin for Engineering Education - Wilking, Fabian; Behringer, Marc; Fett, Michel; Götz, Stefan; Kirchner, Eckhard; Wartzack, Sandro (IEEE International Conference on System of Systems Engineering (SoSE), 2023)
Driven by the opportunities for condition monitoring and new business models, Digital Twins have become a popular topic within research and industrial application over the last years. Therefore, universities must integrate the development of Digital Twins into their educational program to enable future engineers to overcome the challenges concomitant with Digital Twins. While a theoretical basis for Digital Twins is crucial e.g., hardware-software integration, Internet of Things (IoT) or simulation models, a practical combination of these heterogeneous components is also necessary to introduce the Digital Twin as a whole concept. With Model-Based Systems Engineering (MBSE) an approach was introduced to grasp complexity by using system models e.g., through SysML diagrams. Digital Twins are an example for advanced systems shaped by high complexity. The usage of system models is therefore likely. With this contribution, a concept is presented to combine system models and Digital Twins to create a prototype for academic education and the conduction of student projects.<br

Conceptual Model for (Semi-) Automated Derivation of Evaluation Criteria in Requirements Modelling - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2020)
Requirements act as a limitation of the solution space, which represents the stakeholders’ needs and guides the whole product development process. Therefore, forgotten requirements can lead to wrong decisions when using them as a basis for decision-making. This contribution introduces a novel approach to link the requirement and evaluation criteria models to address this problem. For setting up those criteria consistently, the requirements are classified using natural language processing and derived by a ruleset based on a developed mapping between requirement classes and criteria type
Keywords: requirements management; decision making; design evaluation; natural language processing

Concurrent Machine and Batch Size Selection in Sampling-based Tolerance-Cost Optimization - Roth, Martin; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2022)
Tolerance allocation is an essential part of detail design and an important interface between design and production. Its goal is to select tolerance values as tight as necessary, to reliably assure total product quality considering variation, but at the same time as wide as possible, to allow for a cost-optimal fabrication of the individual parts. A consequent front-loading of manufacturing information is thus inevitable for a realistic consideration of the given manufacturing conditions enabling an early, optimal process planning. In this context, sampling-based tolerance-cost optimization has proven its suitability as an optimization-based tolerance allocation technique because it allows a realistic consideration of part tolerance distributions as well as the selection of cost-minimal combinations of manufacturing machines and processes for each part. However, the potential of machine selection in tolerance-cost optimization is currently limited since it does not support distributed manufacturing on several machines with individual batch sizes. Motivated to close this gap, this article presents a novel optimization-based method for concurrent tolerance and machine allocation. The consideration of mixed batches from individually allocated machines requires the extension of the mathematical definition of the tolerance-cost optimization problem and its solution by advanced optimization and sampling strategies. Its exemplary application to a use case shows its potentials and proves that balancing tolerance values, machines and batch sizes can help to further increase the potential of tolerance-cost optimization. Hence, the presented approach supports a further shift to a manufacturing-oriented interpretation of tolerance allocation in design.
Keywords: Least-cost tolerance allocation; Tolerance-cost optimization; Machine selection; Batch size; Process planning

Consideration and impact assessment of measurement uncertainty in the context of tolerance analysis - Heling, Björn; Müller, Andreas; Schleich, Benjamin; Hausotte, Tino; Wartzack, Sandro (Proceedings of the ASME 2019 International Mechanical Engineering Congress and Exposition, 2019)

Consideration of anisotropic material properties in mechanical design within early design phases - Gruber, Georg; Klein, Daniel; Ziegler, Philipp; Wartzack, Sandro (NordDesign 2012 - Proceedings of the 9th NordDesign Conference, 2012)
To achieve the goal of simulating the structural behavior of parts made of short fiber reinforced polymers with satisfactory accuracy and justifiable modeling effort, a new approach adapted to the needs of the early design steps was developed at the Chair of Engineering Design (KTmfk). Hereby, the various effects of material behavior are modeled by overlapping two different material models in one finite element definition. The anisotropic material properties are determined by an injection molding simulation. The complexity of the resulting fiber distribution is reduced to just three values per finite element. The paper's focus is the introduction of an automated method supporting the determination of the numerical material parameter and a new tensor based method enabling the averaging of the complex orientation state. The benefits of the new methods and a validation are presented.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Early design steps; Fiber reinforced polymers; Lightweight design; Simulation

Consideration of Anisotropic Material Properties in Mechanical Design within Early Design Steps - Gruber, Georg; Klein, Daniel; Ziegler, Philipp; Wartzack, Sandro (Proceedings of the 9th Norddesign, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.consid_2

Consideration of operational wear in tolerance analysis for process-oriented tolerancing - Bode, Christoph; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2022)
Besides manufacturing-induced part deviations, operational wear in persistent moving assemblies leads to time-dependent deviations of part geometries and the functionality of the mechanism. This article presents an approach based on the Archard wear model to predict the lifetime functionality of an assembly by carrying out a tolerance analysis, considering both, time-dependent variations in wear activity due to volume loss and the impact of process-induced geometrical variation on the wear. The novelty of this approach lies in the consideration of time-varying operational wear effects in tolerance analysis and non-conformance rate estimation. To prove its applicability, the approach is applied to a one-way-clutch.<br
Keywords: Tolerance analysis; Operational wear; Non-conformance rates

Consideration of Orientation Properties of Short Fiber Reinforced Polymers within Early Design Steps - Gruber, Georg; Haimerl, Andreas; Wartzack, Sandro (12th International LS-DYNA® Users Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.consid

Consideration of uncertainties in the product-oriented development process - Reitmeier, Jochen; Luft, Thomas; Wartzack, Sandro; Paetzold, Kristin (Modelling and Management of Engineering Processes, 2015)
Product developers have to develop modern products with increasing functionality and complexity in order to achieve the required functionality or property profile of products. Due to the multiple dependencies of defined characteristics and properties it is not always possible for developers to detect causes reliably, to identify possible alternatives and to analyze and evaluate their consequences completely. Hence, mainly the effects are combated or stemmed in the context of improvements (= iterations), but their causes are not eliminated. Therefore, the overall objective of the authors is to develop a procedure model for iteration and product maturity management as well as for an appropriate planning of virtual validations in the property-based product development. In this contribution the handling of uncertainties within the development process is focussed. This is shown by using the example of a wheel hub and thereby can be demonstrated that it is not only possible to optimize the development process but also to improve the product itself.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.consid
Keywords: Process optimization; process management; uncertainty; matrix-based product description; virtual property validation

Considering Emotional impressions in Product Design: Quality of Life Theory and its impact on Design Strategy - Kett, Susan; Wartzack, Sandro (Proceedings of the DESIGN 2016 14th International Design Conference, 2016)
In this paper, the necessity of emotional considerations in the context of Universal Design is treated. To work out an alternative approach how to integrate emotional aspects in product design processes, we look at quality of life models to locate emotional design in Universal Design research. Based on identified challenges such as complexity, interdisciplinarity, vagueness or subjectivity we present a way to consider emotional impressions by integrating resources from other disciplines. Hence we introduce ACADE - an Application for Computer Aided Design of Emotional impressions.
Keywords: universal design; emotions in design; user centered design; engineering design tools; data analysis

Considering Emotional Impressions in Product Design: Taking on the Challenges Ahead - Kett, Susan; Wartzack, Sandro (Entwerfen Entwickeln Erleben 2016 - Beiträge zum Industrial Design, 2016)
There is a stronger focus on emotional aspects affecting users' product selection as ever before. Recent User Centred Design (UCD) approaches already take up this fact, but still this is at the very beginning regarding UCD implementation. As on addressing emotional aspects in particular, the big challenge lies in the management of their low grade of concretisation and intense complexity. From other disciplines such as marketing strategy, psychology or sociology, we know instruments that help to describe this fuzzy theme. But still, its discrete integration into product development processes and high complexity remains as one main issue. In this paper, the challenges in design for emotions in the context of UCD are firstly examined to understand possible starting points. We give potential reasons for the insufficiency of current approaches, answering the question why there is no adequate tool for their consideration so far. Therefore, we summarize some of the challenges that exist both in UCD itself and its relevant enhancement for emotional consideration. We extract these findings during our studies reviewing several relevant surveys and research literature. Often, it is hard to make decisions only based on implicit information. Even though the designer can make good decisions based on his own well trained emotional perception ability, he might not be able to do so for whole target groups. Moreover, the communication between different parties in the interdisciplinary field needs improvement. In the field of UCD, it is obligatory both to manage the future users' and the developer teams' heterogeneity. So a reliable objectification of subjective information in an interdisciplinary field becomes necessary. Based on the findings on the present knowledge, an approach called ACADE - Application for Computer Aided Design of Emotional impressions - is presented. ACADE is a tool that systematically processes and links subjective and implicit information to objective, measurable data that can be used as basis for high-quality decision making in product design. To get an overview of the different elements in its architecture, they will be carefully explained. Giving a firm example, we show the general workflow and linkages. Thus we illustrate the potential of ACADE for future research in emotional design by addressing the aforementioned identified UCD problems. ACADE supports strategic product design decisions. Its application in product development environments can be extremely extended to support decision making in product development throughout the whole process. It enables the transparency and the traceability of decisions in a highly implicit domain. Barriers in communication caused by the interdisciplinary of decision-makers may be reduced. Moreover, it forces the product developer to look at his product to be designed through the emotional profile of the user. With ACADE, an important step forward to a holistic, interdisciplinary UCD is given.
Keywords: User Centered Design; Emotional Design; Designing for User Attitudes; Product Design; ACADE

Considering Users’ Emotions in Product Development Processes and the Need to Design for Attitudes - Kett, Susan; Wartzack, Sandro (Emotional Engineering, 2017)
In recent times there has been an increasing need to consider subjective values in user-centred design for technical products. Therefore, the relations between perceived value to the user and different product design elements have been investigated in former research. Although there are many approaches that address this issue, little advice has been given so far on how to use this knowledge truly to consider the users’ preference. Even if we know that a product appears to be “sporty” to the user, and even if we know how to design the product to look “sporty”, we still do not know “how sporty” he might like it to be. Moreover, studies have revealed that there are huge differences in user groups that cannot easily be detected using only common segmentation criteria like age, family situation or income. Depending on their personal attitudes and values, individuals’ preferences for products may differ widely despite the objective user characteristics looking similar. Therefore, an approach called the ACADE is presented, which combines interdisciplinary knowledge of users’ long-term evaluation system and preference choice.
Keywords: Emotional Engineering; User-centered Design; Attitudes; Subjective Quality; Kansei Engineering

Consistent digitalization of engineering design – an ontology-based approach - Kügler, Patricia; Schleich, Benjamin; Wartzack, Sandro (Norddesign, 2018)
Digitalization and Industry 4.0 are currently trend words in companies and research, which express the striving for digitalized manufacturing environments and autonomous manufacturing processes enabled by cyber-physical production systems. But where do we stand in product development? Modern virtual product development tools and processes allow the definition of product geometry and shape in fully three-dimensional computer-aided design environments. Additionally, even semantic information, for instance about the subsequent manufacturing, can be included employing feature-technology. Moreover, virtual testing of these three-dimensional product models can be performed using sophisticated computer-aided engineering and simulation tools leading to digitally supplied output data. However, CAD and simulation tools mainly support later design activities, while there is a lack of computer support in early design stages. This lack of digitalization in such early design stages eliminates the possibility of retracing the customer requirements in the product at late design activities. In consequence, the decisions made during the design process are hardly comprehensible and therefore existing product knowledge is difficult to reuse. This contribution shows the needs for a consistent digitalization of engineering design with focus on the early stages. This consistent digitalization refers to a representation and linkage of work results in design processes, which allows inference and reasoning between them. Thus, reusing of product knowledge becomes more comprehensible. Moreover, this contribution presents an ontology-based approach for this consistent digitalization, which particularly enables product developers to link early design stages to late design stages and to establish relations between customer requirements and the finished product. The approach thus supports the efficient reuse of relevant design knowledge employing an ontology. Besides this, the paper discusses the general advantages of ontologies for transparently storing and efficiently providing product knowledge. With the novel ontology-based approach proposed in this contribution, the reuse of finished product development processes becomes more efficient and transparent.<br
Keywords: Ontologies; Knowledge-based Engineering; Requirements Engineering; Information Integration

Contact and Mobility Simulation for Mechanical Assemblies Based on Skin Model Shapes - Schleich, Benjamin; Anwer, Nabil; Mathieu, Luc; Wartzack, Sandro (Journal of Computing and Information Science in Engineering, 2015)
Assembly modeling as one of the most important steps in the product development activity relies more and more on the extensive use of computer-aided design (cad) systems. The modeling of geometric interfaces between the components of the assembly is of central importance in the simulation of mechanical assemblies. Over the past decades, many researchers have devoted their efforts to establish theories and systems covering assembly modeling. Although the product form or shape has been extensively investigated considering the nominal cad geometry, inevitable limitations can be reported. Computer aided tolerancing (CAT) systems provide simulation tools for modeling the effects of tolerances on the assembly but still lack of form deviation considerations. The skin model concept which stemmed from the theoretical foundations of geometrical product specification and verification (GPS) has been developed to enrich the nominal geometry considering realistic physical shapes. However, the digital representation of the skin model has been investigated only recently. This paper presents a novel approach for a skin model based simulation of contact and mobility for assemblies. Three important issues are addressed: the geometric modeling of the contact, the contact quality evaluation, and the motion analysis. The main contribution to CAT can be found in the analysis of the effects of geometric form deviations on the assembly and motion behavior of solid mechanics, which comprises models for the assembly simulation, for the contact quality evaluation, and for the motion analysis. A case study is presented to illustrate the proposed approaches.

Continuous simulation of variations during the design of endless fiber reinforced composite structure assemblies - Freitag, Stephan; Götz, Stefan; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)

Co-Simulationsmodell zur nutzerzentrierten Entwicklung von Unterstützungssystemen: Am Beispiel von Tätigkeiten in und über Kopfhöhe mit einem Schulter-Exoskelett und einem Akkuschrauber - Yao, Zhejun; Molz, Carla; Sänger, Johannes; Miehling, Jörg; Germann, René; Wartzack, Sandro; Matthiesen, Sven; Weidner, Robert (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2021)
Unterstützungssysteme zeichnen sich durch eine erhöhte Mensch- Maschine-Interaktion aus. Diese Interaktion und ihre Auswirkungen haben große Bedeutung für die Entwicklung und Anwendung von Unterstützungssystemen und führen zu einer besonderen Herausforderung bei der Simulation entsprechender Systeme. Um diesen gerecht zu werden, wird ein Co-Simulationsmodell von Menschen, Exoskelett und Power-Tool entwickelt. Derartige Co-Simulationsmodelle ermöglichen bereits in der frühen Phase der Entwicklung der Unterstützungssysteme eine digitale Integration des Anwenders.<br
Keywords: Mensch-Maschine-Interaktion; Unterstützungssysteme; Produktentwicklung; Co-Simulation; Muskuloskelettales Menschmodell; Exoskelett und Power-Tool-Modelle; Biomechanik

Coupling Sampling-Based Tolerance-Cost Optimization and Selective Assembly – An Integrated Approach for Optimal Tolerance Allocation - Roth, Martin; Seitz, Markus Johannes; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the ASME 2022 International Mechanical Engineering Congress and Exposition (IMECE2022), 2023)
Optimization has gained increased attention in product development and is nowadays profitably used to solve complex design problems. In tolerance design, tolerance-cost optimization is a systematic and efficient approach to allocate part tolerance values in a cost-optimal way. The usage of sampling-based tolerance analysis techniques thereby enables the consideration of machine-specific part tolerance distributions as well as individual batch sizes and thus facilitates a concurrent allocation of tolerances and machines. With the aim to further exploit its potential by embedding assembly aspects, this article presents a novel approach combining tolerance-cost optimization and optimal selective assembly. Based on an initial introduction of its general idea, a global optimization problem is defined to simultaneously identify the best combination of tolerance values, machines with their batch sizes and sorting orders of the individual batches. Subsequently, its solution using metaheuristic optimization algorithms and mixed-integer variables is presented. The theoretical findings are finally confirmed by its exemplary application to a use case indicating that it can reveal hidden cost improvement potentials in tolerance desig
Keywords: tolerance-cost optimization; tolerance allocation; selective assembly; mixed-integer optimization; Monte Carlo sampling

Crashgerechter Leichtbau - Wartzack, Sandro; Gruber, Georg (Konstruktion, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.crashg

Crashsimulation kurzfaserverstärkter Kunststoffbauteile - Ein Ansatz für frühe Entwicklungsphasen - Gruber, Georg; Wartzack, Sandro (Kunststoffe + SIMULATION, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.crashs

Crash simulation of mechanically fatigued short-fibre reinforced thermoplastics: anisotropic failure considering previous damage - Witzgall, Christian; Wartzack, Sandro (VDI-Berichte, 2022)

Creating Sustainable Products - Ries, Lena; Wartzack, Sandro; Zipse, Oliver (Road to Net Zero, 2023)
On the Road to Net Zero, products must not only become CO2-neutral in the consumption phase, but the environmental impact needs to be mitigated from the extraction of the raw materials to their end-of-life disposal. The consideration of the entire life cycle—cradle to cradle—as well as rising consumer demand for sustainable products—requires a new paradigm in product design: Design for circularity. Circular design focuses on developing design strategies that enable circularity, such as material selection, design for disassembly, product lifetime extension strategies, and the design of closed-loop systems. Thus, the first section after the introduction of this chapter (Sect. 5.2) provides an overview of the research field of design for circularity. After reviewing the concept of the circular economy (CE), different frameworks for operationalizing the CE are outlined. Based on this review and discussion, we derive three implications for circular design: a change in product design, a change in service design, and a change in user behavior. Finally, we address the implementation challenges that manufacturing companies face when transitioning to a CE. In the subsequent expert discussion (Sect. 5.3) between Oliver Zipse and Prof.-Ing. Sandro Wartzack, these issues are reflected upon from a practitioner’s perspective. In the final section of this chapter (Sect. 5.4), future avenues of research are presented, and the challenges and opportunities of circular design strategies are discussed.<br
Keywords: Design for circularity; Circular economy; R-strategies; Product life cycle; Product service systems

Cross-Skates mit Elektroantrieb und hybridem Fahrmodus - Wartzack, Sandro; Miehling, Jörg; Kramer, Vincent (WiGeP News, 2023)

Das FEA-Assistenzsystem - Analyseteil FEdelM - Sprügel, Tobias; Wartzack, Sandro (Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik, 2016)
Die simulative Absicherung von Produkten in den frühen Phasen der Produktentwicklung wird immer wichtiger, um den Anforderungen nach steigender Effizienz gerecht zu werden. Da das Angebot an erfahrenen Berechnungsingenieuren mit langjähriger Berufserfahrung begrenzt ist gilt es weniger erfahrene Simulationsanwender bei der Durchführung von aussagekräftigen Finite-Elemente-Simulationen zu unterstützen. Die Autoren stellen im Rahmen des Beitrags das Konzept des Analyseteils FEdelM eines FEA-Assistenzsystems vor, welches strukturmechanische Finite-Elemente (FE) Simulationen auf Plausibilität überprüft und auftretende Fehler möglichst automatisiert zu erkennt und behebt. Hierbei werden die einzelnen Module und deren Verknüpfungen untereinander und zu anderen Anwendungen vorgestellt.
Keywords: FEA-Assistenzssstem; FEdelM; Plausibilitätsprüfung; FORPRO²

Data-driven analysis of cold-formed pin structure characteristics in the context of versatile joining processes - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (IOP Conference Series, 2021)
Due to increasingly strict emission targets and regulatory requirements, especially for companies in the transport industry, the demand for multi-material-systems is continuously rising in order to lower energy consumption. In this context, mechanical joining processes offer an environmentally friendly and flexible alternative to established joining methods, especially in the field of lightweight design. For example, cold-formed cylindrical pin structures show high potentials in joining multi-material-systems without auxiliary elements. The pin structures are joined either by pressing them directly into the joining partner or by caulking with a pre-punched part. However, to evaluate the strength of the joint and to ensure the joining reliability for versatile processes, such as changing joining partners or batch variations, engineering designers currently have only limited design principles available compared to thermal joining processes. Consequently, the design of an optimal pin joint requires cost- and time-intensive experimental investigations and adjustments to design or process parameters. As a solution, data-driven methods offer procedures for structuring data and identifying dependencies between varying process parameters and resulting pin structure characteristics. Motivated by this, the paper presents an approach for the data-driven analysis of cold-formed pin structures and offers a deeper understanding of how versatile processes affect the pin characteristics. Therefore, the application of an intelligent design of experiment in combination with several machine learning methods enable the setup of a best-fitting meta-model. Resulting, the determination of a mathematical model provides the opportunity to accurately estimate the pin height considering only relevant geometrical and process parameters with a prediction quality of 95

Data-driven design challenges in the early stages of the product development process - Briard, Tristan; Jean, Camille; Aoussat, Améziane; Véron, Philippe; Le Cardinal, Julie; Wartzack, Sandro (Proceedings of the Design Society, 2021)
With the rapid development of digital technologies, products connectivity is increasing as well as the data produced and collected. Forecasts on product development predict that this trend will keep on growing. In this context, new design solutions based on data are emerging. Those data-driven design approaches are common for identifying the customers’ need when developing a new product. However, few studies cover data-driven design in the other early stages of product design. Thus, the research question addressed in this paper is: what are the challenges of data-driven design research in the early phases of the product development process? Through a literature review and a workshop proposed at the conference DESIGN 2020, this paper offers a first glimpse of future research leads. A list of 5 challenges for data-driven design in the early stages of product design is proposed and ranked from short term to long term.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Big data; Data-driven design; Design practice; Early design phases; Internet of Things

Data Driven Design Selection and Generation - An Industrial Case Study on Electric Motors - Tüchsen, Johann; Pop, Adrian-Cornel; Koch, Matthias; Schleich, Benjamin; Wartzack, Sandro (DESIGN 2018 - 15th International Design Conference, 2018)
This paper presents a novel design selection and generation mechanism for fast and efficient solution-finding based on the knowledge-based systems concept. Such a mechanism can be fully exploited in the early design phases (i.e. quotation phase), when the supplier has to propose both a technically feasible and pricewise attractive solution to the OEM's request. The benefits of the presented method are a massive time reduction from several weeks to less than one day as well as an improvement of the overall solutions quality as all possible technologies are evaluated parallel.<br
Keywords: selection and generation; electric motor design; data driven design; knowledge based engineering (KBE); decision making

Data driven product portfolio analysis of electric motors based on product platforms using knowledge-based systems - Tüchsen, Johann; Pop, Adrian-Cornel; Koch, Matthias; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
For a company it is necessary to know, which products can be configured using carry-over-parts or the same technology. This can become quite relevant in the context of automobile electrification, where complex mechatronic systems are used. Consisting of various mechanical components, these systems perform the required function while being actuated by electronically controlled motors. To solve this, a novel mechanism for data driven portfolio analysis based on product platforms using knowledge-based systems is proposed in this paper. Further, the mechanism is tested by applying it to an electrical motors' case study. Using this method, all possible combinations of a product platform are calculated and finally displayed in different product portfolios. Additionally, all the non-feasible motor designs are removed from the solutions portfolio using the acquired knowledge base and performing design checks. The latter are employed for penalising and eliminating from the pareto-front of the designs, which violate the thermal, mechanical and acoustic constraints. The generated product portfolio can be used further to expand the systems engineering collaboration and support decision-making.<br
Keywords: Knowledge-Based Systems; Electric Motors; Platform strategies; Portfolio management; Knowledge management

Datenakquisition und -analyse im Assistenzsystem zur lärmreduzierten Auslegung rotierender Maschinen - Küstner, Christof; Wachsmuth, Philipp; Wartzack, Sandro (Beiträge zum Stuttgarter Symposium für Produktentwicklung (SSP2015), 2015)
In diesem Beitrag wird die Datenakquisition und -analyse der wissensbasierten Navigation des Assistenzsystems (AS) ALARM für die lärmreduzierte Auslegung rotierender Maschinen vorgestellt. Zu Beginn werden die Wissensakquisitionskomponenten unterschiedlicher AS diskutiert. Danach wird der Prozess der Datenakquisition und -analyse und die Struktur der Wissensbasis des AS ALARM vorgestellt. Im Anschluss wird die Datenakquisition gezeigt, die so konzipiert ist, dass möglichst alle erhobenen Daten im Produktentwicklungsprozess ins AS ALARM überführt werden können. Hierzu wird eine Unterteilung der Daten in Datentupel und Datensätze vorgenommen, sowie die Datenquellen spezifiziert. Anhand eines Anwendungsbeispiels wird abschließend gezeigt, wie der Produktentwickler bei der Datenakquisition unterstützt wird.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.datena
Keywords: Assistenzsystem; Wissensakquisition; Datenakquisition; Schall und Schwingungen

Deep learning in sheet-bulk metal forming part design - Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (DS92: Proceedings of the DESIGN 2018 15th International Design Conference, 2018)
Within the Transregional Collaborative Research Centre 73, a self-learning engineering workbench is being developed. It assists product developers in designing sheet-bulk metal formed (SBMF) parts by computing the effects of given product and process characteristics on the product properties. This contribution presents a novel approach to using deep learning methods for the properties prediction. By making use of a parameter study of 20 SBMF part designs, a metamodel is trained and used to predict the total equivalent plastic strain on local level as an indicator for part manufacturability.<br
Keywords: data mining; data driven design; characteristics and properties; deep learning

Definition, Klassen und Anwendungsmöglichkeiten des Digitalen Zwillings für die Antriebstechnik - Wilking, Fabian; Schleich, Benjamin; Wartzack, Sandro (WiGeP News, 2020)

Der Einfluss der Sortierung auf das statistische Verhalten von Funktionsmaßen - Aschenbrenner, Alexander; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
In an automated assembly process, the exchangeability of the components is a necessity. This could imply harsh requirements concerning the geometric definition and tolerancing of components. The classification of components is one way to decrease these requirements. Classification used to be limited to manual assembly and small-scale production. Advances in online measuring technology make the classification of components also applicable for mass fabrication. Employing classification, accuracy and process capability of the production could be increased. Besides these positive effects, classification also poses some challenges for the variation simulation. This contribution addresses approaches on how to tackle these challenges and which effects can arise from classification.
Keywords: Sorting and Classification; Combinatorial Analysis; Variation Simulation; Tolerance Management

Derivation and Validation of Linear Elastic Orthotropic Material Properties for Short Fibre Reinforced FLM Parts - Witzgall, Christian; Völkl, Harald; Wartzack, Sandro (Journal of Composites Science, 2022)
Additively manufactured parts play an increasingly important role in structural applications. Fused Layer Modeling (FLM) has gained popularity due to its cost-efficiency and broad choice of materials, among them, short fibre reinforced filaments with high specific stiffness and strength. To design functional FLM parts, adequate material models for simulations are crucial, as these allow for reliable simulation within virtual product development. In this contribution, a new approach to derive FLM material models for short fibre reinforced parts is presented; it is based on simultaneous fitting of the nine orthotropic constants of a linear elastic material model using six specifically conceived tensile specimen geometries with varying build direction and different extrusion path patterns. The approach is applied to a 15 wt.% short carbon-fibre reinforced PETG filament with own experiments, conducted on a Zwick HTM 5020 servo-hydraulic high-speed testing machine. For validation, the displacement behavior of a geometrically more intricate demonstrator part, printed upright, under bending is predicted using simulation and compared to experimental data. The workflow proves stable and functional in calibration and validation. Open research questions are outline
Keywords: short fibre reinforced plastics; SFRP; fused layer modeling; FLM; fused deposition modeling; FDM; material models; simulation

Der KTmfk und die Arbeitsgruppe "Toleranzmanagement" - Wartzack, Sandro; Walter, Michael; Schleich, Benjamin; Aschenbrenner, Alexander; Heling, Björn (Summer School Toleranzmanagement - Beiträge zur 2. Summer School - September 2015, 2015)

Design and Additive Manufacturing of a Passive Ankle–Foot Orthosis Incorporating Material Characterization for Fiber-Reinforced PETG-CF15 - Steck, Patrick; Scherb, David; Witzgall, Christian; Miehling, Jörg; Wartzack, Sandro (Materials, 2023)
The individualization of patient-specific ankle joint orthoses is becoming increasingly important and can be ideally realized by means of additive manufacturing. However, currently, there are no functional additively manufactured fiber-reinforced products that are used in the field of orthopedic treatment. In this paper, an approach as to how additively manufactured orthopedic products can be designed and produced quickly and flexibly in the future is presented. This is demonstrated using the example of a solid ankle–foot orthosis. For this purpose, test results on PETG-CF15, which were determined in a previous work, were integrated into a material map for an FEA simulation. Therewith, the question can be answered as to whether production parameters that were determined at the test specimen level can also be adapted to real, usable components. Furthermore, gait recordings were used as loading conditions to obtain exact results for the final product. In order to perfectly adapt the design of the splint to the user, a 3D scan of a foot was performed to obtain a perfect design space for topology optimization. This resulted in a patient-specific and stiffness-optimized product. Subsequently, it was demonstrated that the orthosis could be manufactured using fused layer modelling. Finally, a comparison between the conventional design and the consideration of AM-specific properties was made. On this basis, it can be stated that the wearing comfort of the patient-specific design is very good, but the tightening of the splint still needs to be improved.<br
Keywords: ankle–foot orthoses; additive manufacturing; ankle splints; fused layer modelling; topology optimization; fiber reinforcement; material characterization; user-centered design

Design for composites: Derivation of manufacturable geometries for unidirectional tape laying - Völkl, Harald; Kießkalt, Andreas; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Even though providing excellent specific stiffness and strength properties, high specific energy absorption and a great degree of design freedom, fibre-reinforced plastics still have to make their way into higher volume applications. Addressing the manufacturing challenges, particularly efficient production techniques are Automated Tape Laying (ATL) and Automated Fiber Placement (AFP), as pointed out by various studies and use cases. However, current Computer Aided Engineering approaches for optimised laminate design still lack the capability to produce results suitable for ATL/AFP. A new method for deriving tape courses from any finite element laminate optimisation result is presented and applied to a virtual demonstrator. An outlook is given on further necessities of extending current laminate optimisation approache
Keywords: Optimisation; Computational design methods; Design for X (DfX); Fibre Reinforced Plastics; Manufacturing

Design for composites: Tailor-made, bio-inspired topology optimization for fiber-reinforced plastics - Völkl, Harald; Wartzack, Sandro (DESIGN 2018 - 15th International Design Conference, 2018)
A bio-inspired topology optimization approach with simultaneous fiber orientation optimization for fiber-reinforced plastics is introduced. To scrutinize the optimization potential of the new approach when compared to methods not considering fiber orientation during the optimization process, a case study using a bike rocker arm is presented. In this study, slightly better stiffness behavior of the new approach compared to its counterparts could be observed. However, as far as strength behavior (matrix failure) is concerned, significant gains could be achieved, both in numbers and visually.<br
Keywords: Lightweight Design; Bio-inspired design; Topology optimization; Fiber-reinforced plastics

Design for Friction Reduction – Durchgängige Unterstützung des Konstrukteurs durch den gezielten Einsatz von Wälzlagerreibungs-Berechnungswerkzeugen - Seiler, Katrin; Tremmel, Stephan; Wartzack, Sandro (25. DfX-Symposium, 2014)
Keywords: Wälzlager; Reibung; MKS; Tribologie; Hydrodynamik

Design-for-manufacture of sheet-bulk metal formed parts - Breitsprecher, Thilo; Sauer, Christopher; Sperber, Christian; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), Vol. 4: Design for X, 27.-30. Juli 2015, Mailand, 2015, S. 11-20., 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.design

Design for mobility - A methodical approach - Schmidt, Johanna; Krüger, Daniel; Eilmus, Sandra; Paetzold, Kristin; Wartzack, Sandro; Krause, Dieter (Proceedings of DESIGN 2012, the 12th International Design Conference, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.design_9
Keywords: Design for the elderly; Digital human modeling; Mobility; Product family; Variety

Design for noise reduction – The architecture of an engineering assistance system for the development of noise-reduced rotating systems - Küstner, Christof; Breitsprecher, Thilo; Wartzack, Sandro (DS 75-5: Proceedings of the 19th International Conference on Engineering Design (ICED13), 2013)
Despite detailed planning, conceptual and embodiment design important product properties like the acoustical behavior of complex machinery are only revealed in the later development phases (e. g. prototyping phase). If annoying acoustical behavior of machinery is identified in the later development phases, there will be the need to time- and money-consuming macro-iterations, which sometimes go back to the conceptual phase. This means a high financial risk especially for capital goods like wind turbines, because the operating license of wind turbines can be refused. In this paper, the demands and the basic architecture of a knowledge-based engineering (KBE) assistance system for the development of noise reduced rotating machines will be presented. It will assist the development engineers by context-sensitive allocation of design-relevant knowledge that enables them to identify components of complex machinery which are critical with respect to noise creation, noise transmission or noise radiation. With the aid of this assistance system, which is called ALARM, the risk of a drop back to the conceptual phase regarding undesirable acoustic product properties will be reduced.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.design
Keywords: Design for x; Information management; Knowledge management; Knowledge-based engineering; Wind energy

Design for X (DFX) - Wartzack, Sandro; Meerkamm, Harald; Bauer, Stefan; Krehmer, Hartmut; Stockinger, Andreas; Walter, Michael; Schleich, Benjamin (Handbuch Konstruktion, 2018)
Erfolgreiche Produkte müssen sowohl die Kundenanforderungen als auch die Restriktionen erfüllen, die sich aus dem gesamten Produktenstehungsprozess und -lebenszyklus, d. h. von der Fertigung bis hin zur Entsorgung ergeben. In der Konzeptphase, vor allem aber beim Entwerfen, haben die Entwickler und Konstrukteure eine Fülle von Gestaltungsrichtlinien zu beachten, die sich in ihrer Gesamtheit unter dem Kürzel DFX (Design for X) subsumieren lassen. Natürlich ist die Erfüllung der Funktion die wichtigste Hauptforderung bei der Konstruktion eines Produkts. Darüber hinaus gilt es aber, eine Vielzahl von gegenseitig vernetzten Forderungen und Restriktionen unter Abwägung ihrer Wichtigkeit/Gewichtung zu berücksichtigen (Ehrlenspiel 2009). Dabei ist zu beachten, dass vor allem die frühen Phasen des Konstruktionsprozesses von entscheidender Bedeutung sind, denn hier werden bekanntlich zwei Drittel aller Produkteigenschaften festgelegt. DFX steht einerseits für ein umfassendes und komplexes Wissensgebiet aus zum Teil verschiedenen Fachdomänen, andererseits aber auch für eine geeignete methodische Vorgehensweise mit Entscheidungen zwischen sich zum Teil widersprechenden Aspekten und dem Einsatz leistungsfähiger Methoden und vor allem aber rechnerunterstützter Werkzeuge. DFX kann auch verstanden werden als eine ganzheitliche Denkweise (Philosophie), die den Konstrukteuren zweifache Unterstützung bieten kann – und zwar als eine Organisationshilfe, mit der sich die grundlegenden Randbedingungen für ein Produkt bereits in der Planungs- und Konzeptphase festlegen lassen, und als detaillierte Beschreibungen/Richtlinien für die Konstrukteure, nach denen sich in den späten Phasen des Produktenwicklungsprozesses die Gestalt eines Produktes bestimmen lässt. Es muss festgehalten werden, dass der Begriff DFX in der industriellen Praxis noch wenig gebräuchlich ist, obwohl sich doch alle Entwicklungs- und Konstruktionsprozesse um diese Thematik drehen. Vielfach hat sich in jüngster Zeit in Unternehmen der Begriff Frontloading etabliert. DFX ist in der hier aufzuzeigenden begrifflichen Strenge und stringenten Strukturierung sowie Anwendung von Methoden und Werkzeugen vor allem in der Forschungslandschaft geläufig. Gleichwohl sind die hier angesprochenen Inhalte für die Praxis von hoher Relevanz.<br

Designing Amorphous Carbon Coatings Using Numerical and Experimental Methods within a Multi-Scale Approach - Tremmel, Stephan; Marian, Max; Rothammer, Benedict; Weikert, Tim; Wartzack, Sandro (14th International Conference THE A Coatings, 2020)
Amorphous carbon coatings have the potential to effectively reduce friction and wear in tribotechnical systems. The appropriate application of amorphous carbon layers requires both, a very good understanding of the tribological system and knowledge of the relationships between the fabrication of the coatings and their properties. In technical practice, however, the coatings’ development and their selection on the one hand and the design of the tribological system and its environment on the other hand are usually very strongly separated. The present work therefore aims to motivate the integrated development of tribotechnical systems with early consideration of the potential of amorphous carbon coatings. An efficient integrated development process is presented, which makes it possible to determine the boundary conditions and the load collective of the tribological system based upon an overall system and to derive the requirements for a tailored coating. In line with the nature of tribology, this approach must cover several scales. In this respect, the development process follows a V-model. The left branch of the V-model is mainly based upon a simulation chain including multibody and contact simulations. The right branch defines an experimental test chain comprising coating characterization to refine the contact simulation iteratively and tribological testing on different levels to validate the function fulfillment. Within this contribution, the outlined approach is illustrated by two use cases, namely the cam/tappet-pairing and the total knee replacement.<br
Keywords: Coating; Design Method; Tribology

Designing Amorphous Carbon Coatings Using Numerical and Experimental Methods within a Multi-Scale Approach - Tremmel, Stephan; Marian, Max; Rothammer, Benedict; Weikert, Tim; Wartzack, Sandro (Defect and Diffusion Forum, 2020)
Amorphous carbon coatings have the potential to effectively reduce friction and wear in tribotechnical systems. The appropriate application of amorphous carbon layers requires both, a very good understanding of the tribological system and knowledge of the relationships between the fabrication of the coatings and their properties. In technical practice, however, the coatings’ development and their selection on the one hand and the design of the tribological system and its environment on the other hand are usually very strongly separated. The present work therefore aims to motivate the integrated development of tribotechnical systems with early consideration of the potential of amorphous carbon coatings. An efficient integrated development process is presented, which makes it possible to determine the boundary conditions and the load collective of the tribological system based upon an overall system and to derive the requirements for a tailored coating. In line with the nature of tribology, this approach must cover several scales. In this respect, the development process follows a V-model. The left branch of the V-model is mainly based upon a simulation chain including multibody and contact simulations. The right branch defines an experimental test chain comprising coating characterization to refine the contact simulation iteratively and tribological testing on different levels to validate the function fulfillment. Within this contribution, the outlined approach is illustrated by two use cases, namely the cam/tappet-pairing and the total knee replacement.
Keywords: Tribology; Coating; Design method

Designing lightweight structures under consideration of material and structure uncertainties on different levels of the building block approach - Hartwich, Tobias S.; Völkl, Harald; Wartzack, Sandro; Krause, Dieter (Proceedings of the 31st Symposium Design for X, DFX 2020, 2020)
Lightweight design is an important aspect in the development of components to reduce material use and obtain energy-efficient structures. Frequently, lightweight structures are designed for one or a few load cases. Therefore, optimized designs can be less robust against changes in boundary conditions, scattering material parameters or deviating tolerances. Thus, these structures must be designed with safety factors that counteract the targeted lightweight design goal. In this article, an approach for the consideration of uncertainties is presented. The approach allows evaluating potentials of the accurate consideration of uncertainties. Finally, the developed approach is implemented for the calculation of the buckling load and torsional strength of thin-walled CFRP cylinderical shells.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Buckling; Building Block Approach; CFRP; Lightweight Design; Uncertainties

Designing of hybrid joints at the early embodiment design stage - Kellermeyer, Markus; Klein, Daniel; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), Vol. 4: Design for X, 27.-30. Juli 2015, Mailand, 2015, S. 11-20., 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.design_9
Keywords: Leichtbau; Composites; Simulation

Designing surface textures for EHL point-contacts - Transient 3D simulations, meta-modeling and experimental validation - Marian, Max; Grützmacher, Philipp; Rosenkranz, Andreas; Tremmel, Stephan; Mücklich, Frank; Wartzack, Sandro (Tribology International, 2019)
Micro-textures applied on rubbing surfaces have gained tremendous attention in the tribological community. Numerous studies deal with the deduction and testing of beneficial micro-textures. Nevertheless, not all questions have been answered yet. Will texturing really deliver as good effects as frequently claimed? Are there optimum texture designs? Are there occasions where texturing could enhance the tribological performance but is questionable from other perspectives? Therefore, ball-on-disc experiments are carried out with a special emphasis on the relative position of micro-texture and counter body. Furthermore, transient EHL simulations are performed, addressing the effects of structural parameters and relative texture's position on the tribological performance. Finally, meta-modeling with subsequent optimization is applied to predict numerically derived optima and robust texture designs.
Keywords: Surface texturing; Elastohydrodynamic lubrication; Optimization; Texture design

Design, Manufacturing and Tribological Performance of Microtextured Bucket Tappets for Friction Reduction in the Valve Train - Marian, Max; Zahner, Michael; Tremmel, Stephan; Andreas, Kolja; Merklein, Marion; Wartzack, Sandro (6th World Tribology Congress, 2017)
In order to improve lubricating conditions as well as friction and wear behavior, the surfaces of contacting bodies in lubricated tribological contacts can be microtextured. While this approach has already reached industrial application for lower loaded contacts, the effects for higher loaded contacts, where elastic deformation plays a significant role, are still topic of basic research. For this reason, microtextures are adapted to the conditions of the tribological system of the bucket tappet/camshaft contact in the valve train as a demonstrator and major contributor to combustion engine losses. The tribological performance of various microtexture geometries and arrangements is analyzed on a one bucket tappet/one cam test-rig using series production valve train parts. A resistive measurement system is first applied to the highly dynamic tappet/camshaft contact and allows the investigation of the correlation between lubricating conditions and friction force. In the tests, a significant friction force reduction using microtextured surfaces compared to polished surfaces is achieved. Additionally, quantitative ex-situ wear characterization is carried out for long-run test cycles, using Laser Scanning Microscopy. Thus, wear mechanisms and rates are compared with the measurements of lubricating conditions and friction force. Besides the identification of advantageous microtexture geometries and arrangements regarding the tribological performance, possibilities and limitations of the manufacturing technology are examined. In order to realize high-volume production, a micro coining process was studied. In this regard the manufacturing of the coining punch using µEDM and the coining process itself were analyzed with respect to accuracy and reproducibility. Additionally, the durability of the pins was investigated for the micro coining process. The limitations of the manufacturing process and of the micro coining process are summarized in a process windo
Keywords: Microtextures; Micro Coining; EHL Contact

Design of Amorphous Carbon Coatings Using Gaussian Processes and Advanced Data Visualization - Sauer, Christopher; Rothammer, Benedict; Pottin, Nicolai; Bartz, Marcel; Schleich, Benjamin; Wartzack, Sandro (Lubricants, 2022)
In recent years, an increasing number of machine learning applications in tribology and coating design have been reported. Motivated by this, this contribution highlights the use of Gaussian processes for the prediction of the resulting coating characteristics to enhance the design of amorphous carbon coatings. In this regard, by using Gaussian process regression (GPR) models, a visualization of the process map of available coating design is created. The training of the GPR models is based on the experimental results of a centrally composed full factorial 23 experimental design for the deposition of a‑C:H coatings on medical UHMWPE. In addition, different supervised machine learning (ML) models, such as Polynomial Regression (PR), Support Vector Machines (SVM) and Neural Networks (NN) are trained. All models are then used to predict the resulting indentation hardness of a complete statistical experimental design using the Box–Behnken design. The results are finally compared, with the GPR being of superior performance. The performance of the overall approach, in terms of quality and quantity of predictions as well as in terms of usage in visualization, is demonstrated using an initial dataset of 10 characterized amorphous carbon coatings on UHMWPE.
Keywords: Machine Learning; Amorphopus Carbon Coatings; UHWMPE; Total Knee Replacement; Gaussian Processes

Detection and Classification of Symbols in Principle Sketches using Deep Learning - Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the International Conference on Engineering Design (ICED21), 2021)
Data-driven methods from the field of Artificial Intelligence or Machine Learning are increasingly applied in mechanical engineering. This refers to the development of digital engineering in recent years, which aims to bring these methods into practice in order to realize cost and time savings. However, a necessary step towards the implementation of such methods is the utilization of existing data. This problem is essential because the mere availability of data does not automatically imply data usability. Therefore, this paper presents a method to automatically recognize symbols from principle sketches, which allows the generation of training data for machine learning algorithms. In this approach, the symbols are created randomly and their illustration varies with each generation. . A deep learning network from the field of computer vision is used to test the generated data set and thus to recognize symbols on principle sketches. This type of drawing is especially interesting because the cost-saving potential is very high due to the application in the early phases of the product development proces
Keywords: Artificial intelligence Machine learning Early design phases

Detection of Plausibility and Error Reasons in Finite Element Simulations with Deep Learning Networks - Bickel, Sebastian; Götz, Stefan; Wartzack, Sandro (Algorithms, 2023)
The field of application of data-driven product development is diverse and ranges from requirements through the early phases to the detailed design of the product. The goal is to consistently analyze data to support and improve individual steps in the development process. In the context of this work, the focus is on the design and detailing phase, represented by the virtual testing of products through Finite Element (FE) simulations. However, due to the heterogeneous data of a simulation model, automatic use is a big challenge. A method is therefore presented that utilizes the entire stock of calculated simulations to predict the plausibility of new simulations. Correspondingly, a large amount of data is utilized to support less experienced users of FE software in the application. Thus, obvious errors in the simulation should be detected immediately with this procedure and unnecessary iterations are therefore avoided. Previous solutions were only able to perform a general plausibility classification, whereas the approach presented in this paper is intended to predict specific error sources in FE simulations.<br

DETECTION OF SINGULARITIES IN FINITE ELEMENT SIMULATIONS: A 3D DEEP LEARNING APPROACH - Bickel, Sebastian; Götz, Stefan; Wartzack, Sandro (Proceedings of the ASME Design Engineering Technical Conference, 2023)
The growing digitalization trend has a great influence and impact on the entire product development domain. The new algorithms and methods transform and improve many established processes and workflows. In addition to converting existing know-how into the new processes, available data can also be used to implement various models to enhance the development process. At the same time, the lack of experienced engineers leads to an increasing number of novice engineers from the field of 3D design, who have to perform tasks from the simulation department. Therefore, support for these less experienced users of product development software through newly available methods from the field of data-driven methods is reasonable. Correspondingly, the goal of this paper is to present a method for singularity detection in Finite Element (FE) simulations that detects the presence of a singularity in a computed simulation with the help of Deep Learning. For this purpose, a dataset of calculated simulations with several components with and without singularities is first generated. Then, a new approach based on PointNet and labeled datasets of FE simulations is proposed. Afterwards, the new procedure is compared against a classic Machine Learning approach, whereby different parameter settings were investigated for both approaches.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Data-Driven Product Development; Deep Learning; Finite Element Simulation; Machine Learning

Determination of the Young´s Modulus of Hard Coatings on Soft Polymer Substrates - Sander, Thomas; Tremmel, Stephan; Wartzack, Sandro (40th International Conference on Metallurgical Coatings and Thin Films ICMCTF 2013, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.determ

Determining the influence of different process parameters on the versatile self-piercing riveting process using numerical methods - Kappe, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Bobbert, Mathias; Wartzack, Sandro; Meschut, Gerson (Journal of Manufacturing Processes, 2022)

Development and Evaluation of Tool Sided Surface Modifications for Dry Deep Drawing of Steel and Aluminum Alloys - Merklein, Marion; Schmidt, Michael; Wartzack, Sandro; Tremmel, Stephan; Andreas, Kolja; Häfner, Tom; Zhao, Rong; Steiner, Jennifer (Dry Metal Forming Open Access Journal, 2015)

Development of a hoop-strength test for model sphero-cylindrical dental ceramic crowns: FEA and fractography - Belli, Renan; Völkl, Harald; Csato, Stefan; Tremmel, Stephan; Wartzack, Sandro; Lohbauer, Ulrich (Journal of the European Ceramic Society, 2020)
Here we describe the development of a mechanical test that simulates a circumferential “hoop-stress” at the margins of model dental ceramic crowns. A simplified sphero-cylindrical geometry was modelled in two thicknesses and machined out of two glass-ceramic materials. The specimens were loaded by a conical metallic piston to induce circumferential hoop-stresses at the margins until fracture. Broken specimens were fractographically analyzed to determine the location of the fracture origin and to measure the dimensions of the critical defect, allowing the calculation of the stress at failure from fracture mechanics relations. For thick specimens, machining defects at the outer margins barely played a role in fracture initiation. For thin specimens, outer defects started to dominate the failure mode. CAD/CAM machining showed to predispose thinner margins to early fracture. Crowns should be designed with increased thickness in order to minimize the effect of marginal damage in the circumferential stress field inducing fracture.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Dental; Finite element analysis; Fractography; Glass-ceramic; Mechanical test

Development of a Toolkit of Methods for Simulations in Product Development - Carro Saavedra, Cristina; Marahrens, Nils-Jorge; Schweigert, Sebastian; Kestel, Philipp; Kremer, Simon; Wartzack, Sandro; Lindemann, Udo (IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2016)
Simulations contribute to the efficiency of the product development process and the quality of the developed products. However, their integration in the development process can be improved. We propose a knowledge-based framework, containing a toolkit of simulation methods as its central element to integrate simulations in the product development process. Within this paper, we briefly introduce the knowledge-based framework and we present the toolkit structure and the methodology for its development.

DFG-Forschergruppe "Prozessorientiertes Toleranzmanagement" an der FAU gestartet - Wartzack, Sandro; Schleich, Benjamin; Heling, Björn (WiGeP News, 2016)
Fünf Lehrstühle der FAU Erlangen-Nürnberg forschen gemeinsam an Fragestellungen des ganzheitlichen Toleranzmanagements

Die Auswirkung der Reihenfolge von Mess- und Simulationsdaten auf das Ergebnis der Kreuzvalidierung in KDD Prozessen - Küstner, Christof; Breitsprecher, Thilo; Wartzack, Sandro (Design for X - Beiträge zum 24. DfX-Symposium 2013, 2013)
Knowledge Discovery in Databases (KDD) is an emerging computer-aided methodology that enables design engineers to acquire design-relevant knowledge from complex data. Sources for this data are experiments and simulations in nearly every domain that is related to the product life cycle (e. g. structural mechanics, manufacturing engineering, prototyping). The inter-European research project EUREKA ALARM (assistance system for the development of noise reduced rotating machines), inter alia, aims at the automatic knowledge acquisition from data sources like multi body simulation results and noise measurements of modern wind turbines. The design-relevant knowledge is represented by so called metamodels, behavior or surrogate models. These models enable the design engineer to predict the noise behavior of a wind turbine, based on different parameters like gear geometry, gear number, etc.. It is obvious that design engineers need to estimate the prediction quality of the models quantitatively for example by means of prediction performance values as relative prediction error, root mean squared error or root mean absolute error. The use of metamodels with poor prediction behavior are of cause not the objective of KDD methodology. In order to derive these performance values different procedures are suggested according to KDD literature, whereas the k-fold cross validation is the most common one. To ensure a statistically robust performance estimation it is advised to repeat this procedure which has led to a ten-times ten-fold cross validation. During the research efforts of ALARM a new issue appeared. It can be shown that the structure of the input dataset has an impact on the performance estimation. In this contribution an approach is presented how to handle this issue.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.dieaus

Die Crux der Faserorientierung - Klein, Daniel; Gruber, Georg; Wartzack, Sandro (Kunststoffe, 2014)
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.diecru
Keywords: Leichtbau; Composites; kurzfaserverstärkte Thermoplaste

Die eigenschaftsbasierte Produktentwicklung unter Berücksichtigung der differenziellen Anforderungen älterer Nutzer - Luft, Thomas; Kamin, Stefan; Miehling, Jörg; Lang, Frieder; Wartzack, Sandro (Design for X: Beiträge zum 24. DfX-Symposium 2013, 2013)
Population aging is one of the most important challenges in human history. Adapting this challenge involves the development of products and services for improving activity, health and quality of life in old age. The development of such products requires interdisciplinary collaboration between disciplines of aging and engineering sciences. This involves integrating the specific needs of older users into product development. The aim of this work is to describe a methodical approach combining behavioural and psychological perspectives on technology use in old age with engineering sciences. This interdisciplinary procedure is described based on the development of a bicycle for improving mobility in old age and focused on the analysis and assessment of differential user requirements. These requirements are translated into a matrix-based product description allowing product developers to derive product properties and to set the required characteristics for each of these properties. As a consequence, this approach may contribute to the improved development of innovative products in old ag
Keywords: design methodology; property-based product development; matrix-based product description; user-centred design; technology and aging

Die Einbettung des Toleranzmanagements in den Produktentwicklungsprozess - Wartzack, Sandro; Schleich, Benjamin; Walter, Michael; Ziegler, Philipp (Summer School Toleranzmanagement: Beiträge zur 1. Summer School, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.dieein

Die matrixbasierte Produktbeschreibung als Bestandteil des Vorgehensmodells in der eigenschaftsbasierten Produktentwicklung - Luft, Thomas; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung (SSP), 2013)
Die zentrale Aufgabe von Produktentwicklern besteht darin, die stetig steigenden Anforderungen an Qualität, Kosten und Funktionalität technischer Produkte zu erfüllen, indem durch die Festlegung geeigneter Merkmale die vom Kunden gewünschten Produkteigenschaften realisiert werden. Das Ziel der Autoren ist daher die Entwicklung eines geeigneten Vorgehensmodells in der eigenschaftsbasierten Produktentwicklung, welches die Entwickler zielgerichtet durch den Entwicklungsprozess führt sowie bei der Erfassung des erreichten Produktreifegrades und bei der Durchführung von nötigen Iterationen unterstützt. Die dafür erforderliche matrixbasierte Produktbeschreibung steht im Fokus des Beitrags. Dabei wird das Wechselspiel der Abhängigkeiten zwischen Merkmalen, Eigenschaften und dem daraus resultierenden Verhalten am Beispiel eines Fahrwerkes aufgezeigt.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.diemat
Keywords: Konstruktionsmethodik; eigenschaftsbasierte Produktentwicklung; Vorgehensmodell; matrixbasierte Produktbeschreibung

Die neue VDI-Richtlinie 5610 Blatt 2 „Wissensbasierte Konstruktion“ - Luft, Thomas; Roth, Daniel; Wartzack, Sandro; Binz, Hansgeorg (Stuttgarter Symposium für Produktentwicklung (SSP), 2017)
The targeted and systematic handling of knowledge is a key factor in the product development process. When capturing and formalizing the knowledge relevant for engineering and integrating it into CAD systems one is faced with high requirements. Various methods and tools of Knowledge Based Engineering (abbr. KBE) can help designers to successfully meet those challenges. However, a generally valid description for the realization of KBE applications does not exist yet. Therefore, this paper aims to introduce a procedure for the implementation of KBE applications consisting of the following four phases: planning, development, test, and the operation of a KBE application. Furthermore, the roles involved as well as the issue of knowledge protection are considered. The final chapter introduces basic (software) technical solutions for KBE and one specific implementation of a KBE system application. Ein entscheidender Faktor innerhalb des Produktentwicklungsprozesses ist der zielgerichtete und systematische Umgang mit Wissen. Das konstruktionsrele-vante Wissen zu erfassen, zu formalisieren und in CAD-Systeme zu integrieren ist dabei von hohen Anforderungen geprägt. Verschiedene Methoden und Werkzeuge des „Wissensbasierten Konstruierens“ (Knowledge Based Engineering, kurz: KBE) können Konstrukteure dabei unterstützen, diese Herausforderungen erfolgreich zu bewältigen. Bislang existiert jedoch keine allgemeingültige Beschreibung zur Realisierung von KBE-Anwendungen. Daher ist die Zielsetzung des Beitrags die Vorstellung einer Vorgehensweise zur Umsetzung von KBE-Anwendungen, die sich aus den vier Phasen Planung, Entwicklung, Test sowie Betrieb einer KBE-Anwendung zusammensetzt. Zudem werden beteiligte Rollen und das Thema Wissensschutz betrachtet. Im abschließenden Kapitel erfolgen die Vorstellung grundsätzlicher (software-)technischer Lösungen zum wissensbasierten Konstruieren sowie eine konkrete Implementierung einer KBE-Systemanwendung.
Keywords: Knowledge Management; Knowledge Based Engineering; Construction Methodology; Guideline Activities; Wissensmanagement; Wissensbasierte Konstruktion; CAD; Konstruktionsmethodik; Richtlinienarbeit

Die Rolle des Wissensingenieurs im Unternehmen – Ergebnisse einer Umfrage und Darstellung in der VDI-Richtlinie "Wissensbasiertes Konstruieren" - Luft, Thomas; Breitsprecher, Thilo; Roth, Daniel; Lindow, Kai; Binz, Hansgeorg; Wartzack, Sandro (DFX 2012: Proceedings of the 23rd Symposium Design for X, 2012)
Knowledge Based Engineering (KBE) offers a variety of methods and tools to design engineers in order to meet the challenges of modern product development processes. However, no universal and consistent approach exists to guide design engineers through the process of developing, implementing and running a KBE application. This led to the establishment of a working group within the VDI (Verein Deutscher Ingenieure). The members are from German companies and research institutes that deal with KBE applications, methods and tools. The aim is to develop a new VDI guideline that describes a methodical procedure for the implementation of a KBE application (referred to as KBE project). A unique approach is the definition of roles within a KBEproject that contribute in different manners depending on the actual project step. The most important role in this case is the knowledge engineer. The role of the knowledge engineer is described in this paper according to the VDI guideline and subsequently this description is compared with the result of a current industrial survey.
Keywords: knowledge based engineering; engineering standards; wissensbasiertes Konstruieren

Digitale Durchgängigkeit im Toleranzmanagement am Beispiel der ganzheitlichen Robustheitsbewertung in frühen Phasen - Horber, Dennis; Brand, Otto; Li, Jiahang; Götz, Stefan; Matthiesen, Sven; Wartzack, Sandro (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

Digital Engineering Methods in Practical Use during Mechatronic Design Processes - Gerschütz, Benjamin; Sauer, Christopher; Kormann, Andreas; Nicklas, Simon J.; Götz, Stefan; Roppel, Matthias; Tremmel, Stephan; Paetzold-Byhain, Kristin; Wartzack, Sandro (Designs, 2023)
This work aims to evaluate the current state of research on the use of artificial intelligence, deep learning, digitalization, and Data Mining in product development, mainly in the mechanical and mechatronic domain. These methods, collectively referred to as “digital engineering”, have the potential to disrupt the way products are developed and improve the efficiency of the product development process. However, their integration into current product development processes is not yet widespread. This work presents a novel consolidated view of the current state of research on digital engineering in product development by a literature review. This includes discussing the methods of digital engineering, introducing a product development process, and presenting results classified by their individual area of application. The work concludes with an evaluation of the literature analysis results and a discussion of future research potentials. <br
Keywords: digital engineering; product development; data mining; machine learning; data-driven methods; system design; system integration; implementation; validation

Digitaler zwilling oder digitales zwillingspärchen? - Wartzack, Sandro (Konstruktion, 2019)
CRIS-Team Scopus Importer:2021-04-20

Digitale Zwillinge und Digitale Zwillingspaare im Kontext des Digital Engineerings - Mögliche Anwendungen und Herausforderungen - Miehling, Jörg; Schleich, Benjamin; Wartzack, Sandro (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2020)
Neben der gezielten Nutzung von Daten und Informationen aus dem gesamten Produktlebenszyklus stellt die Integration des Nutzers und die Absicherung der Nutzer-Produkt-Interaktion im Digital Engineering eine wesentliche Herausforderung dar. Motiviert hierdurch beleuchtet der vorliegende Beitrag wesentliche Potentiale digitaler Zwillinge im Kontext des Digital Engineerings und stellt das Konzept des Digitalen Zwillingspaares als Möglichkeit der digitalen Einbindung des Nutzers in den Produktentstehungsprozess vor.<br

Digital Twins - Definitions, Classes and Business Scenarios for Different Industry Sectors - Wilking, Fabian; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2021)
Over the recent years, several attempts were made to define the concept of the Digital Twin and to create a generic view for utilizing it within the industry. Still, many industry sectors are not able to transfer a generic definition into their product portfolio, as Digital Twins differ from each other to the same degree as physical products differ from each other. Hence, it is crucial to enlarge the definition towards a classification and business scenarios which enable sector specific views on the concept of the Digital Twin and help SME to utilize the concept towards their products. Future engineers will have to design physical products besides a digital counterpart and therefore have to identify interdependencies between these two products during the development. This paper discusses a generic definition of a Digital Twin that can be applied throughout different sectors as well as a classification for Digital Twins to enable the implementation of the concept on several maturity levels regarding the constraints of the product portfolio. In addition, these classes are viewed in different business scenarios and an outlook is given to further increase the usability of Digital Twins within new industry sector

Durchgängige Rechnerunterstützung in der Produktentwicklung aufgrund des Einsatzes von semantisch hochwertiger Features - Wartzack, Sandro; Meerkamm, Harald (Konstruktion, 2000)
UnivIS-Import:2015-03-09:Pub.2000.tech.FT.FT-KLMEFK.durchg

Durchgängiges Toleranzmanagement aus Sicht des Lehrstuhls für Konstruktionstechnik - Wartzack, Sandro; Schleich, Benjamin; Heling, Björn; Götz, Stefan; Hallmann, Martin; Schächtl, Paul; Franz, Michael; Kramer, Vincent (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)

Durchgängige Systemmodellierung - Integration von Zielen in technische Systemmodelle im Kontext des Anforderungsmanagements - Horber, Dennis; Wilking, Fabian; Schleich, Benjamin; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung SSP 2021, 2021)
Durch die steigende Komplexität technischer Konsumentenprodukte beschäftigen sich immer mehr Unternehmen mit Ansätzen, um diese Komplexität greifbarer zu machen. Ein Ansatz dafür ist das Model-Based Systems Engineering (MBSE). Ein zentrales Element dieses Ansatzes ist die Verwendung von Systemmodellen, die zur Beschreibung von Struktur und Verhalten des Systems dienen. Anforderungen lassen sich somit unmittelbar mit Systemelementen verbinden und verifizieren. Die im entwicklungsmethodischen Vorgehen oft vernachlässigten Ziele, die den Anforderungen hierarchisch übergeordnet sind, finden aber auch in diesen Modellen noch keine Anwendung. Dieser Beitrag beschäftigt sich damit, inwiefern sich Ziele konsistent in technische Systemmodelle integrieren lassen, sodass eine durchgängige Modellierung von den Zielen bis hin zu den einzelnen Elementen ermöglicht wird. Dabei werden bereits bestehende Möglichkeiten, hier beispielhaft in der System Modelling Language (SysML), um Systemelemente und Verbindungen ergänzt, um eine konsistente Integration von Zielen gewährleisten zu können und die Syntax der Notationen nicht erheblich zu beeinflussen.<br
Keywords: Model-Based Systems Engineering; MBSE; Systemmodell; Zielmodellierung; Anforderungsmanagement

Dynamics simulation of rolling element bearings considering elastohydrodynamic cage contacts - Seiler, Katrin; Hahn, Bodo; Plogmann, Michael; Tremmel, Stephan; Graf-Goller, Oliver; Wartzack, Sandro (Bearing World, 2016)
Keywords: Hydrodynamik; Elastohydrodynamik; Käfigelastizität; Wälzlager

Dynamics simulation of rolling element bearings considering elastohydrodynamic cage contacts - Seiler, Katrin; Tremmel, Stephan; Wartzack, Sandro; Hahn, Bodo; Plogmann, Michael; Graf-Goller, Oliver (Bearing World Journal, 2016)
Rolling bearings that run under high centripetal acceleration show increased friction in their cage contacts. Hence, the hydrodynamics as well as the deformation of the cage have to be taken into consideration in rolling element bearing dynamics simulations. This paper shows how to consider a full-elastically modelled cage in an elastic dynamics simulation for rolling element bearings to improve the accuracy of simulation results (esp. relating to friction torque). The deformed contact geometry is reconstructed from the cage’s nodes through cubic splines. After that the distance between the deformed cage geometry and the outer ring is calculated, which is considered as the lubrication film thickness. Finally, the contact pressure is calculated depending on the lubrication film thickness by using the short journal bearing theory. The contact calculation is compared to the elastic multi-body dynamics simulation program AVL ExciteTM. Furthermore, the simulation results considering the elastically modelled cage are evaluated to simulation results of a rigidly modelled cage using the rolling element bearings multi-body dynamics simulation program Caba3D. It can be seen that there is a significant influence on the pressure distribution and the friction torque if a rigidly modelled or a full-elastically modelled cage is utilized. The hydrodynamics and the cage’s elasticity should not be neglected in rolling bearing dynamics simulations for bearings that run under high centripetal accelerations.
Keywords: Simulation; Wälzlager; Elastohydrodynamik; Dynamik; Mehrkörpersimulation; MKS

Edge Pressures Obtained Using FEM and Half-Space: A Study of Truncated Contact Ellipses - Jüttner, Michael; Bartz, Marcel; Tremmel, Stephan; Correns, Martin; Wartzack, Sandro (Lubricants, 2022)
In rolling or gear contacts, truncation of the contact ellipse can occur, for example, when an undercut extends into the contact area. For an elastic calculation approach, the edge constitutes a mathematical singularity, which is revealed by a theoretically infinitely high pressure peak. However, when elastic–plastic material behavior is taken into account, the pressure peak is limited by local hardening and yielding of the material, leading to plastic deformations. As a result, those calculations are rather challenging and the results partly unexpected due to the discontinuity contained in the geometry. Nevertheless, to the authors’ knowledge, hardly any published studies exist on elastic–plastic simulations of truncated contact ellipses. Therefore, a numerical study concerning the contact of a rigid ball with an elastic–plastic plane is presented. Due to an undercut in the plane, a quarter of the theoretical Hertzian contact ellipse is cut off. The aim of the study is to investigate the influence of the undercut angle on the pressure distribution and the elastic and plastic deformation at the edge. The use of FEM shows that the undercut angle has a significant effect on the characteristics of the contact. The results obtained using FEM are then used as a reference for comparison with a semi-analytical method (SAM). It is shown that the SAM, based on the half-space, provides comparable results only for very small undercut angles.<br
Keywords: truncated contact; elastic-plastic; finite element method; semi-analytical method; undercut; edge pressure

Effective usage of 2D MXene nanosheets as solid lubricant – Influence of contact pressure and relative humidity - Marian, Max; Song, Gui Cheng; Wang, Bo; Fuenzalida, Victor M.; Krauß, Sebastian; Merle, Benoit; Tremmel, Stephan; Wartzack, Sandro; Yu, Jinhong; Rosenkranz, Andreas (Applied Surface Science, 2020)
Newly emerging Ti3C2Tx–nanosheets (MXenes) have attracted considerable attention in energy storage, catalysis and, more recently, tribology. MXene nanosheets are characterized by a weakly-bonded multi-layered structure with self-lubricating ability, making them a suitable candidate for solid lubrication. This contribution aims at addressing for the first time their application in higher loaded steel/steel dry sliding contacts by investigating the influence of contact pressure and relative humidity on friction and wear performance. Compared to the uncoated reference, a 2.3-fold friction reduction and a 2.7-fold reduction of the wear volume were verified for MXene-coated specimens for moderate contact pressures and low relative humidity. This was due to the in-situ formation of a compacted tribo-film consisting of densified Ti3C2Tx–nanosheets. In contrast, too high pressures induced a partial rupture of the wear-protecting tribo-layer, thus reducing its beneficial effects. Additionally, no beneficial effects regarding friction and/or wear were found at higher relative humidities, which was correlated with the expansion of the basal spacings. Therefore, this study summarizes favorable operating conditions for MXene nanosheets when used as solid lubricant to improve friction and/or wear thus making them excellent candidates for advanced, next-generation solid lubricants.<br
Keywords: MXene-nanosheets; Contact pressure; Relative humidity; Friction reduction; Wear reduction

Effects of deposition parameters on hardness and lubrication properties of thin MoS2 films - Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro (Materialwissenschaft und Werkstofftechnik, 2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.effect

Effects of Nitrogen Modification of Porous PVD–MoS2 Coatings on the Tribological Behavior under Rolling–Sliding Conditions in Vacuum - Seynstahl, Armin; Polzer, Markus; Bartz, Marcel; Wartzack, Sandro; Tremmel, Stephan (Lubricants, 2023)
In order to improve the tribological performance of PVD–MoS2 coatings, which are frequently used as a solid lubricant for operating in challenging environments, e.g., in a vacuum, they can be modified with nitrogen. This work evaluates the tribological behavior and a possible compaction occurring during the initial tribological load in the rolling contact for pure and nitrogen-modified PVD–MoS2 coatings in a vacuum. Short-running tests (1000 cycles) of coated steel discs paired with uncoated steel discs made from 100Cr6 (1.3505, AISI 52100) were conducted on a two-disc tribometer. The slide-to-roll ratio of 10.5% was kept constant, while the load was varied in two steps from 1.1 GPa to 1.6 GPa. Subsequently, a comparison was made between the worn and the pristine coatings by means of nanoindentation and an optical analysis of the wear track. The formation of a load-bearing solid lubrication was achieved for both MoS2-variants. The main differences affected the material transfer and wear mechanisms. The worn coatings reached a similar wear coefficient of 4 × 10−6 mm3N−1m−1 and a possible compaction of the coatings was found, indicated through an increased indentation hardness (for MoS2 1158% and MoS2:N 96% at a 1.1 GPa load). The assumed tribological mechanism changed with nitrogen modification, but scales with increasing load. The nitrogen-modified MoS2 coating showed less compaction than pure MoS2, while the frictional behavior was improved by a 17°% reduction of the coefficient of friction. <br
Keywords: MoS2; tribology; vacuum; solid lubrication; transfer layer; two-disc

Efficiency improvement in automobile bucket tappet/camshaft contacts by DLC coatings – Influence of engine oil, temperature and camshaft speed - Dobrenizki, Ladislaus; Tremmel, Stephan; Wartzack, Sandro; Hoffmann, Dennis; Brögelmann, Tobias; Bobzin, Kirsten; Bagcivan, Nazlim; Musayev, Yashar; Hosenfeldt, Tim (Surface & Coatings Technology, 2016)
With the aim to fulfill legal regulations concerning energy efficiency and greenhouse gas emissions, diamond-like carbon (DLC) coatings are increasingly used on highly stressed components of internal combustion engines to reduce friction and prolong component lifetime. The valve train is one of a key system of the combustion engine considerably contributing to frictional losses, especially under boundary and mixed lubrication conditions at lower crankshaft speeds. In this regard, the tribological contact bucket tappet/camshaft offers high potential for friction reduction but imposes high demands on DLC coatings due to highly complex kinematics and repetitive loads depending on the cam contours and the camshaft angle and speed. The aim of this work was to analyze the influence of DLC coatings on the frictional and wear behavior within the contact bucket tappet/camshaft. This tribological contact was analyzed in a one tappet/one cam friction test-rig using series-production tappets, cams and valve springs ensuring high transferability of the results into the real application. Two amorphous hydrogen containing carbon based coatings were deposited on series-production bucket tappets. The zirconium based DLC coating a-C:H/ZrCg was compared to a DLC coating system a-C:H:X deposited under industrial conditions. One mineral motor oil of SAE viscosity grade 0W20 and one synthetic motor oil polyalphaolefin (PAO) of SAE viscosity grade 5W30 formulated with different additive packages containing the anti-wear (AW)/extreme pressure (EP) additive zinc dialkyl dithiophosphate (ZDDP) and the friction modifier (FM) additives molybdenum dialkyl dithiocarbamate (MoDTC) and glycerol monooleate (GMO) were used in the test-rig. Special attention was paid to the interactions of the additive packages in the low viscosity oils with the functional surfaces of the a-C:H:ZrCg coated bucket tappets. The frictional behavior determined by time-resolved measurements of friction forces reveals that higher camshaft speeds led to increased lubrication film formation contributing to reduced frictional losses. Higher motor oil temperature resulted in temperature induced reduced viscosity of the motor oils leading to higher frictional losses. The DLC coatings a-C:H:ZrCg and a-C:H:X caused significant reduction of frictional losses under the operating conditions in the test-rig. The a-C:H:ZrCg coated bucket tappets caused higher frictional losses than uncoated bucket tappets at low camshaft in boundary friction conditions. Friction reduction at all operating points was ensured by a-C:H:X regardless of camshaft speed, motor oil temperature and the choice of motor base oil and additive package proving the great potential for application on components under challenging lubricating and loading conditions. The wear of the uncoated and a-C:H:ZrCg coated functional surfaces was analyzed by means of confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The a-C:H:ZrCg coating contributed to wear protection in the highly loaded tribological contact despite the different lubricating and loading conditions regardless of the base oil and additive packages. The a-C:H:X coating revealed similar favorable behavior. Comprehensive surface sensitive analysis of the uncoated and a-C:H:ZrCg coated bucket tappets by means of Raman spectroscopy and XPS indicated that no tribo-chemical reaction layer was formed from the motor oil and the additive packages on a-C:H:ZrCg coated bucket tappets under the operating conditions. Moreover, the combination of additives ZDDP and GMO in PAO appears to be disadvantageous in terms of reaction layer formation since no tribo-chemical reaction layer was found on uncoated steel bucket tappets after tribological tests in contrast to the mineral oil containing ZDDP and MoDTC.
Keywords: Valve train; Bucket tappet/camshaft contact; Friction test-rig; DLC PVD coating; Friction; Wear; Motor oil; Additives; ZDDP; MoDTC; GMO; Tribo-chemical reaction layer; Raman analysis; XPS analysis

Efficient Computation of Spatial Truss Structures for Design Optimization Approaches Using Tube-Shaped Thin-Walled Composite Beams - Jäger, Michael; Wartzack, Sandro (Proceedings of the Munich Symposium on Lightweight Design 2021, 2022)
Spatial truss structures are a stiff, economical, and effective lightweight design method, especially when using composites instead of isotropic materials for the struts. An efficient computation of these structures is crucial for optimization approaches during the product design process. The most common method for computing spatial truss structures relies on hinged connections with tension/compression-only struts, which ignores the bending and coupling effects of composite beams. However, especially when using asymmetric laminates, these effects are no longer neglectable. Within commercial finite element tools, the computation of large truss structures - which include these effects - is a very time-consuming process. Particularly for slender, thin-walled beams a large number of solid/shell elements is required. In this paper, an analytical solution of the stiffness matrix for a tube-shaped thin-walled composite beam is provided. It is based on the classical laminate plate theory and Timoshenko’s exact solutin including shear deformation and coupling effects. By using three-dimensional exact Timoshenko beam elements, the number of degrees of freedom can be reduced significantly while coupling effects are maintained. This results in a remarkably lower computation time especially needed for topology optimization. The results are compared to a commercial finite element tool using both solid and shell elements.<br
Keywords: Lightweight design; Spatial truss structures; Structural optimization; Thin-walled composite beams; Timoshenko beam

Effiziente, prozessorientierte Konformitätsbewertung bei Toleranzsimulationen auf Basis von Klassifikationsmodellen - Schächtl, Paul; Roth, Martin; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

Effiziente, strukturierte Auslegung beanspruchungsgerechter Faserverbundbauteile - Völkl, Harald; Wartzack, Sandro (Tagungsband LLC 2019, Leichtbau in Forschung und industrieller Anwendung von der Nano- bis zur Makroebene, 2019)
Effiziente CAE-Auslegungsansätze helfen, den steigenden Anforderungen an Qualität, Zeit- und Kostendruck zu begegnen. Insbesondere die komplizierte Auslegung von Faserverbundbauteilen erfordert adäquate Unterstützung. Ein neu entwickelter Ansatz für diesen Zweck wird vorgestellt und dessen Ergebnis anhand eines Schalensitzes mit konventionellen Laminaten vergliche

Eine Näherungsmethode zur schnellen Simulation von mehrfach überrollten elasto-plastischen Kontakten in Wälzlagern - Jüttner, Michael; Wartzack, Sandro; Bartz, Marcel; Tremmel, Stephan; Correns, Martin (14. VDI-Fachtagung Gleit- und Wälzlagerungen 2021. Gestaltung - Berechnung - Einsatz, 2021)
Zur Bewertung von Pressungsspitzen in den Kontakten von Wälzlagern, die bei zum Lastfall unpassender Lagergeometrie oder bei ungünstigen Betriebsbedingungen auftreten können, ist die Berücksichtigung von elasto-plastischem Materialverhalten notwendig, sobald die aus der Pressung resultierenden Spannungen lokal die Fließgrenze des Werkstoffes überschreiten. Eine gegebenenfalls fortschreitende Plastifizierung und die daraus folgende Veränderung der Kontaktgeometrie bei mehrfacher Überrollung lässt sich somit erfassen. Die Simulation von mehrfach überrollten elasto-plastischen Kontakten erfolgt in der Regel mit einem transienten Ansatz, was mit herkömmlichen Verfahren sehr zeitaufwändig ist. Um die Bewertung von Pressungsspitzen in den Zeitrahmen der etablierten Lagerauslegung eingliedern zu können wird in diesem Beitrag, ausgehend von einer transienten Simulation einer Mehrfachüberrollung, eine schnelle Näherungsmethode vorgestellt. Als Beispiel wird der Kontakt von Kugel und Innenringlaufbahn eines Rillenkugellagers untersucht und es werden die Ergebnisse der Näherungsmethode diskutiert.<br
Keywords: elasto-plastischer Kontakt; Mehrfachüberrollung; Näherungsmethode

Eine Untersuchung mechanisch gealterter kurzfaserverstärkter Thermoplaste unter hochdynamischen Lasten - Witzgall, Christian; Wartzack, Sandro (Design for X - Beiträge zum 27. DfX-Symposium, 2016)

Einfluss der Mikrostruktur gesputterter Molybdändisulfid-(MoS2) Schichten auf die Lagergebrauchsdauer im Trockenlauf - Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro (11. VDI-Fachtagung Gleit- und Wälzlagerungen 2015: Gestaltung, Berechnung, Einsatz (VDI-Berichte 2257), 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.einflu_6

Einfluss der Schmierstoffhydrodynamik in der Käfigführung auf die Wälzlagerreibung und -kinematik - Seiler, Katrin; Tremmel, Stephan; Wartzack, Sandro; Hahn, Bodo; Graf-Goller, Oliver (VDI-Berichte 2257, 2015)
Werden Wälzlager hohen Zentripetalbeschleunigungen ausgesetzt kann die Reibung an den Käfigkontakten sehr stark ansteigen. In solchen Anwendungsfällen ist in der Wälzlagermehrkörpersimulation die Schmierstoffhydrodynamik in den Käfigkontakten zu berücksichtigen. Hierbei reicht es im Fall des Kontakts zwischen Käfig und Außenring nicht aus, ausschließlich den hydrodynamischen Kontakt an den Käfigstirnringen zu berücksichtigen. Um die Käfigführung realistisch abbilden zu können ist zusätzlich der Kontakt an den Käfigstegen, an denen ebenfalls hydrodynamische Effekte auftreten, zu berücksichtigen. Der vorliegende Beitrag stellt analytische und validierte Berechnungsmodelle für die Berücksichtigung der Hydrodynamik an den Käfigstegen vor. Rolling bearings that run under high centripetal acceleration show high friction at their cage contacts. That is why the hydrodynamic lubrication has to be taken into consideration in a rolling bearing multi-body dynamic simulation. In case of the contact between cage and outer ring the hydrodynamic has to be calculated for the cage’s bars and sideway rings. This paper presents an analytical and validated hydrodynamic model for the use in a multi-body dynamic simulation and shows simulation results of a piston rod needle bearing.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.einflu
Keywords: Wälzlager; MKS; Tribologie; Hydrodynamik

Einfluss des tribochemischen Schichtaufbaus auf die Ausbildung elektrisch induzierter Wälzlagerschäden - Pohrer, Benjamin; Zürcher, Manuel; Tremmel, Stephan; Wartzack, Sandro; Schlücker, Eberhard (Tribologie und Schmierungstechnik, 2016)
Gleichstrombelastete Wälzlager zeigen bereits bei sehr geringen Stromdichten unter bestimmten Bedingungen Schädigungen der Laufbahnoberflächen oder Veränderungen des Gefüges. Erste Untersuchungen deuten darauf hin, dass diese Phänomene im Zusammenhang mit der Ausbildung isolierend wirkender, tribochemischer Schichten im Wälzkontakt stehen. Dieser Schichtaufbau kann anhand der elektrischen Eigenschaften des Prüflagers und einer begleitenden in-situ-IR-Analyse des Schmierstoffs während des Betries nachvollzogen werden. Under specific conditions, rolling bearings exposed to direct currents show surface demages on the raceway or microstructural changes even at very low current densities. Initial investigations indicate that these phenomena are related to the formation of insulating tribochemical layers in the rolling contact. These surface processes can be understood with reference to the electrical properties of the bearing and an accompanying in-situ IR analysis of the lubricant.
Keywords: IR-Spektroskopie; Schmierstoffe; Additive; Wälzlagerschäden; Tribochemie; Schichtaufbau; IR-Spectroscopy; Lubricants; Additives; Rolling bearing failures; Tribochemistry; Tribolayers; White Structure Flaking

Einfluss des tribochemischen Schichtaufbaus auf die Ausbildung elektrisch induzierter Wälzlagerschäden - Pohrer, Benjamin; Zürcher, Manuel; Tremmel, Stephan; Wartzack, Sandro; Schlücker, Eberhard (56. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Band II, 2016)
Gleichstrombelastete Wälzlager zeigen bereits bei sehr geringen Stromdichten unter bestimmten Bedingungen Schädigungen der Laufbahnoberflächen oder Veränderungen des Gefüges. Erste Untersuchungen deuten darauf hin, dass diese Phänomene im Zusammenhang mit der Ausbildung isolierend wirkender, tribochemischer Schichten im Wälzkontakt stehen. Dieser Schichtaufbau kann anhand der elektrischen Eigenschaften des Prüflagers und einer begleitenden in-situ IR-Analyse des Schmierstoffs während des Betriebs nachvollzogen werden.     Under specific conditions, rolling bearings exposed to direct currents show surface damages on the raceway or microstructural changes even at very low current densities. Initial investigations indicate that these phenomena are related to the formation of insulating tribochemical layers in the rolling contact. These surface processes can be understood with reference to the electrical properties of the bearing and an accompanying insitu IR analysis of the lubricant.

Einfluss masseerhaltender Kavitationsmodelle bei der Simulation hydro- und elastohydrodynamischer Kontakte - Marian, Max; Weschta, Martin; Tremmel, Stephan; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2017)
Numerische Simulationen können bei der Auslegung hydro- (HD) und elastohydrodynamischer (EHD) Kontakte in geschmierten tribologischen Systemen bereits in einer frühen Phase der Produktentwicklung helfen, fundierte Kenntnisse über vorliegende Beanspruchungen und Schmierungszustände zu erlangen. Die Eigenschaften der beteiligten Systempartner und die auftretenden Phänomene – unter anderem Kavitation – sind durch physikalische Modelle möglichst exakt zu repräsentieren, wohingegen Rechenzeiten gering gehalten werden sollen. Vor diesem Hintergrund wird ein effizienter Ansatz für ein masseerhaltendes Kavitationsmodell vorgestellt und dessen Einfluss auf die berechnete Verteilung von Druck und Schmierspalthöhe im Vergleich zu nicht-masseerhaltenden Alternativen anhand beispielhafter Fälle aufgezeig
Keywords: Elastohydrodynamik; Finite-Elemente; Hydrodynamik; Masseerhaltendes Kavitationsmodell; Mikrostrukturierte Oberflächen; Simulation

Einfluss masseerhaltender Kavitationsmodelle bei der Simulation hydro- und elastohydrodynamischer Kontakte - Marian, Max; Weschta, Martin; Tremmel, Stephan; Wartzack, Sandro (57. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Band I, 2016)
Numerische Simulationen können bei der Auslegung hydro- (HD) und elastohydrodynamischer (EHD) Kontakte in geschmierten tribologischen Systemen bereits in einer frühen Phase der Produktentwicklung helfen, fundierte Kenntnisse über vorliegende Beanspruchungen und Schmierungszustände zu erlangen. Die Eigenschaften der beteiligten Systempartner und die auftretenden Phänomene – unter anderem Kavitation – sind durch physikalische Modelle  möglichst exakt zu repräsentieren, wohingegen Rechenzeiten gering gehalten werden sollen. Vor diesem Hintergrund wird ein effizienter Ansatz für ein masseerhaltendes Kavitationsmodell vorgestellt und dessen Einfluss auf die berechnete Verteilung von Druck und Schmierspalthöhe im Vergleich zu nicht-masseerhaltenden Alternativen anhand beispielhafter Fälle aufgezeigt.
Keywords: Elastohydrodynamik; Finite-Elemente; Hydrodynamik; Masseerhaltendes Kavitationsmodell; Mikrostrukturierte Oberflächen; Simulation

Einfluss statistisch verteilter geometrischer Formabweichungen auf Reibmoment und Schwingungsanregung von Zylinderrollenlagern - Kramer, Vincent; Atalay, Onur; Koch, Oliver; Bartz, Marcel; Schleich, Benjamin; Wartzack, Sandro (63. Tribologie-Fachtagung, 2022)
Wälzlager ermöglichen eine kostengünstige und präzise Führung rotierender Bauelemente und kommen daher im gesamten Maschinenbau in großer Stückzahl zum Einsatz. Bei der Auslegung von Wälzlagerungen wird üblicherweise von idealen Geometrien von Lagern und Anschlusskonstruktion ausgegangen. Reale Bauteile weisen jedoch unvermeidlich Abweichungen von ihrer nominalen Gestalt auf. Diese können zu einer Veränderung der lagerinternen Kontakt- und Lastverhältnisse führen, was sich in der Folge auch auf das Betriebsverhalten des Lagers – wie etwa das entstehende Reibmoment oder das Schwingungsverhalten – auswirken kann. Durch Berücksichtigung dieser Effekte können die Ergebnisqualität bei der Auslegung von Wälzlagerungen verbessert sowie konstruktive Optimierungspotentiale aufgezeigt werden. Der vorliegende Beitrag stellt daher eine Methode zur Integration dieser geometrischen Nichtidealitäten bei der Auslegung von Zylinderrollenlagerungen vor. Die statistische Natur der in der Realität auftretenden Abweichungen wird dabei durch Auswertung einer Vielzahl zufällig generierter Einzelfälle (sog. Sampling) abgebildet. Hierzu erfolgt zunächst eine zufallsbasierte Erzeugung einer beliebigen Anzahl abweichungsbehafteter Lagergeometrien, welche anschließend statistisch evaluiert werden können. Für kritische Fälle kann dann in einer Mehrkörpersimulation (MKS) eine detaillierte Auswertung hinsichtlich Reibmoment und Schwingungsverhalten durchgeführt werden. Der Neuheitswert des vorgestellten Verfahrens besteht somit in der Berücksichtigung von in der Realität unvermeidlichen statistisch verteilten geometrischen Abweichungen bei der Auslegung von Wälzlagerungen. Die Vorgehensweise wird dabei im Rahmen des Beitrags anhand eines Beispiels erläuter
Keywords: Wälzlager; Zylinderrollenlager; Toleranzanalyse; Reibung; Schwingungen; Mehrkörpersimulation

Einfluss von Dotierungselementen in ta-C Beschichtungen auf Reibungs- und Verschleißeigenschaften im geschmierten Tribokontakt - Polzer, Markus; Bartz, Marcel; Schulz, Edgar; Procelewska, Joanna; Wartzack, Sandro (Tribologie-Fachtagung, 2021)
Tetraedrisch amorphe Kohlenstoffschichten (ta-C) werden bereits vielfach als reibungsarme, verschleißbeständige Funktionsschichten auf mechanisch beanspruchten Komponenten genutzt. In geschmierten Systemen kann es jedoch auf Grund der komplexen Wechselwirkung von Beschichtungssystem, Schmierstoffadditiven und Belastungskollektiv zu unvorhergesehenen Wechselwirkungen im Tribokontakt kommen. Die Wirkmechanismen dieser Wechselwirkungen beeinträchtigen im schlimmsten Fall die Lebensdauer oder die allgemeine Effizienz des vorliegenden Tribosystems und können allein durch eine Betrachtung der Dotierungselemente und den mechanischen Eigenschaften der Schichten nicht vorhergesagt werden. Um diese komplexen Wirkmechanismen besser verstehen zu können und um weitere Effizienz und Lebensdauer steigernde Effekte zu untersuchen, soll in diesem Beitrag der Einfluss unterschiedlicher Dotierungselemente im geschmierten Tribokontakt untersucht werden. Dafür werden, neben der Analyse der mechanischen und topographischen Eigenschaften, die verschiedenen dotierten ta-C Schichtsysteme mit einer undotierten ta-C Schicht verglichen. Durchgeführt werden die Untersuchungen an beschichteten Proben auf einem Tassenstößel-Reibungsprüfstand mit realen Motorkomponenten und auf einem Kugel-Scheibe-Tribometer. Bei dem verwendeten Schmierstoff handelt es sich um ein kommerziell standardisiertes, nicht additiviertes Öl. Ziel ist die Auswirkungen der Dotierungselemente auf das Reibungs- und Verschleißverhalten darzustellen und zu vergleichen.<br

Ein Klassifizierungssystem zur Anforderungssystematisierung - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 30. DfX-Symposium, 2019)
This paper presents a holistic approach to structure and classify requirements of the product life cycle systematically and make them accessible for the evaluation process. In a first analysis step, process models of selected literature are analyzed regarding classification and structuring of requirements as well as their derivation into evaluation criteria. In a subsequent synthesis step, the classification system is developed with a consistent consideration of the multi-criteria evaluation process. This approach therefore contributes to raise the awareness of an appropriate handling of requirements and to minimize forgotten requirements as well as evaluation criteria. As a result, costly iterations in the development process can be reduced sustainably by using the proposed approac
Keywords: requirement engineering; requirement classification; multi criteria decision making; product development

Ein Kommentar zum mehrachsigen Spannungszustand im reibungsfrei überrollten Kontakt elastischer Körper und zur Anwendung von Vergleichsspannungshypothesen - Jüttner, Michael; Tremmel, Stephan; Correns, Martin; Koch, Oliver; Wartzack, Sandro (61. Tribologie-Fachtagung 2020, 2020)
Zur Bewertung eines überrollten Kontaktes sind insbesondere Wissen über den inhomogenen mehrachsigen Spannungszustand sowie die Einschränkungen verfügbarer Vergleichsspannungshypothesen maßgeblich. Der Beitrag beleuchtet deshalb am Beispiel des reibungsfrei überrollten elastischen Hertzschen Kugel-Ebene-Kontaktes zunächst den mehrachsigen Spannungszustand, um daraus anschließend die Beanspruchungshistorie bei Überrollung abzuleiten. Abschließend werden anhand der Gestaltänderungsenergiehypothese die Chancen und Einschränkungen bei der Nutzung von Vergleichsspannungen aufgezeigt.
Keywords: Hertzscher Kontakt; überrollter Kontakt; mehrachsiger Spannungszustand; Festigkeitshypothese

Ein Kommentar zum mehrachsigen Spannungszustand im reibungsfrei überrollten Kontakt elastischer Körper und zur Anwendung von Vergleichsspannungshypothesen - Jüttner, Michael; Tremmel, Stephan; Correns, Martin; Koch, Oliver; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2021)
Zur Bewertung der Tragfähigkeit eines überrollten Kontaktes sind insbesondere Wissen über den inhomogenen mehrachsigen Spannungszustand sowie die Einschränkungen verfügbarer Vergleichsspannungshypothesen maßgeblich. Der Beitrag beleuchtet deshalb am Beispiel des HERTZschen Kontaktes Kugel/Ebene zunächst den mehrachsigen Spannungszustand, um daraus anschließend die Beanspruchungshistorie bei reibungsfreier Überrollung abzuleiten. Abschließend werden anhand der Gestaltänderungsenergiehypothese die Chancen und Einschränkungen bei der Nutzung von Vergleichsspannungen aufgezeigt.<br
Keywords: Kontaktmechanik; HERTZscher Kontakt; Spannungsfeld; Hauptspannungsorientierung; von Mises-Spannung; contact mechanics; HERTZian contact; stress field; principal stress orientation; von Mises stress

Ein methodisches Framework für das prozessorientierte Toleranzmanagement - Schleich, Benjamin; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung (SSP) 2013, 2013)
Aufgrund steigender Ansprüche an technische Produkte ist eine ganzheitliche Berücksichtigung aller qualitätsmindernden Faktoren, zu denen besonders geometrische Abweichungen zählen, bereits während der Produktentwicklung eine Voraussetzung für erfolgreiche Produkte. Während der Produktentwicklung müssen daher geometrische Toleranzen festgelegt werden um die Qualität und Funktion des Produktes sicherzustellen. Mit dem Ziel die Toleranzvergabe zu vereinfachen, wird ein methodisches Framework für die Integration von Abweichungsinformationen aus den verschiedenen Phasen des Produktlebenszyklus in Toleranzsimulationen entwickelt. Um virtuelle Absicherungsmethoden effizient zu integrieren, baut das Framework auf einer diskreten Geometrierepräsentation abweichungsbehafteter Bauteile auf. Durch die Integration von Informationen aus späteren Phasen des Produktlebenszyklus ergibt sich ein ganzheitliches Bild aller Prozessparameter, die Einfluss auf die Qualität des Produktes haben. Darauf aufbauend können durch die gezielte Wahl von Toleranzen ein gefordertes Qualitätsniveau sichergestellt und unnötig enge Toleranzen vermieden werden.
Keywords: Toleranzmanagement; Virtuelle Produktentwicklung; Oberflächenmodell

Ein ontologiebasierter Ansatz zur Wissensrepräsentation für die smarte Produktentwicklung - Sauer, Christopher; Kügler, Patricia; Kestel, Philipp; Graf, Michaela; Göbel, Kyra; Niessen, Cornelia; Schleich, Benjamin; Wartzack, Sandro (Tagungsband 16. Gemeinsames Kolloquium Konstruktionstechnik, 2018)
The amount of knowledge shared between or inside engineering design teams, often working in different engineering environments, needs to be increased. For instance, such knowledge refers to design-relevant manufacturing knowledge or methods for checking the properties and the behaviour of components using numerical simulations. An efficient knowledge exchange is essential. To support this new collaborative design approach, this contribution proposes an interface in engineering design, which provides all relevant knowledge to a design. It is based on the knowledge representation employing ontologies. The novelty of the presented approach can be found in using an ontology for the relevant engineering design knowledge and in the description of the whole ontology design process.<br
Keywords: Smart Engineering; Knowledge Management; Transparency; Ontologies

Einsatz von Data-Mining in modernen Produktentstehungsprozessen - Breitsprecher, Thilo; Kestel, Philipp; Küstner, Christof; Sprügel, Tobias; Wartzack, Sandro (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2015)
Das Arbeitsumfeld von Produktentwicklern und Konstrukteuren unterliegt einem ständigen Wandel. Die fortschreitende Globalisierung der Märkte, der steigenden Innovationsdruck und die erhöhten Individualität und Dynamik der einzelnen Absatzregionen, lassen die Anforderungen an Produkte sowie an Produktentstehungsprozesse immer differenzierter werden. Der Lehrstuhl für Konstruktionstechnik (KTmfk) der Friedrich-Alexander Universität Erlangen-Nürnberg (FAU) erforscht Data-Mining-Lösungen für die Produktentstehung, die den Unternehmen helfen mit dieser Entwicklung Schritt halten zu können.
Keywords: Industrie 4.0; Data Mining

Einsatz von Deep Learning zur ortsaufgelösten Beschreibung von Bauteileigenschaften - Sauer, Christopher; Küstner, Christof; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
Within the Transregional Collaborative Research Centre 73 (SFB/TR 73) a self-learning engineering workbench (SLASSY) is being developed. SLASSY assists product developers in designing sheet-bulk metal formed (SBMF) parts by computing product properties based on given product and process characteristics. SLASSY enables product developers to evaluate the manufacturability of their current part design. For this, SLASSY uses data from manufacturing experts to create metamodels. Currently, it can handle product properties which apply for a whole part variant (on whole part level), for instance the minimum form filling degree. The further development of the SBMF manufacturing technology requires the consideration of the product properties in higher detail (on local level). This requires a higher data density, that is, data for each part variant and product property need to be acquired on every point of interest. Due to the increased amount of data, the currently used data mining algorithms in SLASSY for creating the metamodels cannot be reused. To face this challenge, deep learning algorithms are utilized which are good in processing big data. In this contribution, two approaches for the use of deep learning to compute product properties on local level are presented.
Keywords: product properties; deep learning; data mining; neural networks

Einsatz von gedruckten Sensoren zur Messung der Dehnung von Wälzlagern unter isolierten Randbedingungen - Halmos, Fabian; Jüttner, Michael; Bartz, Marcel; Ankenbrand, Markus; Häusler, Felix; Franke, Jörg; Wartzack, Sandro (WiGeP News, 2023)

Einsatz von Graphdatenbanken für das Produktdatenmanagement im Kontext von Industrie 4.0 - Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Entwickeln Entwerfen Erleben in Produktentwicklung und Design 2019, 2019)
Im Zuge der digitalen Transformation im Kontext von Industrie 4.0 tun sich eine Vielzahl neuer Datenquellen auf, die im Produktdatenmanagement berücksichtigt werden müssen. Kennzeichen dieser Datenquellen sind die zunehmende Heterogenität der Daten. Dieser Umstand führt zum Aufbau vieler einzelner neuer Silos, die abgeschottet von den restlichen Silos Daten speichern. Daneben führt eine Vielzahl neuer Autorensysteme zu einer gesteigerten Datenmenge, die nicht mehr in klassischen tabellenbasierten und rein-relationalen Datenbanksystemen sinnvoll erfasst werden können. Um an Informationen zu gelangen, sind oft komplizierte Abfragen nötig, die auf mehrere unterschiedliche Datenbanken zugreifen, um daraus wiederum relevante Informationen bereitzustellen. Dies schafft ungewollt eine Redundanz innerhalb des Produktdaten-managements, da nicht direkt mit den zugrundeliegenden Daten gearbeitet werden kann. Somit büßen rein-relationale Datenbanksysteme einen Großteil ihrer Vorteile ein. Um den oben genannten Problemen zu begegnen, können neue Ansätze aus dem Bereich der Linked Data für das Produktdatenmanagement herangezogen werden. Hierbei wird es in einem ersten Schritt möglich, heterogene Produktdaten, also Daten aus verschiedensten Quellen wie zum Beispiel CAD, Simulation, Qualitätssicherung und Einkauf miteinander zu verknüpfen. Dabei können auch Themen aus dem Umfeld von Industrie 4.0 aufgegriffen werden. So lassen sich zum Beispiel Felddaten aus Sensoren direkt integrieren und als Datenquelle bereitstellen. Durch diese Verknüpfung kann eine neue höherwertige Repräsentationsform für das Produktdatenmanagement geschaffen werden, die neben den reinen Daten und Metadaten auch die sinnvolle Verknüpfung der zugrundeliegenden Daten und Datenquellen enthält und so eine semantische höherwertige Repräsentation darstellt. Das Produktdatenmanagement entwickelt sich so von der reinen Ablage in teilweise kompliziert strukturierten Datenbanken hin zu einem verknüpften System, das Produktdaten beliebiger Repräsentationsform in einem ersten Schritt erhalten und im nächsten Schritt miteinander in Beziehung setzen und verknüpfen kann. Die entstandenen Silos lassen sich dabei intelligent verknüpfen, so dass jeder Bereich trotzdem innerhalb des Silos arbeiten kann, jedoch nach außen hin verknüpft wird. Dabei werden nicht nur rein dokumentenbasierte Ansätze unterstützt, sondern auch die direkte Verknüpfung mit neuartigen Datenquellen, die in Echtzeit Daten bereitstellen. Das so entstehende vernetzte System kann z.B. über eine graphenorientierte Datenbank oder Graphdatenbank umgesetzt werden. Im vorliegenden Beitrag wird untersucht, inwieweit die Modellierung mit gegenwärtig existierenden Lösungen für Graphdatenbanken möglich ist und welche Widrigkeiten dabei noch auftreten. Ausgehend von einem Beispiel mit einem vereinfachten Produkt- und Prozessdatenmodell der Blechmassivumformung, wird eine allgemeine Methode vorgestellt, durch die ein relationales Datenbanksystem in eine Graphdatenbank überführt werden kann. Anhand dieser Methode wird dargestellt, wie bestehende Lösungen teilweise auch parallel zu neuartigen Linked Data Datenbanken existieren können, um diese Schritt für Schritt in eine Graphdatenbank zu überführen. Anschließend wird die einfache Abfrage und Darstellung von Produktdaten aufgezeigt und Möglichkeiten beschrieben neuartige Datenquellen (z.B. Sensordaten aus dem Feld) für die Anbindung an die Graphdatenbank bereitzustellen. Darüber hinaus können die so erfassten Produkt- und Prozessdaten über semantische Schnittstellen für Prozesse auf organisational höherliegenden Ebenen bereitgestellt werden. Die Ergebnisse des Beitrags sind auf der einen Seite das allgemeine Vorgehensmodell zur Einführung von Graphdatenbanken. Auf der anderen Seite die Nutzbarkeitsanalyse der vorgestellten Lösung für das Produktdatenmanagement.<br
Keywords: Graphdatenbanken; Produkdaten; Prozessdaten; PLM; Datenmodell

Einsatz von Process-Mining zur Erweiterung der semantischen Produktbeschreibung - Sauer, Christopher; Dworschak, Fabian; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 29. DfX-Symposium, 2018)
Due to the increased data volume in product development, the use of PDM systems has become established. Current trends show a shift away from the monolithic integrated product model towards a semantic product model. In order to extend this product model by a description of the manufacturing process, which is particularly important against the background of the digital twin, methods of process mining are suitable. The result of these methods is always a model of the given process, which is to be fed to the higher-level system via a semantic interface. Thus, ontologies that enable a semantic description are suitable for the interface definition. Within the scope of this article, based on an exemplary manufacturing process, process mining is applied and a prototypical interface is designed.<br
Keywords: process mining; semantic product modeling; ontologies

Einsatz von Rousseau Modellen für die Vorhersage menschlicher Bewegung zur muskuloskelettalen Simulation im AnyBody Modeling System - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (7. CADFEM medical conference, 2017)
Biomechanische Simulationsmethoden ermöglichen die Analyse und Bewertung von Bewegungen und Kräften des menschlichen Bewegungsapparates. Dadurch wird es möglich Fragestellungen bezüglich ergonomischer/ biomechanischer Parameter in frühen Planungsphasen zu beantworten und diese entsprechend in die Planung einfließen zu lassen. So lässt sich beispielsweise ein Arbeitsablauf bereits bei der Planung nach ergonomischen Gesichtspunkten ausrichten, oder ein Produkt schon in den frühen Entwicklungs- und Konstruktionsabschnitten nach nutzerspezifischen Kriterien gestalten. Dennoch sind biomechanische Simulationsmethoden im industriellen Umfeld bei weitem nicht so verbreitet, wie herkömmliche Simulationsmethoden der Mehrkörpersimulation, oder der Strukturmechanik. Dies liegt insbesondere daran, dass für jedes neu erstellte biomechanische Modell neue Messungen stattfinden müssen, damit dieses berechnet werden kann. Für den weitläufig genutzten Ansatz der inversen Dynamik werden als Eingangsdaten die Bewegung und die externen Kräfte benötigt, welche klassischerweise in Bewegungsanalyselaboren erfasst werden müssen. Unter deren Angabe können die Muskelkräfte und die Beanspruchung der Gelenke berechnet werden. Gegenwärtig erscheint dieser Aufwand gegenüber dem Nutzen allerdings als nicht gerechtfertigt. Der Nutzen der biomechanischen Simulationsmethoden steht indes außer Frage. Deshalb gilt es den zu betreibenden Aufwand zu reduzieren. Dies kann durch Modelle geschehen, die eine Vorhersage der üblicherweise zu messenden Eingangsdaten ermöglichen. Die Vorhersage der äußeren Kräfte lässt sich im Rahmen des Optimierungsproblems der inversen Dynamik durchführen. Die Vorhersage der Bewegung kann mittels der Verwendung von Rousseau Modellen gelingen. Diese zwingen einem muskuloskelettalen Menschmodell gewisse Zwangsbedingungen auf, welche gemäß der zu erzeugenden Bewegung unterschiedlich gewichtet werden. Durch dieses Aufzwingen, von sich teilweise wiedersprechenden Zwangsbedingungen, wird das muskuloskelettale Menschmodell zu einem kinematisch überbestimmten Fall. Mithilfe eines Optimierungsverfahrens lässt sich der bestmögliche Kompromiss zur Erfüllung der Zwangsbedingungen finden, wodurch wiederum die Vorhersage einer nachvollziehbaren Bewegung möglich wird. Diese Vorgehensweise wird anhand eines konkreten Anwendungsfalles unter Zuhilfenahme des AnyBody Modeling System vorgestellt.

Ein Vergleich von Datenanalysemethoden für eine Affective Engineering Methode - Zöller, Susan; Schröppel, Tina; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
Affective Engineering (AE) is an engineering genre that deals with users’ subjective value creation in technical product design. Therein, quantitative instruments to map subjective quality criteria are dominant. ACADE is such an instrument that focuses on a long-term alignment of product design impres-sions to the subjective needs of users. Due to its quantitative backbone, sev-eral mathematical analysis methods seem convenient, whereas their specific benefits and drawbacks are not yet clear in the AE context. Therefore, anal-yses of nonlinear regression, artificial neural networks, fuzzy logic systems and hybrids are examined under the aspect of ACADE applicability. Different quality indicators unveil characteristics which the designer may use to mine their potential for future AE analyses.
Keywords: affective engineering; nonlinear regression; fuzzy logic systems; artificial neural networks

Ein von nachgiebigen Mechanismen inspirierter Ansatz zur Konzeptionierung von additiv gefertigten Soft Robots - Steck, Patrick; Völkl, Harald; Wartzack, Sandro (Konstruktion, 2023)
Die ausgeprägten Designfreiheiten durch die additive Fertigung finden besonders in der Gestaltung von Soft Robots Anwendung. UnterSoft Robotic wird ein junges und schnell wachsendes Forschungsgebiet verstanden, welches durch variable und steuerbare Nachgiebigkeiten innerhalb der Strukturen Lösungen für verschiedene Bewegungsprobleme finden möchte. Die Bauteile werden dabei häufig als Vorabmodell aus Gründen der Funktionsintegration additiv hergestellt. Durch die Funktionsintegration können z. B. bewegliche Baugruppen durch ein Einzelbauteil höherer Komplexität substituiert und somit Wirkungsgrade verbessert, Massen reduziert und Montagezeiten verkürzt werden. Dies entspricht in den Zielen den Nachgiebigen Mechanismen, welche jedoch aktuell noch nicht im Kontext von Soft-Robotics betrachtet werden und deshalb auch keine Konzeptions- oder Designvorschriften für diesen Anwendungsfall existieren. Im vorliegenden Beitrag wird ein Ansatz zur Konzeptionierung von Soft Robots vorgestellt, welche auf einer Kombination aus der Konstruktionsmethodik nach Pahl/Beitz und einer Auslegungsmethodik für nachgiebige Mechanismen basiert. Hierbei wurden verschiedene additiv gefertigte Soft Robotic Greiferkonzepte verglichen und parallel unterschiedliche Aktivierungsformen in der Soft Robotic untersucht. Die Soft Robotic Greifer können zur Manipulation von Gegenständen, beispielsweise in der Lebensmittelindustrie, verwendet werde
Keywords: Soft Robotic; Compliant Mechanism; Multi-Material; Fused-Layer-Modelling

Ein Werkzeug zur schnellen Konfiguration biomechanischer Simulationen in der Produktentwicklung - Krüger, Daniel; Wartzack, Sandro (Entwerfen Entwickeln Erleben. Methoden und Werkzeuge in der Produktentwicklung (10. Gemeinsames Kolloquium Konstruktionstechnik 2012), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.einwer

Elastohydrodynamische Simulation tribologischer Kontakte in Wälzlagern - Wirsching, Sven; Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (Konstruktion, 2023)
Using the thermo elastohydrodynamic simulation tool „TriboFEM“ developed at the KTmfk, the friction of secondary roller face/ring side contacts is calculated taking into account exact geometries as well as the wear-induced profile change of primary raceway contacts. The results of the simulations are discussed and the potential for use in the design of rolling bearings is shown. TriboFEM can thus support the development of energy-efficient technical drive systems, which is becoming increasingly important against the background of resource scarcity and climate protection.<br

Electrified cross skate as a micromobility solution | Elektrifizierter Cross-Skate als Mikromobilitätslösung - Kramer, Vincent; Wirsching, Sven; Wartzack, Sandro; Miehling, Jörg (Konstruktion, 2023)
Climate change, resource scarcity and progressing urbanization give rise to challenges in the development of contemporary mobility solutions. In this context, electrically powered vehicles are becoming increasingly important. Innovative micromobility solutions can contribute to resource-, environment- and infrastructure-friendly passenger transport, especially in urban areas. This paper presents such a solution in the form of an electrified cross skate with a steerable front axle. The electric drive can compensate for the relatively high rolling resistance of conventional cross-skates, while the steering enables easier cornering. As another special feature, the skate has a hybrid driving mode in which the rider moves by muscle power in the skating technique with support of an electric motor.
Created from Fastlane, Scopus look-up

Elementary affordances: A study on physical user-product interactions - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP 91, 2020)
Digital human models enable a pro-active and virtual assessment of ergonomics in design. Despite this huge potential, possibilities of user-product interaction modelling, in terms of postures or movement generation, are limited and poorly integrated in common virtual design tools. To address this deficiency, we propose the concept of “elementary affordances”. These universally describe parts of human interaction behavior and shall serve as a modelling interface for posture and movement prediction algorithms. This paper presents an empirical study, identifying 18 elementary affordances, proving that parts of human interaction behavior can be described via a relatively small set of elementary affordances.<br
Keywords: design for ergonomics; human centered design; user centred design; user-product interaction; digital human models; affordances; human factors; computer aided engineering; virtual engineering; computer aided design

Emotional Bionics - A Pickup truck is a Lion! A Study Using Emotional Profiling to Analyse Bionic Analogies in Car Design - Zöller, Susan; Schröppel, Tina; Wartzack, Sandro (7th International Conference on Kansei Engineering & Emotion Research 2018, 19-22 March 2018, Kuching, Malaysia, 2018)
So far, bionic design has mainly been systematically applied to support functional solutions. But in recent times, subjective aspects in product quality became increasingly important to users too. Under the aspect of a sustainable, targeted value creation for users, bionic design may also help to better address users' subjective needs in product design. Therefore, a new method is presented. Its first step is the numeric and perception-related investigation of main geometrical criteria in object shape changes between technical solutions and their bionic models. The second step is the identification and utilization of impressions analogies between  the two domains. Thus, subjective similarities between the product and its bionic model are examined both in geometrical and in impressions respect in order to derive implications for the field of Emotional Bionics.
Keywords: Emotional Bionics; Subjective Value Creation; Kansei Engineering; Design Analytics

Enabling Initial Design-Checks of Parametric Designs Using Digital Engineering Methods - Gerschütz, Benjamin; Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
The world consequently gets faster, so does product development. Therefore, the stock of development and simulation data increases continuously. Unfortunately, inexperienced users cannot cope with the rising number of simulation requests in the time needed. Digital Engineering opens potentials to support the users with newly developed methods and tools. In this contribution, we present a method to assist designers, inexperienced in finite-element simulations to perform an initial check of changed parametric designs independently, quickly and with support in interpreting the results.<br
Keywords: digital design; data-driven design; supportive technologies; finite element method (FEM)

Energieeffizienz durch Tribometrie: Untersuchung von Reibungsmessgrößen am Beispiel des Kontakts beschichteter Tassenstößel/Nocken - Dobrenizki, Ladislaus; Musayev, Yashar; Tremmel, Stephan; Hosenfeldt, Tim; Wartzack, Sandro (Reibung, Schmierung und Verschleiß - Forschung und praktische Anwendungen, 2015)
Aufgrund der Systemabhängigkeit tribologischer Kenngrößen wird die Übertragbarkeit von Reibungsmessgrößen zwischen unterschiedlichen tribologischen Systemen erschwert. Am Beispiel des komplexen tribologischen Kontakts Tassenstößel/Nocken wurde der Einfluss der in diesem Tribosystem vorliegenden Pressungen auf die Reibung im Kugel-Scheibe-Tribometerversuch untersucht. Bei beiden tribologischen Prüfständen wurden gleiche Materialpaarungen und das gleiche Motorenöl verwendet. Für die Versuche wurden DLC beschichtete und nicht beschichtete mechanische Tassenstößel aus dem Werkstoff 16MnCr5 herangezogen. Die Betrachtung der Pressung im Kugel/Scheibe-Kontakt erfolgte über die Auswahl initialer Pressungen auf Basis einer Beanspruchungsanalyse des betrachteten Tassenstößel/Nocken-Kontakts. Weiterhin wurde noch die Gleitgeschwindigkeit variiert. Die aus dem Tribometerversuch gewonnen Zusammenhänge wurden mit Ergebnissen aus Versuchsläufen an einem Tassenstößel-Reibungsprüfstand verglichen. Es konnte ein unterschiedliches Reibungs- und Verschleißverhalten der Kontaktpartner in Abhängigkeit von der Initialpressung am Kugel-Scheibe Tribometer festgestellt werden. Zudem konnten bei den unbeschichteten und DLC beschichteten Tassenstößel unterschiedlich wirkende Tribomechanismen bei verschiedenen Lastkollektiven nachgewiesen werden. Im Falle gleicher Öltemperaturen wurden ähnliche Zusammenhänge im Tassen/Nocken-Kontakt wie im Kugel-Scheibe-Kontakt beobachtet.
Keywords: Energieeffizienz im Ventiltrieb; Mechanischer Tassenstößel; Diamantähnlicher amorpher Kohlenstoff; Tribometrie

Energieeffizienz und Ressourcenschonung durch beschichtete Wälzlager - Sander, Thomas; Kröner, Julia; Dobrenizki, Ladislaus; Tremmel, Stephan; Wartzack, Sandro; Hosenfeldt, Tim; Musayev, Yashar (Konstruktion, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.energi

Enhancement of Surgical Planning through Patient-Specific Biomechanical Modeling and Simulation - Sesselmann, Stefan; Miehling, Jörg; Wartzack, Sandro; Forst, Raimund (37th SICOT Orthopaedic World Congress, 2016)
Current surgical planning software for total endoprostheses of hip and knee joints focuses mainly on geometric arrangements in 2D or in some cases even in 3D. Since this standard process relies highly on the experience of the orthopedic surgeon, poorly adjusted planning parameters may impede the expected mobility outcome. Therefore, we propose the inclusion of a methodology for the individualization of generic musculoskeletal models based on a limited number of input parameters into the planning process. These parameters can ideally directly be taken from the standard tests in advance of the joint replacement to allow for a highly usable planning tool. For example the bones and rotational axes are adjusted using landmark distances measured in the compulsory X-ray images, joint mobility can be localized using the neutral zero method and muscular dysfunctions can be semiquantified by measuring the degree of force according to the BMRC. Also irregularities or deformities can be considered. The resulting model is eventually used for patient-specific simulations to derive useful information on how the total endoprosthesis has to be geometrically set up to yield the best biomechanical result. Sensitivity analysis is to be performed as the orthopedist can hardly reproduce the specified values exactly. He rather needs intervals in which the postoperative outcome is robust to variations in the geometric parameters to be able to choose the best parameter configuration. This analysis can also predict which parameters have to be precisely met and which play a subordinate role.

Enhancing Dynamic Consistency of Multimodal Motion Data in Musculoskeletal Simulation - Wechsler, Iris; Wolf, Alexander; Wartzack, Sandro; Miehling, Jörg (27th Congress of the European Society of Biomechanics, 2022)
Introduction Digital human models can be used to determine biomechanical parameters (e.g. muscle or joint reaction forces) virtually and in a non-invasive way [1]. Hereby, subject-specific models lead to more reliable simulation results in this context [2]. Moreover, even though current sensor and measuring systems can achieve high-quality data, the measurements are still error-prone and subject to uncertainties such as noise or jumps. Furthermore, kinematic and dynamic inconsistencies between the measured data and the motion capabilities of the human body can occur. We assume that motion tracking accuracy and consistency will be increased when multimodal data, e.g., some combination of position, orientation, EMG, or surface data, is considered. Therefore, our goal is to research and develop methods for filtering and analysing multimodal motion measurement data in conjunction with individualized digital human models. In this paper we want to discuss available approaches. Methods Subject-specific individualization of the applied musculoskeletal human models in multiple domains (anthropometry, mobility, strength) is to be achieved through a combination of subject-specific manual measurements and population data [3]. Further, we aim to develop a method for kinematically consistent and precise motion tracking. The standard method, Inverse Kinematics, minimises the difference between measured and virtual marker and coordinate positions in a least squares approach to compute generalized coordinate trajectories [4]. The novel tracking algorithm should include different types of data, which are weighted in relation to each other. This way the observed movement information from different data sources should be transferred to the digital model in order to get the most accurate and consistent simulation results possible. Nevertheless, the problem regarding the dynamic consistencies between the motion of the model and the measurements still remains. For this we also want to investigate methods to enhance dynamic consistency and further develop a dynamic tracking method that is able to generate kinematically and also dynamically consistent motion data. Therefore, dynamic components (e.g. muscle activation, accelerations) are to be included in the tracking method. Results There are various approaches available in literature for enhancing dynamic consistency (cf. figure 1). The EMG-informed forward simulation approach, for example, tracks measured marker trajectories while replicating EMG measurements to obtain dynamic consistency [5-7]. Controller-based solution approaches optimise measured trajectories through forward simulation with a time-limited observation interval to enhance dynamic consistency [8]. Also, trajectory optimization using direct collocation and a Kalman filter have already been used to achieve dynamically consistent movement simulations [9,10]. Discussion In the next step, a systematic literature review will be conducted based on the mentioned results, in order to identify and analyse all relevant dynamic tracking solutions regarding multimodal motion data. Main focus will be the classification into different solution approaches. Moreover, input and output variables, the used model and the regarded dynamic component will be explored. Based on these results the solution approach for our application of multimodal motion data is to be set up. This new musculoskeletal simulation approach is then to be evaluated regarding accuracy and usability and to be benchmarked against the standard methods of biomechanical motion capture and analysis. References 1. Seth et al, Computational Biol, 14(7), 2018. 2. Lund et al, Internat Biomech, 2:1-11, 2015. 3. Miehling, Comput Methods Biomech Biomed Engin, 22(15):1209-1218, 2019. 4. Delp et al, IEEE Trans Biomed Eng, 54: 1940-1950, 2007. 5. Sartori et al, PLoS One, 7(12), 2012. 6. Bailly et al, Front Bioeng Biotechnol, 2021. 7. Moissenet et, Front. Neurorobot, 2019. 8. Thelen et al, J Biomech, 39:1107-1115, 2006. 9. Dembia et al, PLoS Comput Biol, 16(12), 2020. 10. Bonnet et al, J Biomech, 62:140-147, 2017. Acknowledgements This work was (partly) supported by the Deutsche Forschungs-gemeinschaft (DFG, German Research Foundation) under Grant SFB 1483–Project-ID 442419336. <br

Enhancing the Design of Experiments on the Fatigue Life Characterisation of Fibre-Reinforced Plastics by Incorporating Artificial Neural Networks - Witzgall, Christian; Ashhab, Moh’d Sami; Wartzack, Sandro (Materials, 2024)
Fatigue life testing is a complex and costly matter, especially in the case of fibre-reinforced thermoplastics, where other parameters in addition to force alone must be taken into account. The number of tests required therefore increases significantly, especially if the influence of different fibre orientations is to be taken into account. It is therefore important to gain the greatest possible amount of knowledge from the limited number of available tests. In order to achieve this, this study aims to utilise adaptive sampling, which is used in numerous areas of computational engineering, for the design of experiments on fatigue life testing. Artificial neural networks (ANNs) are therefore trained on data for the short-fibre-reinforced material PBT GF30, and their areas of greatest model uncertainty are queried. This was undertaken with ANNs from various numbers of hidden layers, which were analysed for their performance. The ideal case turned out to be four hidden layers, for which a squared error as small as 1 × 10−3 was recorded. Locally resolved, the ANN was used to identify the region of greatest uncertainty for samples of vertical orientation and small numbers of cycles. With information such as this, additional data can be obtained in such uncertain regions in order to improve the model prediction—almost halving the recorded error to only 0.55 × 10−3. In this way, a model of comparable value can be found with less experimental effort, or a model of better quality can be set up with the same experimental effort.
CRIS-Team Scopus Importer:2024-02-23
Keywords: artificial neural networks; composites; design of experiments; fatigue life; increased efficiency; short-fibre-reinforced thermoplastics

Enhancing the flow of information in the PLM by using numerical DSMs – an industrial case study - Luft, Thomas; Bochmann, Johanna; Wartzack, Sandro (Proceedings of the IFIP WG5.1, 2013)
This paper proposes a methodology to enhance the information flow in the product life cycle through the example of the product development process. The methodology refines the existing approaches of revealing indirect dependencies with a multiple domain matrix by introducing the numerical derived design structure matrix as indicator of quantifying indirect dependencies between process steps, information and people. These dependencies are quantified by the pieces of information causing the indirect linkage. The subsequent analysis is narrowed down to the content level of information to identify the root causes. This methodology has been successfully tested in an industrial case study. As a result, this paper helps to manage the complexity in the PLM by making the linkages caused by the information flow visible to improve collaborative product development.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.enhanc
Keywords: Collaborative product development; information management; process management; design structure matrix; multiple domain matrix; case study

Entwicklung beanspruchungsgerechter CFK-Laminate in den frühen Phasen der Produktentwicklung - Klein, Daniel; Caballero, Steffen; Wartzack, Sandro (ANSYS Conference & 32. CADFEM Users' Meeting, 2014)
Keywords: Leichtbau; Composites; Simulation

Entwicklung eines Vorgehens zur Toleranzoptimierung an Faser-Kunststoff-Verbund Bauteilen - Franz, Michael; Schleich, Benjamin; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)

Erarbeitung von Gestaltungsrichtlinien für die Konstruktion additiv gefertigter Mechanismen - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (Konstruktion für die Additive Fertigung 2018, 2020)
Additive Fertigungsverfahren haben sich aufgrund ihrer losgrößenunabhängigen Fertigungskosten und der großen Gestaltungsfreiheit sowohl in der Forschung als auch in der industriellen Anwendung erfolgreich etabliert. So werden die verschiedenen additiven Verfahren nicht mehr nur für die Herstellung von Prototypen, sondern vermehrt zur Fertigung komplexer, endkonturnaher Bauteile und gesamter Baugruppen angewendet. Dabei konnten in den letzten Jahren zahlreiche Richtlinien für die Gestaltung der schichtweise aufgebauten Bauteile hergeleitet werden. Eine umfassende Betrachtung additiv gefertigter Gelenke fehlt jedoch bisher. Um den Produktentwickler bzw. Konstrukteur bei der Gestaltung von mittels Fused Deposition Modeling (FDM) hergestellten Drehgelenken zu unterstützen, werden im nachfolgenden Beitrag relevante Aspekte, wie z. B erforderliche Mindestspalte zur Trennung von nicht- und einfach-gekrümmten Elementen, aufgezeigt. Versuchsergebnisse dienen dabei als Basis für die Ableitung von Richtlinien für das Design FDM-gedruckter Gelenke und ergänzen dadurch die Grundsätze des Design for Additive Manufacturing. Die Umsetzung der erarbeiteten Gestaltungsrichtlinien wird anschließend exemplarisch an einem ebenen Mechanismus dargelegt.<br
Keywords: Design for Additive Manufacturing; Montagefreie; additiv gefertigte Mechanismen; Gestaltungsrichtlinien; Fused Deposition Modeling; Gelenke

Ermittlung eines Skelettierungsverfahrens zur Konvertierung von Topologieoptimierungsergebnissen - Mayer, Johannes; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
By showing where to place material in a specified design space, the continuous topology optimization is very useful in product development of structural loaded components. However the optimizations design proposal is far from being a parametric CAD-model. Instead it usually consists of a tesselated surface, that has to be re-engineered. As this is often done manually, it takes a lot of time and expert knowledge. Curve skeleton algorithms have proven their ability to support the restructuring of truss-like design proposals by providing references for construction elements. To investigate a similar design concept for general optimization results, showing truss-like structures as well as surface-like sections, the suitability of surface skeletons for topology reconstruction is examined.<br
Keywords: Computational Geometry; Topology Optimization; Medial Axis Transform; Surface Skeleton

Erweiterte Systemmodellierung - Integration impliziter Wissenselemente in die Erstellung technischer Systemmodelle - Wilking, Fabian; Walter, Leonie; Schleich, Benjamin; Wartzack, Sandro (Beiträge zum 31. DfX Symposium, 2020)
The increasing complexity of technical consumer products has led to the integration of Model-Based Systems Engineering (MBSE) approaches into sectors that are not viewed as classic users of Systems Engineering. The approach helps grasping the complexity and keeping costs at a low level. However, many companies struggle with the implementation of the approach into their processes. A regularly mentioned reason for this is a missing visibility of a clear benefit. Especially smaller enterprises are facing these problems within the value chain. This paper presents an approach to contribute towards the enhancement of MBSE accessibility. It shows different strategies for the integration of tacit knowledge into system models and discusses their feasibility and contribution towards this enhancement.
Keywords: Systems Engineering; Model-Based Systems Engineering; System Model; Knowledge Management; Tacit Knowledge

Erweiterung der Wälzlagerdynamiksimulation um die Schmierstoffhydrodynamik des Kontakts Käfig/Außenring - Seiler, Katrin; Stadler, Marion; Tremmel, Stephan; Hahn, Bodo; Graf-Goller, Oliver; Wartzack, Sandro (3. Wissenschaftliches Wälzlagerkolloquium, 2014)
Keywords: Wälzlager; MKS; Tribologie; Hydrodynamik

Estimation of Clinch Joint Characteristics Based on Limited Input Data Using Pre-Trained Metamodels - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (AI, 2022)
Given strict emission targets and legal requirements, especially in the automotive industry, environmentally friendly and simultaneously versatile applicable production technologies are gaining importance. In this regard, the use of mechanical joining processes, such as clinching, enable assembly sheet metals to achieve strength properties similar to those of established thermal joining technologies. However, to guarantee a high reliability of the generated joint connection, the selection of a best-fitting joining technology as well as the meaningful description of individual joint properties is essential. In the context of clinching, few contributions have to date investigated the metamodel-based estimation and optimization of joint characteristics, such as neck or interlock thickness, by applying machine learning and genetic algorithms. Therefore, several regression models have been trained on varying databases and amounts of input parameters. However, if product engineers can only provide limited data for a new joining task, such as incomplete information on applied joining tool dimensions, previously trained metamodels often reach their limits. This often results in a significant loss of prediction quality and leads to increasing uncertainties and inaccuracies within the metamodel-based design of a clinch joint connection. Motivated by this, the presented contribution investigates different machine learning algorithms regarding their ability to achieve a satisfying estimation accuracy on limited input data applying a statistically based feature selection method. Through this, it is possible to identify which regression models are suitable to predict clinch joint characteristics considering only a minimum set of required input features. Thus, in addition to the opportunity to decrease the training effort as well as the model complexity, the subsequent formulation of design equations can pave the way to a more versatile application and reuse of pretrained metamodels on varying tool configurations for a given clinch joining task.<br

Estimation of Composite Laminate Ply Angles Using an Inverse Bayesian Approach Based on Surrogate Models - Franz, Michael; Pfingstl, S.; Zimmermann, M.; Wartzack, Sandro (2022)
A digital twin (DT) relies on a detailed, virtual representation of a physical product. Since uncertainties and deviations can lead to significant changes in the functionality and quality of products, they should be considered in the DT. However, valuable product properties are often hidden and thus difficult to integrate into a DT. In this work, a Bayesian inverse approach based on surrogate models is applied to infer hidden composite laminate ply angles from strain measurements. The approach is able to find the true values even for ill-posed problems and shows good results up to 6 plies.<br
Keywords: digital twin; inverse problem; simulation-based design; data-driven design; structural analysis

Evaluation of Active Shoulder Exoskeleton Support to Deduce Application-Oriented Optimization Potentials for Overhead Work - Sänger, Johannes; Yao, Zhejun; Schubert, Tim; Wolf, Alexander; Molz, Carla; Miehling, Jörg; Wartzack, Sandro; Gwosch, Thomas; Matthiesen, Sven; Weidner, Robert (Applied Sciences, 2022)
Repetitive overhead work with a heavy load increases the risk for work-related shoulder disorders. Occupational exoskeletons supporting arm elevation are potential solutions to reduce that risk by lowering the physical strains on the shoulder. Many studies have reported a reduction in shoulder stress in various overhead tasks by using such exoskeletons. However, the support demand can vary in each phase of motion as well as in each individual task. This paper presents a laboratory study with five participants to evaluate the influence of the support level of an active shoulder exoskeleton in different motion phases (e.g., arm lifting, screw-in, and arm lowering of two overhead tasks) to identify the potential optimization of support at each phase. Results show that the support level of the exoskeleton should be adapted to the motion phase of the two chosen tasks. A higher support force is desired for the screw phase compared to the arm lifting and lowering phases, and the support level needs to be reduced immediately for arm lowering after the screw phase. The time for switching the support levels can be recognized by the electric current of the screwdrive
Keywords: human–machine interaction; biomechanical analysis; sEMG; interaction forces; user experience; power tool; exoskeleton

Evaluation of geometric tolerances and generation of variational part representatives for tolerance analysis - Schleich, Benjamin; Wartzack, Sandro (International Journal of Advanced Manufacturing Technology, 2015)
Managing geometric part deviations to control their effects on the product function and quality is an important task in the design of physical artefacts. Consequently, computer-aided tolerancing tools are widely applied in industrial practice to evaluate the effects of geometric part deviations on assembly and functional requirements. However, most established models and approaches for the representation of geometric part deviations, geometric tolerances, and geometric requirements in such tools lack of a realistic consideration of form deviations and are often not conform to international standards for the geometric product specification and verification. With the aim to provide a further step towards a computer-aided tolerancing theory employing variational part representatives in discrete geometry, approaches for the generation of such representatives, which conform to pre-defined tolerance specifications, are presented. These approaches ground on algorithms for the evaluation of geometric tolerances from point clouds and are essential for the tolerance analysis employing point based models. We highlight the usefulness of the presented methods for the tolerance analysis in a typical case study.
Keywords: Tolerance design; Computer-aided tolerancing; Geometric tolerances; Variational model; Inspection

Evaluation of the effects of geometrical deviations on the fatigue life and vibrations of cylindrical roller bearings - Dahiwal, Rahul; Aschenbrenner, Alexander; Schleich, Benjamin; Wiesker, Sebastian; Kiekbusch, Timo; Tremmel, Stephan; Wartzack, Sandro; Sauer, Bernd (Bearing World Journal, 2018)
Due to uncertainties in manufacturing processes all components suffer from geometric deviations and imperfections, even high-precision components like roller bearings. In general, tolerances define the allowable deviations of components and ensure their manufacturability, mountability and operational behavior. Nevertheless, geometric deviations can still unpredictably influence the operational behavior of components. Indeed, studies have shown that deviations together with the operating clearance can significantly affect the dynamic behavior and thus the fatigue life of roller bearings. In this contribution, two simulation methods are employed in order to consider and study the effect of geometric deviations like roundness or dimensional deviations of bearings and their adjacent components (shaft and housing) on a cylindrical roller bearing’s vibrational behavior and fatigue life. First, a statistical simulation model is introduced allowing an easy way to screen the operational clearance and fatigue life of a large number of cylindrical roller bearings. Afterward, a multibody dynamic model is used to gather detailed information about the load distribution on each rolling element and the inner ring displacement during operation. These methods allow a user of roller bearings a better understanding of the correlation between geometric deviations and a roller bearing’s vibrational behavior as well as fatigue life. The methods should also aid a user to optimize the geometric definition and tolerancing of their components. After a detailed description of the methods, their application is demonstrated for a use case.
Keywords: Cylindrical Roller Bearing; Geometric Definition and Tolerancing; Statistical Variation Simulation; Dynamic simulation method

Evaluation of the surface fatigue behavior of amorphous carbon coatings through cyclic nanoindentation - Weikert, Tim; Wartzack, Sandro; Baloglu, Maximilian Volkan; Willner, Kai; Gabel, Stefan; Merle, Benoit; Pineda, Fabiola; Walczak, Magdalena; Marian, Max; Rosenkranz, Andreas; Tremmel, Stephan (Surface & Coatings Technology, 2021)
Diamond-like carbon (DLC) coatings, frequently used to reduce wear and friction in machine components as well as on forming tools, are often subjected to cyclic loading. Doping of DLC coatings with metals or metal carbides as well as the usage of multilayer architectures represent promising approaches to enhance toughness, which is beneficial for the coatings’ behavior under cyclic loading. In this study, we utilized cyclic nanoindentation to characterize the tribologically induced surface fatigue behavior of single-layer tungsten-doped (a-C:H:W) and multilayer silicon oxide containing (a-C:H:Si:O/a-C:H)25 amorphous carbon coatings under cyclic loading. Columnar growth was observed for both coatings by focused ion beam microscopy and scanning electron microscopy, while the multilayer architecture of the (a-C:H:Si:O/a-C:H)25 coating was verified by the silicon content using glow-discharge optical emission spectroscopy. In cyclic nanoindentation of the (a-C:H:Si:O/a-C:H)25 multilayer coating, stepwise small changes in indentation depth were observed over several indentation cycles. The surface fatigue process of the single-layer a-C:H:W covered a smaller number of indentation cycles and was characterized by an early steep increase of the static displacement signal. Microscopical analyses hint at grain deformation, sliding at columnar boundaries, and grain detachment as underlying fatigue mechanisms of the a-C:H:W coating, while the (a-C:H:Si:O/a-C:H)25 multilayer coating showed transgranular crack propagation and gradual fracturing. In case of the (a-C:H:Si:O/a-C:H)25 multilayer coating, superior indentation hardness (HIT) and indentation modulus (EIT) as well as a higher HIT3/EIT2 ratio suggest a higher resistance to plastic deformation. A high HIT3/EIT2 ratio, being an indicator for hindered crack initiation, combined with the capability of stress relaxation in soft layers contributed to the favorable surface fatigue behavior of the (a-C:H:Si:O/a-C:H)25 multilayer coating observed in this cyclic nanoindentation studies.
Keywords: Diamond-like carbon; Cyclic nanoindentation; Surface fatigue; Multilayer architecture

Evaluation of the Wear-Resistance of DLC-Coated Hard-on-Soft Pairings for Biomedical Applications - Rothammer, Benedict; Neusser, Kevin; Bartz, Marcel; Wartzack, Sandro; Schubert, Andreas; Marian, Max (24th International Conference on Wear of Materials, 2023)
Diamond-like carbon (DLC) coatings deposited on the articulating surfaces of total hip or knee arthroplasties have the potential to enhance the overall biotribological behavior and longevity. In this contribution, we employ an ultrahigh molecular weight polyethylene ball-on-three cobalt chromium or titanium alloy pin configuration lubricated by simulated body fluid to effectively carry out screening tests. Thus, the influence of the choice of the coated component (metallic and/or polymeric) as well as the differences between a higher and lower load case with non- and conventionally cross-linked polyethylene were studied. The studied coating systems featured excellent mechanical properties with a substantial enhancement of indentation hardness and elastic modulus ratios. The adhesion of the coatings as determined in modified scratch tests can be considered as very good to polymeric and as satisfactory to metallic substrates, thus confirming the potential for the use in total joint arthroplasties. Although the coatings predominantly led to an increase in friction due to the considerably higher roughness, wear was substantially reduced. While only the metallic components were mostly coated in studies reported in literature, our investigation showed that a coating of the polymer component in particular is of decisive importance for enhancing the wear performance and increasing the service life of load-bearing implants. Moreover, single sided coating results in higher wear of the uncoated counter-part. Therefore, coating systems deposited on both articulating surfaces, polymeric and metallic, should be pursued in the future.<br
Keywords: Bio-tribology; Joint-prostheses; Carbon-based coatings; PVD coatings; Wear testing

Evaluation of the wear-resistance of DLC-coated hard-on-soft pairings for biomedical applications - Rothammer, Benedict; Neusser, Kevin; Bartz, Marcel; Wartzack, Sandro; Schubert, Andreas; Marian, Max (Wear, 2023)
Diamond-like carbon (DLC) coatings deposited on the articulating surfaces of total hip or knee arthroplasties have the potential to enhance the overall biotribological behavior and longevity. In this contribution, we employ an ultrahigh molecular weight polyethylene ball-on-three cobalt chromium or titanium alloy pin configuration lubricated by simulated body fluid to effectively carry out screening tests. Thus, the influence of the choice of the coated component (metallic and/or polymeric) as well as the differences between a higher and lower load case with non- and conventionally cross-linked polyethylene were studied. The studied coating systems featured excellent mechanical properties with a substantial enhancement of indentation hardness and elastic modulus ratios. The adhesion of the coatings as determined in modified scratch tests can be considered as very good to polymeric and as satisfactory to metallic substrates, thus confirming the potential for the use in total joint arthroplasties. Although the coatings predominantly led to an increase in friction due to the considerably higher roughness, wear was substantially reduced. While only the metallic components were mostly coated in studies reported in literature, our investigation showed that a coating of the polymer component in particular is of decisive importance for enhancing the wear performance and increasing the service life of load-bearing implants. Moreover, single sided coating results in higher wear of the uncoated counter-part. Therefore, coating systems deposited on both articulating surfaces, polymeric and metallic, should be pursued in the futur
Keywords: Bio-tribology; Joint-prostheses; Carbon-based coatings; PVD coatings; Wear testing

Evaluierung der orientierungsbezogenen Leichtbaugüte - Gruber, Georg; Wartzack, Sandro (Konstruktion, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.evalui_2

Evaluierung Integrativer Simulationsansätze zur Prognose des Strukturverhaltens kurzfaserverstärkter Kunststoffproben - Gruber, Georg; Wartzack, Sandro (6. Landshuter Leichtbau-Colloquium, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.evalui

Evaluierung unterschiedlicher Theorien zur Berechnung beanspruchungsgerechter Faserorientierungen in CFK-Strukturen - Klein, Daniel; Caballero, Steffen; Wartzack, Sandro (Design for X. Beiträge zum 24. DfX-Symposium, 2013)
A Young’s Modulus of up to 100 GPa, high strength and low density are only a few features that make carbon fiber reinforced plastic (CFRP) an ideal material for lightweight constructions. But the potential of CFRP can only be exploited if the fibers are oriented correctly. It is shown in this article that a deviation of only 10° from the ideal fiber orientation leads to a decrease of nearly 40 % in relative stiffness. Furthermore analytical methods to compute the fiber orientation within lightweight structures are only appropriate for geometrically less complex structures. Therefore, two different theories to computationally determine the ideal fiber orientation within structures made of CFRP are introduced. The first one is the load path theory developed by KELLY who originally wanted to visualize load paths within structures and the other is the CAIO method which imitates the adaptive growth of trees. After a short comparison of these different theories with the help of Mohr’s circle the fiber orientation within a b-pillar is computed according to both theories and evaluated with respect to its mechanical behavior. It can be shown that in the case of the b-pillar the fiber orientation according to the CAIO method leads to higher part stiffness and a lower Puck criterion. Additionally a few negative aspects of the load path theory that occur during the design process are pointed out.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.evalui_7
Keywords: Leichtbau; Composites; Kraftfluss

Evidence for the Applicability of Musculoskeletal Human Models to Improve Outcomes of Total Hip Arthroplasty - Scherb, David; Fleischmann, Christopher; Sesselmann, Stefan; Miehling, Jörg; Wartzack, Sandro (Computer Methods, Imaging and Visualization in Biomechanics and Biomedical Engineering II, 2023)
During the preoperative planning of total hip replacements (THR) the patient’s biomechanical condition is widely neglected. The result can be a suboptimal implant selection and positioning, which may cause muscular dysfunctions, especially for revision THR. Thus, this study provides evidence in the use of musculoskeletal human models (MHM) during preoperative planning to improve postoperative outcomes. Therefore, a patient-specific MHM is placed in the pose of single leg stance. First, gluteus medius muscle activation is simulated in three adapted situations: healthy, after primary THR and after revision THR. In a second step, a parameter study with adjustable implant parameters (neck-shaft angle, femoral offset and antetorsion angle) is executed to investigate the effects on the gluteus medius activation. The gluteus medius activation of all three situations shows a remarkable increase to the status after revision THR, with a high risk of muscular impairments occurring due to muscle weakening. The parameter study demonstrates a considerable influence of the adjustable parameters not only on gluteus medius activation but also on hip joint contact force. Concluding, MHM not only allow the analysis of a patient’s individual biomechanical condition, but also improve biomechanical outcomes by enabling the simulation of different geometrical THR implant parameters during surgery planning to support the surgeon in identifying the optimal implant parameters and positioning from both the muscle function and a kinematical (bony) perspectiv

Evidence for the Applicability of Musculoskeletal Human Models to Improve Outcomes of Total Hip Arthroplasty - Scherb, David; Fleischmann, Christopher; Sesselmann, Stefan; Miehling, Jörg; Wartzack, Sandro (Computer Methods, Imaging and Visualization in Biomechanics and Biomedical Engineering II, 2023)
During the preoperative planning of total hip replacements (THR) the patient’s biomechanical condition is widely neglected. The result can be a suboptimal implant selection and positioning, which may cause muscular dysfunctions, especially for revision THR. Thus, this study provides evidence in the use of musculoskeletal human models (MHM) during preoperative planning to improve postoperative outcomes. Therefore, a patient-specific MHM is placed in the pose of single leg stance. First, gluteus medius muscle activation is simulated in three adapted situations: healthy, after primary THR and after revision THR. In a second step, a parameter study with adjustable implant parameters (neck-shaft angle, femoral offset and antetorsion angle) is executed to investigate the effects on the gluteus medius activation. The gluteus medius activation of all three situations shows a remarkable increase to the status after revision THR, with a high risk of muscular impairments occurring due to muscle weakening. The parameter study demonstrates a considerable influence of the adjustable parameters not only on gluteus medius activation but also on hip joint contact force. Concluding, MHM not only allow the analysis of a patient’s individual biomechanical condition, but also improve biomechanical outcomes by enabling the simulation of different geometrical THR implant parameters during surgery planning to support the surgeon in identifying the optimal implant parameters and positioning from both the muscle function and a kinematical (bony) perspective.
CRIS-Team WoS Importer:2022-11-18
Keywords: Musculoskeletal human models; Patient-specific modelling; Revision hip arthroplasty; Biomechanics; Fatty degeneration; Computer aided surgery

Experimental and Numerical Studies on Microtextured Surfaces for Sliding Point Contacts under EHL Conditions - Marian, Max; Grützmacher, Philipp; Tremmel, Stephan; Rosenkranz, Andreas; Mücklich, Frank; Wartzack, Sandro (The 18th Nordic Symposium on Tribology – NORDTRIB 2018, 2018)
Microtextures on the rubbing surfaces may influence the friction and wear performance of lubricated contacts. While this approach has already reached industrial application for sliding contacts with lower contact pressures, the effects for higher loaded EHL contacts are still topic of basic research. For this reason, geometrically defined microtextures, manufactured by a hot micro-coining process, were used for ball-on-disk experiments and characterized with regard to their friction and wear behavior. Numerical EHL simulation based on the full-system approach is applied, acting as a numerical zoom into the contact and contributing to a better understanding of the observed effects and phenomena. Particular attention is paid to the influence of geometrical parameters of microtextures regarding depth, lateral dimensions and position within the contact area. Hence, the importance of structural parameters and microtexture position regarding the tribological behavior is verified numerically and experimentally. Thus, it can be seen that deviations in those parameters can have a strong influence on lubricating conditions, possibly overcompensating beneficial effects induced by microtexturin
Keywords: Microtexturing; Elastohydrodynamic Lubrication; Micro-Coining; Lasertexturing

Experimental and simulative assessment of crashworthiness of mechanically aged short-fibre reinforced thermoplastics - Witzgall, Christian; Wartzack, Sandro (Proceedings of the International Conference on Engineering Design, ICEDVolume 1, Issue DS87-1, 2017)
Short-fibre reinforced thermoplastics (SFRT) are increasingly used in 21st century's automotive construction. Besides statically loaded parts, SFRT are also used for safety-relevant components such as door modules and crash absorbers. Temperature, chemically aggressive media as well as mechanical loading lead to aging effects within the plastic, which generally, weakens the material's mechanical properties. Thus, within the present paper, a series of tests is introduced in order to investigate the effect of mechanical ageing on the material's crashworthiness behaviour. Furthermore, a concept for consideration the effects of ageing within numerical simulation is introduced.

Experimental investigations of lubrication mechanisms in total knee replacements - Nečas, David; Vrbka, Martin; Marian, Max; Wartzack, Sandro; Galandáková, Adéla; Gallo, Jiří; Wimmer, Markus A; Hartl, Martin (5th International Conference on BioTribology, 2021)
Introduction: Total knee arthroplasty (TKA) has become a routine procedure for patients suffering from knee osteoarthritis. Since tribological processes influence the service-life of implants, the present study is targeted to identify lubrication mechanisms occurring in the knee replacement, focusing on the role of specific synovial fluid constituents under application of realistic operating conditions. Methods: The contact of a femoral knee component articulating on a tibial plateau made of transparent polymer was observed using fluorescent microscopy. A knee simulator was used for contact analysis, while the joint was lubricated by various model synovial fluids. Prior to the main phase of testing, the contact zone was lubricated by a mineral oil, while the data were compared to those obtained by the numerical model presented in another contribution. Results: The contact zone showed considerable changes in terms of size and shape of the contact throughout the cycle. The experiments with oil showed very satisfactory agreement with numerical prediction. Subsequent tests performed with model synovial fluid enabled to design a lubrication model of TKA focusing on the role of specific synovial fluid constituents. In particular, it was found that hyaluronic acid together with phospholipids support formation of thin stable boundary layer of γ-globulin. Further enhancement of the lubricating film is attributed to increasing thickness of albumin layer being adsorbed on γ-globulin base. Discussion: The present study employed a unique experimental set-up enabling direct in-situ observation of knee replacement components allowing the actual geometry of the rubbing surfaces together with the application of transient operating conditions. Results revealed that formation of the lubricating film is substantially influenced by the applied testing fluid. Moreover, time test showed that the film exhibits decreasing tendency under continuous loading; thus, rest periods enabling film recovery are recommended in order to enhance implant longevit

Experimental Investigations of Rolling Element Bearings Exposed to Centrifugal Load at a Centripetal Acceleration up to 3 000 Times Gravity - Hochrein, David; Tremmel, Stephan; Graf-Goller, Oliver; Hahn, Bodo; Wartzack, Sandro (The 6th World Tribology Congress, 2017)
Keywords: rolling element bearing; centripetal acceleration; frictional moment

Experimental study on the tribological behavior of ceramic disks for application inmixer taps under different lubrication conditions - Ziegler, Marlene; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Beau, Patrick; Patzer, Gregor; Henzler, Stephan; Marian, Max (Industrial Lubrication and Tribology, 2023)
Purpose – The evaluation of the haptics of water taps and wear-related changes during usage usually involves time- and cost-intensive testing. The purpose of this paper is to abstract the tribo-system between technical ceramic disks of water tap mixer cartridges to the model level and study the tribological behavior. Design/methodology/approach – The friction and wear behavior was studied by means of an alumina ball-on-original alumina disk setup at different temperatures as well as under dry conditions and under lubrication by different greases. Thereby, the frictional behavior was measured in situ, and the wear losses were analyzed by means of laser scanning microscopy. Findings – It was shown that friction and wear can behave in a contrasting way, whereby one grease might lead to low friction, that is, an easygoing movability of the water tap, but to increased wear losses. The latter, in turn, is an indicator for the usability and service life, which cannot be explained from friction alone. Thereby, the viscosity of the base oil, the grease consistency and additives were identified as relevant grease formulation parameters to allow for fluid film (re-)formation and removal of wear particles. Originality/value – To the authors’ best knowledge, this is the first approach to systematically analyze the friction and wear behavior of technical ceramic disks of water tap mixer cartridges in dependency on the temperature as well as the used lubricating grease. This approach is relevant for developing screening test strategies as well as for the selection of lubricants for water tap applications.<br
Keywords: Tribology; Grease; Ceramics; Wear; Friction; Water grade lubricants

Experimentelle Ermittlung von Verschleißkoeffizienten ölgeschmierter Kontakte an einem Zwei-Scheiben-Tribometer - Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2023)
Im Rahmen dieses Beitrags wird ein Vorgehensmodell zur experimentellen Bestimmung von Verschleißkoeffizienten mittels eines Zwei-Scheiben-Tribometers vorgestellt. Mithilfe dieses Vorgehensmodells lassen sich beliebige Slide-to-Roll Ratios (SRR) einstellen, um somit neben reinen Gleitkontakten auch Wälzkontakte abbilden zu können. Die Verschleißkoeffizienten wurden zum einen mittels taktiler Oberflächenmessung und zum anderen mittels gravimetrischer Messung berechnet. Beide Methoden weisen eine sehr gute Übereinstimmung auf. Die vorgestellten Tribometerversuche orientieren sich an einem Anwendungsbeispiel aus dem Bereich der Wälzlagertechnik. Abschließend wird die experimentell gemessene Verschleißtiefe der Prüfscheiben mit einer numerischen Verschleißsimulation abgegliche

Experimentelles Prüfverfahren an einem Vierlagerprüfstand zur Ermitt-lung des Reibungsmomentes einer einzelnen Angular Roller Unit unter axialer und radialer Last - Wirsching, Sven; Hierold, Patrick; Stahl, Thomas; Tremmel, Stephan; Wartzack, Sandro (61. Tribologie-Fachtagung 2020 Reibung, Schmierung und Verschleiß Forschung und praktische Anwendungen, 2020)
Different types of rolling bearing arrangements are used in gearbox applications. The load carrying capacity and fric-tional power of the rolling bearings has a significant influence on the efficiency and performance of the gear unit. A precise knowledge of the load condition of the rolling bearings can be used to reduce friction, so that energy can be saved and the performance can be optimally used. The experimental determination of the frictional torque is an im-portant component for the further development and validation of new bearing geometries. The performance of the rolling bearing must be checked over the speed and load ranges. In many cases, the bearing arrangements are not under purely axial or radial load but under combined load. Initially, only purely axial or purely radial loads can be usefully investigated on conventional two or four bearing test rigs. For this purpose, the total frictional torque of both or all four bearings is measured. Due to the symmetrical distribution of the load to the bearings, it is possible to derive the frictional torque of the individual bearing. Therefore, the evaluation of the frictional torque of the single bearing on a four-bearing test rig would be a cost-effective alternative to a single bearing test rig. This procedure is not allowed for bearings under combined load, because in the present case the outer bearings receive a combination of axial and radial force and the middle bearings the radial force. For this reason, the following paper presents an experimental test method that allows the determination of the frictional torque of a single bearing on a four-bearing test rig. In the test, the total frictional torque of all two or four bearings is measured. The outer two bearings can be loaded axially and simultaneously radially. The middle bearings transmit the radial load. In order to determine the frictional torque for the outer bearings, first, tests are executed with four purely radially loaded ball bearings. In the next step, tests are performed with the testing bearings under purely radial load. In a further step, the rolling bearings are combined so that the testing bearings are inserted at the outer positions and the ball bearings at the middle once. By evaluating the total frictional moment in the tests, the frictional moments of the individual bearings can be calculated and an error estimation is possible. Finally, this bearing arrangement is tested under a combined load condition and the frictional torque of the testing bearings is determined under consideration of the error. The results of the tests are analyzed and discussed.<br
Keywords: rolling bearing; friction; combined load; four bearing test rig; experiment

Exploring the importance of a usable and emotional product design from the user’s perspective - Buker, Tina; Schmitt, Teresa; Miehling, Jörg; Wartzack, Sandro (Ergonomics, 2022)
Usability and emotionality are important components of user experience. However, an equal consideration of both constructs in product design is not always possible due to sometimes competitive objectives. In order to foster a user-oriented design decision in such conflicting situations, this paper examines the general importance of both constructs and their dimensions from the user’s perspective while taking into account socio-demographic variables. Examination was realised by conducting a product independent anonymous online survey (n = 130). The findings confirm that both constructs are important, yet in a direct comparison, usability is perceived as more important than emotionality. Taking selected dimensions of both constructs into account, an intuitive, easy and learnable usage, suitability for the user's task and freedom from impairment are particularly important in terms of usability. An aesthetic and pleasurable product design as well as originality is essential in terms of emotionalit
Keywords: usability; emotional design; product design; user-centred design; empirical study

Exploring the lubrication mechanisms of synovial fluids for joint longevity – A perspective - Marian, Max; Shah, Raj; Gashi, Blerim; Zhang, Stanley; Bhavnani, Kiran; Wartzack, Sandro; Rosenkranz, Andreas (Colloids and Surfaces B: Biointerfaces, 2021)
Synovial fluids are complex fluids responsible for the exceptional lubrication present in synovial joints. These fluids consist of various constituents, including hyaluronic acid, surface-active proteins (i.e., lubricin), surface-active phospholipids, as well as various other proteins such as human serum albumin and gamma-globulin seric proteins, each of them playing an essential role in lubrication. Being the key to the most efficient biotribological systems, this article is intended to review the current understanding of the underlying lubrication mechanisms of the synovial fluids enables prospective usage in numerous applications, especially as a lubricant for hip and knee prosthetics in combatting osteoarthritis. Current research focuses on the determination of the role of proteins in prosthetic lubrication, optimal material combinations for prosthesis, and the effects of relevant physical variables in prosthetic lubrication. The characterization of prosthetic lubrication and wear mechanisms by synovial fluids represents a prominent challenge in tribological research, yet also an important hurdle to overcome towards optimal lubrication of articular prosthetic
Keywords: Biotribology; Lubrication; Synovial fluid; Synovial joint; Hip replacement; Knee replacement

Failure mechanisms of a hydrogenated amorphous carbon coating in load-scanning tests - Hetzner, Harald; Schaufler, Jens; Tremmel, Stephan; Durst, Karsten; Wartzack, Sandro (Surface & Coatings Technology, 2012)
A diamond-like carbon (DLC) coating with a top layer of pure hydrogenated amorphous carbon (a-C:H) and an interlayer of tungsten-modified hydrogenated amorphous carbon (a-C:H:W) was deposited onto polished cylindrical specimens of a hardened and tempered cold work tool steel. On a load-scanning test rig, tribological-mechanical tests under dry conditions with DLC coated specimens sliding against identical, but uncoated specimens were performed. Additionally, comparative tests with DLC sliding against DLC and tool steel sliding against tool steel were carried out. During each test cycle, the normal load was gradually increased from 13 to 350. N, corresponding to a Hertzian contact pressure of 1.0 to 3.0. GPa. The coefficient of friction was monitored as a function of the normal load, with a significant increase in friction indicating failure of the coating. The tests were repeated and stopped at different total numbers of load cycles. After the tests, a FIB-assisted microscopical analysis in terms of wear and damage of the DLC coating was performed, revealing the (subsurface) failure mechanisms. For DLC sliding against steel, the coating fails within only few load cycles; first tribologically and after that mechanically. Failure is initiated by adherence and subsequent transfer of steel of the counter body. Below adhered steel flakes, tensile cracks form in the a-C:H top layer, with sharp crack edges removing even more steel from the counter body. In following load cycles, coating fragments are being pulled out at these spots, representing the final failure mode. In contrast, for DLC sliding against DLC, no coating failure and also no significant wear are observed, even after a considerably higher number of load cycles. © 2012 Elsevier B.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.failur
Keywords: a-C:H; Coating failure; Diamond-like carbon; Load-scanning test

Failure mechanisms of a tungsten-modified hydrogenated amorphous carbon coating in load-scanning tests - Hetzner, Harald; Schaufler, Jens; Tremmel, Stephan; Durst, Karsten; Wartzack, Sandro (Surface & Coatings Technology, 2012)
Polished cylindrical specimens of a hardened and tempered cold work steel were coated with a tungsten-modified hydrogenated amorphous carbon coating (a-C:H:W). On a load-scanning test rig, tribological-mechanical tests under dry conditions with coated specimens sliding against identical, but uncoated specimens were performed. Additionally, comparative tests with a-C:H:W coated specimens sliding against a-C:H:W coated specimens were carried out. During each test cycle, the normal load was gradually increased from 13 to 350. N (Hertzian contact pressure of 1.0 to 3.0. GPa). The coefficient of friction was monitored as a function of the normal load, with a significant increase in friction indicating failure of the coating. These tests were repeated and stopped at different total numbers of load cycles. After the tests, a FIB-assisted microscopical analysis in terms of wear and damage of the coating was performed, revealing the (subsurface) failure mechanisms. The results obtained show that at Hertzian pressures of more than 2. GPa and after about eight load cycles, failure of the a-C:H:W coating is initiated by locally accumulated adhesion of steel flakes, repeatedly occurring at random contact pressures in this load range. The adherence of steel goes along with a local increase in friction, inducing the formation of small shear cracks in the coating top layer. Continued crack formation finally results in partial delamination of coating material and disruption of the surface, in affected areas only. Reference tests with the pairing a-C:H:W/a-C:H:W underline that, very much unlike pure hydrogenated amorphous carbon (a-C:H), a-C:H:W is a rather ductile material with the ability to stick to itself. A discussion of this study's results against the background of a similarly conducted previous study of an a-C:H-based coating system reveals some similarities, but also significant differences in the tribological and mechanical behaviour of both types of amorphous carbon. © 2012 Elsevier B.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.failur_1
Keywords: a-C:H:W; Coating failure; Diamond-like carbon; Load-scanning test

Fatigue Behaviour and Its Effect on the Residual Strength of Long-Fibre-Reinforced Thermoplastic PP LGF30 - Witzgall, Christian; Gadinger, Marc; Wartzack, Sandro (Materials, 2023)
It is undeniable that mechanical properties, such as the stiffness or residual strength of fibre-reinforced thermoplastics, are adversely affected by fatigue damage caused by cyclic loading. In order to quantify and predict this damage influence, a calculation approach was developed in the past for the subgroup of short-fibre-reinforced thermoplastics. In order to test and expand the applicability of this approach to the field of long-fibre-reinforced thermoplastics, the decrease in mechanical properties is investigated experimentally in this paper using PP LGF30, propylene reinforced with long glass fibres, as an example. The paper describes both the fatigue behaviour and the residual strength of the material after fatigue damage. A decrease in the residual strength of up to about 35% could be recorded. The paper also presents a modelling approach that predicts the orientation-dependent fatigue strength of the material, and furthermore allows for the calculation of its residual strength as a function of fatigue damage. The novelty of the contribution lies in the continuous modelling of fatigue behaviour for arbitrary oriented samples of long-fibre-reinforced thermoplastics and also in the prediction of its residual strength depending on previously induced fatigue damage. <br
Keywords: fatigue; residual strength; long-fibre-reinforced plastics; PP LGF30; material data

Fatigue Damage of Short Fibre-Reinforced Thermoplastics in Crashworthiness Simulation - Witzgall, Christian; Wartzack, Sandro (Applied Mechanics, 2023)
Service loads repeatedly stress components on a regular basis and lead to fatigue damage in the material. In the case of components made of short fibre-reinforced thermoplastics, which are also crash-relevant in addition to only bearing service loads, however, a significant deterioration in mechanical properties can be observed after fatigue damage has been introduced. This is where the approach presented in this paper comes in: in order to enable a realistic simulation of such components in their used conditions, the material data are assigned depending on previously determined damage. The approach, which combines the domains of highly dynamic and cyclic experiments as well as different types of numerical simulations, is tested for its performance in the present paper. For this purpose, component tests are carried out on cross-rib beams, which serve to validate the method. The novelty and uniqueness of this paper lies in the linking of fatigue life and crashworthiness considerations for short fibre-reinforced thermoplastics, which, in this case, is raised to a new level by considering the component level for the first time.<br
Keywords: fatigue; crashworthiness; short fibre-reinforced plastics; PBT GF30; component testing

FEA-Assistenzsystem – Plausibilitätsprüfung für Finite-Elemente-Simulationen mittels sphärischer Detektorflächen - Sprügel, Tobias; Kestel, Philipp; Wartzack, Sandro (Beiträge zum 27. DfX-Symposium, 2016)
Finite Element Analysis (FEA) is a very efficient tool for optimizing product performance and quality. Hence, more simulation engineers with a lot of experience are needed, but they are not available. Consequently other users, such as design engineers, should be able to perform valid, reliable FEA. One of the goals of the research cooperation FORPRO² is to create a knowledgebased FEA assistance system with an integrated plausibility check for structural mechanics. Within this paper a methodology for a plausibility check using spherical detector surfaces is presented. Thereby it is possible to reduce any FE simulation to matrices of fixed size for each boundary condition and each FEA result variable. The created matrices can then be combined to form a single larger image. These images can afterwards be classified as plausible or implausible by a Deep Learning Neural Network.

Feature-based approach for the automated setup of accurate, design-accompanying Finite Element Analyses - Kestel, Philipp; Schneyer, Thomas; Wartzack, Sandro (Proceedings of the 14th International Design Conference, 2016)
Finite element analyses (FEA) gain huge attention in engineering design practice. However, an efficient use of FEA requires early application in the product development process. Furthermore, extensive specialist knowledge is a crucial prerequisite to perform reliable simulations. Due to time constraints, design accompanying FEA are performed too rarely by experienced simulation engineers or, if they are applied by non-expert simulation users, are not sufficiently accurate. Hence, a feature-based approach is presented, to support and automate the setup of design accompanying simulations.
Keywords: knowledge-based simulation; assistance system; feature; data mining

Feature based interpretation and reconstruction of structural topology optimization results - Stangl, Thomas; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), 2015)
The application of structural topology optimization is a common computer aided method to define the ideal design of a mechanical part. However, the problem remains, that the optimized component in its triangulated surface form cannot directly be used as model in the CAD based product development process. Due to different design aspects (even when using additive layer manufacturing technologies) the result needs to be interpreted and converted into a parametric feature based CAD model. After all, the current standard method is a time consuming, long-winded manual reconstruction. To put this right, this paper presents a semi-automatic approach to support the design engineer. The tool provides a way to interpret and reconstruct three dimensional topology optimization results as a parametric feature based CAD model. This approach automates the manual proceeding in order to generate a high quality solid CAD part. The functionality is demonstrated in a case study by an optimized and reconstructed motorcycle swing arm.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.featur
Keywords: Computational design synthesis; Computer aided design (CAD); Optimisation; Embodiment design

Feature-Based Reconstruction of Non-Beam-Like Topology Optimization Design Proposals in Boundary-Representation - Mayer, Johannes; Völkl, Harald; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
Geometry reconstruction from 3D topology optimization results to Computer Aided Design (CAD) is challenging, especially for automation and non-beam-like geometry. While the optimized model has polygonal format, product development with CAD requires analytical surfaces in Boundary Representation (B-Rep). In this paper, we present two approaches for an automated interpretation of surface-skeletons for CAD-reconstruction. This includes the question, when to convert the skeleton’s polygonal to analytical surfaces and how to conceptually incorporate CAD- features. One approach is based on decomposing the input in analytical, the other in polygonal surfaces. Both approaches work with specific skeleton-features and lead to a CAD-model with B-Rep-reconstruction. Exemplary results are presente
Keywords: Topology Optimization; Computer Aided Design; Geometry Post-Processing; Medial Axis Transform; Skeletonization

Feature-basierte Modellierung und Bauteilerkennung in automatisierten, konstruktionsbegleitenden Finite-Elemente-Analysen - Kestel, Philipp; Sprügel, Tobias; Wartzack, Sandro (34. CADFEM ANSYS Simulation Conference, 2016)
Computer-based simulation techniques such as Finite Element Analyses (FEA) gain huge attention in engineering design practice. However, an efficient simulation use requires an early application in the product development process. Furthermore, extensive specialist knowledge is a crucial prerequisite to perform reliable and efficient FEA. Due to time constraints, design accompanying FEA are performed only rarely by experienced simulation engineers or, if they are applied by non-expert simulation users, are not sufficiently accurate. In order to meet the increasing requirements on product development, the required expert knowledge has to be available for less experienced simulation users in design departments. Furthermore, recurring working steps like setting up FEA in Pre-Processing as well as evaluating the analysis results in Post-Processing have to be automated in order to accelerate these processes and ensure the computation accuracy. Thus, a knowledge-based FEA assistance system is developed to support less experienced simulation users setting up high-quality structural-mechanical FEA and to evaluate the results. The necessary knowledge is acquired and stored in a central knowledge base by expert interviews as well as by analyzing computation models and reports of previous applied and validated simulations in automated Text and Data Mining processes. In order to couple the design and FEA environments as well as to identify and specifically prepare the relevant model regions in automated simulation processes an extended feature library is developed and implemented. In addition, to recognize non-feature-based parts in the FEA results an approach based on spherical detector surfaces is used.

Femoral Shape and Size Variability from segmented CT datasets for patient-specific THA planning - Fleischmann, Christopher; Leher, Irina; Sesselmann, Stefan; Scherb, David; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Current Directions in Biomedical Engineering, 2020)
Biomechanical functionality of artificial hips strongly correlates with quality of life of patients after total hip arthroplasty. As the numbers of total hip arthroplasty are growing due to increasing life expectancy, biomechanical research is of utmost importance to improve the implants used and the operative procedures applied. Multibody simulation is used to predict forces and moments inside the human body. Generic scaling is usually performed to adapt the human models used in multibody simulation to individual patients. However, since the shape and size of the bones can vary considerably, this type of scaling often is not sufficient. In this work various CT datasets were used to quantify differences of individual femoral shapes, especially with regard to important biomechanical hip parameters, such as the CCD angle or the femoral offset. Our results prove that multibody simulations should be modeled more patientspecific to be able to calculate articular forces and moments more precisely, and thus, to improve surgical planning.

Fertigungsgerechtes Konstruieren - Potenzial und aktuelle Tendenzen - Wartzack, Sandro; Meerkamm, Harald (Werkstatt und Betrieb, 2000)
UnivIS-Import:2015-03-09:Pub.2000.tech.FT.FT-KLMEFK.fertig

FORCuDE@BEV: Neuer Forschungsverbund zum Customized Digital Engineering - Schleich, Benjamin; Wartzack, Sandro (WiGeP News, 2020)

Forschungsgruppe zum prozessorientierten Toleranzmanagement geht in die zweite Phase - Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (WiGeP News, 2020)

Fostering self-efficacy through usability and emotional product design? An explorative study - Buker, Tina; Kamin, Stefan; van Remmen, Judith Sophie; Wartzack, Sandro; Miehling, Jörg (Research in Engineering Design, 2024)
Raising the user’s self-confidence is a promising strategy to reduce product-related user stigma. In the context of product usage, the commonly used term self-confidence refers to the psychological construct of self-efficacy. To strengthen a user’s self-efficacy through product design, providing both good usability and emotionality in a product seems to be a reasonable starting point. However, their suitability and validity for this purpose has not yet been sufficiently assessed. This paper examines whether self-efficacy would be associated with perceptions of a product’s usability and emotionality. By conducting an online survey (n = 105; stigma-sensitive product demonstrator: walker), it was confirmed that the perception of good usability and emotionality of walkers were positively associated with the user’s perceived self-efficacy. Moreover, a negative interaction effect was identified showing that the association between emotionality and self-efficacy increased with lower levels of perceived usability and vice versa. This may indicate that emotions can compensate the importance of usability at least to some exten
Keywords: User-centred design; Inclusive design; Product design; Product-related user stigma; Empirical study

Friction reduction in EHL contacts by surface microtexturing – tribological performance, manufacturing and tailored design - Tremmel, Stephan; Marian, Max; Zahner, Michael; Wartzack, Sandro; Merklein, Marion (Industrial Lubrication and Tribology, 2019)
Purpose – This paper aims to derive tailor-made microtextures for elastohydrodynamically lubricated (EHL) contacts under consideration of manufacturing possibilities. Design/methodology/approach – Component tests were used for the evaluation of the influence of surface texturing on the friction behavior in the cam/tappet contact. Furthermore, the manufacturing possibilities and limitations of a combined mEDM and micro coining process and the feasibility of integration into a forming process were studied. Finally, a methodology based on transient EHL simulations and a meta-model of optimal prognosis was exemplarily used for microtexture optimization. Findings – It was found that surface texturing in EHL contacts with high amount of sliding is promising. Moreover, the combination of mEDM and micro coining and the integration into established production processes allow the manufacturing of microtextures with desirable structural parameters and sufficient accuracy. Originality/value – This paper gives a holistic view on surface microtexturing over several phases of the product life cycle, from the design, over efficient manufacturing to application-related testin
Keywords: Friction; Elastohydrodynamic lubrication; Micro coining

Fringe projection profilometry in production metrology: A multi-scale comparison in sheet-bulk metal forming - Hinz, Lennart; Metzner, Sebastian; Müller, Philipp; Schulte, Robert Karl; Besserer, Hans-Bernward; Wackenrohr, Steffen; Sauer, Christopher; Kästner, Markus; Hausotte, Tino; Hübner, Sven; Nuernberger, Florian; Schleich, Benjamin; et al. (Sensors, 2021)
Fringe projection profilometry in combination with other optical measuring technologies has established itself over the last decades as an essential complement to conventional, tactile measuring devices. The non-contact, holistic reconstruction of complex geometries within fractions of a second in conjunction with the lightweight and transportable sensor design open up many fields of application in production metrology. Furthermore, triangulation-based measuring principles feature good scalability, which has led to 3D scanners for various scale ranges. Innovative and modern production processes, such as sheet-bulk metal forming, thus, utilize fringe projection profilometry in many respects to monitor the process, quantify possible wear and improve production technology. Therefore, it is essential to identify the appropriate 3D scanner for each application and to properly evaluate the acquired data. Through precise knowledge of the measurement volume and the relative uncertainty with respect to the specimen and scanner position, adapted measurement strategies and integrated production concepts can be realized. Although there are extensive industrial standards and guidelines for the quantification of sensor performance, evaluation and tolerancing is mainly global and can, therefore, neither provide assistance in the correct, application-specific positioning and alignment of the sensor nor reflect the local characteristics within the measuring volume. Therefore, this article compares fringe projection systems across various scale ranges by positioning and scanning a calibrated sphere in a high resolution grid.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Coordinate metrology; Fringe projection; Production metrology; Sheet-bulk metal forming

FROM SKETCHES TO GRAPHS: A DEEP LEARNING BASED METHOD FOR DETECTION AND CONTEXTUALISATION OF PRINCIPLE SKETCHES IN THE EARLY PHASE OF PRODUCT DEVELOPMENT - Bickel, Sebastian; Götz, Stefan; Wartzack, Sandro (Proceedings of the Design Society, 2023)
The digitalization trend is finding its way more and more into product development, resulting in new frameworks to enhance product engineering. An integral element is the application of new techniques to existing data, which offers an enormous potential for time and cost savings, because duplicate work in product design and subsequent steps is avoided. The reduction of costs can be further increased through the application as early as possible in the product development process. One solution is outlined in this publication, where the source of available data is principle sketches from engineering design. These represent the basic solution for technical products in a simplified way and are often deployed in the early stages of the development process. This representation enables not only a search of similar sketches but also other fields of interest such as product optimization or the search of CAD-geometries. To utilize this data in a practical way, a procedure is presented which recognizes the symbols of the sketches and subsequently converts them into graphs. An exemplary dataset from different gearbox layouts is used to present the application opportunities by performing similarity searches with multiple input formats.<br
Keywords: Early design phases; Machine learning; Artificial intelligence; object detection; deep learning

From solid modelling to skin model shapes: Shifting paradigms in computer-aided tolerancing - Anwer, Nabil; Schleich, Benjamin; Mathieu, Luc; Wartzack, Sandro (CIRP Annals - Manufacturing Technology, 2014)
Product design requires the consideration of geometric models and representations that reflect shape deviations and support tolerance management issues. Computer-Aided Tolerancing (CAT) systems have been developed as simulation tools for modelling the effects of tolerances on digital product simulation. However, geometric variations cannot be addressed efficiently with regard to form deviations. This paper investigates the concepts of Skin Model Shapes, which provide a finite describability and the digital representation of the Skin Model concept, and their unified discrete geometry representation. New contributions to tolerance representation and analysis are presented. Applications and perspectives for CAT systems are highlighted as well.
Keywords: Product development; Tolerancing; Skin Model

From tolerance allocation to tolerance-cost optimization: a comprehensive literature review - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (International Journal of Advanced Manufacturing Technology, 2020)
It is widely acknowledged that the allocation of part tolerances is a highly responsible task due to the complex repercussions on both product quality and cost. As a consequence, since its beginnings in the 1960s, least-cost tolerance allocation using optimization techniques, i.e. tolerance-cost optimization, was continuously in focus of numerous research activities. Nowadays, increasing cost and quality pressure, availability of real manufacturing data driven by Industry 4.0 technologies, and rising computational power result in a continuously growing interest in tolerance-cost optimization in both research and industry. However, inconsistent terminology and the lack of a classification of the various relevant aspects is an obstacle for the application of tolerance-cost optimization approaches. There is no literature comprehensively and clearly summarizing the current state of the art and illustrating the relevant key aspects. Motivated to overcome this drawback, this article provides a comprehensive as well as detailed overview of the broad research field in tolerance-cost optimization for both beginners and experts. To facilitate the first steps for readers who are less familiar with the topic, the paper initially outlines the fundamentals of tolerance-cost optimization including its basic idea, elementary terminology and mathematical formulation. These fundamentals serve as a basis for a subsequent detailed discussion of the key elements with focus on the different characteristics concerning the optimization problem, tolerance-cost model, technical system model and the tolerance analysis model. These aspects are gathered and summarized in a structured mind map, which equips the reader with a comprehensive graphical overview of all the various facets and aspects of tolerance-cost optimization. Beside this, the paper gives a retrospect of the past fifty years of research in tolerance cost-optimization, considering 290 relevant publications. Based thereon, current issues and future research needs in tolerance-cost optimization were identified.<br

From vector-chain-based to geometrical Tolerance Analyses of Systems in Motion- the Use of Metamodels and their Evaluation - Walter, Michael; Wartzack, Sandro (Weimarer Stochastik- und Optimierungstage WOST 9.0, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.fromve

Fully Automated Reconstruction of Topology Optimization Results with Feature Transformation and Curve Skeletonization! - Denk, Martin; Mayer, Johannes; Wartzack, Sandro (20. VDI-Kongress mit Fachausstellung SIMVEC, Aktuelle Herausforderungen bei der Auslegung und Absicherung von Fahrzeugsystemen, 2022)
The results of a topology optimization are oft en available as so-called dead geometry in the form of cell models or polygon meshes. This fo rmat can be derived directly from finite element meshes, but no feature-based CAD parametric is available. In this work, such results are automatically transformed into a be am parametric via so-called curve skeletons. However, the curves start within the geometry and often have to be manually extruded onto the surface. In this work, this skeletonization is modified so that the individual curves usefully begin at the surface. The improved approach is then tested on a variety of model
Keywords: Skeletonization; Topology Optimization; Reconstruction; Feature Transformation

Functional Analysis of Components Manufactured by a Sheet-Bulk Metal Forming Process - Hetzel, Andreas; Schulte, Robert Karl; Vogel, Manfred; Lechner, Michael; Besserer, Hans-Bernward; Maier, Hans Juergen; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2021)
Due to rising demands regarding the functionality and load-bearing capacity of functional components such as synchronizer rings in gear systems, conventional forming operations are reaching their limits with respect to formability and efficiency. One way to meet these challenges is the application of the innovative process class of sheet-bulk metal forming (SBMF). By applying bulk forming operations to sheet metal, the advantages of both process classes can be combined, thus realizing an optimized part weight and an adapted load-bearing capacity. Different approaches to manufacturing relevant part geometries were presented and evaluated regarding the process properties and applicability. In this contribution, a self-learning engineering workbench was used to provide geometry-based data regarding a novel component geometry with circumferential involute gearing manufactured in an SBMF process combination of deep drawing and upsetting. Within the comprehensive investigations, the mechanical and geometrical properties of the part were analyzed. Moreover, the manufactured components were compared regarding the increased fatigue strength in cyclic load tests. With the gained experimental and numerical data, the workbench was used for the first time to generate the desired component as a CAD model, as well as to derive design guidelines referring to the investigated properties and fatigue behavior.<br
Keywords: sheet-bulk metal forming; mechanical properties; self-learning engineering workbench; functional behavior; fatigue life modeling; Z-integral approach

Funktionsorientiertes Interaktionsmodell zur Simulation menschlicher Bewegungen während der Nutzer-Produkt Interaktion - Krüger, Daniel; Wartzack, Sandro (Design for X - Beiträge zum 25. DfX-Symposium, 2014)
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.funkti

Fuzzy Sensitivity Analysis in the Context of Dimensional Management - Oberleiter, Thomas; Heling, Björn; Schleich, Benjamin; Willner, Kai; Wartzack, Sandro (ASCE-ASME Journal of Risk and Uncertainty in Engineering Systems, Part B: Mechanical Engineering, 2018)
Real components always deviate from their ideal dimensions. This makes every component, even a serial production, unique. Although they look the same, differences can always be observed due to different scattering factors and variations in the manufacturing process. All these factors inevitably lead to parts that deviate from their ideal shape and, therefore, have different properties than the ideal component. Changing properties can lead to major problems or even failure during operation. It is necessary to specify the permitted deviations to ensure that every single product nevertheless meets its technical requirements. Furthermore, it is necessary to estimate the consequences of the permitted deviations, which is done via tolerance analysis. During this process, components are assembled virtually and varied with the uncertainties specified by the tolerances. A variation simulation is one opportunity to calculate these effects for geometric deviations. Since tolerance analysis enables engineers to identify weak points in an early design stage, it is important to know the contribution that every single tolerance has on a certain quality-relevant characteristic, to restrict or increase the correct tolerances. In this paper, a fuzzy-based method to calculate the sensitivity is introduced and compared with the commonly used extended Fourier amplitude sensitivity test (EFAST) method. Special focus of this work is the differentiation of the sensitivity for the total system and the sensitivities for the subsystems defined by the α-cuts of the fuzzy numbers. It discusses the impact of the number of evaluations and nonlinearity on sensitivity for EFAST and the fuzzy-based meth

Gap hull estimation for rigid mechanical joints considering form deviations and multiple pairs of mating surfaces - Schleich, Benjamin; Wartzack, Sandro (Mechanism and Machine Theory, 2018)
The embodiment of mechanical joints is a demanding activity during the design of mechanism. In this context, particularly the assessment of the effects of geometrical deviations on the behaviour of the mechanical joint is of strong importance. This paper presents an approach to the gap hull estimation for mechanical joints considering form deviations. The novelty of this approach lies in the ability to analyse the behaviour of mechanical joints considering multiple pairs of mating surfaces. The application of this method to a prismatic as well as to a cylindrical joint prove the versatility of the method regarding different kinds of joints with multiple pairs of contact surfaces. Moreover, the results of the application of this approach to the tolerance analysis of a two-pin-two-hole assembly confirm the importance of considering form deviations in the tolerance analysis and in the design of mechanical joints and mechanism. <br
Keywords: Gap hull; Clearance space; Skin model shapes; Tolerance analysis

Gaussian Process based approach for automatic knowledge acquisition - Breitsprecher, Thilo; Kestel, Philipp; Dingfelder, Christian; Wartzack, Sandro (Proceedings of the 13th International Design Conference, 2014)
New manufacturing processes like sheet-bulk metal forming offer a high degree of freedom to the design engineer, because complex features elements (teeth, grooves, etc.) can be manufactured, that were not realizable before or only at high costs. In order to make use of this new design freedom the design engineer can be assisted by knowledge based systems, whereas the knowledge acquisition is the most crucial step in the development of a KBE-system. This paper presents a Gaussian process based approach for automatic acquisition of design-relevant and manufacturing related knowledge.

Generating Digital Twins for Path-Planning of Autonomous Robots and Drones Using Constrained Homotopic Shrinking for 2D and 3D Environment Modeling - Denk, Martin; Bickel, Sebastian; Steck, Patrick; Götz, Stefan; Völkl, Harald; Wartzack, Sandro (Applied Sciences, 2022)
A digital twin describes the virtual representation of a real process. This twin is constantly updated with real data and can thus control and adapt the real model. Designing suitable digital twins for path planning of autonomous robots or drones is often challenging due to the large number of different dynamic environments and multi-task and agent systems. However, common path algorithms are often limited to two tasks and to finding shortest paths. In real applications, not only a short path but also the width of the passage with a path as centered as possible are crucial, since robotic systems are not ideal and require recalibration frequently. In this work, so-called homotopic shrinking is used to generate the digital twin, which can be used to extract all possible path proposals including their passage widths for 2D and 3D environments and multiple tasks and robots. The erosion of the environment is controlled by constraints such that the task stations, the robot or drone positions, and the topology of the environment are considered. Such a deterministic path algorithm can flexibly respond to changing environmental conditions and consider multiple tasks simultaneously for path generation. A distinctive feature of these paths is the central orientation to the non-passable areas, which can have significant benefits for worker and patient safety. The method is tested on 2D and 3D maps with different tasks, obstacles, and multiple robots. For example, the robust generation of the digital twin for a maze and also the dynamic adaptation in case of sudden changes in the environment is covered. This variety of use cases and the comparison with alternative methods result in significant advantages, such as high robustness, consideration of multiple targets, and high safety distances to obstacles and areas that cannot be traversed. Finally, it was shown that the environment for the digital twin can be reduced to reasonable paths by constrained shrinking, both for real 2D maps and for complex virtual 2D and 3D maps.

Generating hybrid geometry models for more precise simulations by combining parametric CAD-models with 3d surface detected geometry inserts - Katona, Sebastian; Koch, Michael; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED2015), 2015)
In general, every component shows differences to its ideal geometry of the designed CAD-model, i.e. due to deformations in the production process. Despite knowing the effects of deformations, the product developer always uses the ideal, non-deformed design model of the CAD-system for FE-simulations of a component. It seems rather doubtful that further refinement of simulation methods (e.g. using different non-linearities) makes sense, if the real manufactured geometry of the component is not considered for in the simulation process. Therefore, this paper describes an approach to use hybrid geometry models for simulations, which are mostly built of the parametric CAD-model, but areas with large deviations are substituted with surface reconstructed scan-inserts based on 3d surface scanned data, reconstructed to NURBS-patches. This procedure allows a more precise simulation as it considers deviations by minimizing the amount of data and the time for model preparation.
Keywords: CAD; Product modelling; models; Simulation; Reverse Engineering

Generation of deviated geometry based on manufacturing process simulations - Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 9th Optimization and Stochastic Days 2012, 2012)
Every process underlies fluctuations of input and ambient parameters. In manufacturing processes, these fluctuations manifest i.a. in geometric deviations of manufactured workpieces which in turn hugely decrease the function and quality of technical products. Therefore, these deviations have to be limited by geometric tolerances. In this regard, tolerance simulations aim at determining and quantifying the effects of deviations on the product quality. However, in order to obtain resilient predictions about the impacts of process fluctuations on the quality of technical products realistic samples of deviated geometries have to be available which reflect the observable geometric manufacturing deviations. The proposed approach employs methods from computer vision and regression analysis for generating realistic geometry samples based on a limited set of observations, e.g. gathered from manufacturing process simulations or measurements, considering manufacturing process parameters. An exemplary application using the software "Statistics on Structure" (SoS) and "optiSLang" by dynardo GmbH is given.

Generative adversarial networks for tolerance analysis - Schleich, Benjamin; Qie, Yifan; Wartzack, Sandro; Anwer, Nabil (CIRP Annals - Manufacturing Technology, 2022)
Many activities in design and manufacturing rely on realistic product representations considering geometrical deviations to assess their effects on the product function and quality. Though several approaches for tolerance analysis have been developed, they imply several shortcomings, such as the lack of form deviations consideration and the high manual modelling effort. In this paper, a novel shape-agnostic approach supported by generative adversarial networks is developed for the automated generation of part representatives with geometrical deviations. A workflow for generating these variational part representatives is highlighted and tolerance analysis case studies demonstrate the effectiveness of the proposed approach.<br
Keywords: Design; Tolerancing; Machine learning

GENERIC APPROACH TO PLAUSIBILITY CHECKS FOR STRUCTURAL MECHANICS WITH DEEP LEARNING - Sprügel, Tobias; Schröppel, Tina; Wartzack, Sandro (Proceedings of the 21st International Conference on Engineering Design (ICED17), 2017)
The simulation of product behavior is a vital part in virtual product development, but currently there is no tool or method available that can examine the quality of FE simulations and decide automatically on whether a simulation is plausible or non-plausible. In the paper a method is presented that enables automatic plausibility checks on basis of empirical simulation datasets. Nodal simulation data is transformed to numerical arrays, of fixed size, using virtual spherical detector surfaces. Afterwards the arrays are used to train a Deep Convolutional Neural Network (AlexNet). The Neural Network can then be used for plausibility checks of FE simulations (structural mechanics). In a first application a Deep Convolutional Neural Network is trained with simulation data of a demonstrator part, the rail of speed inline skates. After the GPU training of the Neural Network, further simulations are evaluated with the net. These simulations were not part of the training data and are used to calculate the prediction quality of the Neural Network. This approach is to support development engineers during design accompanying FEA in virtual product development.

Geometrical Optimization of the EHL Roller Face/Rib Contact for Energy Efficiency in Tapered Roller - Wirsching, Sven; Marian, Max; Bartz, Marcel; Stahl, Thomas; Wartzack, Sandro (Lubricants, 2021)
In the context of targeted improvements in energy efficiency, secondary rolling bearing contacts are gaining relevance. As such, the elastohydrodynamically lubricated (EHL) roller face/rib contact of tapered roller bearings significantly affects power losses. Consequently, this contribution aimed at numerical optimization of the pairing’s macro-geometric parameters. The latter were sampled by a statistical design of experiments (DoE) and the tribological behavior was predicted by means of EHL contact simulations. For each of the geometric pairings considered, a database was generated. Key target variables such as pressure, lubricant gap and friction were approximated by a meta-model of optimal prognosis (MOP) and optimization was carried out using an evolutionary algorithm (EA). It was shown that the tribological behavior was mainly determined by the basic geometric pairing and the radii while eccentricity was of subordinate role. Furthermore, there was a trade-off between high load carrying capacity and low frictional losses. Thereby, spherical or toroidal geometries on the roller end face featuring a large radius paired with a tapered rib geometry were found to be advantageous in terms of low friction. For larger lubricant film heights and load carrying capacity, spherical or toroidal roller on toroidal rib geometries with medium radii were favorable.
Keywords: tapered roller bearing; energy efficiency; elastohydrodynamic lubrication; macro-geometry; machine learning; meta-modeling; multi-objective optimization; genetic algorithm

Geometrical Variations Management 4.0: towards next Generation Geometry Assurance - Schleich, Benjamin; Wärmefjord, Kristina; Söderberg, Rikard; Wartzack, Sandro (Procedia CIRP, Volume 75, 2018)
Product realization processes are undergoing radical change considering the increasing digitalization of manufacturing fostered by cyber-physical production systems, the internet of things, big data, cloud computing, and the advancing use of digital twins. These trends are subsumed under the term “industry 4.0” describing the vision of a digitally connected manufacturing environment. The contribution gives an overview of future challenges and potentials for next generation geometry assurance and geometrical variations management in the context of industry 4.0. Particularly, the focus is set on potentials and risks of increasingly available manufacturing data and the use of digital twins in geometrical variations management.
Keywords: Industry 4.0; Digital Twin; Geometry Assurance

Gesputterte MoS2-Gleitschichten für wechselnde Umgebungsbedingungen - Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro; Schneider, Thomas; Gradt, Thomas (Tagungsband zur 10. VDI-Fachtagung Gleit- und Wälzlagerungen 2015: Gestaltung, Berechnung, Einsatz (VDI-Berichte 2202), 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.gesput

Gezielte Anpassung lokaler Reibungszustände unter Einsatz wolframmodifizierter amorpher Kohlenstoffschichten (a-C:H:W) - Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro (56. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Band I, 2015)
Im Rahmen der Herstellung funktionsintegrierter Blechbauteile mithilfe von Umformoperationen der Blechmassivumformung stellen lokal angepasste Reibungszustände eine Möglichkeit zur besseren Ausformung kompliziert geformter Bauteilgeometrien dar. Vor diesem Hintergrund finden unterschiedliche tribologische Beschichtungen in der Umformtechnik nicht nur zum Schutz hoch beanspruchter Werkzeugoberflächen, sondern vielmehr auch zur Anpassung der Reibungszustände Verwendung. Als globale Oberflächenmodifikation auf das Werkzeug aufgebracht, ist eine lokale Anpassung der Reibungszustände mithilfe von Beschichtungen jedoch nur eingeschränkt möglich. Im Rahmen dieses Beitrags wurde daher der Einsatz verschiedener Maskierungsverfahren bei der Herstellung von in der Umformtechnik häufig eingesetzten Beschichtungen untersucht. Mithilfe starrer und flexibler Masken wurden in definierten Oberflächenbereichen beschichteter Probekörper unterschiedliche funktionale Schichtlagen eines Mehrlagenschichtsystems offengelegt. Als funktionale Schichtlagen wurden Schichtlagen aus CrN und einer Variante einer wolframmodifizierten amorphen Kohlenstoffschicht (a-C:H:W) (Typ A), sowie verschiedene a-C:H:W-Schichtvarianten mit unterschiedlichen Reibungszahlen (Typ B) gewählt. Die durch die Maskierung entstehenden Schichtkantenbereiche zeigten Einflüsse der Maskierungsverfahren sowie der eingesetzten Masken. Darüber hinaus konnten in Stift-Scheibe-Versuchen unterschiedliche Reibungsniveaus in den Verläufen der Reibungszahlen lediglich bei Proben des Schichtsystems Typ A infolge verschiedener Tribomechanismen der funktionalen Schichtlagen identifiziert werden.
Keywords: Lokal angepasste Reibungszustände; diamantähnlicher amorpher Kohlenstoff; Stift-Scheibe-Versuch; Maskierungsverfahren

Gezielte Anpassung lokaler Reibungszustände unter Einsatz wolframmodifizierter amorpher Kohlenstoffschichten - Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2016)
Bei der Herstellung funktionsintegrierter Blechbauteile mithilfe von Umformoperationen der Blechmassivumformung stellen lokal angepasste Reibungszustände eine Möglichkeit zur besseren Ausformung kompliziert geformter Bauteilgeometrien dar. Im Rahmen dieser Untersuchungen wird daher der Einsatz verschiedener Maskierungsverfahren bei der Herstellung typischer Werkzeugbeschichtungen betrachtet, um auf diese Weise tribologisch wirksame Oberflächenbereiche lokal voneinander abzugrenzen. Mithilfe starrer und flexibler Masken werden in definierten Oberflächenbereichen beschichteter Probekörper unterschiedliche funktionale Schichtlagen eines Mehrlagenschichtsystems offengelegt. Hierbei kommen funktionale Schichtlagen aus Chromnitrid (CrN) und verschiedenen Varianten wolframmodifizierter amorpher Kohlenstoffschichten (a‑C:H:W) mit unterschiedlichen Reibungszahlen zum Einsatz. Dabei zeigen die durch die Maskierung entstehenden Schichtkantenbereiche Einflüsse der Maskierungsverfahren sowie der eingesetzten Masken. Für maskiert beschichtete Probekörper können in Stift-Scheibe-Versuchen unterschiedliche Reibungszustände identifiziert werden.
Keywords: Lokal angepasste Reibungszustände; amorphe Kohlenstoffschichten; a-C:H:W; Blechmassivumformung; Stift-Scheibe-Versuch; Maskierungsverfahren

Graphenbasierte Toleranzbetrachtung in der frühen Entwurfsphase des Produktentwicklungsprozesses - Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 3. Summer School - September 2017, 2017)

GreenBearings 2 - Vermeidung konventioneller Schmierstoffe in Wälzlagerungen durch tribologische Schichten und Erhöhung der Gebrauchsdauer trockenlaufender Wälzlager - Kröner, Julia; Tremmel, Stephan; Kursawe, Serge; Musayev, Yashar; Wartzack, Sandro (2016)

GreenBearings – Friction Behaviour of DLC-Coated Dry Running Deep Groove Ball Bearings - Kröner, Julia; Tremmel, Stephan; Kursawe, Serge; Musayev, Yashar; Hosenfeldt, Tim; Wartzack, Sandro (Applied Mechanics and Materials, 2015)
Due to the use of rolling bearings instead of plain bearings friction and wear are drastically reduced in all kind of machines. However, despite the high technical standard of modern rolling bearings there is still a significant potential for optimization. Preliminary Studies show a reduction of the friction torque of up to 44 % compared to conventional rolling bearings because of the use of tribological coatings in certain applications. Based on the millionfold usage of rolling bearings in all industrial fields the reduced lost energy adds up to a remarkable potential for energy savings. If friction and wear are lowered sufficiently, the use of conventional lubricants based on mineral oil can be successively decreased or even completely avoided. In the latter case, the so-called dry running of the rolling bearing, the energy consumption of machines and systems can additionally be reduced significantly. For example, pumping stations or compressed air units, which would be necessary for transporting or spraying the lubricants, can then be saved. This paper presents first results of DLC-coated deep groove ball bearings, which are tested in a four-bearing-test-rig under purely radial load with respect to their friction and wear behaviou
Keywords: Dry Running; DLC Coating; Friction Reduction; Deep Groove Ball Bearings; Four-Bearing-Test-Rig; Energy Efficiency

GreenBearings: Minimierung und Vermeidung konventioneller Schmierstoffe in Wälzlagerungen durch tribologische Schichten - Kröner, Julia; Tremmel, Stephan; Kursawe, Serge; Musayev, Yashar; Hosenfeldt, Tim; Wartzack, Sandro (2015)

GreenBearings: Minimization and Avoidance of Conventional Lubricants in Rolling Bearings by Tribological Coatings - Kröner, Julia; Tremmel, Stephan; Kursawe, Serge; Musayev, Yashar; Hosenfeldt, Tim; Wartzack, Sandro (2014)

Halide-Free Synthesis and Tribological Performance of Oil-Miscible Ammonium and Phosphonium-Based Ionic Liquids - Westerholt, Antje; Weschta, Martin; Bösmann, Andreas; Tremmel, Stephan; Korth, Yasmin; Wolf, Marcus J.; Schlücker, Eberhard; Wehrum, Natalie; Lennert, Angela; Uerdingen, Marc; Holweger, Walter; Wartzack, Sandro; et al. (ACS Sustainable Chemistry & Engineering, 2015)
Due to their low vapor pressures, nonflammability, high thermal stabilities, and excellent tribological properties ionic liquids (ILs) are highly attractive lubricant base oils and additives. However, for practical applications of ILs in lubrication, two requirements are often limiting, the required miscibility with standard mineral oils (≥5 wt %) and the complete absence of corrosive halide ions in the ionic liquid. Moreover, the need for full compatibility with standard oil additives reduces the number of potential IL-based lubricant additives even further. In this contribution, an economic halide-free synthesis route to oil-miscible ionic liquids is presented, and very promising tribological properties of such ILs as base oil or additive are demonstrated. Therefore, sliding tests on bearing steel and XPS analysis of the formed surface films are shown. Corrosion test results of different bearing metals in contact with our halide-free ILs and (salt) water prove their applicability as real life lubricants. In the sustainable chemistry and engineering context, we present a halide-free design approach for ionic performance chemicals that may contribute to significant energy savings due to their enhanced lubrication properties.
Keywords: Halide-free; Ionic liquid; Lubrication; Noncorrosive; Oil-miscible; XPS

Handling Sampling-induced Uncertainties in Tolerance-Cost Optimization - Roth, Martin; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2022)
Tolerance allocation is an essential part of detail design and an important interface between design and production. Its goal is to select tolerance values as tight as necessary, to reliably assure total product quality considering variation, but at the same time as wide as possible, to allow for a cost-optimal fabrication of the individual parts. A consequent front-loading of manufacturing information is thus inevitable for a realistic consideration of the given manufacturing conditions enabling an early, optimal process planning. In this context, sampling-based tolerance-cost optimization has proven its suitability as an optimization-based tolerance allocation technique because it allows a realistic consideration of part tolerance distributions as well as the selection of cost-minimal combinations of manufacturing machines and processes for each part. However, the potential of machine selection in tolerance-cost optimization is currently limited since it does not support distributed manufacturing on several machines with individual batch sizes. Motivated to close this gap, this article presents a novel optimization-based method for concurrent tolerance and machine allocation. The consideration of mixed batches from individually allocated machines requires the extension of the mathematical definition of the tolerance-cost optimization problem and its solution by advanced optimization and sampling strategies. Its exemplary application to a use case shows its potentials and proves that balancing tolerance values, machines and batch sizes can help to further increase the potential of tolerance-cost optimization. Hence, the presented approach supports a further shift to a manufacturing-oriented interpretation of tolerance allocation in design.<br
Keywords: Tolerance-cost optimization; Tolerance allocation; Sampling-based tolerance analysis; Uncertainty; Metaheuristic optimization

Handlungsempfehlungen für die Entwicklung Digitaler Zwillinge in der Antriebstechnik - Wilking, Fabian; Fett, Michel; Götz, Stefan; Kirchner, Eckhard; Wartzack, Sandro (WiGeP News, 2023)

Handlungsempfehlungen für die Produktentwicklung nicht-idealer bewegter technischer Systeme - Walter, Michael; Wartzack, Sandro (Design for X. Beiträge zum 22. DfX-Symposium, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.handlu

Herausforderungen bei der Verknüpfung von Gestaltungs- und Toleranzdomäne zur Robustheitsbewertung von Produktkonzepten - Grauberger, Patric; Bremer, Frank; Matthiesen, Sven; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)

Holistisches Toleranzmanagement am Lehrstuhl für Konstruktionstechnik - Wartzack, Sandro; Götz, Stefan; Bode, Christoph; Franz, Michael; Freitag, Stephan; Horber, Dennis; Kramer, Vincent; Roth, Martin; Schächtl, Paul (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

How can Computer Aided Tolerancing support Closed Loop Tolerance Engineering? - Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2014)
Since geometric deviations decrease the quality and functional compliance of mechanical products, geometric variations management is an important issue for quality-aware companies in all phases of the product life-cycle. In this regard, the Closed Loop Tolerance Engineering Model highlights the main activities during geometric variations management and can be used to analyse the relations between the different involved actors. Though computer aided engineering tools are widely spread in product development practice with the aim to ease product design and analysis, these tools are mainly used separately and are not integrated in a coherent virtual geometric variations management process. Therefore, in this paper, the prerequisites for a holistic computer aided tolerancing process during product development based on the CLTE model are analysed. The main question answered is, which tolerance simulation tools are required and how should they be connected in order to enable a coherent and integrated computer-aided tolerancing process. Based thereon, important software tools are identified and drawbacks as well as main potentials for improvement are carved out. The novelty of the contribution can be found in the consideration of the geometric variations management process from a computer-aided tolerancing point of view and in addressing possible improvements for the development of software tools for a coherent and complete computer aided geometric variations management process.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.howcan
Keywords: Design for X; Robust Design; Product Quality

How Do Digital Engineering and Included AI Based Assistance Tools Change the Product Development Process and the Involved Engineers - Bickel, Sebastian; Sprügel, Tobias; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Current trends in product development are digital engineering, the increasing use of assistance tools based on artificial intelligence and in general shorter product lifecycles. These trends and new tools strongly rely on available data and will irreversibly change established product development processes. One example for such a new data driven tool is the plausibility check of linear finite element simulations with Convolutional Neural Networks (CNN). This tool is capable of determining whether new simulation results are plausible or non-plausible according to numeric input data. The digitalization and the increased use of data driven tools employing algorithms known from Artificial Intelligence also shifts the roles of many involved engineers. This paper describes and highlights this transition from current product development processes to a data driven / simulation driven product development process. Particularly, the shifts and changes of different roles and domains are illustrated and an example for changing roles in the design and simulation department is described. Furthermore, required adjustments in the design process are derived and compared to the current status.<br
Keywords: Digital Engineering; Machine learning; Data Driven Design; Organisation of product development; Artificial intelligence

How to consider Over-constrained Assemblies with Gaps in Tolerance-Cost Optimization? - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2020)
Exact Constraint Design is well established in design theory to ensure a robust and predictable system behavior. In practice, however, it is often inevitable to deviate from this basic concept so that parts are constrained several times for rigidity or resilience. In doing so, gaps between mating parts have to be added to ensure assemblability and functionality. Despite the essential impact of gaps on the total product functionality, occurring uncertainties in part positioning are mostly neglected in tolerance analysis. In the context of tolerance-cost optimization, they have not been studied in detail so far. To overcome this drawback, this article addresses the research question how over-constrained systems with gaps can be considered in tolerance-cost optimization ensuring the identification of both reliable and cost-optimal tolerance values. Based on an initial discussion on the complexity of tolerance analysis of over-constrained systems with gaps, their impact on the results and the efficiency of tolerance-cost optimization are discussed. With the aim to ensure a sufficient model accuracy in time-consuming applications, a framework for tolerance-cost optimization considering assemblies with multiple gap configurations based on surrogate models is presented and applied to a case study of industrial complexity. In doing so, a novel framework for a proper and efficient modelling of systems with gaps in tolerance-cost optimization supporting both researchers and practitioners is presente
Keywords: Tolerance-cost optimization; Least-cost tolerance allocation; Over-constrained assembly; Tolerance analysis

How to determine the influence of geometric deviations on elastic deformations and the structural performance? - Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2013)
Geometric deviations are observable on every manufactured part since manufacturing processes are inherently imprecise and measuring processes always involve uncertainties. These geometric deviations have influences on the function and the quality of the product. Therefore, allowable limits for these geometric deviations, depicted as geometric tolerances, have to be set. They define the allowable geometric deviations of a part for which the product function is guaranteed. In this context, elastic deformations and the structural performance are key aspects. However, the manufacturing-caused geometric deviations have an influence on the elastic deformations during use and the structural performance of the parts. In other words, there are interdependencies between geometric deviations and elastic deformations which affect the dimensional accuracy of a loaded part in an assembly. Therefore, this article proposes an approach for determining the impact of geometric deviations on the structural performance. This approach employs techniques such as sensitivity analysis, analysis of robustness and evaluation of reliability, and aims at providing information about the expectable elastic deformations and structural performance to geometric tolerancing. It can be concluded that geometric deviations can have a big impact on the structural performance, and thus, not only parametric deviations but also geometric deviations regarding the form and shape of a part itself should be taken into account within the structural performance analysis and tolerance simulations.
Keywords: Structural Performance; Computer-Aided Tolerancing; Geometric deviations

How to identify relevant product properties in the context of user-product interaction? - Schröppel, Tina; Miehling, Jörg; Wartzack, Sandro (Procedia CIRP, 2020)
A smooth and pleasurable user-product interaction (UPI) forms the basis of a successful user-centred design. An essential part of achieving this is the consideration of the ‘right’ product properties whose identification currently requires huge monetary, temporal and personnel effort. This contribution presents a more sufficient approach for identifying relevant product properties in the context of UPI as well as its first evaluation. To identify relevant properties, the UPI is first described by standard interactions which are secondly used as input for searching a knowledge base. For the initial evaluation an application example (percussing drill) is conducted. It shows that the outcome of the approach is indeed plausible but usability should be improved. Future research focuses on a deeper evaluation and improvements regarding accessibility and traceability.<br
Keywords: user-centred design; user-product interaction; product properties; relevance; evaluation; user-satisfaction; user experience; usability

Humidity resistant MoS2 coatings deposited by unbalanced magnetron sputtering - Vierneusel, Bernd; Schneider, Thomas; Tremmel, Stephan; Wartzack, Sandro; Gradt, Thomas (Surface & Coatings Technology, 2013)
MoS2 is a suitable solid lubricant for environments free of oxygen or water vapor (i.e. vacuum). Humid air degrades film properties due to oxidation accompanied by high wear and increasing coefficients of friction. The present study aims at the further development of sputtered pure MoS2 coatings, extending their applicability to varying environmental conditions by increasing the resistance against humidity. The systematic coating development process is supported by using an experimental Box-Behnken design with variations of the deposition parameters cathode voltage, target/substrate distance, temperature and argon gas pressure. In contrast to common one-factor-at-a-time (OFAT) studies, this approach enables a determination of interactions between deposition process parameters and tribological-mechanical MoS2 film properties. The tribological improvement focuses on a maximization of wear resistance in air and vacuum measured in ball-on-disk experiments. The evaluated mechanical properties are hardness, elastic modulus and residual stresses. These stresses were determined by the substrate curvature method. The study reveals that the residual stress state in the films and the hardness-to-modulus ratio are crucial for their tribological performance in humid air and vacuum environments. After a detailed determination of the relationships between deposition conditions and film properties, some selected microstructural analyses are presented which show that a substantially basal orientation of the lattice has positive effects on wear but also causes anisotropic film properties which result in fissile fracture of the coating if strong shock or point loads occur.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.humidi
Keywords: Humidity resistance; MoS2; Residual stress; Unbalanced magnetron sputtering

Hybrider Zusammenhalt - Witzgall, Christian; Wartzack, Sandro (CADFEM Journal, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.hybrid
Keywords: Klebeverbindung; Hybrider Leichtbau

Hybride Strukturen einfach und effizient berechnen - Witzgall, Christian; Kellermeyer, Markus; Wartzack, Sandro (Adhaesion Kleben und Dichten, 2015)

Hybrid Tolerance Representation of Systems in Motion - Heling, Björn; Hallmann, Martin; Wartzack, Sandro (27th CIRP Design Conference, 2017)
Dimensional management deals with the fact that the real geometry of every manufactured part deviates from its ideal shape. To evaluate the effects of these deviations tolerance analysis, which are often based on vectorial models, are carried out. Nevertheless the use of vectorial models has one major disadvantage – they cannot adequately represent form deviations. As a consequence new concepts of representations based on the GPS’ Skin Model have been established. Since the use of Skin Model Shapes (SMS) is time-consuming and does not always offer advantages over vectorial models, the Hybrid Tolerance Representation (HTR) which combines the advantages of vectorial and discretely represented tolerances is introduced in this paper. The HTR is based on a classification of the contact situation of the cinematic chain into lower and higher kinematic pairs. Based in this classification all higher kinematic pairs are going to be represented by SMS whereas lower pairs, are represented by vectors. Besides the simulation of the contact situation of all higher kinematic pairs the coupling of vectorial and discrete geometry representations is a challenge. The practical implementation of the presented method is shown on an X-ray shutter.
Keywords: Tolerance Analysis; Systems in motion; Hybrid Tolerance Representation

Identification of Property Change Impacts Based on Requirements-Oriented, Multi-Criteria Decision Models - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
As an outcome of the multi-criteria evaluation of different alternatives, product developers receive information on whether the evaluation alternatives meet the demanded property profile. If not, product characteristic and property changes are required, which can have desired and undesired effects. This contribution presents an MBSE-based approach, which extends the relational requirement model by value functions and product properties. Its novelty can be found in the integration of multi-criteria decision models, which are used to improve alternatives based on property change impact analyse
Keywords: decision making; requirements management; characteristics and properties; engineering change; model-based systems engineering (MBSE)

Impact of collaborative space on team work in engineering design education - Fechter, Marius; Kett, Susan; Luft, Thomas; Wartzack, Sandro (DS 84: Proceedings of the DESIGN 2016 14th International Design Conference, 2016)
This paper presents a study investigating the impact of space design on behaviour and creative outcome of team work in learning environments. A dedicated space was especially designed and equipped to facilitate creativity during collaboration. A student course in engineering design was held both in conventional classroom settings and in the newly designed space. The observations and measurements made relating to the two environments are shown and discussed in the paper. The results indicate noteworthy differences that can help to positively influence learning and creativity in future lectures.
Keywords: collaboration; space design; creativity; design education

Implementation And Interpretation Of A Scrap And Failure Oriented Multi-Objective Optimization Considering Operational Wear - Bode, Christoph; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2023)
The tolerancing of products for manufacturing is usually performed at the end of the design process and the responsibility of the designer. Although components are commonly tolerated to ensure functionality, time-based influences, like wear, that occur during operation, are often neglected. This could result in small amounts of scrap after production, but high quantities of failure during operation. To overcome this issue, this paper presents an approach to perform a multi-objective optimization considering tolerances based on a wear simulation. Thereby, mean shifts serve as optimization variables, while the aim of the optimization is to generate an optimal ratio of scrap to failure. In addition, the optimization results are interpreted and further options for the designer are presented. Moreover, the approach is exemplary applied to a use cas
Keywords: Tolerance representation and management; Optimisation; Simulation; Scrap and failure; Operational wear

Improved Sheet Bulk Metal Forming Processes by Local Adjustment of Tribological Properties - Hetzner, Harald; Koch, Johannes Peter Karl; Tremmel, Stephan; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing Science and Engineering, 2011)
This paper is focused on a combined deep drawing and extrusion process dedicated to the new process class of sheet bulk metal forming (SBMF). Exemplified by the forming of gearings, combined sheet and bulk forming operations are applied to sheet metal in order to form local functional features through an intended and controlled change of the sheet thickness. For investigations on the form filling and the identification of significant influencing factors on the material flow, a FE simulation model has been built. The FE model is validated by the results of manufacturing experiments using DC04 with a thickness of 2.0 mm as blank material. Due to the fact that the workpiece is in extensive contact to the tool surface and that the pressure reaches locally up to 2500 MPa, the tribological conditions are a determining factor of the process. Thus, their influence is discussed in detail in this paper. In the first instance, different frictional zones having a distinct effect on the resulting material flow are identified and their effect on improved form filling is demonstrated. Subsequently, a more comprehensive methodology is developed to define tribological zones of forming tools. For this, a system analysis of the digital mock-up of the forming process is performed. Besides friction, other relevant aspects of forming tool tribology like contact pressure, sliding velocity, and surface magnification are considered. The gathered information is employed to partition the tools into tribological zones. This is done by systematically intersecting and re-merging zones identified for each of the criterion. The so-called load-scanning test allows the investigation of the friction coefficient in dependence of the contact pressure and possible loading limits of tribological pairings. It provides an appropriate tribological model test to evaluate tribological measures like coatings, surface textures and lubricants with respect to their targeted application in particular zones. The obtained results can be employed in the layout of further forming processes to reach the desired process behavior. This can be, for example, an improved form filling, less abrasive wear and adhesive damage or lower forming forces, respectively tool load for an improved durability of the die.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KLMEFK.improv
Keywords: load-scanning test; material flow; sheet bulk metal forming; tribology

Improving Products by Combining Usability and Emotions - Buker, Tina; Miehling, Jörg; Wartzack, Sandro (Design Methodology for Future Products, 2022)
User-friendly and successful products usually emerge when pure functionality meets good usability as well as an emotional and aesthetic design. Modern theoretical approaches consider all of those three aspects as equally important. In practice, however, they are often still treated independently from one another. Thus, neither positive nor negative interdependencies can be taken into account. This chapter tries to close this gap by examining the relationship of usability and emotions and introducing the idea of dual user integration that aims for combining both aspects. A concrete approach to balance both aspects focusing on emotional impressions and physical capacities of the user is presented to make dual user integration applicable. This proactive approach is called Application for Computer-Aided Design of Emotional impressions and Physical capacities (ACADE+P) and consists of three main steps: (1) user/product description, (2) product evaluation and (3) data-based derivation of quantitative recommendations for design improvements. In addition to the general framework, the specific workflow of the method including an analysis and synthesis phase is explained in detail.<br

Influence of geometrical parameters of conic pin structures in thermoplastic composite/steel hybrid joining - Popp, Julian; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Drummer, Dietmar (Materials Research Proceedings, 2023)
Hybrid parts consisting of continuous fiber reinforced thermoplastic (CFRT) and steel components offer promising potential in lightweight construction. In this approach, the joining operation poses the major challenge due to different physical and chemical properties of both materials. This paper studies a joining method in which conical pin structures, protruding from the surface of the metal component, are inserted into the locally heated CFRT component to create a form fitting joint. The aim is to identify and quantify the influence of the parameters pin height and pin head diameter on the mechanical performance in single lab shear and cross head normal experiments. Based on the results it can be shown, that both an increased pin height and head diameter are beneficial under shear load in means of increased maximum load capacity while under normal load only an increased head diameter has clear benefits. Those effects are led back to the geometrical properties and the resulting stress distributions in the joining area.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Composite; Hybrid Manufacturing; Joining

Influence of layer thickness variations on the structural behaviour of optimised fibre reinforced plastic parts - Franz, Michael; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP Volume 85, 2019)
Fibre reinforced plastics (FRP) are considered as a modern high-tech material. The enormous lightweight potential, especially of carbon fibre reinforced plastics, accelerates its spreading in many industrial applications. However, as good as the lightweight potential of FRP is, as difficult is the optimal use in products because of its anisotropic material properties. Recently, methods considering the anisotropic material behavior during the product development process have been developed. These result in optimized nominal laminate layouts with defined laminate parameters like fibre orientation, ply thickness and ply stack-up order. Yet, during the manufacturing process, variations of these parameters, compared to the nominal design, occur. The variations result in asymmetric laminates, which causes couplings in the stiffness matrix and consequently undesired deformations. The effects of varying laminate design parameters have so far mainly been investigated with focus on manufacturing activities. However, to support the design engineer in considering the influence of varying laminate parameters on product behavior, this paper studies the effects on the structural behavior of optimized FRP-parts. The main novelty and contribution of the paper can be found in providing a new approach for the consideration of uncertainties in the ply thickness on FRP parts with optimized fibre layout. For this purpose, sensitivity analyses are performed with the aim of investigating the importance of the parameters on the structural behavior. With this knowledge, the product developer is able to distinguish between critical and non-critical laminate parameters and consider their variations in the product development process as early as possible.<br
Keywords: Fibre reinforced plastic; Product development; Structural analysis; Tolerancing

Influence of metal gear tooth geometry on load and wear within metal-polymer gear pairs - Rohrmoser, Andreas; Bode, Christoph; Schleich, Benjamin; Hagenah, Hinnerk; Wartzack, Sandro; Merklein, Marion (Applied Sciences, 2022)
Gear pairs made of the material pairing metal-polymer provide advantages, such as a reduced weight, beneficial damping properties and the possibility to be operated in dry running conditions. However, the service life of the pairing is limited due to wear. The properties of the metallic gearing have a significant influence on the wear behavior of the material pairing. From previous investigations, the influence of the surface topography and the flank hardness of the metal pinion is known. With regard to resource saving and efficient manufacturing of the metal pinion, cold forging offers benefits. Through cold forging, metallic gears for the material pairing can be produced ready-to-use in a process suitable for serial production. In order to enable manufacturing by extrusion, the application of gear radii is necessary. The gear radii significantly affect the extrusion process and the achievable gear properties. However, the influence of gear radii on wear within the metal-polymer material pairing has not yet been investigated. Within this contribution, the influence of the gear radii on the contact behavior as well as the resulting local load and wear of the tooth flank is determined. For this purpose, wear tests with aluminum (AlMgSi1) and steel (16MnCr5) gears with different gear radii within the pairing with polyamide (PA66) gears were performed. It has been shown that the local wear of the tooth flank can be attributed to the local load and that adjusted gear radii lead to a varying load and wear of the metal and polymer gears. Based on the findings, functional relationships regarding the choice of gear radii and the wear behavior are derived which can be applied in the design of cold forged gears.
Created from Fastlane, Scopus look-up
Keywords: Gear; Metal; Polymer; Tooth contact; Tooth geometry; Wear

Influence of microstructure shape, non-Newtonian lubricant and thermal effects on microstructured surfaces in rolling/sliding EHL contacts - Weschta, Martin; Tremmel, Stephan; Wartzack, Sandro (STLE 70th Annual Meeting & Exhibition, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.influe
Keywords: EHL Film Geometry; Surface Modification; Non-Newtonian Lubricant; Thermal Effects

Influence of the engine oil additives ZnDTP and MoDTP on the tribological behavior of hydrogenated and not hydrogenated amorphous carbon coatings - Schulz, Edgar; Wackerbauer, Veit; Musayev, Yashar; Tremmel, Stephan; Hosenfeldt, Tim; Wartzack, Sandro; Meerkamm, Harald (Proceedings of the 9th International Conference THE"A" coatings, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.influe

Inner marginal strength of CAD/CAM materials is not affected by machining protocol - Lubauer, Julia; Belli, Renan; Schünemann, Fernanda H.; Matta, Ragai; Wichmann, Manfred; Wartzack, Sandro; Völkl, Harald; Petschelt, Anselm; Lohbauer, Ulrich (Biomaterial Investigations in Dentistry, 2021)
Purpose Here we aimed to compare two machining strategies regarding the marginal strength of CAD/CAM materials using a hoop-strength test in model sphero-cylindrical dental crowns, coupled with finite element analysis. Materials and Methods Five CAD/CAM materials indicated for single posterior crowns were selected, including a lithium disilicate (IPS e.max® CAD), a lithium (di)silicate (Suprinity® PC), a polymer-infiltrated ceramic scaffold (Enamic®), and two indirect resin composites (Grandio® Blocs and Lava™ Ultimate). A sphero-cylindrical model crown was built on CAD Software onto a geometrical abutment and machined using a Cerec MC XL system according to the two available protocols: rough-fast and fine-slow. Specimens were fractured using a novel hoop-strength test and analyzed using the finite element method to obtain the inner marginal strength. Data were evaluated using Weibull statistics. Results Machining strategy did not affect the marginal strength of any restorative material tested here. Ceramic materials showed a higher density of chippings in the outer margin, but this did not reduce inner marginal strength. IPS e.max® CAD showed the statistically highest marginal strength, and Enamic® and Lava™ Ultimate were the lowest. Grandio® Blocs showed higher performance than Suprinity® PC. Conclusions The rough-fast machining strategy available in Cerec MC XL does not degrade the marginal strength of the evaluated CAD/CAD materials when compared to its fine-fast machining strategy. Depending on the material, resin composites have the potential to perform better than some glass-ceramic materials.
Keywords: CAD/CAM; strength; finite element

Integrated approach enabling robust and tolerance design in product concept development - Götz, Stefan; Kirchner, Philipp; Schleich, Benjamin; Wartzack, Sandro (Design Science, 2021)
Along with the ever-increasing customer demands, early consideration of variation in terms of robust design is important to avoid expensive iterations in the product development. However, existing methods are detached from the development process and can therefore only be applied at a late stage or only with comprehensive expert knowledge. Especially in the concept stage, where the geometry of a product is not yet defined and the optimisation potential is high, effective solution proposals for systematic consideration of variation are lacking. Therefore, this paper describes a new integrated approach facilitating robust and tolerance design in the concept stage. The novelty of the approach using ontologies and graph-based visualisation is the close linkage of product development and tolerance knowledge, which allows automation and helps to avoid time- and cost-intensive iteration loops. As a result, a robust and tolerance-compliant concept design, an initial qualitative tolerance specification and instructions for the further tolerancing process are already available at the end of the concept stage. The applicability and the benefits of the approach are illustrated by representative case studies and a user study allowing a critical comparison between the conventional, mostly subjective procedure and the presented approach.
Keywords: robust; designtolerance; designconcept; designgraphontology

Integrated Tolerance and Fixture Layout Design for Compliant Sheet Metal Assemblies - Rezaei Aderiani, Abolfazl; Hallmann, Martin; Wärmefjord, Kristina; Schleich, Benjamin; Söderberg, Rikard; Wartzack, Sandro (Applied Sciences, 2021)
Part tolerances and fixture layouts are two pivotal factors in the geometrical quality of a compliant assembly. The independent design and optimization of these factors for compliant assemblies have been thoroughly studied. However, this paper presents the dependency of these factors and, consequently, the demand for an integrated design of them. A method is developed in order to address this issue by utilizing compliant variation simulation tools and evolutionary optimization algorithms. Thereby, integrated and non-integrated optimization of the tolerances and fixture layouts are conducted for an industrial sample case. The objective of this optimization is defined as minimizing the production cost while fulfilling the geometrical requirements. The results evidence the superiority of the integrated approach to the non-integrated in terms of the production cost and geometrical quality of the assemblies.<br
Keywords: tolerance-cost optimization; fixture layout optimization; variation simulations; non-rigid assemblies

Integrating Machine Learning in Digital Twins by utilizing SysML System Models - Wilking, Fabian; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (17th Annual System of Systems Engineering Conference (SOSE), 2022)

Integrating optical 3D measurement techniques in pipe bending: a model-based approach minimising waste by deriving real functional design behaviour - Katona, Sebastian; Lušić, Mario; Koch, Michael; Wartzack, Sandro (Procedia CIRP, 2016)
Due to springback, deviations compared to the designed ideal modal occur during pipe bending processes. With quality control gauges no quantitative statements can be made regarding the process stability. The components are either good or bad and no production trends can be determined. This leads to high scrap rates and in addition, the real performance of the produced components may differ from the target behaviour of the initially designed CAD model. As addressed within this contribution, with integrating optical 3D measuring systems into the bending process, the actual state can be detected continuously. This enables to give feedback to the bending device for automatically readjust of bending parameters and thus prevent producing defective components. Moreover, the digitalisation of the actual contour allows a parametric correction of the designed CAD model, whereby the functional behaviour can be closer to reality within simulation models.
Keywords: In-process measurement; bending; springback; computer aided design (CAD); simulation; real function design behaviour

Integrating real geometry models into product simulations: an approach of knowledge-based process - Katona, Sebastian; Koch, Michael; Wartzack, Sandro (Proceedings of the 14th International Design Conference DESIGN 2016, 2016)
Simulation driven product development is state of the art to insure that the desired characteristics in use behave as requested without performing a time-consuming testing using expensive prototypes. To achieve the aim of realistic and confidential results within this product simulations, a tremendous afford (i.e. when taking different non-linearities into account, like material behavior, contact situations, large deflections etc.) is necessary. Conflicting to this, the ideal CAD-model is always used for the analysis, despite knowing the effect, that every manufactured component shows differences to its ideal geometry. Within this paper an approach of a knowledge-based process to integrate real geometry data into product simulations is given. Furthermore, different methods for preparation of the simulation models are represented.
Keywords: CAx; computer aided design (CAD); product development; structural analysis; knowledge based engineering

Integrating The Mechanical Domain Into Seed Approach - Dworschak, Fabian; Kügler, Patricia; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Data-driven technologies have found their way into all areas of engineering. In product development they can accelerate the customization to individualized requirements. Therefore, they need a database that exceeds common product data management systems. The creation of this database proves to be challenging because in addition to explicit standards and regulations the product design contains implicit knowledge of product developers. Hence, this paper presents an approach for the semantic integration of the engineering design (SeED). The goal is an automated design of an ontology, which represents the product design in detail. SeED fulfils two tasks. First, the ontology provides a machine-processable representation of the products design, which enables all kind of data-driven technologies. Among other representations, the ontology contains formal logics and semantics. Accordingly, it is a more comprehensible solution for product developers and knowledge engineers. Second, the detailed representation enables discovering of intrinsic knowledge, e.g. design patterns in product generations. Consequently, SeED is a novel approach for efficient semantic integration of the product d
Keywords: Semantic data processing; Engineering ontologies; Engineering data acquisition; Implicit knowledge integration

Integration of musculoskeletal and model order reduced FE simulation for passive ankle foot orthosis design - Scherb, David; Steck, Patrick; Wartzack, Sandro; Miehling, Jörg (27th Congress of the European Society of Biomechanics, 2022)
Introduction Motor disorders are caused by nerve damages that affect the control of muscles resulting in paralysis or paresis [1]. A common example is the paralysis / paresis of the lower leg muscles (e.g. caused by stroke) leading to a pathologic gait, so called foot drop syndrome [2]. For the treatment of this disease, technical devices are increasingly used, like ankle foot orthoses (AFOs). There are two distinguishing types of AFOs. The first ones are active AFOs that are mainly driven by motors and actuation algorithms. However, there are issues with weight and power supply. The second type of AFOs, passive AFOs, on the other side have a low weight, are mobile and do not use external power supply, but lack to provide sufficient support in the stance phase of gait. New, innovative designs, however, prove to be able to address this problem [3]. Therefore, we decided to develop a new passive AFO design that is provided with fiber-reinforced composites (FRCs) [4] for simultaneously maximizing the stiffness of the stressed areas during load phases while keeping the design lightweight. In order to ensure a suitable support of the human gait behaviour, a model order reduced finite element model (MOR-FEA) [5] of the AFO is linked with a musculoskeletal human model (MHM) [6] (Fig.1) Methods To realize the new AFO, in the first step the basics for the further work had to be compiled. Thus, the conceptual design of the orthosis was developed using methods of engineering design. The main requirement was that the AFO is capable of supplying different support in different directions during gait. Furthermore, this required support in the gait phases had to be determined. For this purpose, healthy subjects are recorded in gait laboratory and their muscle activation is computed with MHMs. Afterwards, the muscles are weakened according to the condition in foot drop and a supportive torque is applied to the models. The torque was applied as a reserve actuator and adjusted in such way that the muscle activation shall remain the same as in healthy condition. Results A conceptual design is found that is able to detect different phases during gait. By triggering a coupling, movement of the ankle can either be blocked or allowed. Additionally, a ratchet clutch mechanism is controlled to load and unload the force-generating structures, which results in the supportive torques during the gait. In the stance phase of gait the most support from the AFO is required. The required quantitative supportive torque depends on the condition of the patient. Patients with less remaining force capability in the lower leg muscles require more support than patients with more remaining force capability. The resulting muscle activations can be decreased by applying more support torque until the muscle activations of the non-paralyzed muscles are similar to the corresponding ones of healthy subjects for all diseased conditions. Discussion The design concept is characterized by the possibility to support all phases during gait. The main criteria for a successful application is the design of the force generating structure. Together with the simulated supportive torques, which mainly match the previous expectations, the development of the method to link the MOR-FEA with MHMs can be approached in the next step to reach an agreement between supplied force and gait behaviour of the patients. In order to enable an evaluation of the simulated results and generated method, a validation with a manufactured prototype of the AFO is planned. References 1. Younger, Lippincott Williams & Wilkins, 1999. 2. Stewart, Pract Neurol, 3: 158–169, 2008 3. Collins, et al., Nature, 7555: 212–215, 2015 4. Völkl, et al., Composite Structures: 359–367, 2018 5. Schilders, et al., Springer Berlin Heidelberg, 2008. 6. Miehling, et al., Biosystems & Biorobotics: 219–227, 2018. Acknowledgements This work was supported by the German Research Foundation (DFG) under Grant WA 2913/43-1 and MI 2608/2-1.<br

Integration of robust and tolerance design in early stages of the product development process - Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Research in Engineering Design, 2020)

Integration of structural optimization in the engineering design process - Stangl, Thomas; Pribek, Michael; Wartzack, Sandro (Proceedings of the DESIGN 2014 13th International Design Conference, 2014)
Structural optimization enables the product developer to compute a lightweight design proposal of a considered component during the design process. If topology optimization is integrated as early as possible in the product development process, the design engineer will act more and more frequently as a simulation engineer. To support the product developer to use topology optimization successfully in a methodical way, the paper focuses on the development of an extended design guideline during a design study.
Keywords: topology optimization; CAE; CAD; initial design proposal; design methodology

Integration of Universal Design principles into early phases of product design - a case study. - Kett, Susan; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED 15) Vol 9: User Centred Design - Design of Socio-Technical Systems, 2015)
Universal design (UD) is a strategy for designing societal and individual living environments. We outline how its generic guidelines need more concretization to be applicable to product development processes. Although the value of UD is widely known, its potentials are often still left unused. This paper’s contribution is to bring UD theory into product development practice by extending the processes that are currently used. Therefore, an appropriate application scenario in mobility and daily needs is proposed. It is proven that this area affects a wide range of users with different requirements and thus has great value for UD. By using the example of a shopping aid, several approaches in creativity can be used in the early phases of product design. Two exemplary methodologies are presented to demonstrate UD integration. We outline that research success can be met in multiple ways. Among other things, we show the integration of UD into systematic product design and the controllability of its value in an ex-ante and accompanying way. Within this process, the holistic view of users will be extendable, e.g. taking sociological, psychological or cultural aspects into account.
Keywords: Design for Life; Inclusive design; Design methodology; Early design phases

Integrierte Gestaltoptimierung für die Produktentwicklung - Wartzack, Sandro; Stangl, Thomas (Konstruktion, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.integr
Keywords: Formoptimierung; CAD; Rückführung

Integrierte Gestaltoptimierung für die Produktentwicklung - Wartzack, Sandro; Stangl, Thomas (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2013)
Keywords: Formoptimierung; CAD; Rückführung

Interactive immersive engineering system for distant collaboration - Fechter, Marius; Damgrave, Roy Gerhardus Johannes; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), 2015)
Complex products consisting of various components are designed in collaboration of multi-disciplinary engineering teams with different expertise. Expert groups involved in the development process are possibly based at geographically distributed locations. The purpose of this contribution therefore is the development of a framework, enhancing the quality of communication and facilitating the exchange of information and expertise in engineering projects over distance. This framework provides the capability to visualise a product model and the avatars of distant people in one shared immersive virtual environment. Furthermore the integration of product information exceeding the pure geometry and features for direct modification of the visualised product are achieved through the connection to CAD software. The intuitive interaction interface utilises hand gestures based on normal physical interaction with real objects. Being able to see both the 3D model and the other participant in one shared virtual environment creates a natural communication and interaction process, without being distracted by new communication or interaction methods forced by the technology.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.intera
Keywords: Collaborative Design; Communication; Human-Computer Interaction; Virtual Reality

Interdisziplinäres prozessorientiertes Toleranzmanagement – ein Konzept - Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (Summer School Toleranzmanagement Beiträge zur 3. Summer School, 2017)
Keywords: Toleranzmanagement; interdisziplinäres Toleranzmanagement

Introducing Emotional Bionics to Support Subjective Value Creation in Technical Products - Zöller, Susan; Schröppel, Tina; Wartzack, Sandro (International Journal of Affective Engineering, 2019)
So far, bionic design has mainly been applied to support functional solutions. In recent times, subjective aspects in product quality become increasingly important to users, too. Under the aspect of targeting a sustainable value creation for users, bionic design may also help to better address users’ subjective needs in product design. Therefore, a new methodology is presented. Its first step is the numeric and perception-related investigation of main geometrical criteria in object shape changes between technical solutions and their bionic models. The second step is the identification and utilization of impressions analogies between the two domains. Thus subjective similarities between the product and its bionic model are examined both in geometrical and in impressions respect in order to derive implications for the field of Emotional Bionics. The methodology is explained in detail by applying a pilot stud
Keywords: Emotional bionics; Subjective value creation; Design analytics

Introduction of a computational approach for the design of composite structures at the early embodiment design stage - Klein, Daniel; Malezki, Waldemar; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), Vol. 4: Design for X, 27.-30. Juli 2015, Mailand, 2015, S. 11-20., 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.introd

Intuitive virtual reality - CAD assembly system - Fechter, Marius; Miehling, Jörg; Stangl, Thomas; Wartzack, Sandro (Proceedings of the DESIGN 2014 13th International Design Conference, 2014)
The application of virtual reality during the design engineering process possesses the potential to experience and to interact with virtual products in a natural and intuitive manner. Some workflows in the field of computer-aided design, like assembling components, exhibit disadvantages that result from the two-dimensional vision and the limitations of common human-computer interaction. To support the design engineer, this paper focuses on developing a framework that harnesses the benefits of intuitive gesture based hand interaction and stereoscopic visualisation.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.intuit
Keywords: virtual reality; computer-aided design; gesture interaction

Investigation of surface skeletonization methods for reconstruction of topology optimized structures - Mayer, Johannes; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X, DFX 2020, 2020)
By showing where to place material in a specified design space, the continuous topology optimization is very useful in product development of structural loaded components. However the optimizations design proposal is far from being a parametric CAD-model. Instead it usually consists of a tesselated surface, that has to be re-engineered. As this is often done manually, it takes a lot of time and expert knowledge. Curve skeleton algorithms have proven their ability to support the restructuring of truss-like design proposals by providing references for construction elements. To investigate a similar design concept for general optimization results, showing truss-like structures as well as surface-like sections, the suitability of surface skeletons for topology reconstruction is examined.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Computational Geometry; Medial Axis Transform; Surface Skeleton; Topology Optimization

Investigation of the tribological behavior of amorphous carbon coatings for total knee replacement using a pin-on-disk tribometer - Rothammer, Benedict; Neusser, Kevin; Marian, Max; Bartz, Marcel; Wartzack, Sandro (7th World Tribology Congress, WTC 2022, 2022)
Great efforts are made to reduce the aseptic loosening of total knee replacements, for example by biotribologically effective surface modifications in order to decrease the wear of polymer inlays. This study focused on the characterization and tribological testing of wear-reducing amorphous carbon coatings with good adhesion to the medical technology materials Co28Cr6Mo and PE-UHMW. Thereby, the present study showed the applicability of coatings to the considered materials and the high potential for wear reductio
Keywords: Total knee replacement; Biotribology; PVD Coatings; Wear

Investigation of Tribological Systems for Dry Deep Drawing by Tailored Surfaces - Merklein, Marion; Schmidt, Michael; Tremmel, Stephan; Wartzack, Sandro; Andreas, Kolja; Häfner, Tom; Zhao, Rong; Steiner, Jennifer (Dry Metal Forming Open Access Journal, 2015)

Investigation on the tribological-mechanical behavior of amorphous carbon coatings by load-scanning tests - Hetzner, Harald; Schaufler, Jens; Pejic, Goran; Tremmel, Stephan; Durst, Karsten; Wartzack, Sandro (Materialwissenschaft und Werkstofftechnik, 2012)
Amorphous carbon coatings have a beneficial tribological behaviour since they provide low friction even under dry sliding conditions and at the same time they offer a good wear protection. Under high loads, the applicability of state-of-the-art amorphous carbon coatings is limited by mechanical failure. However, there is still little knowledge concerning the precise failure mechanisms under application-oriented conditions. In the present study, cylindrical specimens of a cold work tool steel were coated with two commercial amorphous carbon coating systems: a WCC coating with an a-C:H:W top layer and a DLC coating which architecture is based on that of the WCC coating, but contains an additional a-C:H top layer. The coated specimens were tested on a load-scanning test rig in dry sliding contact against uncoated specimens of the same steel substrate. In the tests, the specimens were loaded with a normal force in the range of 13 and 350 N, corresponding to a maximum contact pressure of 1 to 3 GPa. The number of load cycles was varied between 1 and 60. Firstly, the load-dependent friction behaviour was monitored. Secondly, the tests were stopped at different total cycle numbers allowing for an evaluation of the progress of wear and damage by scanning electron microscopy. For both coating systems, adhesive pick-up of counter body steel was observed prior to mechanical failure. Whilst the WCC coating system showed first indications of local failure after several load cycles and at contact pressures exceeding 2 GPa, the DLC coating system showed catastrophic failure on a global scale only after few load cycles and over the whole investigated load range.
EAM Import::2019-03-13

Investigations on the rolling bearing cage dynamics with regard to different operating conditions and cage properties - Schwarz, Sebastian; Grillenberger, Hannes; Tremmel, Stephan; Wartzack, Sandro (IOP Conference Series: Materials Science and Engineering, 2021)
The dynamic behavior of a cage can have a significant influence on the performance and the noise of a rolling bearing. In case of an unstable or high-frequency cage movement, vibrations are transmitted to the adjacent machine elements and the environment, which can influence the operating behavior of the whole system. In addition, a loud noise can often be perceived, which is referred to in the literature as cage rattling or squealing. In this paper, characteristics of different cage movements are investigated using multibody simulations and experimental investigations. For this purpose, essential properties of the fundamentally observable cage movement types "stable", "unstable" and "circling" are presented. The calculated cage dynamics and the type of cage motion are used to show dependencies between the operating conditions and the resulting cage movement such as inner ring rotational speed, bearing load or cage characteristics such as pocket clearance. Based on the simulations, interactions between the input parameters can also be determined. The results are used to identify operation-critical conditions and cage properties that lead to high cage dynamics. Finally, a comparison between the results of the multibody calculations and optical measurements is made. The optical measurements are performed using high-speed cameras. Reference markers fixed on the cage and digital image correlation allow the evaluation of the kinematics as well as the deformation of the cage. These results are compared with the simulation data to ensure a high quality of dynamics simulatio
Keywords: Rolling Bearing; Rolling Bearing Cage Dynamics; Dynamics

KI in der Entwicklung – Eine Revolution für die Konstruktion - Wartzack, Sandro (Konstruktion, 2023)
CRIS-Team Scopus Importer:2023-08-04

Klassifikation und Handhabung von Unsicherheiten zur entwicklungsbegleitenden Erfassung des Produktreifegrades - Luft, Thomas; Wartzack, Sandro (Entwerfen Entwickeln Erleben 2014 – Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik, 2014)
1. Motivation und Zielsetzung Das heutige Unternehmensumfeld ist besonders gekennzeichnet durch eine hohe Komplexität und Dynamik, bedingt durch den zunehmenden technologischen Fortschritt, die gestiegenen und individuelleren Kundenanforderungen sowie die Vielzahl interner und externer Einflussfaktoren. Um trotz dieser Aspekte Wettbewerbsfähigkeit  zu gewährleisten, ist die rasche und gleichzeitig zuverlässige Entwicklung marktfähiger Produkte von herausragender Bedeutung. Um einen erfolgreichen Verlauf eines Entwicklungsprojektes sicher zu stellen, kommt neben der kontinuierlichen Verfolgung von vergangener Zeit und entstandenen Kosten auch der Produktreife eine Schlüsselrolle zu. Sie stellt die Ermittlung und den Abgleich der aktuellen mit der ursprünglich geplanten Produktreife zu einem bestimmten Zeitpunkt dar und dient als Grundlage für die Ergreifung entsprechender Maßnahmen zur Einhaltung der Ziele. Vor diesem Hintergrund und der Zielvorgabe, Produkte schnell, kostengünstig und ausgereift auf den Markt zu bringen, sieht sich die moderne Produktentwicklung mit einer Reihe von Unsicherheiten konfrontiert, die nicht nur das Entwicklungsprojekt an sich erschweren, sondern sich auch auf die Reifegradermittlung eines Produktes auswirken. Die Ermittlung der Produktreife erfordert die Verwendung von Informationen, deren Inhalt vor allem zu Beginn der Entwicklungstätigkeiten größtenteils auf Annahmen beruht und daher in hohem Maße unsicher ist. Der Grad an Unsicherheit wird noch verstärkt durch die Möglichkeit, dass bestimmte Daten und Fakten möglicherweise vollkommen unbekannt sind bzw. vernachlässigt werden. Wird diese Vielzahl an Unsicherheiten nicht rechtzeitig bei der Entwicklung eines Produktes berücksichtigt, hat dies unter Umständen weitreichende Konsequenzen für das Entwicklungsprojekt und das betroffene Unternehmen, da besonders die Entscheidungen in den frühen Phasen der Entwicklung einen großen Einfluss auf Kosten, Qualität und Produktfunktionalität haben. Die Zielsetzung des Beitrages ist daher zum einen die Erarbeitung eines Ansatzes zur Ermittlung und Handhabung von Unsicherheiten, die während des Entwicklungsprozesses auftreten können. Zum anderen ist es das Ziel, die klassifizierten Unsicherheiten bei der Reifegradbestimmung eines Produktes zu berücksichtigen und sie derartig (mathematisch) zu integrieren, dass trotz vorliegender Unsicherheiten eine möglichst zuverlässige Aussage zum Produktreifegrad getroffen werden kann.   2. Stand der Technik und Wissenschaft Im Grundlagenteil werden zunächst die für diesen Beitrag relevanten Methoden und Ansätze in der Produktentwicklung dargelegt. So werden die beiden Ansätze „Simultaneous Engineering“ und „Design for X“ vorgestellt, um schließlich auf das Konzept der integrierten Produktentwicklung einzugehen. Die Grundidee der integrierten Produktentwicklung ist eine gleichzeitige, eng miteinander verknüpfte Entwicklung des Produktes und der mit diesem in Verbindung stehenden Prozesse. Darüber hinaus werden unter Betrachtung des gesamten Produktlebenszyklus bereits frühzeitig alle relevanten internen und externen Einflüsse und Rahmenbedingungen in der Entwicklungsphase berücksichtigt. Anschließend wird neben der Definition des Begriffes „Unsicherheit“ und der Abgrenzung zu verwandten Begriffen wie „Risiko“ und „Ungewissheit“ erläutert, weshalb die Analyse von Unsicherheiten während des Produktentwicklungsprozesses eine hohe Relevanz besitzt und welchen Einfluss der Neuheitsgrad eines Produktes auf das Ausmaß der Unsicherheiten hat. Abschließend werden die in der Literatur für die Bestimmung des Entwicklungsfortschrittes existierenden Ansätze ausführlich betrachtet und deren Schwächen (z.B. keine Berücksichtigung von Unsicherheiten in der Berechnung des Produktreifegrades) aufgezeigt.   3. Betrachtung von Unsicherheiten in der Produktentwicklung Im Rahmen des Beitrages erfolgt eine Unterscheidung zwischen internen und externen Unsicherheiten, da zwischen beiden Typen ein großer Unterschied im Hinblick auf die Beeinflussbarkeit der auftretenden Unsicherheiten durch Unternehmen existiert. Anschließend erfolgen die Klassifizierung der Unsicherheiten bezüglich ihrer Quelle (z.B. produktinhärente Unsicherheiten, Unsicherheiten aus dem Produktlebenszyklus) und Art (z.B. Ungenauigkeit, Unzuverlässigkeit) sowie die Eingrenzung der Unsicherheiten hinsichtlich ihres zeitlichen Auftretens während des Entwicklungsprozesses. Darauf aufbauend wird eine Vorgehensweise entwickelt, die potenzielle Unsicherheiten in einem Entwicklungsprojekt identifiziert und priorisiert. Über die Bestimmung der Unsicherheitsgrade der als relevant eingestuften Unsicherheiten wird schließlich eine Matrix aufgestellt, mit deren Hilfe ein Überblick über die Unsicherheiten eines Entwicklungsprojektes gewonnen und das projektspezifische Unsicherheitsprofil gebildet werden kann. Dazu werden spezifische Unsicherheitsfunktionen verwendet, die eine grafische Abbildung des Zusammenhangs zwischen dem Kriterium einer Unsicherheitsart und dem Unsicherheitsgrad ermöglichen. Die sich daran anschließende Ableitung von Normstrategien für die Handhabung von Unsicherheiten dient der Behebung bzw. Minimierung der ermittelten Unsicherheiten und der mit ihnen verbundenen Risiken im Entwicklungsprozess.   4. Integration von Unsicherheiten in die Produktreifegradermittlung Nach der Betrachtung von Unsicherheiten in der Produktentwicklung wird zunächst das erstellte Modell zur Reifegradermittlung vorgestellt, um anschließend die Vorgehensweise zur Integration von Unsicherheiten in dieses Modell darzustellen. Da vorhandene Reifegradmodelle aus der Literatur nur unzureichend für die spätere Integration der Ergebnisse aus der Unsicherheitsanalyse geeignet sind, wird das neu entwickelte Modell zur Bestimmung des Produktreifegrades, das die vorhandenen Ansätze als Basis nutzt und diese kombiniert, ausführlich erläutert. Prinzipiell dient hierbei der nach VDI 2221 definierte Konstruktionsprozess als Grundlage zur Ermittlung des Produktreifegrades. Um diesen abzuschätzen bzw. zu bewerten, müssen die zum Ermittlungszeitpunkt tatsächlich erfüllten Ist-Vorgaben an das Produkt mit den festgelegten Sollvorgaben verglichen werden. Neben der Erläuterung des Aufbaus und der einzelnen Bestandteile des Reifegradmodells wird zusätzlich eine beispielhafte Berechnung des Gesamtreifegrades eines Produktes, der sich aus dem Planungs- und Konzeptionsreifegrad, dem Konstruktionsreifegrad und dem Dokumentationsreifegrad zusammensetzt, durchgeführt. Auf Basis dieses Modells wird schließlich ein Schema entwickelt, das die zuvor ermittelten Unsicherheiten in das Reifegradmodell integriert. Hierfür sind zunächst die entsprechenden Faktoren im Modell zu identifizieren, die durch die Unsicherheiten potenziell beeinflusst werden. Über die Einführung verschiedener Unsicherheitsvariablen werden schließlich die Unsicherheitsgrade der verschiedenen Unsicherheiten aggregiert und dadurch der Ist-Wert des Reifegrades verringert. Anschließend wird darauf eingegangen, dass der berechnete Reifegrad unter Unsicherheit als Minimum anzusehen ist. Dieses Ergebnis dient als Ausgangsbasis zur Berechnung des Erwartungswertes des Reifegrades unter Zuhilfenahme von Erkenntnissen aus der Wahrscheinlichkeitstheorie. Zur besseren Nachvollziehbarkeit wird der vorgestellte Ansatz durch Integration von Unsicherheiten in das zuvor verwendete Beispiel zur Reifegradermittlung nochmals nachgerechnet und dadurch anschaulich dargestellt.   5. Zusammenfassung und Nutzen Mit den beiden vorliegenden Ansätzen zur Klassifizierung von Unsicherheiten und zur Integration von Unsicherheiten in den Prozess der Reifegradermittlung wurde eine Basis geschaffen, die dazu beiträgt, die eingangs erwähnten Probleme und Schwierigkeiten in der heutigen Produktentwicklung greifbarer zu machen und letztendlich auch zu reduzieren. Neben der Sicherstellung einer entsprechenden Produktreife bei Entwicklungsende können durch die kontinuierliche Ermittlung des Reifegrades unter Berücksichtigung der Unsicherheiten frühzeitig Verzögerungen und Abweichungen im Projektverlauf identifiziert werden und entsprechende Maßnahmen zur Gegensteuerung ergriffen werden. Somit rechtfertigt sich auch der durch Realisation des Ansatzes entstehende Mehraufwand zur Erfassung und Auswertung bestimmter Informationen. Durch eine reifegradgesteuerte Produktentwicklung wird nicht nur ein stetiger Anstieg des Entwicklungsfortschritts gewährleistet, sondern auch die Gefahr von zeit- und kostenintensiven Iterationen im Konstruktionsprozess verringert. Der Produktreifegrad ist somit ein essenzieller Bestandteil einer Projektüberwachung im Bereich der Produktentwicklung.
Keywords: Produktreifegradmanagement; Unsicherheiten; Entwicklungscontrolling; Entscheidungsfindung

Knowledge and Data-Based Design and Dimensioning of Mechanical Joining Connections - Zirngibl, Christoph; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the ASME 2022 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, 2022)

Knowledge-based and calculation-supported concept validation in the early stages of product development using the example of the electric motor - Tüchsen, Johann; Richter, Michael; Heydenreich, Johannes; Koch, Matthias; Schleich, Benjamin; Wartzack, Sandro (NAFEMS 18 DACH Conference, 2018)
In order to prevent costs and unneeded effort in product development, design verifications in early development phases are used to identify non-suitable designs and errors. Therefore, this contribution proposes a concept for a completely automated design check based on simplified one-dimensional calculations including knowledge-based correction factors optimized for electric drives. Using knowledge-based systems (KBS) structure in combination with compiled template computer scripts, a very fast and multidisciplinary solution is given to evaluate the suitability of the created solution regarding the requirements. Furthermore, this concept is expandable for additional modules or motors and easy to maintain. <br
Keywords: Concept validation; knowledge-based systems; KBS; analytical models

Knowledge-based design of surface textures for TEHL contacts - Marian, Max; Tremmel, Stephan; Wartzack, Sandro (3rd Young Tribological Researcher Symposium, 2019)
Dwindling resources and stricter legal requirements call for efficient machine elements and engine components. Therefore, tribological contacts with low frictional losses are vital. This can be achieved, for example, by applying discrete micro-textures to the surfaces of contacting bodies in lubricated tribological systems. While this approach has already been intensively investigated for lower loaded conformal contacts under hydrodynamic lubrication, the application and design of surface textures for higher loaded, non-conformal contacts under thermo-elastohydrodynamic lubrication (TEHL) is much more controversially discussed and still under basic research. In this context, tribo-simulations offer the great potential to explore the underlying basic mechanisms in terms of friction and wear reduction and to facilitate design optimization in order to avoid time-consuming and costly trial-and-error experiments. The aim of this contribution was therefore to investigate the impact of different micro-texture’s characteristics on the tribological behavior using transient 3D TEHL simulations based upon a full-system approach. Meta-models of optimal prognosis (MOP) and evolutionary algorithms (EA) were utilized to predict optimized and robust texture designs with reasonable computational effor
Keywords: Micro-texturing; Elastohydrodynamic lubrication; Optimization; Texture design

Knowledge-driven Design for Additive Manufacturing: A Framework for Design Adaptation - Schächtl, Paul; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Due to the high freedom of design, additive manufacturing (AM) is increasingly substituting conventional manufacturing technology in several sectors. However, the knowledge and the awareness for the suitable design of additively manufactured components or assemblies ensuring manufacturability and fully realizing its potential is still lacking. In recent years, approaches and tools have emerged that allow the incorporation of existing knowledge of Design for Additive Manufacturing (DfAM) into the design process. Nevertheless, these applications mostly do not consider the formalisation of both restrictive and opportunistic DfAM guidelines for their integration in design tools. Therefore, the following article presents a framework for the knowledge-driven adaptation of existing designs in the context of DfAM within an expert system. The novelty of the presented approach lies in the interdisciplinarity between the formalization of design guidelines and their integration and consideration within computeraided design for the semi-automated adaptation of functional non-assembly mechanisms. The application of the presented framework to a case study manufactured via Fused Layer Modeling (FLM) illustrates the applicability and benefits.<br
Keywords: Additive Manufacturing; Knowledge-driven Design; Design for Additive Manufacturing (DfAM); Ontologies

Komplexitätsreduzierte integrative Struktursimulation kurzfaserverstärkter Kunststoffbauteile mit LS-Dyna - Gruber, Georg; Liebst, Fabian; Wartzack, Sandro (ANSYS Conference & 32th CADFEM Users' Meeting., 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.komple

Konzept einer CAE-Methode zur systematischen Auslegung beanspruchungsgerechter, kurzfaserverstärkter AM-Fachwerksknoten für hochoptimierte Fachwerke - Jäger, Michael; Völkl, Harald; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
Trusses represent an economical, rigid and effective lightweight construction method. However, the connecting parts (nodes) between the struts are a design challenge, especially in highly optimized trusses. Several struts with different geometries (diameter, cross-sections) must be connected at any spatial angle in one point in a manner that is suitable for the load. The use of fibre-reinforced materials for the struts is common practice, for the nodes, metals are usually used. However, these do not exploit the full lightweight construction potential of the truss. The proposed method allows the design of truss nodes using fibre-reinforced materials and additive manufacturing, while taking into account the geometric boundary conditions of the connection points for the strut
Keywords: Structural optimization; CFRP truss; lightweight design; short fibre reinforced plastics

Konzept eines erweiterten Produktbeschreibungsansatzes basierend auf dem Vergleich des Characteristics-Properties-Modelling und der matrixbasierten Produktbeschreibung - Crostack, Alexander; Luft, Thomas; Binz, Hansgeorg; Wartzack, Sandro; Roth, Daniel (Stuttgarter Symposium für Produktentwicklung (SSP), 2015)
Die Produktentwicklung ist geprägt von steigenden Anforderungen an Qualität, Kosten und Funktionalitäten technischer Produkte. Zur Unterstützung der Produktentwickler wurden verschiedene Ansätze zur Modellierung von Produkten und Prozessen entwickelt. Im Rahmen des Beitrags werden die beiden Ansätze, das Characteristic-Properties-Modelling (CPM) und die matrixbasierte Produktbeschreibung (MBPB), analysiert. Die Vorteile des CPM liegen in der Genauigkeit der Modellierung und die Vorteile der MBPB in der Unterstützung der Produktentwickler. Darauf aufbauend wird das Konzept eines weiterentwickelten Ansatzes, der er-weiterten matrixbasierten Produktbeschreibung (eMBPB), entwickelt. Die eMBPB kombiniert die MBPB von Produkten mit der grafischen Darstellung und der Genauigkeit des CPM. Zur Veranschaulichung werden beide Ansätze exemplarisch anhand eines vereinfachten Modells eines Fahrradrahmens angewendet. Der Beitrag endet mit einer kritischen Diskussion und zeigt weiteres Forschungspotenzial auf.
Keywords: Characteristics-Properties Modelling (CPM); Matrixbasierte Produktbeschreibung (MBPB); Konstruktionsmethodik; Produktmodellierung

Konzept für den MBSE-Einsatz zur automatisierten Individualisierung von komplexen Produkten - Dworschak, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (Beiträge zum 30. DfX-Symposium, 2019)
Due to increasing market transparency, companies are mainly focusing on development of customized products. In this course, a competitive advantage should be achieved through the automated adaptation of product characteristics. In order to achieve this, development engineers focus primarily on modifying existing designs and refrain from re-running the entire product development process (PDP). However, this approach is primarily limited to the CAD environment. Previous phases of the PDP are not integrated, leading to a lack of traceability and continuity. Media breaks and API conflicts arise which increase costs. In order to make use of this potential, this article shows a concept for integration of all phases of the RFLP approach into a tool for customization of adaptation construction
Keywords: Model Based Systems Engineering; RFLP; Design for X

Konzept für eine simulationsgetriebene-wissensbasierte Produktentwicklung im Umfeld mechatronischer Produkte - Breitsprecher, Thilo; Röhner, Sebastian; Wartzack, Sandro (Design for X. Beiträge zum 21. DfX-Symposium, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.konzep_3

Konzept für ein VR-System zur intuitiven Modellierung durch natürliche Interaktion - Fechter, Marius; Wartzack, Sandro (Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik, 2016)
Durch den Einsatz von virtueller Realität (VR) eröffnet sich die Möglichkeit zur Entwicklung intuitiver Interaktionsmethoden, die dem Produktentwickler erlauben, natürlich mit den virtuellen Modellen umzugehen. Dazu wird in diesem Beitrag ein System konzipiert, aufgebaut und angewendet mit dem sich Komponenten innerhalb eines CAD-Systems durch Abhängigkeiten zusammenfügen lassen. Dabei werden Verfahren zum markenlosen Finger-Tracking sowie eine aktuelle VR-Brille verwendet. In einer Fallstudie wird abschließend die Anwendbarkeit des Hard- und Softwaresystems demonstriert. Link zu einem Video zur Veröffentlichung: https://vimeo.com/159390784
Keywords: Virtual Reality; CAD; Natural User Interface

Konzept für ein wissensbasiertes FEA-Assistenzsystem zur Unterstützung konstruktionsbegleitender Simulationen - Kestel, Philipp; Wartzack, Sandro (Beiträge zum 26. DfX-Symposium, 2015)
Computer-based simulation techniques such as finite element analysis gain huge attention in engineering design practice. However, an efficient use of simulation requires an early application in the product development pro-cess. Furthermore, extensive specialist knowledge is a crucial prerequisite to perform reliable and meaningful simulations. Due to time constraints, design accompanying simulations are performed only rarely by experienced simula-tion engineers or, if they are performed by less experienced users, are not sufficiently accurate. Hence, this paper presents a concept for a knowledge-based FEA assistance system for designers to efficiently capture and provide necessary knowledge of simulation experts in early development phases.

Konzeption biomechanischer digitaler Senioren-Menschmodelle zur Anwendung in der altersgerechten Produktentwicklung - Miehling, Jörg; Geißler, Bastian; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung (SSP) 2013, 2013)
Aufgrund des demographischen Wandels wird die Entwicklung von Produkten, die auch von älteren Menschen nutzbar sind, immer wichtiger. Heutzutage sollen Produkte zunehmend nach dem Grundsatz der virtuellen Produktentwicklung, nämlich möglichst ohne physische Prototypen, entwickelt werden. Dieser Ansatz soll helfen die Kosten und den Zeitbedarf, die in der Entwicklung und Herstellung anfallen, zu reduzieren sowie die Qualität der Endprodukte zu erhöhen. In der menschzentrierten Produktentwicklung kommen dafür biomechanische digitale Menschmodelle zum Einsatz, welche jedoch meist nur einen Durchschnittsmenschen abbilden. Dieser Beitrag zeigt eine Methodik um die Parameter, die zur Anpassung der muskuloskeletalen Modelle an unterschiedliche Alters- und Leistungsklassen notwendig sind, abzuleiten, damit diese schließlich zur Entwicklung altersgerechter Produkte herangezogen werden können. Der Konzeptionsprozess umfasst die Modifikation von Anthropometrie, Muskelkräften, Beweglichkeit und Bewegungsgeschwindigkeit basierend auf Literaturwerten oder auch Messungen an realen Versuchspersonen.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.konzep
Keywords: Altersgerechte Produktentwicklung; Virtuelle Methoden; Digitale Menschmodelle; Biomechanik

Konzeption eines Assistenzsystems für die modulare und datengetriebene Entwicklung elektrischer Antriebe - Tüchsen, Johann; Koch, Matthias; Schleich, Benjamin; Wartzack, Sandro (VDI-Berichte 2333, 2018)
Die Automobilindustrie ist geprägt von immer kürzeren Entwicklungszeiten bei gleichzeitig steigenden Funktions- und Qualitätsansprüchen. Um diese Herausforderungen zu bewältigen ist es notwendig, die Effizienz der Entwicklungsabteilungen durch Automatisierung zu steigern. In dieser Arbeit wird daher die Konzeption eines Assistenzsystems für die modulare und datengetriebene Entwicklung elektrischer Antriebe basierend auf der Methodik des V-Modells und der wissensbasierten Produktentwicklung dargestellt. Für die digitale Transformation der Produktentwicklung werden auf Basis des Zielprozesses Arbeitsschritte in Module unterteilt, welche parallel mit definierten Schnittstellen bearbeitbar sind. Mithilfe des vorgestellten Konzepts können Anfragen von Kunden schneller und mit höherem Reifegrad beantwortet werden. Die intelligente Logik im Assistenzsystem verwaltet dabei die Entwicklungs- und Produktionsdaten und steuert jedes Modul an, sobald alle Daten in ausreichender Güte vorhanden sind. So werden die Kommunikationswege verkürzt und sämtliche entwicklungsrelevante Informationen können jederzeit abgerufen werden. Weiterhin erhält der Entwickler die Möglichkeit, verschiedene Motoren digital miteinander zu vergleichen, mit verschiedenen Optima zu gewichten und letztlich das finale Produkt auszuwählen. <br

Konzept zur Auslegung beschichteter Bauteile im Wälz-Gleit-Kontakt - Tremmel, Stephan; Wartzack, Sandro; Meerkamm, Harald (Tagungsband zur 51. Tribologie-Fachtagung der GfT: : Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendung, 2010)
Tribologische Schichten können als ein Konstruktionselement angesehen werden, welches es auszulegen gilt. In dem beschriebenen Auslegungskonzept wird der vorhandene, komplexe Beanspruchungszustand im Schicht-Substrat-Verbund auf der Grundlage von FE-Kontaktspannungssimulationen unter Zuhilfenahme der Vergleichsspannung nach von Mises ermittelt. Der damit einhergehende Informationsverlust über den Grad der Mehrachsigkeit des Spannungszustandes – welcher wiederum maßgeblichen Einfluss auf die Beanspruchbarkeit des Schicht-Substrat-Verbundes besitzt – wird kompensiert durch die Berücksichtigung des Mehrachsigkeitsquotienten nach Clausmeyer. Die Beanspruchbarkeit wird in relativ einfachen Schwingversuchen an ausgewählten Probekörpern unter definierten Beanspruchungszuständen ermittelt. Auf Grundlage dieser Versuche kann eine verallgemeinerbare Grenzspannungskurve für den Schicht-Substrat-Verbund in Abhängigkeit des Mehrachsigkeitsquotienten aufgestellt werden. Somit ist es möglich, für unterschiedliche Anwendungsfälle an beliebigen Punkten im Kontaktbereich „lokale Sicherheiten“ zu definieren und „kritische Orte“ zu erkennen. Diese „kritischen Orte“ müssen nicht unbedingt an der Stelle der größten Vergleichsspannung liegen. Tatsächlich stellt man auch in der Praxis fest, dass Schicht-Substrat-Verbünde im Wälz-Gleit-Kontakt nicht zwangsläufig am Ort der größten Vergleichsspannung versagen.
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.konzep
Keywords: Schichten; Auslegung; Kontaktspannungen; FE-Simulation; Vergleichsspannung; Mehrachsigkeitsquotient

Konzept zur automatischen Bauteilerkennung innerhalb der FE-Software-Umgebung mittels Künstlichen Neuronalen Netzen - Sprügel, Tobias; Wartzack, Sandro (Design for X. Beiträge zum 25. DfX-Symposium, 2014)
The Finite Element Method is a very powerful tool to enhance product quality and to reduce unnecessary and costly iterations during the product development process. However numerous errors can occur during the FE simulation. A promising way to realize precise and quick FE simulations is the comparison of the FE solution with analytical machine elements equations. This is only possible if the components in an assembly can be identified automatically. A promising way is to use the presented approach in this paper for part recognition with artificial neural networks and the use of detection surfaces.
Keywords: automatic part recognition; Artificial Neural Network; ANN; FEM; detection surface

Konzept zur Erkennung von Singularitäten in FE-Simulationen mittels Machine-Learning Algorithmen - Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (37. CADFEM ANSYS Simulation Conference (22719), 2019)

Konzept zur hochdynamischen Kraftregelung mit nachgiebigen Mechanismen - Mauser, Kristian; Wartzack, Sandro; Hasse, Alexander (Design for X - Beiträge zum 27. DfX-Symposium, 2016)
The traditional approach to robotics includes a stiff serial-kinematic structure. Although this solution is efficient for position control tasks, such a concept is problematic for force control. The performance of control strategies is limited amongst others by the proper inertia which sets strong boundaries to control. Here, we propose an attractive concept for the realization of force control by means of an elastic interface based on variable-stiffness compliant-mechanism. Interposition of our elastic interface between the robot free-end and end effector 'decouples' the entire robot inertia from the end effector. Furthermore, the proposed system provides a frictionless operation and offers adaptive compliance, which allows for a high range of bandwidth.
Keywords: Series elastic actuation; compliant mechanism; highly dynamic force control; variable stiffness actuator

Konzept zur Identifikation relevanter Produkteigenschaften zur Unterstützung einer positiven User Experience - Schröppel, Tina; Miehling, Jörg; Wartzack, Sandro (Entwerfen Entwickeln Erleben in Produktentwicklung und Design 2019, 2019)
Technische Raffinesse, eine hohe Funktionalität und eine gute Gebrauchstauglichkeit reichen längst nicht mehr für eine Differenzierung am Markt aus, denn sie werden oftmals vom Nutzer als gegeben vorausgesetzt. Um die Begeisterung zur Nutzung trotz gewandelter Ansprüche zu wecken, gewinnt zunehmend das positive Erleben von Technologie, also die positive User Experience, an Bedeutung. Hierbei spielt insbesondere die Interaktion mit dem Produkt eine maßgebende Rolle, denn diese muss frei von Störungen sein. Um das garantieren zu können, ist die Nutzer-Produkt-Interaktion (kurz NPI) bereits bei grundsätzlichen Gestaltungsüberlegungen einzubeziehen. Aufgrund zahlreicher Eigenschaften und Merkmale von Produkten ist dabei jedoch oftmals nicht klar, an welchen Stellschrauben über-haupt gedreht werden muss, um die NPI besser gestalten zu können. Um diesem Problem entgegen-zuwirken, stellt der vorliegende Beitrag ein erstes Konzept zur Identifikation relevanter Produkteigen-schaften basierend auf der NPI vor. Das konzeptionelle Vorgehen besteht aus mehreren Schritten. Als erstes muss der Produktentwickler diejenigen Bereiche des Produkts identifizieren, bei denen während der Nutzung eine physische oder nicht physische NPI zustande kommt. Diese einzelnen Bereiche werden anschließend präzisiert, indem diesen eine oder mehrere von maximal fünf möglichen Interaktionsarten zugeordnet wird – sie leiten sich aus den fünf menschlichen Sinnen ab. Jedem Bereich kann somit ein visueller, taktiler, geschmack-licher, hörender und/oder riechender Kontakt zugeordnet werden. Diese Interaktionsarten werden im nächsten Schritt noch einmal konkretisiert, indem der Produktentwickler ihnen vordefinierte Standar-dinteraktionen zuordnet. Für taktile Bereiche lassen sich z. B. Interaktionen wie das Greifen, Drücken oder Drehen auswählen. Vorteil dieser Standardinteraktionen ist es, dass selbst komplexe Vorgänge als Kombination mehrerer einfach zu handhabender Interaktionen dargestellt werden können. Sind die allgemeinen Interaktionsbereiche identifiziert, die Interaktionsarten zugeordnet und die Standar-dinteraktionen ausgewählt, kann nun die eigentliche Ableitung relevanter Produkteigenschaften erfol-gen. Dies erfolgt auf Grundlage einer hinterlegten Wissensbasis, in der den einzelnen Standardinter-aktionen (z. B. Greifen) allgemeingültige und produktunabhängige Eigenschaften zugeordnet sind. Die Abfrage findet mittels einer einfachen WENN/DANN-Logik statt, in der die zur jeweiligen Standardin-teraktion gehörenden Eigenschaften abgefragt werden. Die für die Wissensbasis nötigen Informatio-nen kommen aus Datenbanken, Normen, Richtlinien und Konstruktionskatalogen sowie allgemein aus Ansätzen der Ergonomie und Gestaltlehre. Für die Standardinteraktion „Greifen“ ist bspw. ein sicherer Halt nötig. Um diesen gewährleisten zu können, sind Eigenschaften wie die Oberflächenbeschaffenheit und die Form der Greiffläche wichtig. Diese werden dem Produktentwickler dementsprechend als re-levant ausgegeben. Durch die anfangs durchgeführte Einteilung des Produkts in Interaktionsbereiche wird dem Anwender nicht nur angezeigt, was allgemein relevant wäre, sondern auch an welchen Stel-len des Produkts diese Informationen Berücksichtigung finden sollten. Die Kombination und Zuord-nung produktspezifischer Merkmale zu den allgemein gehaltenen Eigenschaften sind durch den An-wender am Ende nach wie vor individuell vorzunehmen. Im Rahmen des vorliegenden Beitrags wird neben der Vorstellung eines ersten Entwurfs des Konzepts das Vorgehen anhand eines kurzen Fallbeispiels verdeutlicht. Zudem werden die Potenziale und Gren-zen des Ansatzes diskutiert. Parallel wird der weiterführende Forschungsbedarf herausgearbeitet. Zusammenfassend, soll das Konzept letztlich den Produktentwickler dafür sensibilisieren, welche Ei-genschaften an welcher Stelle für eine nutzerorientierte Gestaltung des Produkts besonders wichtig sind. Damit soll die Interaktion zwischen Mensch und Technik transparenter und störungsfreier ge-macht und so eine positivere und nutzungsfreundlichere Ausgestaltung des Produkts gefördert werden.<br
Keywords: nutzerzentrierte Produktentwicklung; Produkt-Nutzer-Interaktion; Wissensdatenbank

Konzept zur Umsetzung einer zentralen Wissensbasis für Simulationswissen in ANSYS Engineering Knowledge Manager - Kestel, Philipp; Sprügel, Tobias; Katona, Sebastian; Wartzack, Sandro (ANSYS Conference & 33th CADFEM Users' Meeting, 2015)
An efficient use of Finite Element Analyses requires an early application in the product development process. Furthermore, extensive specialist knowledge is a crucial prerequisite to perform reliable and meaningful simulations. However, due to the strongly expanding field of application, Finite Element Analyses are increasingly performed by less experienced simulation users. Against this background, the objective of the Bavarian Research Association FORPRO² is to enhance virtual product and process development through strategically planned and operationally supported simulations. For this purpose the required expert knowledge is compiled in a structured and suitable manner and provided targeted through a central knowledge base. ANSYS Engineering Knowledge Manager (EKM) offers high potential to handle and context-sensitively apply the wide range of necessary simulation knowledge in versatile fields of application. This knowledge ranges from modeling rules for recurring components in product and process simulations depending on the development stages and tasks through to analytical equations for checking the plausibility of simulation results. In this presentation a concept for the implementation of a context-sentive knowledge-base in EKM for simulation knowledge will be presented.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.konzep

Konzept zur Verbesserung des realitätsgetreuen, visuellen Erlebens in virtuellen Umgebungen durch Eye-Tracking - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Entwerfen Entwickeln Erleben in Produktentwicklung und Design 2019, 2019)
Ein positives Nutzungserlebnis (engl. User Experience) ist einer der Schlüsselaspekte erfolgreicher Produkte und damit auch die Grundlage für den wirtschaftlichen Erfolg des Unternehmens. Ergonomische Bedienbarkeit und ansprechende Gestaltung des Produkts haben hierauf einen starken Einfluss. Entwickler und Designer versuchen deshalb, dieses Erlebnis bereits in einer möglichst frühen Phase des Produktenwicklungsprozesses zu erfassen und zu bewerten. Ein in der Automobilbranche erfolgreich eingesetztes Werkzeug zur Bewertung des Nutzererlebnisses ist der Prototypenbau. Der Einsatz von Prototypen ist allerdings mit einem hohen zeitlichen und finanziellen Aufwand verbunden und erst in späteren Phasen des Produktentwicklungsprozesses möglich. Zu diesem Zeitpunkt können Produktänderungen einen hohen zeitlichen und finanziellen Mehraufwand bedeuten. Im Sinne des „Frontloadings“ ist es daher wünschenswert, für die Bewertung des Nutzererlebnisses früh zur Verfügung stehende, digitale Modelle zu nutzen. Damit können frühzeitig erste Erkenntnisse über das Nutzungserlebnis unterschiedlicher Konzepte in die Entwicklung des Produkts einfließen. Durch Einsatz von Methoden der Virtuellen Realität (VR) besteht die theoretische Möglichkeit, eine Bewertung des Produkts hinsichtlich Design und Ergonomie bereits in frühen Phasen des Produktentwicklungsprozesses durchzuführen. Jedoch besteht bei der visuellen Wahrnehmung von Größe, Distanz und Form in einem Head-Mounted Display (HMD), insbesondere im Nahbereich, eine signifikante Diskrepanz zwischen der virtuellen Darstellung eines Modells und dessen realen Aufbaus. Die Ursachen dieser Wahrnehmungsdiskrepanzen konnten in bisherigen empirischen Studien nicht exakt festgestellt werden. Im Allgemeinen werden diese mit fehlenden Tiefenhinweisen oder Abweichungen in zur Berechnung der visuellen Darstellung verwendeten Parametern, wie dem Sichtfeld oder dem Pupillenabstand, erklärt. Als Folge der vorhandenen Diskrepanz zwischen der gewünschten und der erzielten Darstellung, sind Ergebnisse aus virtuellen Studien, insbesondere für die Evaluierung ergonomischer Aspekte wie der Erreichbarkeit einzelner Bedienelemente, nur bedingt belastbar. Bisher verwenden die meisten HMDs eine vereinfachte Modellbildung zur Berechnung der visuellen Darstellung von Objekten. Es wird über die räumliche Lage des Kopfes auf die Positionen der Pupillen geschlossen, anstatt die exakten Pupillenpositionen heranzuziehen. Durch den Einsatz von Eye-Tracking innerhalb von HMD‘s eröffnet sich die Möglichkeit, die genaue Pupillenposition bei der Berechnung der visuellen Darstellung zu berücksichtigen. In diesem Beitrag wird ein Konzept vorgestellt, um das Potential des Eye-Trackings zur Erzeugung realitätsgetreuer, visueller Reize zu nutzen. Hierzu erfolgt die Betrachtung verschiedener Tiefenhinweise, die bei der Wahrnehmung im Nahbereich dominanten Einfluss besitzen und in bisherigen technischen Lösungen unzureichend angesprochen werden. Zusätzlich wird der Einfluss der Verzerrung der im HMD verbauten Linsen auf die Blickrichtungsabhängigkeit der Darstellung anhand eines Demonstrators zur Simulation von Linsenbrechung in HMDs aufgezeigt. Ausgehend von den beschriebenen Faktoren werden Lösungskonzepte präzisiert um die Einschränkungen zu überwinden. Der Beitrag endet mit einer Zusammenfassung sowie einem Ausblick auf nachfolgende Schritte zur Überwindung der Wahrnehmungsdiskrepanzen um ein realitätsgetreues, visuelles Nutzungserlebnis des Produkts zu ermögliche
Keywords: visuelle Wahrnehmung; Virtual Reality; Eye-Tracking; Head-Mounted-Display; User Experience

Konzept zur zielgerichteten, ontologiebasierten Wiederverwendung von Produktmodellen - Kestel, Philipp; Luft, Thomas; Schon, Claudia; Kügler, Patricia; Bayer, Thomas; Schleich, Benjamin; Staab, Steffen; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
The reuse of product and process models during the product development process leads to considerable savings of costs and time. Such models are available in digital form in data and knowledge bases. However, the successful reuse of these models also requires the removal of model elements that do not apply to the new product. These removal processes are not yet supported by procedure models or IT systems. Up to now, the direct deletion of model elements by product developers leads to inconsistent and fragmentary knowledge bases or retention of unnecessary data. Thus, the aim of this contribution is to facilitate the reuse of product and process models by adding methods for the efficient removal of obsolete model elements to the existing IT systems.
Keywords: Product Data Management; Knowledge-based Engineering; Ontology-based knowledge representation; Intentional Forgetting

Kraftflussgerechte Fused Layer Modeling-Strukturen mit kurzfaserverstärktem Filament - Völkl, Harald; Steck, Patrick; Franz, Michael; Wartzack, Sandro (Konstruktion, 2020)
Additive Fertigungsverfahren wie Fused Layer Modeling (FLM) bieten hohe Designfreiheiten, die sich durch Design for Additive Manufacturing (DfAM) nutzen lassen. Der vorliegende Beitrag schlägt ein vierschrittiges, systematisches Vorgehen zur Erzeugung und Simulation lastpfadgerechter FLM-Strukturen vor: 1. Eine Topologieoptimierung mit orthotropem Materialmodell erzeugt eine lastpfadoptimierte Struktur und Materialorientierungen. 2. Die gewonnenen Optimierungsergebnisse werden in Extrusionspfade für FLM-Drucker umgesetzt. 3. Druckerspezifische Building Source wird generiert. 4. Eine strukturmechanische FE-Simulation erlaubt die Ermittlung des ausgeschöpften Leichtbaupotential

Kraftflussgerechte Fused Layer Modeling-Strukturen mit kurzfaserverstärktem Filament - Völkl, Harald; Steck, Patrick; Franz, Michael; Wartzack, Sandro (Konstruktion, 2020)
Additive manufacturing processes such as Fused Layer Modeling (FLM) offer a high degree of design freedom exploited by Design for Additive Manufacturing (DfAM). The present paper proposes a systematic approach for design and simulation of load path optimised FLM structures, comprising four steps: 1. Topology optimisation with orthotro-pic material model generates a load-path-optimised structure and provides optimised material orientations. 2 . The obtained optimisation results are converted into extrusion paths for FLM printers. 3. Printer specific building source is generated. 4. A structural mechanics FE simulation allows to determine the lightweight potential exploited.
CRIS-Team Scopus Importer:2021-04-19

Kritische Würdigung eines Werkzeugs zur Messung von Nutzerexklusion im Produktdesign. - Kett, Susan; Ringler, Alexander; Kamin, Stefan; Lang, Frieder; Wartzack, Sandro (Design for X. Beiträge zum 26. DfX-Symposium., 2015)
Inclusive Design strategies are of growing interest to companies serving heterogeneous users, e.g. in the mobile phone market. Therefore, several tools to assess physical and cognitive exclusion exist. The authors outline that with the maturation of physical inclusion management, there is an upcoming deficit in non-physical inclusion such as social or psychological astigmatisa-tion. Therefore, a brief overview of user perception and the different ap-proaches of Inclusive Design are given to outline hitherto existing knowledge. Research needs are illustrated by using an inclusive design tool measuring exclusion through product usability. The author’s suggestions lead to an al-ternative approach including soft factors addressing non-stigmatic design. Concluding, the main findings during this study are presented.
Keywords: inclusive design; user characterization; user centered design

KTmfk gewinnt Ingenieure ohne Grenzen Challenge 2021 - Wartzack, Sandro; Bartz, Marcel; Miehling, Jörg; Rothammer, Benedict; Hufnagel, Thomas; Scherb, David; Wilking, Fabian; Wirsching, Sven (WiGeP News, 2021)

Least Cost Tolerance Allocation for Systems with time-variant Deviations - Walter, Michael; Sprügel, Tobias; Wartzack, Sandro (Procedia CIRP, 2015)
This paper presents a methodology for the least cost tolerance allocation of systems with time-variant deviations, such as deformation, thermal expansion, mobility of parts and wear. By means of the approach, the product developer can identify the system’s optimal tolerance design against the backdrop of the diverging requirements: wide tolerances to reduce costs vs. narrow tolerances to ensure functionality. Therefore, Particle Swarm Optimization – a global statistical optimization technique – is applied to the time-variant tolerance-optimization problem to determine the tolerance range as well as a certain mean shift for each non-ideal dimension. The practical use of the methodology is illustrated for a modified tolerance stack-up problem. We provide a comprehensive walkthrough of the methodology’s application to the stack-up problem. Therefore, the essential mathematical background, the required functional dependencies and the considered parameters are detailed in a step-by-step procedure. So, we aim to establish the application of the statistical tolerance-costoptimization in academia and industry and to motivate students and young graduates to apply this methodology by themselves.
Keywords: tolerance allocation; time-dependent mechanisms; deformation; thermal expansion; particle swarm optimization

Lebenszyklusorientierte Toleranzsimulation zur funktionalen und ästhetischen Produktabsicherung - Wartzack, Sandro; Meerkamm, Harald; Stockinger, Andreas; Stoll, Tobias; Stuppy, Julia; Voß, Ralf; Walter, Michael; et al. (Konstruktion, 2011)
Die Toleranzsimulation ist ein wichtiges Werkzeug in der Produktentwicklung zur frühzeitigen Bestimmung der Auswirkungen von Abweichungen, bevor diese an der realen Baugruppe auftreten. Die in diesem Beitrag vorgestellten Forschungsarbeiten beschränken sich dabei nicht auf die in der Toleranzsimulation typischerweise betrachtete Montage, sondern sie untersuchen den gesamten Produktlebenszyklus von der Produktentwicklung und der dort notwendigen Toleranzspezifikation über die Fertigung und die Montage bis zur Produktnutzung. Für all diese Phasen werden Methoden und Werkzeuge vorgestellt, die am Lehrstuhl für Konstruktionstechnik der Universität Erlangen-Nürnberg innerhalb der letzten fünf Jahre entwickelt wurden und das Toleranzmanagement während der Produktentwicklung unterstützen.
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KLMEFK.lebens

Linking a game-engine with CAD-software to create a flexible platform for researching extended reality interfaces for the industrial design process - Harlan, Jakob; Schleich, Benjamin; Wartzack, Sandro (31st Symposium Design for X (DFX2020), 2020)
Driven by the need to develop highly complex products in short development cycles, many companies are aiming at fully digitized design workflows and continuous data and information flow. XR-interfaces can extend current CAD-functionality to allow the usage of CAD-data in more stages of the product design process. In this paper, a platform linking a game-engine and CAD-software to efficiently explore XR-CAD Interfaces is presented. An architecture meeting the requirements of research environments is designed and implemented using the unreal engine and Siemens NX. The proposed system allows to efficiently explore interfaces for design sketch creation using different hardware setups.<br
Keywords: Virtual Reality; Extended Reality; Computer-Aided-Design; Natural-User-Interface

Lücken und Herausforderungen bei der praktischen Umsetzung des Model-Based Systems Engineering - Fresemann, Carina; Stark, Rainer; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2019)
Im Rahmen der Zusammenarbeit der Friedrich-Alexander-Universität Erlangen-Nürnberg und der Technischen Universität Berlin wurde eine interaktive Studie mit 20 Experten aus großen und kleinen Unternehmen aus dem deutschsprachigen Raum durchgeführt. Ein Ziel der Studie war die Feststellung von Lücken und Herausforderungen, welche die bereits seit einigen Jahren bestehenden wissenschaftlichen Erkenntnisse und damit verbundene neue digitale Fähigkeiten in der industriellen Praxis limi- tieren. Der vorliegende Artikel beschreibt sowohl das Vorgehen als auch die Erkenntnisse der Studie. Darüber hinaus leitet sich weiterer Handlungsbedarf a

"MAGMAKegel": Simulation abweichungsbehafteter Kegelrollenlager - Aschenbrenner, Alexander; Schleich, Benjamin; Tremmel, Stephan; Wartzack, Sandro; Stahl, Thomas (Konstruktion, 2019)
Kegelrollenlager eignen sich hervorragend für tragfähige und führungsgenaue Lagerungen. Wie jedes reale Bauteil unterliegen jedoch auch Kegelrollenlagerkomponenten Maß-, Form- und Lageabweichungen. Diese Abweichungen haben Einfluss auf das Betriebsverhalten von Kegelrollenlagern. In einer Kooperation mit Schaeffler Technologies AG & Co. KG hat der Lehrstuhl für Konstruktionstechnik der Friedrich-Alexander-Universität Erlangen-Nürnberg das Softwarewerkzeug MAGMAKegel entwickelt, mit welchem sich Toleranzanalysen durchführen lassen, um ebendiese Auswirkungen geometrischer Abweichungen auf Kegelrollenlager zu quantifizieren. Im vorliegenden Beitrag wird das Softwarewerkzeug genauer beschriebe

Making a difference: Integrating physiological and psychological needs in user description - Schröppel, Tina; Wartzack, Sandro (Proceedings of NordDesign 2018, Linköping, Sweden, 14th - 17th August 2018, 2018)
Products particularly designed to support physically impaired people often contain for example big buttons in order to remain easy to use and handy for users suffering from diseases like rheumatism, multiple sclerosis or others. There is for example a reported prevalence of more than 31 million people with rheumatoid arthritis in Europe. This condition most commonly affects the joints of the hands. However, the sales volume of specially designed products does not reflect this number of affected people. This discrepancy can result from the design of these products. First of all, they often look very unattractive. In addition, the design itself strongly implies the context of physically impaired people. This fact can lead to negative user stigmatization, which usually makes the user feel uncomfortable. Thus, it seems that subjective quality aspects are from rising importance when it comes to product usage. However, there is a gap between the consideration of physiological and psychological user demands that needs to be filled. In consequence, this gap is to be closed and both demands are to be taken into account equally. Therefore, better products can be designed for individual people. Especially physically impaired persons, which have a high demand of subjective quality, will benefit from those products. Literature already includes various methods for psychological and physiological user description. Physiologically there are norms, standards or medical tests for instance. On a psychological perspective, several methods like affective priming or the use of semantic differentials allow a better understanding of the user’s attitude. Therefore the question arises, whether there are existing methods suitable to consider physiological and psychological needs in combination. This paper examines, whether there are qualified approaches that can be used to efficiently identify and compare psychological and physiological user needs. Therefore, it also interprets the compatibility between both types of user needs. Thus, this paper provides a solid base for developing a novel and integrated user-centered design approach that efficiently combines physiological and psychological user needs to improve the development of future products.<br
Keywords: subjective user needs; physiological user needs; user stigmatization; integrated user centered design

Markerlose Bewegungsaufzeichnung und Bewertungsmethoden für die menschzentrierte Produktentwicklung - Miehling, Jörg; Wartzack, Sandro (Beiträge zum 23. DfX-Symposium, 2012)
Human-centered design focuses on the adaption of product specifications to meet the users’ requirements. In order to save development time, reduce product development costs as well as to enhance the products’ quality, the virtual product development paradigm emphasizes the use of virtual prototypes instead of physical ones. To meet these objectives a digital human modeling system is needed which is capable of representing the human-product interaction. Up to now it is not possible to accurately model real motion sequences at the computer, thus motion capturing is needed. The presented contribution illustrates a system for the markerless tracking of human body movements, which can be used to drive biomechanical simulations, using Microsoft’s Kinect sensor. Additionally further directions for the development of a system to evaluate and visualize the resultant simulation data are outlined.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.marker
Keywords: Motion Capturing; Menschmodell; Microsoft Kinect; menschzentrierte Produktentwicklung; virtuelle Produktentwicklung

Maschinelles Lernen zur schallemissionsarmen Entwicklung von Maschinen - Wartzack, Sandro; Küstner, Christof (WiGeP News, 2017)
Maschinelles Lernen zur schallemissionsarmen Entwicklung von Maschinen: Prognose und Reduzierung der Schallemission am Beispiel von Windenergieanlagen

Maßgeschneidertes Model-based Systems Engineering - Wartzack, Sandro (Konstruktion, 2020)
CRIS-Team Scopus Importer:2021-04-19

Materialparameter-Optimierung für die Crashberechnung in frühen Entwicklungsphasen - Gruber, Georg; Klein, Daniel; Wartzack, Sandro (NAFEMS 2012, 2012)
Durch die drastische Verknappung der Ressourcen und den damit verbundenen Restriktionen seitens der Politik (z.B. CO2-Grenzwerte) hat speziell in der Automobilindustrie der Leichtbau enorm an Bedeutung gewonnen. Um Leichtbaustrategien möglichst effizient durchführen zu können, ist es erforderlich bereits die frühe Entwicklungsphase auszunutzen, da hier noch die maximale Designfreiheit zur Berücksichtigung aller Anforderungen vorliegt. Doch gerade die Berechnung und Auslegung in Bezug auf die Crashsicherheit von Bauteilen aus Verbundwerkstoffen ist aufgrund der komplexen mechanischen Eigenschaften und der fertigungsbedingten Anisotropie bisher noch sehr schwierig und zeitaufwändig. Deshalb wurde ein Ansatz entwickelt, der es ermöglicht eine Materialbeschreibung für die Crashberechnung in frühen Entwicklungsphasen zu generieren. Über die Funktion *PART_COMPOSITE werden in LS-DYNA® für ein einziges Bauteil mehrere bereits bestehende Materialmodelle definiert. Dabei enthalten diese Materialmodelle Parameter, die so aufeinander abgestimmt werden können, dass sich in Summe das gewünschte Materialverhalten einstellen lässt. Die Identifikation dieser Materialparameter wird durch den Einsatz der Optimierungssoftware LS-OPT® entscheidend beschleunigt. Damit kann innerhalb kürzester Zeit ein valides Materialmodell erzeugt werden, das den Anforderungen in frühen Entwicklungsphasen gerecht wird. Das genaue Vorgehen wird im Folgenden am Beispiel eines kurzfaserverstärkten Thermoplasten gezeigt.
Keywords: Simlution; Crash; Composites

MBSE along the Value Chain – An Approach for the Compensation of additional Effort - Wilking, Fabian; Schleich, Benjamin; Wartzack, Sandro (2020 IEEE 15th International Conference of System of Systems Engineering (SoSE), 2020)
Keywords: Proceedings of the 2020 IEEE 15th International Conference of System of Systems Engineering (SoSE)

Medium-Level Architectures for Digital Twins: Bridging Conceptual Reference Architectures to Practical Implementation in Cloud, Edge and Cloud–Edge Deployments - Fett, Michel; Kraft, Marcel; Wilking, Fabian; Götz, Stefan; Wartzack, Sandro; Kirchner, Eckhard (Electronics, 2024)
The integration of Digital Twins (DTs) is becoming increasingly important in various industries. This entails the need for a comprehensive and practical IT infrastructure framework. This paper presents a modifiable medium-level architecture that serves as a link between established reference architectures such as RAMI 4.0 and the pragmatic implementation of Digital Twins. The functionalities of an IT infrastructure are considered, and functional hardware and software components for fulfilling these are described. The proposed architecture is suitable for various deployment scenarios, including local, cloud and hybrid cloud–edge configurations. In order to improve the applicability of the medium-level architecture, a step-by-step procedure is also proposed, which helps to transfer the overarching requirements for a Digital Twin into a suitable IT infrastructure. Finally, the results are demonstrated by an exemplary application to a two-stage industrial gearbox.<br
Keywords: digital twin; cyber–physical system; RAMI 4.0; architecture; IT infrastructure

Meta-model based generation of solution spaces in sheet-bulk metal forming - Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2020)
Sheet-bulk metal forming (SBMF) is an emerging manufacturing technology that offers vast potential for lightweight design and functional integration. However, product designers often lack information about the required manufacturing parameters for their specific design. This problem is currently tackled by a knowledge acquisition process from manufacturing experts in combination with meta-modelling techniques. These meta-models predict resulting manufacturing parameters for given part design properties. When employing this design-for-manufacturing approach, it is key for product designers to evaluate many design alternatives that are all manufacturable with given forming machines. This is currently done by a genetic algorithm-based optimization of the meta-models with regard to manufacturing features. This papers proposes a novel approach for generating many design alternatives based on the meta-models and gathering them in a solution space. In doing so it is possible to review all manufacturable sheet-bulk metal forming part variants and let the product designers decide which part design fits best. The approach is applied to a locking teeth part, which highlights the usability of the new method.<br
Keywords: Meta-Modelling; Multi-objective optimization; Knowledge acquisition; Genetic algorithms

Metaproperty-guided Deletion from the Instance-Level of a Knowledge Base - Schon, Claudia; Staab, Steffen; Kügler, Patricia; Kestel, Philipp; Schleich, Benjamin; Wartzack, Sandro (Knowledge Engineering and Knowledge Management - 21st International Conference, 2018)
The ontology modeling practice of engineering metaproperties of concepts is a well-known technique. Some metaproperties of concepts describe the dynamics of concept instances, i.e. how instances can and cannot be altered. We investigate how deletions in an ontology-based knowledge base interact with the metaproperties rigidity and dependence. A particularly useful effect are delete cascades. We evaluate how rigidity and dependence may guide delete cascades in an engineering application. A case study in the area of product development shows that beyond explicitly defined deletions, our approach achieves further automated and desirable deletions of facts with high precision and good recall.

Methoden der Entscheidungsfindung - Luft, Thomas; Le Cardinal, Julie; Wartzack, Sandro (Handbuch Produktentwicklung, 2016)
Die steigende Dynamik und Komplexität im Unternehmensumfeld sowie ein zunehmender Kostendruck erschweren die Entscheidungsfindung im Rahmen der Produktentwicklung. Um seine Wettbewerbsfähigkeit zu sichern, muss jedes Industrieunternehmen wesentliche Ziele erfüllen: Diese sind vor allem die Erfüllung der Kundenzufriedenheit, der Profitabilität des Unternehmens und die Motivation seiner Mitarbeiter. Jedes Unternehmen versucht diese Ziele durch das Treffen entsprechender Entscheidungen zu erreichen. Der Begriff der „Entscheidung“ beziehungsweise „Entscheidungsfindung“ ist weder in der Literatur noch in der Praxis einheitlich definiert. Daher wird dieser Begriff in der Wissenscha" unterschiedlich interpretiert: Die Entscheidungstheorie wird von einigen Autoren im Allgemeinen als empirische und logische Analyse rationalen Entscheidungsverhaltens definiert (Bamberg et al. 2012). Dagegen beschreiben andere Autoren die Entscheidungstheorie als wissenscha"liche Disziplin, die die Aufgabe hat, „Erkenntnisse über das menschliche Entscheidungsverhalten zu gewinnen und diese [. . .] für die Lösung konkreter Entscheidungsprobleme zur Verfügung zu stellen“ (Obermaier & Saliger 2013). Ratio nales Entscheiden besteht darin, „jene Lösungen zu bevorzugen, die ein möglichst hohes Ausmaß an Zielerfüllung erbringen“ (Haberfellner et al. 2012). Dabei entspricht eine Entscheidung im Allgemeinen der Auswahl zwischen Alternativen. Eine verantwortungsvolle und zielorientierte Auswahl impliziert in der Regel die Vorweg nahme des Ergebnisses der Entscheidung, das dieser Auswahl inhärent zugrunde liegt. Nachfolgend verstehen die Autoren unter der Entscheidung beziehungsweise der Entscheidungsfindung den gesamten Ent schei dungs(findungs)prozess (d. h. das gesamte Vorgehen, um zu einer Entscheidung zu gelangen). Aufgrund der uneinheitlichen Interpretation des Entscheidungsbegriffs werden in diesem Buchkapitel nach Darstellung der Spezifika der Entscheidungsfindung in der Produktentwicklung zunächst die theoretischen Grund la gen zu Komplexität, Unsicherheit, Arten, Ebenen, Formen sowie Kriterien einer guten Entscheidungsfindung kurz beschrieben (Kapitel IV-7.2). Darauf aufbauend wird der Entscheidungsfindungsprozess erläutert ( Kapitel IV-7.3). Dieser besteht aus allgemeinen, generischen Schritten, die grundsätzlich für jede Art von Entscheidungsfindung geeignet sind. Abschließend werden einige ausgewählte Methoden zur multikriteriellen Bewertung als Kernelemente des Entscheidungsfindungsprozesses an einem Praxisbeispiel aufgezeigt (Kapitel IV-7.4). Dadurch sollen Entscheider einen Überblick über die Komplexität und Unsicherheit von Entscheidungssituationen, über den Prozess der Entscheidungsfindung sowie über ausgewählte Bewertungsmethoden bekommen.
Keywords: Grundlagen der Entscheidungsfindung; Spezifika der Entscheidungsfindung in der Entwicklung; Komplexität der Entscheidungsfindung; Unsicherheit bei der Entscheidungsfindung; Arten der Entscheidungsfindung; Ebenen der Entscheidungsfindung; Formen der Entscheidungsfindung; Kriterien für eine gute Entscheidung; Prozess der Entscheidungsfindung; Entscheidungsfindungsprozess; Kompetenzmodell; SACADO-Methodik; Bewertungsverfahren als Kernelemente des Entscheidungsprozesses; Einfache Bewertungsmethoden – Die Punktbewertung; Aufwändige Bewertungsmethoden – Die Nutzwertanalyse; Komplexe Bewertungsmethoden – der Analytische Hierarchieprozess; Komplexe Bewertungsmethoden – Überblick über die ELECTRE- und PROMETHEE-Methode

Methoden der Produktentwicklung - ein subjektiver Vergleich von Theorie und Praxis - Wartzack, Sandro (18. Symposium Design for X, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.FT.FT-KLMEFK.method

Methodengestützte Referenzvorgehensweise für neue Umformverfahren - Weckenmann, Albert; Reithmeier, Eduard; Merklein, Marion; Behrens, B.-A.; Wartzack, Sandro; Kästner, M.; Akkasoglu, Gökhan; Ohrt, Christoph; Schneider, Thomas; Salfeld, V.; et al. (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2012)
LFT Import::2019-07-29 (1782)

Methoden zur Reduzierung und Berücksichtigung der Unsicherheiten von dimensionellen Messgrößen in der Toleranzanalyse - Müller, Andreas; Heling, Björn; Schleich, Benjamin; Oberleiter, Thomas; Willner, Kai; Wartzack, Sandro; Hausotte, Tino (Industriekolloquium der Forschergruppe FOR 2271, 2019)

Methode zur Berücksichtigung geometrischer Abweichungen bei der Auslegung von Zylinderrollenlagern - Atalay, Onur; Koch, Oliver; Kramer, Vincent; Bartz, Marcel; Götz, Stefan; Wartzack, Sandro; Schleich, Benjamin (15. VDI-Fachtagung Gleit- und Wälzlagerungen 2023: Gestaltung – Berechnung – Einsatz, 2023)
Wälzlager sind im Maschinenbau aufgrund ihrer präzisen und reibungsarmen Führung rotierender Bauelemente bei gleichzeitig geringen Kosten von großer Bedeutung. In der Regel werden bei der Auslegung von Wälzlagerungen ideale Geometrien von Lagern und Anschlusskonstruktion zugrunde gelegt. Reale Bauteile weichen jedoch unvermeidlich von ihrer nominalen Gestalt ab, was zu Veränderungen der lagerinternen Kontakt- und Lastverhältnisse führt und somit das Betriebsverhalten des Lagers z. B. hinsichtlich Lebensdauer, Reibmoment und Schwingungsverhalten beeinträchtigen kann. Durch Berücksichtigung dieser Effekte bei der Auslegung von Wälzlagerungen können potentielle Probleme im Betrieb bereits in der Entwicklungsphase erkannt und entsprechende Abhilfemaßnahmen, z. B. durch Anpassung der Bauteiltoleranzen ergriffen werden. Somit kann eine Verbesserung der Produktqualität erzielt werden. Dieser Beitrag stellt daher eine Methode zur Integration von abweichungsbehafteten Bauteilgeometrien bei der Berechnung von Zylinderrollenlagerungen vor.
Keywords: Wälzlager; Toleranzanalyse; Maschinenelemente

Methode zur Einbindung von heuristischem Wissen in die erweiterte matrixbasierte Produktbeschreibung - Tüchsen, Johann; Obendorfer, Moritz; Luft, Thomas; Schleich, Benjamin; Wartzack, Sandro (Tagungsband 16. Gemeinsames Kolloquium Konstruktionstechnik, 2018)
Im Zuge der zunehmenden Vernetzung und Digitalisierung ist es zur Beherrschung von Komplexität im Rahmen der interdisziplinären und kollaborativen Produktentwicklung notwendig, die vielfältigen Abhängigkeiten zwischen Produktmerkmalen und Produkteigenschaften detailliert zu beschreiben. Die vorliegende Arbeit stellt daher eine Methode zur Implementierung und Verarbeitung von heuristischem, impliziten Wissen in der erweiterten matrixbasierten Produktentwicklung (eMBPB) und im Characteristic-Property-Model (CPM) vor. Mittels dieser Methode können das Erfahrungswissen der Entwickler in den holistischen Produktbeschreibungsansatz integriert und Produkte unter der Berücksichtigung von Prozesseinflüssen und Unsicherheiten beschrieben werden. Diese vorgeschlagene Methode wird zudem anhand des industriellen Beispiels der Welle-Rotorblechpaket-Verbindung veranschaulicht und evaluiert.
Keywords: Wissensmanagement; heuristisches Wissen; eMBPB; CPM

Methode zur Parameteroptimierung komplexer Mechanismen hinsichtlich kinematischer Anfor-derungen - Heling, Björn; Wartzack, Sandro (Design for X - Beiträge zum 27. DfX-Symposium, 2016)
Shorter product life cycles along with continuously changing requirements lead to a demand for more efficient product development processes. Result-ing from these upcoming challenges the guiding principle „Right-First-Time“ focuses on a reduction of iteration loops during product development. As a consequence product developers need suitable tools and methods to allow a more efficient product development process. In this contribution a new meth-od, which is based on methods for the conceptions of systems in motion and Robust-Design principles, is presented. This novel combination takes kinemat-ic requirements as well as possible geometric uncertainties into account. As a consequence the designed system not only fulfills the kinematic requirements but is also insensitive to deviations from the ideal state.
Keywords: Robust Design; Parameter Optimization; Taguchi Method; kinematic design

Method for calculating the contact between roller end face and ring rib of roller bearinx in multi-body simulations - Wirsching, Sven; Bohnert, Christof; Tremmel, Stephan; Wartzack, Sandro (STLE 2019 - 74th Annual Meeting and Exhibition of the Society of Tribologists and Lubrication Engineers, 2019)
To summarize, the PinP method provides similarly accurate results as the theory of HERTZ. But in addition, the PinP method can be used to describe more complex geometries that generate curved ellipses as contact zones. These can only be described simplified by HERTZ. Instead, contact situations of two contact zones are not. This is the great benefit of the PinP method, which is suitable for such constellations. In a further step, this has to be examined more precisely. For this purpose, higher numerical methods, such as FEM, will be used for a comparison.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Computation: Dynamic Modelling; Contacts: Contact Mechanics; Rolling Bearings: Tapered Roller Bearings

Method for Using IMU-Based Experimental Motion Data in BVH Format for Musculoskeletal Simulations via OpenSim - Wechsler, Iris; Wolf, Alexander; Fleischmann, Sophie; Waibel, Julian; Molz, Carla; Scherb, David; Shanbhag, Julian; Franz, Michael; Wartzack, Sandro; Miehling, Jörg (Sensors, 2023)
Biomechanical simulation allows for in silico estimations of biomechanical parameters such as muscle, joint and ligament forces. Experimental kinematic measurements are a prerequisite for musculoskeletal simulations using the inverse kinematics approach. Marker-based optical motion capture systems are frequently used to collect this motion data. As an alternative, IMU-based motion capture systems can be used. These systems allow flexible motion collection without nearly any restriction regarding the environment. However, one limitation with these systems is that there is no universal way to transfer IMU data from arbitrary full-body IMU measurement systems into musculoskeletal simulation software such as OpenSim. Thus, the objective of this study was to enable the transfer of collected motion data, stored as a BVH file, to OpenSim 4.4 to visualize and analyse the motion using musculoskeletal models. By using the concept of virtual markers, the motion saved in the BVH file is transferred to a musculoskeletal model. An experimental study with three participants was conducted to verify our method’s performance. Results show that the present method is capable of (1) transferring body dimensions saved in the BVH file to a generic musculoskeletal model and (2) correctly transferring the motion data saved in the BVH file to a musculoskeletal model in OpenSim 4.4.<br
Keywords: biomechanics; musculoskeletal modelling and simulation; inertial sensors; motion tracking; data transfer

Methodical approach for the design and dimensioning of mechanical clinched assemblies - Zirngibl, Christoph; Martin, Sven; Steinfelder, Christian; Schleich, Benjamin; Tröster, Thomas; Brosius, Alexander; Wartzack, Sandro (Materials Research Proceedings, 2023)

Methodik zur Validierung, Verifikation und Auswahl mathematischer Metamodelle im Rahmen der virtuellen Produktentwicklung - Sprügel, Tobias; Wartzack, Sandro (Design for X. Beiträge zum 26. DfX-Symposium, 2015)
Product developers need to describe relations between input and output parameters mathematically. This central problem varies in many ways and starts from the description of measurement data and ends with the integration of results from numerical simulations in downstream simulations of similar problems. Therefor meta-models or surrogate models are used. In this publication a methodology for validation, verification and selection of proper meta-models within the virtual product development is presented.
Keywords: meta-model; surrogate model; goodness-of-fit parameter; plausibility-check

Methodische Bestimmung der Systemgrenzen im Produktentwicklungsprozeß - Wartzack, Sandro (Beiträge zum 18. Symposium Design for X, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.FT.FT-KLMEFK.method

Methodische Entwicklung mobilitätserhaltender Produkte am Beispiel einer Aufstehhilfe - Krüger, Daniel; Wartzack, Sandro; Eilmus, Sandra; Krause, Dieter; Walter, Johanna; Paetzold, Kristin (Stuttgarter Symposium für Produktentwicklung (SSP) 2013, 2013)
In unserer  Gesellschaft ist  eine Veränderung  der  Altersstruktur zu beobachten, ältere  Menschen machen einen  immer  größeren  Anteil  an  der Gesamtbevölkerung aus. Der Erhaltung von Mobilität im Alter wird zukünftig eine steigende Bedeutung zukommen. Mobilität umfasst neben der Bewegungsfähigkeit auch  den  Transport  von  Dingen,  die  Interaktion  mit  der  Umwelt  oder  die Kommunikation  mit Anderen,  was eine Teilhabe am  gesellschaftlichen  Leben erst ermöglicht. Mobilität ist damit ein wichtiger Aspekt für Lebensqualität. Infolge von Krankheit  oder  natürlichem Altern  sind Menschen von  Einschränkungen der motorischen Fähigkeiten betroffen, die ein selbstständiges  Aufstehen aus sitzender Haltung schwierig machen. Der Beitrag zeigt am Beispiel einer Aufstehhilfe, die der Entlastung des Bewegungsapparates dient und damit teilweise die Wiederherstellung der  Mobilität  ermöglicht, welche  besonderen  Herausforderungen  bei  der Entwicklung von Produkten zu diesem Zweck bestehen. Es wird ein methodisches Framework vorgeschlagen, das Aspekte der Anforderungserhebung, die Simulation von  Mensch-Maschine  Interaktionen  mittels digitaler  Menschmodelle  sowie Methoden des Variantenmanagements bereitstellt.
Keywords: seniorengerechte Produktentwicklung; Nutzerbeschreibung; Variantengestaltung; biomechanische Simulation

Methodische Unterstützungsansätze für die Entwicklung additiv gefertigter Bauteile - Gruber, Georg; Kestel, Philipp; Staab, Andreas; Wartzack, Sandro (Tagungsband der Rapid.Tech 2013 - Fachmesse und Anwendertagung für Rapid-Technologie, 2013)
Additive manufacturing allows the creation of individual and highly innovative products. The reasons are high geometric flexibility and the possibility of including additional functions in the part offered by additive manufacturing. However, the complex dependencies between manufacturing parameters and the resulting properties of the parts are challenging. The present paper deals with special characteristics of additive manufacturing regarding form design and feasibility. Furthermore, state of the art approaches assisting the product developer at the design process are discussed. The focus of the paper is the introduction of a concept of a new process chain, supporting the design process of additive manufactured parts. The goal of the new development process is generating the part’s geometry directly by numerical optimization methods like topology optimization. This is possible thanks to the geometric flexibility offered by additive manufacturing. To be able to consider graded and anisotropic material properties within the optimized structure, an enhanced form of optimization – the so called free material optimization – shall be deployed. The distinct setup of the process chain as well as customized pre and post processing tools allow for a development process which does not involve CAD tools being used to generate the parts geometry.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.method

Methodology for plausibility checking of structural mechanics simulations using Deep Learning on existing simulation data - Sprügel, Tobias; Rothfelder, Richard; Bickel, Sebastian; Grauf, Andreas; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Proceedings of NordDesign 2018, 2018)
In modern product development, the use of sophisticated simulation tools for assessing the effects of design changes on the intended product behavior is essential. However, setting up valid simulations requires expert knowledge, acquired skills, and sufficient expertise. Design engineers, who perform finite element analysis (FEA) infrequently, must be assisted and their FEA results need to be checked for plausibility. An automatic plausibility check for finite element (FE) simulations in linear structural mechanics can identify non-plausible simulations and warn the user to interpret the results cautiously or ask for expert help. In this context, currently available tools can only compare very similar simulations. However, as the amount of available simulation data in the industry increases more and more, a data-driven simulation check is an obvious next step. Nevertheless, the question arises how simulation data of very different parts and simulations can be transferred to a single software tool, how this tool can learn the relevant rules behind plausible simulations, and how it can be applied to new simulations. In this context, it is especially important to train a metamodel that is able to generalize the rules so that it can later on be applied to unknown simulations. This paper presents an approach to transfer different FE meshes, corresponding FE results and boundary conditions to an individual matrix of fixed size for very different structural mechanic FE simulation. The novel approach uses spherical detector surfaces to project three-dimensional information on its surface. It allows generating the so-called “DNA of an FE simulation”; classification algorithms i.e. Support Vector Machines or Deep Learning Neural Networks such as Convolutional Neural Networks (CNN) can then classify this information. The whole methodology reduces the dimension of a 3D finite element simulation to a 2D matrix of numeric values. The matrix contains all the relevant information for the classification in “plausible” or “non-plausible”. An implausible simulation contains errors, which would be quickly identified by an experienced simulation engineer, whereas a plausible simulation does not contain such errors. As less experienced simulation users in design departments are not trained to find such errors in their simulation setup, they cannot detect them and take adequate countermeasures. In the paper, every single step of the novel methodology for plausibility checking of structural mechanics simulations will be illustrated and explained in detail for simplified parts and corresponding simulations.<br
Keywords: Plausibility Check; Convolutional Neural Network; Deep Learning; Data-driven approach; design automation; visualization

Methods for integrating postural control into biomechanical human simulations: a systematic review - Shanbhag, Julian; Wolf, Alexander; Wechsler, Iris; Fleischmann, Sophie; Winkler, Jürgen; Leyendecker, Sigrid; Eskofier, Björn; Koelewijn, Anne; Wartzack, Sandro; Miehling, Jörg (Journal of neuroEngineering and rehabilitation, 2023)
Understanding of the human body’s internal processes to maintain balance is fundamental to simulate postural control behaviour. The body uses multiple sensory systems’ information to obtain a reliable estimate about the current body state. This information is used to control the reactive behaviour to maintain balance. To predict a certain motion behaviour with knowledge of the muscle forces, forward dynamic simulations of biomechanical human models can be utilized. We aim to use predictive postural control simulations to give therapy recommendations to patients suffering from postural disorders in the future. It is important to know which types of modelling approaches already exist to apply such predictive forward dynamic simulations. Current literature provides different models that aim to simulate human postural control. We conducted a systematic literature research to identify the different approaches of postural control models. The different approaches are discussed regarding their applied biomechanical models, sensory representation, sensory integration, and control methods in standing and gait simulations. We searched on Scopus, Web of Science and PubMed using a search string, scanned 1253 records, and found 102 studies to be eligible for inclusion. The included studies use different ways for sensory representation and integration, although underlying neural processes still remain unclear. We found that for postural control optimal control methods like linear quadratic regulators and model predictive control methods are used less, when models’ level of details is increasing, and nonlinearities become more important. Considering musculoskeletal models, reflex-based and PD controllers are mainly applied and show promising results, as they aim to create human-like motion behaviour considering physiological processes.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Biomechanical human model; Biomechanics; Forward dynamics; Musculoskeletal model; Postural control; Simulation; Systematic review

Micro-scale deterministic asperity contact FEM simulation - Kolli, Vasu; Winkler, Andreas; Wartzack, Sandro; Marian, Max (Surface Topography: Metrology and Properties, 2022)
There are numerous stochastic approaches to indirectly couple solid asperity contact with the fluid hydrodynamics in the region of boundary or mixed lubrication. In contrast, deterministic approaches for calculating solid contact pressure curves offer advantages in terms of flexibility and accuracy. This contribution aims at providing a publicly available, automated method to derive solid asperity contact pressure curves for given surfaces, implemented in commercial software based upon Finite Element Method (FEM). Solid asperity pressure curves were calculated and compared to various established stochastic models for artificially generated surfaces and surfaces measured via laser scanning microscopy. Thereby, it was shown that the usage of artificially generated surfaces based on stochastic parameters only allowed an approximate representation of real measured surfaces as well as to lower calculated pressures, so that 3D measurement data is preferred to calculate the contact pressure. Moreover, the values of the FEM model were in a similar region but slightly below the stochastic models over a wide range of gap distances and the asperity pressure graphs were more curved/convex. At very small gap height values, the pressure in the FEM model reached values similar to the stochastic models. This was attributed to the fact that real surface topographies were considered, also allowing for peak-to-valley pairings instead of merely asperity-to-asperity contacts, as well as to the fact that the roughness and mean planes were re-calculated in each simulation step, while most stochastic approaches neglect the elastic deformation of asperities when determining the distances between the rough surfaces.
Keywords: multiscale modeling; finite element method; solid contact pressure; contact mechanics; tribology

Microstructured surfaces in highly loaded contacts – differences due to sliding effects - Weschta, Martin; Pausch, Michael; Tremmel, Stephan; Wartzack, Sandro (Proc. Society of Tribologists and Lubrication Engineers Annual Meeting and Exhibition 2014, 2014)
Keywords: EHL film geometry; Surface modification

Microstructured surfaces in highly loaded EHD-contacts - manufacturing and tribological performance - Schrader, Tobias; Weschta, Martin; Engel, Ulf; Tremmel, Stephan; Merklein, Marion; Wartzack, Sandro (Proc. 10th International Conference THE "A" Coatings in Manufacturing Engineering, 2013)
In low loaded sliding contacts, as journal bearings or piston contacts, defined microstructures on surfaces were identified for friction reduction purposes and are well established in industrial applications. It is stated that microstructures act as lubricant reservoirs and support lubricant film development. Within the scope of these investigations microstructures are specifically adapted for the tribological load collective of cam follower systems as a representative of highly loaded contacts. For those contacts, the effects of microstructures are still subject of investigations. In this paper a method for efficient microstructuring by micro laser ablation is described. The investigations focus on the determination of the geometric and mechanical properties of the microstructures as well as on the tribological behavior of the microstructured surfaces by two tribological tests.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.micros_0

Microstructured surfaces in highly loaded elastohydrodynamic (EHD)-contacts - manufacturing and tribological performance - Schrader, Tobias; Weschta, Martin; Engel, Ulf; Tremmel, Stephan; Merklein, Marion; Wartzack, Sandro (Materialwissenschaft und Werkstofftechnik, 2013)
In low loaded sliding contacts, as journal bearings or piston contacts, defined microstructures on surfaces were identified for friction reduction purposes and are well established in industrial applications. It is stated that microstructures act as lubricant reservoirs and support lubricant film development. Within the scope of these investigations microstructures are specifically adapted for the tribological load collective of cam follower systems as a representative of highly loaded contacts. For those contacts, the effects of microstructures are still subject of investigations. In this paper a method for efficient microstructuring by micro laser ablation is described. The investigations focus on the determination of the geometric and mechanical properties of the microstructures as well as on the tribological behavior of the microstructured surfaces by two tribological tests.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.micros_6
Keywords: EHD-Kontakt; Mikrolaserablation; Mikrostrukturen; Reibversuche; Tribologie

Microtextured surfaces in higher loaded rolling-sliding EHL line-contacts - Marian, Max; Tremmel, Stephan; Wartzack, Sandro (Tribology International, 2018)
Due to scarce resources coupled with increasing mobility requirements, resource-efficient machine and motor elements are vital. Therefore, surfaces in lubricated tribological contacts can be microtextured, enabling improved lubricating conditions and friction behavior. While this has already been shown for lower loaded contacts, the effects for higher loaded, application-oriented EHL contacts are topic of basic research. Therefore, geometrically defined microtextures are adapted to the tribological system of the tappet/camshaft contact in the valve train of combustion engines as a demonstrator. The tribological performance in respect to lubricating conditions, friction and wear behavior is analyzed on single cam/tappet component test-rigs. EHL simulation is used as ‘numerical zoom’ into a section of the contact area contributing to better understanding of effects and observed phenomen
Keywords: Surface texture; Friction; Wear; Elastohydrodynamic lubrication

Mikrostrukturierung von Tassenstößeln zur Reibungsreduzierung im Ventiltrieb – Herstellung, Simulation und tribologische Charakterisierung - Weschta, Martin; Schrader, Tobias; Tremmel, Stephan; Merklein, Marion; Wartzack, Sandro; Engel, Ulf (Tribologie und Schmierungstechnik, 2014)
Im Rahmen der in einem Verbundprojekt durchgeführten Untersuchungen wurden Mikrostrukturen mit dem Ziel der Reibungsreduzierung speziell an das tribologische System eines Nocken/Stößel-Kontaktes, als Beispiel für hochbelastete Wälz-Gleit-Kontakte, angepasst. Für diese Art von Reibkontakten sind die Effekte von Mikrostrukturen noch nicht abschließend geklärt. Zur Erlangung disziplinübergreifender Erkenntnisse wurden Mikrostrukturformen durch numerische Simulationen ausgelegt sowie die Genauigkeit der Fertigung und das tribologische Verhalten der mikrostrukturierten Komponenten untersucht. Für die Herstellung der Mikrostrukturen wurde aufgrund der Perspektive für die Großserienanwendung auf den Prozess des Mikroprägens fokussiert, der der Mikrolaserablation hinsichtlich seiner Genauigkeit gegenübergestellt wurde. Für die mikrostrukturierten Ventiltassenoberflächen wurde im Prüfstand eine signifikante Reibungsreduzierung gegenüber polierten Oberflächen erreicht.
LFT Import::2019-07-29 (1977)

Mikrostrukturierung von Tassenstößeln zur Reibungsreduzierung im Ventiltrieb - Herstellung, Simulation und tribologische Charakterisierung - Weschta, Martin; Schrader, Tobias; Tremmel, Stephan; Merklein, Marion; Wartzack, Sandro; Engel, Ulf (54. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Band II, 2013)
Im Rahmen der in einem Verbundprojekt durchgeführten Untersuchungen wurden Mikrostrukturen mit dem Ziel der Reibungsreduzierung speziell an das tribologische System eines Nocken-Stößel-Kontaktes, als Beispiel für hochbelastete Wälz-Gleit-Kontakte, angepasst. Für diese Art von Reibkontakten sind die Effekte von Mikrostrukturen noch nicht abschließend geklärt. Zur Erlangung disziplinübergreifender Erkenntnisse wurden Mikrostrukturformen durch numerische Simulationen ausgelegt sowie die Genauigkeit der Fertigung und das tribologische Verhalten der mikrostrukturierten Komponenten untersucht. Die tribologische Wirkung der Mikrostrukturen wurde in einem zweidimensionalen elastohydrodynamischen Simulationsmodell bestimmt. Für die Herstellung der Mikrostrukturen wurde aufgrund der Perspektive zur Großserienanwendung auf den Prozess des Mikroprägens fokussiert, der der Mikrolaserablation hinsichtlich seiner Genauigkeit gegenübergestellt wurde. Für die mikrostrukturierten Ventiltassenoberflächen wurde im Prüfstand eine signifikante Reibungsreduzierung gegenüber polierten Oberflächen erreicht.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.mikros

Model and Knowledge Representation for the Reuse of Design Process Knowledge Supporting Design Automation in Mass Customization - Dworschak, Fabian; Kügler, Patricia; Schleich, Benjamin; Wartzack, Sandro (Applied Sciences, 2021)
Mass customization aims to meet individual requirements and, therefore, is one way to attract and retain customers—a key challenge in the design industry. The increase in design automation has offered new opportunities to design customized products at high speed in a way that is cost equivalent to mass production. Design automation is built upon the reuse of product and process knowledge. Ontologies have proven to be a feasible, highly aggregated knowledge representation in engineering design. While product and process knowledge from other lifecycle phases are represented in multiple approaches, the design process of the product as well as the adaption process of product variants is missing, causing breakpoints or additional iterations in design automation. Therefore, suitable knowledge representation tailored to design automation is still missing. Accordingly, this contribution proposes a novel knowledge representation approach to enable design automation for mass customization. Methodically, this novel approach uses semantic enrichment of CAD environments to automatically deduce information about a design task, design rationale, and design process represented by a formal ontology. The integration of the design process significantly differentiates the approach from previous ones. The feasibility of the approach is demonstrated by a bike crank customization process.
Keywords: knowledge reuse; knowledge representation; ontology; design automation; mass customization

Model Factory for Additive Manufacturing of Mechatronic Products: Interconnecting World-Class Technology Partnerships with Leading AM Players - Yoo, In Seong; Braun, Thomas; Kästle, Christopher; Spahr, Michael; Kestel, Philipp; Wartzack, Sandro; Franke, Jörg; Bromberger, Jörg; Feige, Erhard (6th CIRP Conference on Learning Factories, 2016)
The additive manufacturing (AM) model factory’s aim is to establish a leading-edge learning academy for the digital and generative production of innovative mechatronic products, where the complete value chain is integrated on a single site. Short courses and deep dives enable easier access to the state of the art technologies and increase the awareness for their potentials. Anchored in key industries such as automotive, aerospace, and medical by major OEMs and regional SMEs, the AM model factory cooperates with world-class partners and leading market players. This paper displays the model factory’s setup, selected technologies, exemplary courses, and benefits.

Modeling of cage guidance in a rolling bearing multi-body dynamic simulation program for a power efficient bearing design - Seiler, Katrin; Stadler, Marion; Tremmel, Stephan; Hahn, Bodo; Wartzack, Sandro; Graf-Goller, Oliver (Volume 2, 2014)
Keywords: Wälzlager; MKS; Tribologie; Hydrodynamik

Modeling of Shape Deviations for the Development of Predictive Models of TEHD Contacts - Feile, Klara; Bartz, Marcel; Wartzack, Sandro (24, 2024)

Modellierung bandgeführter Gelenke der Hand zur Anwendung bei klinischen und biomechanischen Fragestellungen - Miehling, Jörg; Krüger, Daniel; Quadrat, Eric; Jalali, Jalil; Erne, Holger C.; Cerny, Michael; Wartzack, Sandro; Kovacs, Laszlo (6. caMe-Konferenz, 2016)
One of the most common injuries, not only in work-related environments, are hand injuries. In many cases, those are treated by rigid connections of parts or the entire wrist to alleviate the symptoms. This can cause a high limitation of workability and quality of life. Despite all scientific efforts, the biomechanics of the wrist with its complex support structure are still not entirely understood. Frequent injury patterns which lead to painful, arthritic changes and restrictions of the range of motion, cause problems in clinical practice. Often the currently used surgical techniques for reconstructing damaged structures only reach limited success. Additionally the diagnosis and the treatment of many injuries are vague and difficult. For example the functions and interactions of the hand structures are not completely clarified, whether a surgery is useful or not. This problem can only be solved with collaboration of engineering and medical expertise. The main goal of this contribution is to create a simulation model of the hand in order to facilitate a realistic representation and analysis of the interaction between the bones. Thereby future injuries could be better understood, diagnosed and treated. To sum up, a validated 3D hand model focusing on the wrist offers a vast number of possibilities in clinical practice as well as in basic research, such as the detailed exploration of the functional relationships in the wrist. Furthermore there is a positive influence on socio-economic factors, because earlier diagnosis and individualized therapies can minimize the duration of disability and also avoid occupational disability. When developing product and process innovations, the human ever more moves into the center of consideration. In fact, the available human hand models are not detailed enough, for example to describe realistic grasping motions, which are crucial for manual assembly tasks as well as for most user-product interactions. Beside clinical practices, the developed bone and ligament-guided model should also be used in system simulations to adjust work processes and products to compy with the biomechanical requirements of workers or users. Thus, congestion can be uncovered and avoided in early planning stages.
Keywords: hand model; musculoskeletal system; multibody simulation; biomechanics; surgical planning; orthopedics; ergonomics

Modellierung der Käfigführung für Wälzlagerdynamiksimulationsprogramme – Ein Beitrag zur betriebssicheren Lagerauslegung - Seiler, Katrin; Stadler, Marion; Tremmel, Stephan; Hahn, Bodo; Wartzack, Sandro; Graf-Goller, Oliver (Tribologie und Schmierungstechnik, 2013)
In dem Beitrag wird ein analytisches Berechnungsmodell für die Abbildung der Hydrodynamik im Käfig/Ring- Kontakt von Wälzlagern näher betrachtet. Dieses Modell beinhaltet die Berechnung der Kontaktnormalkraft, der Schmierstoffdämpfung und der Reibung resultierend aus der Schmierstoffscherung bei geschmierten Kontakten. Im Fall des bordgeführten Käfigs wird auf die Kurzgleitlager- Theorie zurückgegriffen. Das Berechnungsmodell für den hydrodynamischen Kontakt wurde in das Wälzlagermehrkörpersimulationsprogramm CABA3D implementiert und mit dem Gleitlagerberechnungsprogramm COMBROS abgeglichen. Anhand von Simulationsergebnissen für ein fliehkraftbeanspruchtes Nadellager wird exemplarisch der Einfluss der Hydrodynamik im Käfig/Ring-Kontakt auf das Lagergesamtreibmoment und die Lagerkinematik dargestellt.
Keywords: Wälzlager; MKS; Tribologie

Modellierung der Käfigführung für Wälzlagerdynamiksimulationsprogramme – Ein Beitrag zur betriebssicheren Lagerauslegung - Seiler, Katrin; Stadler, Marion; Tremmel, Stephan; Hahn, Bodo; Wartzack, Sandro; Graf-Goller, Oliver (54. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Band II, 2013)
In dem Beitrag wird ein analytisches Berechnungsmodell für die Abbildung der Hydrodynamik im Käfig/Ring-Kontakt von Wälzlagern näher betrachtet. Dieses Modell beinhaltet die Berechnung der Kontaktnormalkraft, der Schmierstoffdämpfung und der Reibung resultierend aus der Schmierstoffscherung bei geschmierten Kontakten. Im Fall des bordgeführten Käfigs wird auf die Kurzgleitlager-Theorie zurückgegriffen. Das Berechnungsmodell für den hydrodynamischen Kontakt wurde in das Wälzlagermehr-körpersimulationsprogramm CABA3D implementiert und mit dem Gleitlagerberechnungsprogramm COMBROS abgeglichen. Anhand von Simulationsergebnissen für ein fliehkraftbeanspruchtes Nadellager wird exemplarisch der Einfluss der Hydrodynamik im Käfig/Ring-Kontakt auf das Lagergesamtreibmoment und die Lagerkinematik dargestellt. Analytical models for the calculation of hydrodynamics in the contact between cage and ring of roller bearings will be presented in this article. The model contains the calculation of the contact normal force, the lubricant damping and the friction resulting from lubricant shear. In case of the contact between cage and ring in rib guided bearings the hydrodynamic model is based on the theory of a journal short bearing. The hydrodynamic model was implemented in a multibody system for roller bearings named Caba3D and the results are compared to a journal bearing calculation program named COMBROS. Simulation results show exemplary the influence of hydrodynamics on friction and kinematics of a needle bearing under centripetal load.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.modell
Keywords: Wälzlager; MKS; Tribologie; Hydrodynamik

Modelling, Construction and Manufacture of a Lightweight Robot Arm - Hagenah, Hinnerk; Böhm, Wolfgang; Breitsprecher, Thilo; Merklein, Marion; Wartzack, Sandro (Proceedings of the 8th CIRP International Conference on Intelligent Computation in Manufacturing Engineering, 2012)
This contribution will show how modern materials as cellular titanium and nanocrystalline aluminium can be used to build advanced lightweight robot arms. Cellular titanium allowing a specific density distribution and the manufacture of fine structures with desirable properties is produced by selective electron beam melting while the nanocrystalline aluminium results from accumulative roll bonding. The specific properties of both materials will be highlighted. The paper will cover the definition of the product specification, the setting of a basic design and the optimisation of this by means of topology optimisation. This optimisation requires an intelligent modelling to be able to investigate different initial settings and boundary conditions. The optimised part will then be finished with regards to manufacturability. The paper will close with a brief report about the actual manufacture of one of the investigated variants.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.modell

Modelling the interaction between wearable assistive devices and digital human models—A systematic review - Scherb, David; Wartzack, Sandro; Miehling, Jörg (Frontiers in Bioengineering and Biotechnology, 2023)
Exoskeletons, orthoses, exosuits, assisting robots and such devices referred to as wearable assistive devices are devices designed to augment or protect the human body by applying and transmitting force. Due to the problems concerning cost- and time-consuming user tests, in addition to the possibility to test different configurations of a device, the avoidance of a prototype and many more advantages, digital human models become more and more popular for evaluating the effects of wearable assistive devices on humans. The key indicator for the efficiency of assistance is the interface between device and human, consisting mainly of the soft biological tissue. However, the soft biological tissue is mostly missing in digital human models due to their rigid body dynamics. Therefore, this systematic review aims to identify interaction modelling approaches between wearable assistive devices and digital human models and especially to study how the soft biological tissue is considered in the simulation. The review revealed four interaction modelling approaches, which differ in their accuracy to recreate the occurring interactions in reality. Furthermore, within these approaches there are some incorporating the appearing relative motion between device and human body due to the soft biological tissue in the simulation. The influence of the soft biological tissue on the force transmission due to energy absorption on the other side is not considered in any publication yet. Therefore, the development of an approach to integrate the viscoelastic behaviour of soft biological tissue in the digital human models could improve the design of the wearable assistive devices and thus increase its efficiency and efficac
Keywords: digital human model; musculoskeletal modelling; multi-body dynamic; interaction modelling; systematic review; soft tissue; wearable assistive device

Modifikation der Methode der Dimensionsreduktion zur Berechnung von beliebigen Punkt- und Ellipsenkontakten in Wälzlagern - Wirsching, Sven; Bänsch, Dominik; Bartz, Marcel; Wartzack, Sandro (62. Tribologie-Fachtagung 2021 Reibung, Schmierung und Verschleiß Forschung und praktische Anwendungen, 2021)
Inside rolling bearings, there is a large number of different contacts. These include not only linear contacts on the raceways, the cage and the rolling elements, but also point and elliptical contacts between the rolling element end face and the ring rib. Depending on the load situation, these contacts contribute differently to the load carrying capacity, the temperature development and thus the operating capability of the rolling bearing. The axial load carrying capacity of roller bearings is determined primarily by the rib contact, since the axial load components are absorbed by the ribs. To calculate the load capacity, an exact description of the contact between the rolling element end face and the ring rib is necessary. An improved contact calculation allows the targeted development of more efficient and higher-performance rolling bearings. In existing methods for dimensioning rolling bearings, the contact between the rolling element and rib is calculated on the basis of the time- and resource-efficient theory of Hertz, which makes simplifications in the description of the geometries. However, contacts of real, complex geometry pairings of rolling element and rib, as used to optimize the axial load capacity of roller bearings, can only be calculated inaccurately with this method. Compared with time-consuming, high-quality numerical calculations (e.g. finite element analysis), there are greater discrepancies in the size of the contact area and contact pressures. For this reason, this paper presents a new time- and resource-efficient method for the calculation of point and elliptical contacts. Using the method of dimensional reduction (MDR) according to Popov, contacts of rotationally symmetric bodies can be calculated exactly. A modification of MDR allows the calculation of non-rotationally symmetric bodies. The existing contact situation is described and calculated with a superposition of different rotationally symmetric geometries. The modified MDR is compared with the Hertz theory using simple contact situations. The results for more complex contact situations are compared with those from finite element analyses. By comparing the calculated contact area and contact pressure, the possibilities and limitations of the modified MDR are ass
Keywords: contact mechanics; MDR; point contact; ellipse contact; bearings

Modular rapid design of multi-material lightweight truss structures – A novel approach - Rathert, Thomas; Witzgall, Christian; Wartzack, Sandro (Book of Abstracts. Symposium Lightweight Design in Product Development, Zurich, 2018)
The specification of an ideal lightweight design with minimal weight and maximum utilization of the material is often restricted by economic factors. Taking this into account, only an optimized lightweight design can be realized. When utilizing modern composite materials, the design and manufacturing methods are poorly standardized and their implementation usually causes high costs in design and production. Besides that the composite suitability of framework structures – which could be standardized – is only given for uniaxial loaded sections, whereas the connector regions are subject to a (at least) biaxial stress state that is very unfavorable for composite materials. As a consequence it is often advisable to use a multi-material design – also known as hybrid design. The best properties of different materials are combined here, while keeping the economic impact as low as possible. Each individual element of the hybrid structure offers a basic local solution, but in addition they can achieve optimization in a combined state. The main objective of this contribution is to show how to simply use the right material in the right place, thus allowing to optimally exploiting their beneficial lightweight properties and keeping the costs as low as possible. Therefore a methodology is presented, which allows the dimensioning and optimization of multi-material lightweight design systems inside a restricted design space by using modular and rapid building blocks. This enables the product developer to design an optimal framework topology by using a discrete optimization approach and afterwards dimension anisotropic composite tubes for the sections of uniaxial stresses and isotropic connectors to join them. The calculated information is then transferred to the CAD‑System to directly create the product’s embodiment design by using standardized composite profiles and aluminum connectors. Finally using the demonstrator of a motorcycle frame, the method will be evaluated and discussed.
Keywords: hybrid design; multi-material design; discrete topology optimization

Monitoring a property based product development From requirements to a mature product - Krehmer, Hartmut; Meerkamm, Harald; Wartzack, Sandro (Proceedings of the 18th International Conference on Engineering 2011 (ICED 11), 2011)
Increasing customers̀ requirements as well as changing market demands are just two examples for influences that result in an increasing complexity of technical products. To assure the fulfilment of all requirements an effective monitoring of product development is essential. Monitoring is often done by observance of required time and caused costs, and does not take into account product's functionality or properties or behaviour. This contribution introduces a framework which allows combining different approaches for efficient monitoring of product development by focusing the products'properties from requirements to a mature product. Therefore, at first a short introduction in property based product development is given and a model for property based development is introduced, before existing methods for evaluating and monitoring product development are depicted. After that an introduction in monitoring product development is given and approaches are integrated into the model of property based product development with regard to their capabilities and focuses. Finally, this results in an approach for monitoring property based product development from requirements to a mature product.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.monito
Keywords: Monitoring; Product's degree of maturity; Property based product development

Monte Carlo simulation of the MoS2 sputtering process and the influence of the normalized momentum on residual stresses - Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro (Journal of Vacuum Science & Technology A, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.montec

Motion Tolerancing Based on Skin Model Shapes by Form Deviation Parametrization and Meta-Modelling - Schleich, Benjamin; Wartzack, Sandro (ASME 2017 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, Volume 1: 37th Computers and Information in Engineering Conference, 2017)
The inevitable presence of geometrical part deviations and their effects on the product function and quality forces companies to manage these deviations along the product life-cycle. Computer-aided tolerancing and variation simulation tools support these activities by enabling the early prediction and assessment of the effects of such part deviations. However, available approaches for the tolerance analysis and variation simulation imply shortcomings regarding the consideration of form deviations, particularly when analysing mechanism and moving systems. This paper presents an approach for the motion tolerancing, i. e. for the tolerance analysis of mechanism and moving systems, employing discrete geometry representations of parts with geometrical deviations (Skin Model Shapes). In this regard, a novel method for the parametrization of form deviations is proposed and the use of meta-modelling techniques for the reduction of the computational effort is illustrated. Moreover, the presented approach is applied on two case studies. Based on the obtained results, it can be found, that the consideration of form deviations in the tolerance analysis for mechanism and moving systems may lead to more purposeful tolerancing decisions.

Multi-criteria evaluation and decision making on the basis of the matrix-based modeling of the product development - Luft, Thomas; Wartzack, Sandro (Proceedings of 3rd International Spring School on Systems Engineering 2015, 2015)

Musculoskeletal Simulation and Evaluation of Support System Designs - Miehling, Jörg; Wolf, Alexander; Wartzack, Sandro (Developing Support Technologies - Integrating Multiple Perspectives to Create Assistance that People Really Want, 2018)

Mxene nanosheets as an emerging solid lubricant for machine Elements – Towards increased energy efficiency and service life - Marian, Max; Tremmel, Stephan; Wartzack, Sandro; Song, Guichen; Wang, Bo; Yu, Jinhong; Rosenkranz, Andreas (Applied Surface Science, 2020)
Solid lubricants like carbon-based materials, transition metal dichalcogenide compounds, polymers and soft metals, each with their specific merits and limitations, pursue the goal of reducing friction and wear between two rubbing surfaces under substantially dry conditions. Newly emerging early transition metal carbides and carbonitrides, such as Ti3C2Tx-nanosheets (MXenes), seem to be a promising candidate to be used as a solid lubricant due to their weakly bonded multilayer structure with self-lubricating character. For the first time, this paper aims at addressing the application of MXene nanosheets in higher loaded rolling-sliding contacts of machine elements by investigating their friction and wear behavior in thrust ball bearings under ambient conditions. Thereby, a reduction of the frictional torque by a factor of up to 3.2, an extension of the service life by about 2.1 times and a decrease of the linear cumulative wear rate by up to 2.9 compared to uncoated references have been verified. Thus, the Ti3C2Tx-coating already featured results comparable to reports on graphene, amorphous carbon coatings or advanced transition metal dichalcogenide, which demonstrates the tremendous potential of MXene nanosheets as outstanding, next-generation solid lubricant in machine elements.<br
Keywords: 2D materials; Ti3C2Tx-nanosheets; solid lubricants; machine elements; thrust ball bearing

Natural Finger Interaction for CAD Assembly Modeling - Fechter, Marius; Wartzack, Sandro (ASME 2017 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, Volume 1: 37th Computers and Information in Engineering Conference, 2017)
In current CAD software the process of assembly modeling is hindered by a large number of separate rotation and translation actions necessary, especially in case of larger assemblies. Additionally matching faces, edges or points must be selected by clicking to define the appropriate constraint. In contrast to that, the process of assembling two normal sized physical parts in the real world seems to be rather simple. That is because we know how to grasp and move objects with our hands intuitively from our everyday experience. The idea behind this contribution is to enable the product developer to assemble CAD parts in a virtual environment through natural finger interaction like in reality. Therefore we present an overall method that combines the natural finger interaction with virtual objects and the insertion of constraints between rotationally symmetric CAD parts. The developed algorithms identify matching surfaces on the basis of the geometry as well as position and orientation of the parts in 3D space. This paper highlights the method to use a combination of real-time physics simulation and a heuristic approach to achieve an intuitive interaction interface. Additionally, we describe the detection algorithms developed to find assembly relationships between rotationally symmetric CAD parts without prior constraint definition. We also present a prototype system to demonstrate the functionality of the overall method. Furthermore, challenges for future research, such as extending the functionality of the detection algorithms on additional part types, like non-rotationally symmetric shapes, are discussed.
Keywords: Assembly Modeling; Computer-Aided Design; Virtual Reality; Natural User Interface

Natural Language Processing in Requirements Engineering and Its Challenges for Requirements Modelling in the Engineering Design Domain - van Remmen, Judith Sophie; Horber, Dennis; Lungu, Adriana; Chang, Fan; van Putten, Sebastiaan; Götz, Stefan; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Requirements represent a central element in product development. The large number of requirements inevitably results in an increased susceptibility to errors, an expenditure of time and development costs. The associated problems motivate the application of Artificial Intelligence in the form of Natural Language Processing (NLP). In Requirements Engineering one main task is the classification of requirements which serves as the input in architectural models e.g. in SysML. In mechanical engineering there is still little overview regarding the interface between requirements classification and modelling. This paper provides an overview of the requirement classes and entities used in the literature and analyses their utilisation in modelling. Existing requirements classes usually do not offer the flexibility to be transferred to other domains. However, basic structures can be adopted from those classifications. This enables a clear assignment of existing classes to object classes in modelling. Resulting from the conducted literature study the observed predominant focus of research on the software industry requires an extension of the existing requirement classes and entities to enable further use and transfer to mechanical engineerin
Keywords: Requirements; Artificial intelligence; Natural Language Processing; Systems Engineering (SE); Literature review

New Approach on the Allocation of Wear Allowances - a Case Study - Schubert, Dominik; Rohrmoser, Andreas; Hertle, Sebastian; Wartzack, Sandro; Hagenah, Hinnerk; Merklein, Marion; Drummer, Dietmar (22nd International Conference on Engineering Design (ICED19), 2019)

Non-Dimensional Groups, Film Thickness Equations and Correction Factors for Elastohydrodynamic Lubrication: A Review - Marian, Max; Bartz, Marcel; Wartzack, Sandro; Rosenkranz, Andreas (Lubricants, 2020)
Apart from complex numerical models to predict the tribological behavior of elastohydrodynamically lubricated contacts, non-dimensional similarity groups and analytically solvable proximity equations can be used to estimate integral fluid film parameters. Based upon the pioneering work presented by Dowson and Higginson as well as Blok and Moes, these approaches have been continuously improved over the years by modifications or correction factors to capture different contact geometries (line-, point- or elliptical contacts) as well as to include fluid compression, thermal, non-Newtonian, starvation or roughness effects. Consequently, this review article aims at systematically reviewing these modifications/corrections and discussing their applicability as well as limitations before presenting some recommendations for future research activities.<br
Keywords: elastohydrodynamic lubrication; non-dimensional groups; proximity equations; minimum film thickness; central film thickness; correction factors

Novel approaches for the assembly simulation of rigid Skin Model Shapes in tolerance analysis - Schleich, Benjamin; Wartzack, Sandro (Computer-Aided Design, 2018)
While the modelling of nominal assemblies is sufficiently solved in modern computer-aided design tools, the assembly simulation for parts considering geometrical deviations is still an important research issue. Particularly in tolerance analysis, the assessment of the effects of geometrical part deviations on the part assembly behaviour is of central importance. Though established assembly simulation approaches for parts with geometrical deviations cover a moderate range of real assembly problems, they are not suitable for all assembly simulation problems. To overcome this shortcoming, a general framework and new approaches for the assembly simulation of Skin Model Shapes for the use in tolerance analysis are presented. The application of these assembly simulation approaches is highlighted in generalized case studies and recommendations for their use in tolerance simulations are derive
Keywords: Point-based models; Registration; Assembly simulation; Skin Model Shapes; Tolerance analysis

Numerical Investigations on Dimensional and Geometrical Deviations of Surface Textures in EHL Contacts - Marian, Max; Tremmel, Stephan; Wartzack, Sandro (International Tribology Conference Sendai 2019, 2019)
Micro-textures applied on rubbing surfaces of lubricated contacts have gained tremendous attention in the last two decades. Numerous experimental and numerical studies deal with the derivation and testing of advantageous micro-textures. Nevertheless, especially with respect to higher loaded elastohydrodynamically lubricated (EHL) rolling-sliding contacts, not all questions have been answered yet. Will texturing really provide as good effects as often claimed, and are there occasions when texturing could theoretically improve the tribological behavior but is questionable from other perspectives? For these reasons, transient 3D simulations of micro-textured EHL line- and point-contacts based on the full-system approach were performed, which act as a ‘numerical zoom’ into the contact area and contribute to a better understanding of local phenomena. For the hydrodynamics, a modified Reynolds equation was applied. Based upon the finite element method (FEM), the elastic deformation was computed for an equivalent body by applying the linear elasticity equation. Moreover, for example time-dependent squeeze effects, mixed lubrication, microhydrodynamics and cavitation were to be considered. Within this contribution, the effects of dimensional and geometrical deviations of discrete texture elements on lubricating conditions and thus friction and wear are addressed. This ranges from depth, length, width or flank angles of individual texture elements to the lateral distribution in and perpendicular to direction of sliding as well as the relative position of texture and contact area. It is shown that these deviations from nominal or optimized texture designs have a significant impact on the tribological performance, potentially overcompensating theoretical benefits. The findings emphasize the necessity for numerically derived optima and robust designs as well as manufacturing technologies with high precision to exploit the full potential of micro-texturin
Keywords: Micro-texturing; Dimensional Deviations; Geometrical Deviations; Elastohydrodynamic Lubrication

Numerical modeling of lubrication mechanisms in total knee replacements - Marian, Max; Rothammer, Benedict; Bartz, Marcel; Nečas, David; Vrbka, Martin; Wimmer, Markus A; Wartzack, Sandro (5th International Conference on BioTribology, 2021)
For an adequate design of total knee replacements (TKR), knowledge about stresses and lubrication conditions is vital. Within this study, a numerical model based upon the Finite Element Method and fully coupling the fluid’s hydrodynamics (generalized Reynolds equation) with the elastic deformation of the contacting bodies is presented. Thereby, realistic transient kinematics and loading conditions of the gait cycle (ISO 14243) were considered. For the numerical results, good agreement with experimental studies by means of a knee simulator with optical fluorescent measurement technique was achieved. Moreover, it was found that the complexity of numerical modeling has a strong effect on simulation results and thus on the prediction quality, especially for the fluid film height. The consideration of transient squeeze effects, non-Newtonian fluid characteristics, realistic geometries, transient kinematics and loading conditions is vital. The medial compartment was more heavily stressed and experienced higher pressures and smaller minimum film heights compared to the lateral condyle. The swing phase was determined by geometry and kinematics while load and geometry played a dominant role in the stance phase, where the overall lubricant gap was smaller. Generally, the reversal points of motion with zero entrainment speed largely affected the fluid film formation. Furthermore, the individual rheological synovial fluid parameters have a decisive influence on the lubricant film formation. Due to the wide variation between different patients, this can also lead to diverse tribological behavior ranging from full separation of the rubbing surfaces over the whole gait cycle to strong solid asperity contact and associated wear mechanisms.
Keywords: Total knee replacement; Synovial joint tribology; Soft-elastohydrodynamic lubrication; Finite Element Method

Numerical Modeling of Wear in a Thrust Roller Bearing under Mixed Elastohydrodynamic Lubrication - Winkler, Andreas; Marian, Max; Tremmel, Stephan; Wartzack, Sandro (Lubricants, 2020)
Increasing efforts to reduce frictional losses and the associated use of low-viscosity lubricants lead to machine elements being operated under mixed lubrication. Consequently, wear effects are also gaining relevance. Appropriate numerical modeling and predicting wear in a reliable manner offers new possibilities for identifying harmful operating conditions or for designing running-in procedures. However, most previous investigations focused on simplified model contacts and the wear behavior of application-oriented contacts is relatively underexplored. Therefore, the contribution of this paper was to provide a numerical procedure for studying the wear evolution in the mixed elastohydrodynamically lubricated (EHL) roller/raceway contact by coupling a finite element method (FEM)-based 3D EHL model with surface topography changes following a local Archard-type wear model, a Greenwood–Williamson-based load-sharing approach and the Sugimura surface adaption model. This study applied the operating conditions of an 81212 thrust roller bearing, considering realistic geometry and locally varying velocities. The calculated wear profiles in the raceway featured asymmetries, which were in good agreement with the experimental results reported in the literature and could be correlated with the velocity and slip distribution. In addition, the effects of speed, load and oil viscosity were investigated by means of four load cases and two lubricants, demonstrating the broad range of applying the numerical approach.<br
Keywords: multi-scale tribo-simulation; wear modeling; mixed lubrication; elastohydrodynamic lubrication; machine elements; thrust roller bearing

Numerical optimization of the roller face/rib geometry for friction reduction in tapered roller bearings - Wirsching, Sven; Marian, Max; Stahl, Thomas; Bartz, Marcel; Wartzack, Sandro (7th World Tribology Congress 2022, 2022)
In the context of increasing demands for energy efficiency of rolling bearings, secondary contacts are gaining relevance. This demands for an accurate and efficient numerical design of the contacting bodies while considering realistic geometries, movement and lubrication conditions. Within this contribution, the elastohydrodynamically lubricated roller face/ring rib contact of a tapered roller bearing with axial loading was therefore optimized using numerical elastohydrodynamic contact simulation, meta-modeling and evolutionary algorithms.<br

Numerical study on the lubrication in total knee replacements: The influence of dynamics, geometry, material and fluid - Marian, Max; Rothammer, Benedict; Bartz, Marcel; Nečas, David; Vrbka, Martin; Wimmer, Markus A; Wartzack, Sandro (7th World Tribology Congress, WTC 2022, 2022)
For an adequate design of total knee replacements, knowledge about stresses and lubrication conditions is vital. Within this study, a numerical model is presented and validated with experimental data. Good agreement between model predictions and experimental data as well as a strong influence of fluid, material and geometry assumptions as well as transient effects were found. It was demonstrated that the rheological synovial fluid properties have a decisive impact on the tribological behavio
Keywords: Total knee replacement; Synovial joint tribology; Soft-elastohydrodynamic lubrication; Finite Element Method

Numerical Wear Modeling in the Mixed and Boundary Lubrication Regime - Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (Lubricants, 2022)
The increasing use of low-viscosity lubricants in order to reduce the friction in machine elements such as rolling bearings is leading to increased operation in the mixed or boundary lubrication regime. The associated wear can lead to an earlier failure of tribological systems. In this context, a detailed wear simulation offers great potential with regard to the design of machine elements as well as the calculation of lifetimes. This contribution presents an approach for the numerical wear simulation of lubricated rolling/sliding-contacts. Therefore, a finite element method-based simulation model was developed which is able to deal with non-Gaussian surfaces and contacts subject to boundary and mixed lubrication. Using the example of an axial cylindrical roller bearing considering realistic geometry, locally varying velocities, and two load cases, the wear modeling results of the mixed and the boundary lubrication regime were illustrated. The wear coefficient required for Archard’s wear model was determined experimentally by means of a two-disc tribometer.<br
Keywords: wear modeling; contact mechanics; elastohydrodynamic lubrication; mixed lubrication; boundary lubrication; machine elements; thrust roller bearing; two-disc tribometer

Nutzerzentrierte Produktentwicklung durch systematische Integration von Marketingaspekten – ein erster Ansatz. - Kett, Susan; Schröppel, Tina; Wartzack, Sandro (25. DfX-Symposium Design for X., 2014)
The shift from seller’s to buyer’s markets in many different product divi-sions leads to a raising role of the user in product development processes. Especially implicit decision parameters such as comfort feeling need better consideration. This article suggests to consequently integrate models and tools from other disciplines, e.g. marketing, to generate competitive ad-vantages due to a better fulfillment of user’s needs. In those areas, focusing on users is much more established. As a starting point, a first glance of the topic is given by adapting Portfolio Models. The potential to directly link “soft” user decision parameters with product properties without any intermediates offers value to minimize misleading product development efforts. Further investigation in this area is recommended.
Keywords: product development; user integration; methodology; marketing

Oberflächen-Mikrostrukturierung in Wälzkontakten - Weschta, Martin; Pausch, Michael; Tremmel, Stephan; Wartzack, Sandro (Wissenschaftliches Kolloquium Wälzlager, 2013)

On Connected Tolerances in Statistical Tolerance-Cost-Optimization of Assemblies with Interrelated Dimension Chains - Heling, Björn; Aschenbrenner, Alexander; Walter, Michael; Wartzack, Sandro (14th CIRP CAT 2016 - CIRP Conference on Computer Aided Tolerancing, 2016)
Identifying a suitable compromise between tight and thus expensive tolerances and wide tolerances that may negatively influence the product quality is a major challenge. This paper focuses on the tolerance-cost-optimization of mechanical assemblies with interrelated dimension chains considering dependencies between the tolerance–cost-relationships. Taking into account interrelated dimension chains the crux is, however, that modifications of a single tolerance can influence several dimension chains as well as the resulting production costs. Based on different existing approaches for the statistical tolerance-costoptimization, the authors will provide appropriate guidance for the product developer dealing with interrelated dimension chains.
Keywords: tolerance allocation; interrelated tolerance-cost-function; connected dimension chains; modification of tolerance-cost-relation

On Lubrication Mechanisms in Total Knee Replacements - Marian, Max; Orgeldinger, Christian; Rothammer, Benedict; Bartz, Marcel; Tremmel, Stephan; Wartzack, Sandro (62. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen., 2021)
The longevity of total knee arthroplasty (TKA) is considerably affected by the overall biotribological performance and synovial fluid lubrication phenomena. The present study is therefore targeted to identify lubrication mechanisms occurring in TKAs, focusing on the role of synovial fluid propertie
Keywords: Total knee replacement; synovial joint tribology; soft-elastohydrodynamic lubrication; synovial fluid

On Simulation Knowledge Acquisition Using Gaussian Processes for the Design of Electric Motors - Dworschak, Fabian; Tüchsen, Johann; Pinto, Diogo; Pop, Adrian-Cornel; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP Volume 84, 2019)
In the automotive industry, high efforts are made to design high-efficiency, low-cost, requirement-optimized electric drives. Traditionally, time-consuming and expensive 3D finite element analyses are used to assess the effects of different design parameters from various engineering disciplines such as the electromagnetics, heat transfer, and mechanics. Often, to decrease the calculation efforts, scalable, physics-based reduced order models are used. For setting up and interpreting such reduced order models, simulation experts employ implicit knowledge by applying heuristic correction factors. This paper proposes a novel method to formalizing such implicit simulation knowledge using Gaussian Processes. Furthermore, the successful application of the method to a case study of electric motors is reported by validating the aforementioned correction factors for different motor designs.<br
Keywords: Knowledge Acquisition; Meta-Modelling; Gaussian Process; Electric Motor; Case Study

On the impact of geometric deviations on structural performance - Schleich, Benjamin; Stockinger, Andreas; Wartzack, Sandro (Proceedings of the 12th CIRP Conference on Computer Aided Tolerancing, 2012)
Geometric deviations are observed on nearly every manufactured part since manufacturing processes are inherently imprecise and measuring processes always involve uncertainties. Therefore, tolerances have to be set. They define the allowable geometric deviations of a part. However, geometric deviations have an influence on the structural performance of the parts also. In other words, there are interdependencies between geometric deviations and deformations which affect the dimensional accuracy of a loaded part in an assembly. Therefore, this paper proposes an approach to determine the impact of geometric deviations on the structural performance of a part. This method can be used in terms of sensitivity analysis, analysis of robustness and evaluation of reliability. It can be concluded that geometric deviations can have a big impact on the structural performance and thus not only parametric deviations but also geometric deviations regarding the shape of a part itself should be taken into account within the structural performance analysis.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.onthei
Keywords: stochastic finite elements; random fields; computer aided tolerancing; sensitivity analysis; structural performance

On the Influence of Fatigue Damage in Short-Fibre Reinforced Thermoplastic PBT GF30 on Its Residual Strength under High Strain Rates: An Approach towards Simulative Prediction - Witzgall, Christian; Steck, Patrick; Wartzack, Sandro (Journal of Composites Science, 2023)
Only by using accurate material data can precise simulation results be achieved. This principle also and especially applies in the field of crash simulation. However, in the simulation of short-fibre reinforced thermoplastics, material parameters are usually used that originate from the material testing of as-new samples. In order to get closer to the condition on the roads, where not only new vehicles are driving, the influence of service loads on the crashworthiness has to be investigated. This paper reports on studies of PBT GF30, a polybutylene terephthalate reinforced with 30% glass fibres, in which fatigue damage was induced in the material by cyclic loading. The residual strength was then determined in a high-speed experiment and compared with the strength of virgin samples. In order to enable the usability of the findings in the simulation, a modified failure criterion was implemented that takes the previous fatigue damage into account. The prediction quality of the simulation model was compared with the experimental findings and it can be concluded that there is good agreement.<br

On the Potential of Slicing Algorithms in Additive Manufacturing for the Optimization of Geometrical Part Accuracy - Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2022)
Despite its potentials, geometrical inaccuracies remain a major shortcoming for Additive Manufacturing in general and especially for Fused Layer Modeling, even though much research effort is put in enhancing mechanical properties and reducing process-specific deviations by optimizing process parameters. Novel slicing and path planning algorithms, such as non-planar printing, are suitable tools for addressing these problems and thus for improving geometrical part accuracy, but are subject of current research and only partly applicable. With the aim to show and evaluate the potential of these algorithms in the context of tolerancing, this paper proposes an approach for applying one pre-processing technique to 3D-printed parts. The exemplary application shows the applicability and the high potential of advanced slicing and path planning algorithms. The findings therefore indicate that aspects of pre-processing should be matched with the parts geometry and therefore have to be frontloaded into the product and the tolerance design for their consideration.<br

On the Selection of Sensitivity Analysis Methods in the Context of Tolerance Management - Heling, Björn; Oberleiter, Thomas; Schleich, Benjamin; Willner, Kai; Wartzack, Sandro (Journal of Verification, Validation and Uncertainty Quantification, 2019)

On the Transient Effects at the Beginning of 3D Elastic-Plastic Rolling Contacts for a Circular Point Contact Considering Isotropic Hardening - Jüttner, Michael; Bartz, Marcel; Tremmel, Stephan; Wartzack, Sandro (Lubricants, 2022)
In a three-dimensional transient simulation of the elastic–plastic rolling contact, transient effects can be observed at the beginning of the rolling until a stationary state is reached after rolling for a length of several times the contact radius. In most cases, the steady-state regime is in focus of scientific investigations, whereas the transient effects are hardly considered. In the present work, those transient effects at the beginning of a frictionless rolling contact of a rigid sphere on an elastic–plastic plane are studied in detail. The analysis is limited to isotropic strain hardening. In particular, the changes of the contact pressure during rolling, as well as the plastic strain state and plastic deformations remaining after rolling are investigated. This is intended to get to the bottom of existing explanatory approaches from literature, which are based on the change in conformity. Beyond that, a more profound explanation of the transient effects is developed by identifying existing correlations.
Keywords: rolling contact; elastic-plastic; transient simulation; semi-analytical method; transient effects

Ontology-based approach for the provision of simulation knowledge acquired by Data and Text Mining processes - Kestel, Philipp; Kügler, Patricia; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (Advanced Engineering Informatics, 2019)
Numerical simulation techniques such as Finite Element Analyses are essential in today's engineering design practices. However, comprehensive knowledge is required for the setup of reliable simulations to verify strength and further product properties. Due to limited capacities, design-accompanying simulations are performed too rarely by experienced simulation engineers. Therefore, product models are not sufficiently verified or the simulations lead to wrong design decisions, if they are applied by less experienced users. This results in belated redesigns of already detailed product models and to highly cost- and time-intensive iterations in product development. Thus, in order to support less experienced simulation users in setting up reliable Finite Element Analyses, a novel ontology-based approach is presented. The knowledge management tools developed on the basis of this approach allow an automated acquisition and target-oriented provision of necessary simulation knowledge. This knowledge is acquired from existing simulation models and text-based documentations from previous product developments by Text and Data Mining. By offering support to less experienced simulation users, the presented approach may finally lead to a more efficient and extensive application of reliable FEA in product developmen
Keywords: Knowledge-based engineering; Simulation; Finite Element Analysis; Ontology-based knowledge representation; Text Mining; Data Mining

Ontology-based approach for the use of Intentional Forgetting in product development - Kügler, Patricia; Kestel, Philipp; Schon, Claudia; Marian, Max; Schleich, Benjamin; Staab, Steffen; Wartzack, Sandro (DESIGN 2018 - 15th International Design Conference, 2018)
When reusing product knowledge in design processes, developers have to decide which knowledge elements are relevant for a task. Thus, mechanisms of knowledge removal are vital for a successful reuse, but are not yet assisted by procedure models. This contribution introduces Intentional Forgetting as a methodology of intelligent removal processes in ontological knowledge bases. The aim is to support developers by providing relevant contents for reuse systematically. The development process of a testrig, that is highly based on knowledge reuse, is considered as use case.<br
Keywords: intentional forgetting; ontology; knowledge based engineering (KBE); data driven design

Ontology-based knowledge provision for decision support in product development - Pickel, Jessica; Gerschütz, Benjamin; Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)
The product development process confronts engineers with numerous decision problems. In this context, it is a challenge to consider all underlying heterogeneous data sources and decision methods to avoid incorrect decisions. Regarding these issues, ontologies offer the possibility to represent knowledge in a structured and adaptable way. Thus, this contribution proposes a methodical conception of a product development ontology and a novel approach to support developers in solving interrelated decision problems by providing relevant knowledge in a target-oriented way. In addition, the application is demonstrated by an exemplary development scenario for the axle design of a micromobility solutio
Keywords: Ontology; product development process; decision-making; requirements management; knowledge management

Ontology based modelling of the development process for the deduction of a property validation planning - Wartzack, Sandro; Westphal, Christoph (4. Grazer Symposium Virtuelles Fahrzeug, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.ontolo

On uncertainties in simulations in engineering design: A statistical tolerance analysis application - Walter, Michael; Wartzack, Sandro; Storch, Markus (Journal of Simulation, 2014)
Simulations not only facilitate new and unprecedented insights in highly sophisticated science areas, but also support product design in engineering in terms of improved functionality, cost and time issues. However, as a matter of fact, simulations examine limited excerpts of real systems with accompanying simplifications, abstractions and idealizations. Hence, there is a distinct need to be aware of upcoming risks in simulation outcomes caused by uncertainties. These influence every step of forward-thinking simulation design which is not only restrained by modeling practice but begins with reality perception itself.The intention of the paper is to embed an awareness of uncertainty in the context of simulation by linking major classes of uncertainty with uncertainties within simulations in engineering design. Besides the decisive inclusion of reality as the starting point, mathematic approaches are also used to understand how those uncertainty classes evolve through exponential knowledge creation of systems. The transfer to statistical tolerance analysis shall finally put emphasis on the practical classification of uncertainty, starting from data preparation via concept design and mathematical implementation to result depiction. In the end, the reader's conception of possible uncertainties in special simulation cases shall be sharpened which, vice versa, shall lead to even better and well-thought-out simulation outcomes. © 2014 The Society for Modeling and Simulation International.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.onunce
Keywords: statistical tolerance simulation; tolerance analysis; tolerance management; Uncertainties in simulation

Optimal control simulation predicts effects of midsole materials on energy cost of running - Dorschky, Eva; Krüger, Daniel; Kurfess, Nicolai; Schlarb, Heiko; Wartzack, Sandro; Eskofier, Björn; van den Bogert, Antonie J. (Computer Methods in Biomechanics and Biomedical Engineering, 2019)
Testing sports equipment with athletes is costly, time-consuming, hazardous and sometimes impracticable. We propose a method for virtual testing of running shoes and predict how mid- soles made of BOOSTTM affect energy cost of running. We contribute a visco-elastic contact model and identified model parameters based on load-displacement measurements. We pro- pose a virtual study using optimal control simulation of musculoskeletal models. The predicted reduction in energy cost of 1% for BOOSTTM in comparison to conventional materials is consistent with experimental studies. This indicates that the proposed method is capable of replacing experimental studies in the futur
Keywords: Virtual design; footwear; running; musculoskeletal simulation

Optimierung der tribologischen Effizienz von Lagerkomponenten mit modifizierten ta-C Beschichtungen - Polzer, Markus; Bartz, Marcel; Schulz, Edgar; Procelewska, Joanna; Wartzack, Sandro (Tribologie-Fachtagung, 2022)
Tetraedrisch amorphe Kohlenstoffschichten (ta-C-Schichten) werden bereits als reibungsreduzierende, verschleißbeständige Funktionsschichten auf tribologisch beanspruchten Komponenten genutzt. Jedoch stellen die gekrümmten und tribologisch hochbeanspruchten Oberflächen von Lagerkomponenten eine große Herausforderung dar, zumal diese zu deutlich erhöhten Eigenspannungen der ta-C Schichten und somit vorzeitiger Schichtdelamination beitragen. Insbesondere in geschmierten Systemen kann es während tribologischer Beanspruchung zu komplexen Wechselwirkungen zwischen Schichtsystem und Schmierstoffadditiven im tribologischen Kontakt (Tribokontakt) kommen. Dies kann zu unerwünschten Beeinträchtigungen der Lebensdauer und der Effizienz des vorliegenden tribologischen Systems führen. Die alleinige Betrachtung der Dotierungselemente und der mechanischen Eigenschaften der Schichten reichen nicht aus, um derartige Beeinträchtigungen prognostizieren zu können. Um dieses komplexe Verhalten besser verstehen und um weitere effizienz- und lebensdauersteigernde Effekte zu ableiten zu können, soll in diesem Beitrag der Einfluss unterschiedlicher Dotierungselemente im geschmierten Tribokontakt untersucht werden. Dafür werden, neben der Analyse der mechanischen Eigenschaften und Topologie, verschiedene dotierte ta-C-Schichtsysteme mit einer undotierten ta-C-Schicht verglichen. Die beschichteten Proben wurden gegenüber unbeschichteten 100Cr6 in verschiedenen Reibungs- und Verschleißprüfständen getestet. Als Schmierstoffe kamen ein vollformuliertes PKW-Öl auf PAO Basis einmal ohne und einmal mit molybdänhaltigen Additiven zum Einsatz. Die Ziele dieser Untersuchungen sind die Auswirkungen der Dotierungselemente auf das Reibungs- und Verschleißverhalten zu bestimmen, die in den Versuchen auf der Kontaktfläche auftretenden Mechanismen darzustellen und mögliche Wechselwirkungen im Tribokontakt abzuleiten. <

Optimization of Build Time and Support Material Quantity for the Additive Manufacturing of Non-Assembly Mechanisms - Hallmann, Martin; Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP Volume 84, 2019)
In the context of modern industrial manufacturing, Additive Manufacturing processes are gaining more and more importance. Thus, the required quantity of material as well as the production time, which is mainly influenced by the build time required for the layerwise manufacturing process, are decisive for a successful industrial application. At component level, various approaches for minimizing the build time and the quantity of material are discussed in literature and are yet implemented in commercial software tools for preprocessing, the so-called slicing software. However, there is a lack of suitable methods for expediting the manufacturing process of non-assembly mechanisms. Although the positions and orientations of the individual, mutually movable linkages of a mechanism, which are defined in the CAD model, have a significant influence on the resulting build time and quantity of support material, the optimization potential has remained untapped so far. Motivated by this shortcoming, the paper introduces a method for achieving minimum build time and support material quantity using a meta-heuristic optimization technique. By integrating a suitable slicing software in the optimization process, the analysis of build time and support material quantity is based on the machine code, which is adapted to the applied machine and its various settings of the process parameters. The novelty of the contribution can be found in the optimization of build time and support material quantity for the additive manufacturing of non-assembly mechanisms by determining an optimal positioning of the individual movable links for the manufacturing process. A parallel 3RRR mechanism serves as a case study to show the benefits and the applicablity of the proposed method.
Keywords: Optimization; Additive Manufacturing; Non-assembly mechanisms; Build time analysis

PADDME—Process Analysis for Digital Development in Mechanical Engineering - Gerschütz, Benjamin; Consten, Yvonne; Götz, Stefan; Wartzack, Sandro (Processes, 2024)
Design processes are always in motion, since more and more data-driven methods are used for various design and validation tasks. However, small and medium enterprises especially struggle with enhancing their processes with data-driven methods due to a lack of practical and easy-to-use analysis and redesign methods which can handle design process characteristics. In this paper, we present PADDME, which stands for process analysis for digital development in mechanical engineering, as a novel method that, in contrast to currently available analysis methods, considers those design process characteristics with respect to the integration of data-driven methods. Furthermore, a novel technology-readiness framework for digital engineering is introduced. Using the PADDME method, an industrial case study on introducing data-driven methods into the design and evaluation process chain is presented. The usability and novelty of the method are shown by the case study. Thus, PADDME allows a detailed capturing of current design processes and paves the way for process optimisation through data-driven methods. PADDME is a valuable method for advancing digital mechanical engineering processes in small and medium enterprises, and future work will focus on refining and expanding its application and evaluation.<br
Keywords: digital engineering; design process; business process management; process evaluation; digitalisation; data-driven method

Parametric Movement Synthesis: Towards virtual Optimisation of Man-Machine Interaction in Engineering Design - Wolf, Alexander; Wartzack, Sandro (Proceedings of the DESIGN 2018 15th International Design Conference, 2018)
A parametric movement synthesis approach is introduced, which allows the adaptation of a synthesized movement to a specific use case by varying geometrical parameters. This parametric movement synthesis empowers the product developer to optimize products purely virtually in terms of ergonomics and (dis-)comfort by using musculoskeletal simulation. We developed such a parametric model for a lifting movement to analyse several scenarios. The results of the analyses show to what extent this procedure may support the product developer to improve the man-machine interaction of products.<br
Keywords: human centred design; musculoskeletal simulation; movement synthesis; ergonomics; design for x (DfX)

Parametrische biomechanische Simulation am Beispiel des Radfahrens - Miehling, Jörg; Wartzack, Sandro (Beiträge zum 25. DfX-Symposium, 2014)
Shrinking product lifecycles and consequently shorter development times demand a decreasing number of iterations as well as physical prototypes to be manufactured. An efficient implementation of the virtual product development paradigm can contribute to achieve these objectives. As product designers do not need general design guidelines, but specific recommendations on how to design products, especially the field of user-centred design holds high potential for the virtual prediction and optimisation of user-product interactions. This contribution features the parametric biomechanical simulation of cycling creating an approach to directly compare design alternatives based on the inner strain condition of the human musculoskeletal system considering the given external boundary conditions.
Keywords: biomechanics; virtual product development; digital human modelling; parametric simulation

Patientenspezifische Modellierung des passiven Bewegungsapparates als Grundlage für die präoperative Abschätzung postoperativer Folgeerscheinungen des endoprothetischen Hüftgelenkersatzes - Scherb, David; Kurz, Marlene; Fleischmann, Christopher; Wolf, Alexander; Sesselmann, Stefan; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
During preoperative planning of total hip arthroplasty, the patients’ biomechanics is widely reduced to geometrical parameters. To provide the orthopedist more functional biomechanical parameters, a method is shown to model a patient-specific musculoskeletal human model via CT-/MRI-images in OpenSim. Main focus of this contribution is the setup of the passive musculoskeletal system. A generic human model and a segmented dataset of bones from the hip area serve as the basis for the modelling process. During the method the generic model is processed by scaling it to the anthropometry of the patient and adjusting subject-specific kinematics and shapes gathered from the segmented data. Finally, to reach the patient-specific representation the segmented bones are integrated into the mode
Keywords: Patient-specific modeling; Image-based model; Musculoskeletal human model; OpenSim; Total Hip Arthroplasty

Patient-Specific Modelling for Preoperative Estimation of Hip Mechanics for Improved Planning of Total Hip Endoprosthesis Using Multibody Simulations - Leher, Irina; Fleischmann, Christopher; Scherb, David; Kollerer, Marius; Miehling, Jörg; Wartzack, Sandro; Sesselmann, Stefan (International Conference on Emerging Technologies and Future Systems V, 2021)
The increasing number of total hip arthroplasty and the demographic change lead to a rise in the number of revision surgeries. Implementation of musculoskeletal models in surgical planning could improve quality of life after revision surgery, due to the consideration of the individual patient’s biomechanical conditions. In multibody simulation, a distinction is made in the degree of individualization between the anthropometric and patient-specific scaling of musculoskeletal models. In this study, the differences in moment arm length, hip joint reaction force, muscle activation and forces between these two musculoskeletal models were analyzed. Due to high influences of individualized anatomical parameters on simulation results, it is recommended to consider patient-specific biomechanics for future total hip arthroplasty planning.
Keywords: Biomechanics; Magnetic resonance imaging; Maximum isometric force; Muscle segmentation; Musculoskeletal model; OpenSim; Orthopaedics; Patient-specific modelling; Total hip arthroplasty

Phasenübergreifende Unterstützung der Elektromotorenentwicklung mittels eines Assistenzsystems - Tüchsen, Johann; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2021)
Im Zuge der Elektrifizierung des Automobils muss, neben dem Traktionsantrieb, eine große Vielfalt an kleineren Elektromotoren innerhalb kurzer Zeit vom Elektromotorenhersteller angeboten und entwickelt werden. Dieser Problemstellung wird in diesem Beitrag mit einem wissensbasierten Assistenzsystem begegnet, das die Entwicklung von den Anforderungen bis hin zum fertigen Motor phasenübergreifend unterstützt. Dabei wird das modulare, web-basierte Konzept vorgestellt und anschließend seine Anwendung exemplarisch erläutert. Das beim Fallgeber eingesetzte System führt dabei zu einer höheren Transparenz durch standardisierte Dokumentationen und einer fehlerreduzierten und effizienteren Auslegung.

Potential beschichteter Kunststoffe zur Reibungs- und Verschleißreduzierung an Wälzlagerkäfigen - Sander, Thomas; Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro (VDI-Berichte 2202, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.potent

Potentiale datengestützter Methoden zur Gestaltung und Optimierung mechanischer Fügeverbindungen - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
Due to the increasing requirements on lightweight constructions, the demands for efficient joining processes are constantly rising. Therefor cold forming processes provide a faster and less expensive alternative to established thermal joining methods. In order to guarantee the joining reliability, not only the selection of a suitable process, but also the design and dimensioning of the joint is crucial. As a possible solution, data-driven methods offer procedures for the structuring of data and the targeted analysis of product features and key variables. Motivated by this, the paper shows a literature-based approach by using the example of clinching to illustrate the potentials and limits of data-based methods for the design and optimization of mechanical joining processes.<br
Keywords: Clinching; Data-driven optimization; Multiobjective Optimization

Potentiale für den Leichtbau durch Beschichtung von Kunststoffen - Sander, Thomas; Wartzack, Sandro (Design for X. Beiträge zum 21. DfX-Symposium, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.potent

Potentiale von NLP-basierten Assistenzsystemen im Anforderungsmanagement - van Remmen, Judith Sophie; Horber, Dennis; Pickel, Jessica; Götz, Stefan; Wartzack, Sandro (Tagungsband zum Stuttgarter Symposium für Produktentwicklung SSP 2023, 2023)
Die Anwendung und Integration bestehender NLP-basierter Ansätze in das Anforderungsmanagement wird derzeit durch verschiedene Faktoren, darunter mangelndes Expertenwissen und Know-how, gehemmt. Motiviert durch das Fehlen einer Entscheidungshilfe für die Konzeptionierung NLP-basierter Assistenzsysteme fokussiert der vorliegende Beitrag die Entwicklung einer systematischen Handlungsempfehlung zur Potentialidentifikation und Risikominimierung. Die Entscheidungshilfe berücksichtigt dabei die Unternehmensdefinition hinsichtlich der Art des Unternehmens, dessen Produkttypologie und Referenzsysteme. Sie dient dazu, potentiell kritische Anforderungen zu identifizieren und daraus Voraussetzungen für die Umsetzung des NLP-unterstützten Soll-Prozesses abzuleiten. Die qualitative Anforderungs- erfüllung kann dabei als Indikator für das Potential oder Risiko in der Entscheidungsfindung genutzt werden. Diesbezüglich können bereits Herausforderungen für die eigene Implementierung des konzeptionierten Assistenzsystems oder die Beauftragung eines Softwarezulieferers abgeleitet und klar kommuniziert werden. Das entwickelte Konzept wird anhand eines akademischen Beispiels kritisch diskutier
Keywords: Natural Language Processing; Anforderungsmanagement; Digital Engineering

Potentiale von Simulationsdatenmanagementsystemen zur KI-gestützten Vorhersage und Bewertung von Produkteigenschaften - Gerschütz, Benjamin; Sauer, Christopher; Götz, Stefan; Hörmann, Matthias; Wartzack, Sandro (2023)

Potential of arc evaporated TiO2 as an interlayer and its performance in dry sliding - Vierneusel, Bernd; Sander, Thomas; Tremmel, Stephan; Wartzack, Sandro (Proceedings of the 15th Nordic Symposium on Tribology, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.potent

Prädiktive biomechanische Simulation am Beispiel von ergonomischer Produktoptimierung in Burkina Faso / Predictive biomechanical simulation based on the example of ergonomic product optimization in Burkina Faso - Meißner, Ruth; Wolf, Alexander; Wartzack, Sandro; Miehling, Jörg (Konstruktion, 2022)
In der Produktentwicklung gewinnen nutzerzentrierte Designprozesse zunehmend an Bedeutung. Muskuloskelettale Simulationstools ermöglichen die Abbildung und Simulation des menschlichen Bewegungsapparats während der Nutzer-Produkt-Interaktion auf Basis experimentell erhobener Bewegungsdaten. Durch prädiktive Methoden der Bewegungserzeugung soll der Aufwand der experimentellen Bewegungserfassung reduziert und eine proaktive sowie virtuelle Analyse von Produktergonomie und Gebrauchstauglichkeit ermöglicht werden. Dieser Beitrag präsentiert eine solche prädiktive Methode zur Abbildung der Nutzer-Produkt-Interaktion. Diese wurde für die Designoptimierung eines Trikes für Menschen mit Behinderungen in Burkina Faso entwickelt. In product development, the impact of user-centered design processes is growing rapidly. Biomechanical simulation enables the realistic representation of the human musculoskeletal system during user-product interactions based on experimentally captured motion data. Using predictive methods for motion generation, the effort for experimental motion capture can be reduced enabling a proactive and virtual analysis of product ergonomics and usability. This paper presents such a predictive method for modelling user-product interaction. This was developed for the design optimisation of a tricycle for persons with disabilities in Burkina Fas

Praxisorientierte Lehre: Konzeptentwicklung innovativer Produkte (KIP) - Wartzack, Sandro; Luft, Thomas (WiGeP News, 2014)
Praxisorientierte Lehre: Konzeptentwicklung innovativer Produkte (KIP) Innovative Konzepte zur Verbesserung der Sicherheit von Personen im Straßenverkehr
Keywords: Lehre; Konzeptentwicklung; innovative Produkte

Predicting EHL film thickness parameters by machine learning approaches - Marian, Max; Mursak, Jonas; Bartz, Marcel; Profito, Francisco J.; Rosenkranz, Andreas; Wartzack, Sandro (Friction, 2022)
Non-dimensional similarity groups and analytically solvable proximity equations can be used to estimate integral fluid film parameters of elastohydrodynamically lubricated (EHL) contacts. In this contribution, we demonstrate that machine learning (ML) and artificial intelligence (AI) approaches (support vector machines, Gaussian process regressions, and artificial neural networks) can predict relevant film parameters more efficiently and with higher accuracy and flexibility compared to sophisticated EHL simulations and analytically solvable proximity equations, respectively. For this purpose, we use data from EHL simulations based upon the full-system finite element (FE) solution and a Latin hypercube sampling. We verify that the original input data are required to train ML approaches to achieve coefficients of determination above 0.99. It is revealed that the architecture of artificial neural networks (neurons per layer and number of hidden layers) and activation functions influence the prediction accuracy. The impact of the number of training data is exemplified, and recommendations for a minimum database size are given. We ultimately demonstrate that artificial neural networks can predict the locally-resolved film thickness values over the contact domain 25-times faster than FE-based EHL simulations (R-2 values above 0.999). We assume that this will boost the use of ML approaches to predict EHL parameters and traction losses in multibody system dynamics simulations.
CRIS-Team WoS Importer:2022-06-24

Prediction of Rolling Bearing Cage Dynamics Using Dynamics Simulations and Machine Learning Algorithms - Schwarz, Sebastian; Grillenberger, Hannes; Tremmel, Stephan; Wartzack, Sandro (Tribology Transactions, 2021)
Cage instability or highly dynamic cage movement can have a strong influence on the performance of rolling bearings. In addition to very loud and disturbing noises (“squeal”), bearing failure due to cage fracture can occur. This article deals with two topics: the general classification of cage motions and the prediction of application-dependent cage motions to prevent cage instability during operation. The dependencies of the unstable cage movement on the bearing’s load and geometric characteristics of the cage are analyzed using a large number of sophisticated simulations, based on multibody dynamics. To evaluate the cage movements, first a key figure called the “cage dynamics indicator” (CDI) is introduced, which is used to classify the simulation results by means of quadratic discriminant analysis into three types “unstable,” “stable,” and “circling” (= classification of cage motion). Second, a machine learning algorithm trained and tested on the basis of more than 4,000 simulation results enables a time-efficient prediction of the physical correlations between bearing load and cage properties and the resulting cage dynamics (= prediction of cage motion). A comparison of the calculated cage dynamics with the results of an optical measurement of the cage dynamics rounds off this article. This comparison illustrates the high quality of the simulation models and the training data used for machine learning.
Keywords: Wälzlager; Dynamiksimulation; Käfiginstabilität; Digitale Bildkorrelation; Maschinelles Lernen

Proactive Integration of User Data into Engineering Processes - A Generic Approach and Specific Examples - Wolf, Alexander; Buker, Tina; Molz, Carla; Scherb, David; Wartzack, Sandro; Miehling, Jörg (Human-Automation Interaction. Manufacturing, Services and User Experience, 2022)
User-centered design (UCD) describes an approach, which aims to increase customer satisfaction, comfort, usability, user experience, aesthetics and perceived quality by enhancing the fit between products and their users in the respective context of use. To achieve this goal, a multitude of different methods can be applied. All these methods integrate the user into the design process, in order to evaluate and improve the user-product interaction. This integration can be achieved via two different approaches. The classical approach on the one hand, integrates the user personally, e.g. focus groups, user tests, interviews or surveys. The proactive approach on the other hand, integrates the user in form of a user model, which is universally applicable for one aspect of user-product interaction, e.g. digital human models for the evaluation of physiological comfort and ergonomics or generic high-level guidelines for enhancing positive product emotions. The proactive approach is of great interest for industrial and engineering design, as it offers time- and cost-efficient user integration especially in the early, predominantly virtual phases of product design. This chapter takes a closer look at the proactive approach and presents four specific examples concerning computer aided ergonomics, assistive device design, preoperative evaluation of implants and product-related user stigma.
Keywords: User-centered design; User-product interaction; Proactive user integration

Procedural Concept Design with Computer Graphic Applications for Light-Weight Structures using Blender with Subdivision Surfaces - Denk, Martin; Mayer, Johannes; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
In today's concept development, it is important to develop customer requirements in advance via prototypes with little effort. Some of these requirements can be pre-tested through virtual product development, although creating them with computer aided design (CAD) software can be time-consuming. In the context of this work, tools commonly used in animation design are adapted to the early phase of virtual product development. This is primarily to limit the time effort of prototyping in product development. However, the models must be led to non-intersecting 3D manifolds to ensure a transfer into computer aided engineering (CAE) or possible manufacturing. Therfore in this work, so-called procedural designs based on computer graphic applications are described and examined for their suitability for CAE.<br

Procedure Model for Structured Relational Modeling of Requirements to Support Requirements-oriented Decision Making - Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2021)
The development of complex technical systems is characterized by a large number of system elements as well as their interactions. With regard to requirements management, many requirements have to be considered, which can have different relations to each other. If these requirements are used as basis for criteria in the decision making process, these relations must also be considered in the multi-criteria evaluation of product alternatives. Therefore, a computer-aided approach is presented in this paper, which allows the systematic modeling of requirement interactions focusing on multi-criteria decision making. For this purpose, basic relation types are identified, which are used to model submatrices in order to derive the Requirement Relation Matrix (RRM). Matrix-based as well as graph-based visualization methods are used for the RRM in order to improve the alternatives with the knowledge about the relational linkage. In addition, the effects of changes in requirements can be transferred to the decision making process. The approach is exemplarily applied to the extension of a test laboratory by a test benc
Keywords: Decision making; Requirements; Dependency; Graph visualization; Product modelling/models

Process and machine selection in sampling-based tolerance-cost optimisation for dimensional tolerancing - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (International Journal of Production Research, 2021)
Tolerance-cost optimisation, i.e. using optimisation techniques for tolerance allocation, is frequently used to determine a cost-efficient tolerance design that can meet the stringent requirements on high-quality products. Besides various manufacturing aspects, the selection of available alternative machines and processes hold great potential for an early optimal process planning by identifying their best combination. Although machine/process selection by minimum cost and mixed-integer optimisation is often applied in theory and practice, their proper implementation in tolerance-cost optimisation based on sampling techniques for tolerance analysis, which can statistically consider various individual part tolerance distributions, has not been studied so far. With the aim to overcome this drawback, this article focuses on machine/process selection in sampling-based tolerance-cost optimisation for dimensional tolerances considering the respective machine characteristics of several machine options, e.g. process capabilities and manufacturing distributions. A comparative study proves that machine/process selection by mixed-integer optimisation leads to minimum total manufacturing costs since it covers the whole search space, including all technically feasible machine combinations and thus identifies the global cost minimum.
CRIS-Team Scopus Importer:2021-07-30
Keywords: alternative machine/process selection; mixed-integer optimisation; optimal tolerance allocation; process planning; statistical tolerance analysis; Tolerance-cost optimisation

Process-oriented tolerancing - A discrete geometry framework - Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 19th International Conference on Engineering Design, 2013)
Since the requirements on technical products steadily increase, there exists a growing need for considering all effects which may lead to reduced product quality in engineering design. Geometric variations are a main contributor to malfunction and decreased product quality and have thus to be limited by geometric tolerancing. However, geometric tolerances are a source of disharmonies since manufacturing requires loose tolerances for realizing low manufacturing costs whereas design tends to choose tight tolerances for ensuring the product quality. This paper focuses on an integrated view on process-oriented tolerancing considering information from all stages of the product origination. After highlighting barriers for process-oriented tolerancing, a framework is proposed, which integrates process information in a skin model inspired tolerance analysis approach. This framework takes all sources of geometric deviations into account when evaluating their effects on the product quality. Thereby, manufacturing and assembly aspects can be considered in tolerancing during engineering design, which helps to reduce disharmonies, save manufacturing costs, and increase the product quality.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.proces
Keywords: Computer aided design; Computer aided tolerancing; Design for x; Robust design

Produkt- und Prozessdatenmodellierung im Kontext der Blechmassivumformung - Breitsprecher, Thilo; Meinel, Andreas; Thummet, Martin; Wartzack, Sandro (Entwerfen Entwickeln Erleben - EEE2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.produk

Properly test planning on the basis of a combined process and product modeling - Wartzack, Sandro; Westphal, Christoph (8th International Conference on Product Lifecycle Management 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.proper

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering, 2022)

Prüfstand für den Tür-Seitencrash - Wartzack, Sandro (Automotive Engineering Partners, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.FT.FT-KLMEFK.prfsta

Realization of Modern Educational Concepts in Engineering Design - Meerkamm, Harald; Tremmel, Stephan; Wartzack, Sandro; Stockinger, Andreas (Proceedings of ICED 09, the 17th International Conference on Engineering Design, Vol. 10: Design Education and Lifelong Learning, 2009)
This paper gives an overview of engineering design education at University Erlangen-Nuremberg in order to prompt a discussion about the structure and scope of the proposed educational concept compared to other approaches. Due to the transformation of the traditional German degree programs to an educational system based on two cycles (bachelor/master), a new curriculum had to be performed. The curricula and the according lectures were derived based on a review of demands on product developers. This review and the resulting educational concept are presented in this paper. While setting up the lectures, one of the aims for education in engineering design was to build up and emphasize a close relationship between engineering design, engineering mechanics, materials engineering and production technology. Some of the courses, especially a CAD course and a product development and design project, are explained more in detail. In the first mentioned course, a modern way of computer-supported, "blended learning" was realized. In the second mentioned course, new ground was broken by applying subject-specific knowledge in combination with soft skills by offering an obligatory project already in the bachelor program.
UnivIS-Import:2015-04-16:Pub.2009.tech.FT.FT-KLMEFK.realiz
Keywords: Curriculum redesign; Engineering design education; Methodological and practical training

Reconstruction of Topology Optimized Geometry with Casting Constraints in a Feature-Based Approach - Mayer, Johannes; Denk, Martin; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Topology Optimization (TO) is an established method for the development of high strength and lightweight structural components. However, its results have to be geometrically revised to obtain a computational model that meets product development requirements. Design has to be in accordance with manufacturing constraints. Geometry reconstruction therefore still is a typically manual and tedious task, but increasingly supported by computational and automated approaches. In this paper, the inclusion of a casting constraint in an automated Medial Axis based reconstruction method is presented. Since the Medial Axis provides cross-section values by the computation of maximally inscribed spheres, this information is used for geometry reconstruction and even further for the purposeful adaption of the cross-section to match Heuver's circle method. Thereby, the directed solidification of molten material is considered. With a predefined feeder position, the demonstrator of a suspension control arm is used to show the application of the method. Resulting CAD-models are also structurally evaluated for their stiffness characteristic
Keywords: Topology Optimization; Medial Axis Transform; Computational Design Methods; Computer Aided Design (CAD); Lightweight Design

Reibungsreduzierung in EHD-Kontakten durch mikrostrukturierte Bauteiloberflächen - Auslegung, Gestaltung und umformtechnische Herstellung - Tremmel, Stephan; Marian, Max; Zahner, Michael; Weschta, Martin; Engel, Ulf; Wartzack, Sandro; Merklein, Marion (58. Tribologie-Fachtagung. 2017, Son-derband Abschlusskolloquium „Ressourceneffiziente Konstruktionselemente“ SPP 1551 der DFG, 2017)
Gezielt eingebrachte, definierte Oberflächenmikrostrukturen bieten in elastohydrodynamischen (EHD) Kontakten Potential zur Reibungsreduzierung und können damit die Energieeffizienz technischer Systeme erhöhen. Um die größtmögliche Wirksamkeit zu erreichen, sind diese Oberflächenmikrostrukturen auf die jeweilige Anwendung abzustimmen. Die Realisierung theoretisch genauer Mikrostrukturen ist zudem durch die Fertigungstechnik limitiert. Des Weiteren bestimmt das Verschleißverhalten der Mikrostrukturen im Einsatz die Bauteillebensdauer. Für einen wirksamen Einsatz über den gesamten Produktlebenszyklus hinweg bedarf es somit eines grundlegenden Verständnisses der Zusammenhänge zwischen Gestaltung, Herstellung und Einsatzverhalten oberflächenstrukturierter Bauteile. Vor diesem Hintergrund werden im vorliegenden Beitrag ein Simulationsansatz zur Untersuchung der Wirkweise von Oberflächenmikrostrukturen vorgestellt sowie eine Methodik abgeleitet, die die systematische Auslegung und Gestaltung von Oberflächenstrukturen erlaubt. Die Methodik erlaubt die Berücksichtigung individueller tribologischer Belastungskollektive und fertigungstechnischer Restriktionen. Die Fertigungsrestriktionen bei der Strukturerzeugung wurden im Hinblick auf industrielle Maßstäbe für einen Mikroprägeprozess ermittelt. Auf Basis tribologischer Untersuchungen auf einem Nocken/Stößel-Komponentenprüfstand erfolgt die Beurteilung des Reibungs- und Verschleißverhaltens der mikrostrukturierten Bauteil
LFT Import::2019-08-05 (2259)
Keywords: Elastohydrodynamik; Mikrostrukturen; Mikroprägen

Reinforcement Learning As an Alternative for Parameter Prediction In Design for Sheet Bulk Metal Forming - Dworschak, Fabian; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Volume 2: 42nd Computers and Information in Engineering Conference (CIE), 2022)
This contribution presents an approach and a case study to compare Reinforcement Learning (RL) and Genetic Algorithms (GA) for parameter prediction in Sheet Bulk Metal Forming (SBMF). Machine Learning (ML) and Multi-Objective Optimization (MOO) to provide different points of view for the prediction of manufacturing parameters. While supervised learning depends on sufficient training data, GA lack the ability to explain how sufficient parameters were achieved. RL could help to overcome both issues, as it is independent from training data and can be used to learn a policy leading towards suitable parameter combinations, which can be tracked through the solution space. To probe RL in terms of feasibility for parameter prediction and necessary training effort SBMF serves as an appropriate use case because solution and objective function space are multidimensional, and their relations are challenging for MOO. The results of a Reinforcement Learner and a GA are compared and discussed to answer the question under which circumstances RL can provide an alternative for parameter prediction.<br

Reinforcement Learning for Engineering Design Automation - Dworschak, Fabian; Dietze, Sebastian; Wittmann, Maximilian; Schleich, Benjamin; Wartzack, Sandro (Advanced Engineering Informatics, 2022)
Reinforcement Learning has proven to be capable of solving complex tasks like playing video games, robotics control, speech or image recognition and processing. Transferring Reinforcement Learning into engineering design helps to overcome two current issues of data-driven Design Automation in engineering design. First, dealing with sparse training data resulting from differing design samples. Second, overcoming the limited number of samples in the training data as consequence of short or insufficient product history. To introduce an alternative approach for Design Automation, this contribution studies feasiblity, training effort and transferability of Reinforcement Learning in engineering design. The presented method maps engineering requirements and parametric models into learning environments and provides a novel approach for design automation. In addition to that, the contribution summarises the hyperparameters, which design engineers have to set prior to training, and introduces a novel transfer learning concept for Reinforcement Learning in related design tasks. The support is probed by design tasks of performance-oriented bike parts. Case-independent indicators are presented to estimate the case-specific training effort, the effects of hyperparameter variation and the effects of transferring a pretrained agent to related design tasks. Finally, the findings are used to compare Reinforcement Learning to other data-independent Design Automation approaches to assess potential fields of application for Reinforcement Learning in engineering desig
Keywords: Reinforcement Learning; Design Automation; Deep Q-learning

Requirement analysis for contextual management and supply of process- and design knowledge - a case study - Luft, Thomas; Wartzack, Sandro (DS 70: Proceedings of DESIGN 2012, the 12th International Design Conference, 2012)
This paper provides a methodology for analysing requirements for a knowledge management system that consists basically of a management and search functionality. On basis of a theoretical developed methodology, a requirement analysis for a knowledge management system in an industrial case study is presented. Therefore an analysis of the knowledge and information basis as well as of the needs and mentalities of employees is conducted. As a result all requirements for the management functionality and the search functionaly of a holistic knowledge management system are identified and described.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.requir
Keywords: Case study; Knowledge management; Product development process; Requirement analysis

ResNet networks for plausibility detection in Finite Element simulations - Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Proceedings of NordDesign 2022: How Product and Manufacturing Design Enable Sustainable Companies and Societies, 2022)
Nowadays, the efficient execution of product design and process planning activities without the extensive use of Finite Element (FE) simulation is hardly conceivable. The ability to virtually test components at an early stage can reduce costs while significantly increas-ing product quality. In addition, the current business environment promotes ever shorter development times coupled with a greater variety of products. This combination poses the risk that more and more inexperienced users from the field of product design have to perform simulation and validation tasks. An idea to support the less experienced users is to automatically check their FE models and simulations for plausibility. This helps to con-duct simulations independently by alerting the designers when major errors occur. One approach to the automatic plausibility check of FE simulations utilizes simulations that have already been calculated as a database and applies them to train a Deep Learning model that classifies the new simulations into plausible and non-plausible. This requires converting the existing data into a uniform format by the projection method, so it is read-able for a Deep Learning network. However, for this method to be applied in an industrial environment, a high recognition accuracy is required for unknown simulations. Therefore, the goal of this paper is to investigate the ability of a new Deep Learning architecture to check the plausibility of FE simulations. The objective is to achieve the highest possible recognition accuracy. So far, mainly serial network types have been used for this procedure, which will now be extended by the application of ResNet networks. These have different paths in their structure through the addition of skip-connections, allowing for a theoretically better-trained model. This will be analysed together with a new dataset of simulations. These components for the structural mechanical simulation are geometrically varied and served to evaluate the new network types and their achieved accuracy.
CRIS-Team Scopus Importer:2022-12-09
Keywords: data driven design; data mining; Deep Learning; Plausibility checks; structural analysis

Result Visualization and Documentation of Tolerance Simulations of Mechanisms - Walter, Michael; Pribek, Michael; Sprügel, Tobias; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), Vol. 4: Design for X, 27.-30. Juli 2015, Mailand, 2015, S. 11-20., 2015)
Imprecise manufacturing processes lead to products which differ in their dimensions and shape. As a consequence, the product developer has to specify appropriate tolerances to limit these deviations and thus to ensure the adequate functional and aesthetic quality of the final products. These tolerances, however, affect several departments of a company, such as manufacturing, technical procurement, metrology or quality control. Hence, insights gained during tolerance analysis and tolerance synthesis must be documented and visualized in a clear and comprehensive manner toward all departments involved. This paper presents an academic recommendation on a comprehensive visualization and documentation of the results of statistical tolerance simulations, focusing on systems in motion which underlie different kinds of deviations. These so-called mechanisms demand a more detailed result visualization than common static (non-moving) systems. The implemented academic tool called “Tol/Mech–insight” provides a comprehensive result visualization and documentation for tolerance simulations of mechanisms and may serve as a sufficient basis for decision-making among experts in various departments.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.result
Keywords: Robust design; Tolerance representation and management; result visualization

Retrieving knowledge and information by using a systematic search interface - An industrial case study - Luft, Thomas; Wartzack, Sandro (NordDesign 2012 - Proceedings of the 9th NordDesign Conference, 2012)
Knowledge and information are nowadays the most important factors for the development of modern and innovative products. Therefore the efficient management and contextual supply of knowledge is nowadays becoming increasingly essential because more knowledge and information needs to be considered by engineers. However, there are a variety of problems in handling and retrieving knowledge and information in particular in the engineering design process. Existing IT systems do not meet the requirements of the users or do it only in an insufficient way. In this paper which is based on an industrial case study the identification and in particular the classification of “Knowledge and Information-Objects” of the considered company is described. These two steps are one of the most important preconditions for a holistic and computer-based knowledge management system from a management and a supply oriented view. In order to customise a systematic search interface that meets the requirements of the employees, an appropriate number of workshops with experts from different departments have to be organised. The focus of this paper is on a (combined) content- and source-based systematic search interface for knowledge and information retrieval.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Industrial case study; Information retrieval; Information storage; Knowledge management; Product development; Requirement analysis

Retrieving knowledge and information by using a systematic search interface – an industrial case study - Luft, Thomas; Wartzack, Sandro (DS 71: Proceedings of NordDesign 2012, the 9th NordDesign conference, 2012)
Knowledge and information are nowadays the most important factors for the development of modern and innovative products. Therefore the efficient management and contextual supply of knowledge is nowadays becoming increasingly essential because more knowledge and information needs to be considered by engineers. However, there are a variety of problems in handling and retrieving knowledge and information in particular in the engineering design process. Existing IT systems do not meet the requirements of the users or do it only in an insufficient way. In this paper which is based on an industrial case study the identification and in particular the classification of “Knowledge and Information-Objects” of the considered company is described. These two steps are one of the most important preconditions for a holistic and computer-based knowledge management system from a management and a supply oriented view. In order to customise a systematic search interface that meets the requirements of the employees, an appropriate number of workshops with experts from different departments have to be organised. The focus of this paper is on a (combined) content- and source-based systematic search interface for knowledge and information retrieval.
Keywords: knowledge management; product development; requirement analysis; information storage; information retrieval; industrial case study

Reverse Engineering - Prozess, Technologien und Anwendungsfälle - Katona, Sebastian; Koch, Michael; Wartzack, Sandro (16. Bayreuther 3D-Konstrukteurstag, 2014)
Keywords: Reverse Engineering

Rheological behavior of an artificial synovial fluid – influence of temperature, shear rate and pressure - Rothammer, Benedict; Marian, Max; Rummel, Florian; Schroeder, Stefan; Uhler, Maximilian; Kretzer, J. Philippe; Tremmel, Stephan; Wartzack, Sandro (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
Despite the excellent clinical performance of joint replacements, wear-induced aseptic loosening is a main cause of premature implant failure. Tribological testing is usually carried out using bovine serum as an artificial synovial fluid. In order to gain new insights into the suitability to simulate human synovial fluid and provide recommendations for the conditions of tribological testing, accurate rheological measurements on the influence of temperature, shear rate and pressure on density and viscosity were performed. Thus, a temperature dependence of density and viscosity could be verified, whereas both values decreased with higher temperatures. The temperature dependency of viscosity could be approximated by an Arrhenius model. Moreover, shear-thinning characteristics could be demonstrated and fitted to a Cross model, which agreed well with investigations on human synovial fluid reported in literature. Furthermore, an anomaly of pressure dependence of viscosity was found and correlated with the behavior of water as a main constituent. At room temperature, the viscosity initially decreased to a minimum and then increased again as a function of pressure. This was no longer distinct at human body temperatures. Consequently, the present study confirms the suitability of bovine serum as a substitute synovial fluid and emphasizes the importance of realistic testing conditions in order to ensure transferability and comparability.<br
Keywords: Bovine serum; Biomedical rheology; Temperature dependence; Shear-thinning; Pressure dependence

Roadmap für die Entwicklung einer Methodik zur dualen Nutzerintegration - Schröppel, Tina; Miehling, Jörg; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung SSP 2019: Stuttgart, 16. Mai 2019 | Wissenschaftliche Konferenz, 2019)
Um den Herausforderungen wachsender und umkämpfter Märkte begegnen zu können, müssen Produkte heutzutage mehr denn je die Bedürfnisse der Nutzer erfüllen. Neben einer ergonomischen Produktgestaltung treten dabei zunehmend subjektive Faktoren in den Vordergrund. Ein gut für den Nutzer ausgelegtes Produkt berücksichtigt somit physiologische wie subjektive Bedürfnisse gleichermaßen. Bisherige nutzerzentrierte Ansätze fokussieren sich jedoch häufig auf nur einige wenige Nutzeraspekte. Es fehlt demnach an einer systematischen Vorgehensweise, mit der eine objektive Absicherung einer subjektiv-nutzergerechten und zugleich körperlich-geeigneten Produktgestaltung sichergestellt werden kann. Die duale Nutzerintegration stellt eine solche Methodik dar. Basierend auf einer kontextneutralen Nutzer- und Produktbeschreibung sowie einer physiologischen und subjektiven Produktbewertung wird eine zielgruppenorientierte Produktgestaltempfehlung gegeben. Der vorliegende Beitrag stellt die Roadmap für die Entwicklung der Methodik dualer Nutzerintegration inklusive dem hierfür benötigten Forschungsbedarf vor.<br
Keywords: Nutzerintegration; subjektive Produktgestaltung; physiologische Produktgestaltung

Roadmap to Consider Physiological and Psychological Aspects of User-product Interactions in Virtual Product Engineering - Wartzack, Sandro; Schröppel, Tina; Wolf, Alexander; Miehling, Jörg (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
To successfully facilitate user-centred design, a multitude of different aspects has to be considered, from purely physiological to psychological-emotional factors. The overall aim is to increase the customer satisfaction by enhancing the fit between products and their users in the respective context of use. Further virtualisation of user-centred design processes holds the potential to convey the concepts of frontloading and predictive engineering from classical product engineering. Our vision is to facilitate a comprehensive consideration of user-product interactions in virtual product engineering operationalised by the mission to develop methods and tools to assess and design user-product interactions according to physiological and psychological aspects. A variety of work has already been done to model musculoskeletal user groups, to configure, predict, simulate and optimise physical user-product interactions, to integrate such models into CAD or to map individual subjective values to product design. Nevertheless, there are still research areas to be addressed to enable a comprehensive implementation of the mentioned approach. These are discussed in the present contribution
Keywords: User centred design; Simulation; Integrated product development; Affective Engineering; Biomechanical digital human models

Robust-Design-Optimization of mechanisms based on kinematic requirements considering uncertainties - Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (15th CIRP CAT 2018 - CIRP Conference on Computer Aided Tolerancing, 2018)
Today the market environments require products to be developed by multidisciplinary teams, which have to consider contradictory requirements in drastically reduced times-to-market. In this context, the importance of robust design ambitions, which strive for developing products that are insensitive to variations from manufacturing, assembly and use processes, increases. In this paper, a novel methodology for the robust-design optimization of a mechanism is introduced, which allows optimizing the mechanism so that contradictory requirements are met despite the presence of geometrical deviations and uncertainties during use. The result of this optimization process are mechanisms, which do not only fulfill kinematic requirements, but are also insensitive to geometrical part deviations and uncertain ambient parameter
Keywords: Tolerance-CostOptimization; Skin Model Shapes; Process-oriented Tolerancing

Robust design proposal by the use of structural topology optimization considering uncertainties of input parameters and boundary conditions - Stangl, Thomas; Walter, Michael; Wartzack, Sandro; Schneyer, Thomas (Proceedings of the 19th International Conference on Engineering Design, 2013)
Specifying a product's optimal mechanical and functional design primary depends on the requirements defined by the future operating conditions. In today's product design process the usage of topology optimization is a widely applied computer aided method to define an optimal design considering these requirements. However, in an early design stage, input parameters for this structural optimization process (e.g., operation conditions) are usually uncertain. Consequently, the resulting design is not optimal. This paper focuses on a detailed investigation of uncertainties in structural topology optimization. Hence, the different kinds of uncertainties and their effects on the resulting designs are considered in detail. Furthermore, a methodology is presented, which enables the consideration of uncertainties using e.g., a statistical investigation of the topology optimization results and a sensitivity analysis-based result visualization. Therefore, a cam drive rocker arm of a combustion engine is analyzed in a case study. Finally, several recommendations are derived, supporting the product developer to define a robust initial design, causing less computational and time expense.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.robust
Keywords: Design engineering; Early functional validation; Optimisation; Robust design; Uncertainty in topology optimization

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (International Journal of Advanced Manufacturing Technology, 2022)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Clinching; FEM; Machine learning; Mechanical joining; Robust product design

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing, 2022)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
CRIS-Team Scopus Importer:2022-11-04
Keywords: joining by forming; pin joining; robustness analysis; versatile joining process

Robustness evaluation in early phases of product development - Li, Jiahang; Horber, Dennis; Grauberger, Patric; Götz, Stefan; Wartzack, Sandro; Matthiesen, Sven (2023)

Robustness Evaluation of Product Concepts based on Function Structures - Götz, Stefan; Hartung, Jonas; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Due to the varying environment conditions as well as the manufacturing induced deviations, the properties of products vary. In order to still meet the increasingly tightening of functional requirements, tolerancing as well as Robust Design practices became integral parts of the product development. However, despite the fact that the robustness of a product is mainly determined by its conceptual design in early design stages, these activities are usually carried out at the end of the design process. In order to overcome this shortcoming, this contribution shows a method that supports the selection of robust principal solutions and thus contributes to the design of product concepts, which are less sensitive to variations. The novelty lies in the adaption and combination of robust design criteria for the quantitative robustness evaluation in the conceptual design stage. First the product characteristics, which are relevant for the product robustness are determined on the basis of the function structure. By using an adopted VMEA and a newly developed evaluation matrix, this allows a thorough robustness evaluation of product concepts. The method is exemplary shown for a lifting table.<br
Keywords: Robust design; Conceptual design; Tolerance representation and management; QFD; VMEA

Robust optimization of continuously reinforced composites in the motorcycle industry - Kellermeyer, Markus; Perterer, Martin; Wartzack, Sandro (RDO-Journal, 2017)

Robust Tolerance Design of Systems with varying ambient Temperature influence due to worldwide manufacturing and operation - Sprügel, Tobias; Walter, Michael; Wartzack, Sandro (International Design Conference - DESIGN, 2014)
In today’s industrial environment products must be developed and brought to market in short time. To shorten the time-to-market between the product idea and the start-of-production various methods were developed over the last decades, which are applied during product development (e. g. concurrent engineering). However, the product developer still has to face additional challenges in modern product development [Liu 2009]. In this context, an extended relevance and discussion on quality topics and in particular, Robust Design Methods (RDM), both in industry and research, can be found in recent years [Gremyr 2003, Liu 2009, Eifler 2013]. These RDMs (which can be principles, tools, methods, metrics etc.) are used to analyze a product in order to reduce the sensitivity of its design parameters towards variation [Eifler 2013]. However, deviations of parts are inherently inevitable due to “axiom of manufacturing imprecision” [Zhang 2011]. Consequently, the product developer has to define appropriate tolerances to limit these dimensional and geometrical deviations and thus, to ensure a certain quality of the entire product [Wartzack 2011]. Therefore, statistical tolerance analyses are widely used in engineering design to quantify the effects of appearing deviations on functional key characteristics (FKCs) of a product [Jayaprakash 2012, Tsai 2012, Chase 1991, Walter 2013]. Tolerance analyses lead to significant cost reductions, as only required tolerance ranges may be manufactured [Söderberg 2006]. Unnecessarily narrow tolerance ranges, which lead to high production costs can be avoided or significantly reduced. However, the analysis of only dimensional and geometrical tolerances is not sufficient to evaluate functionality and assemblability of a system and thus, to achieve a robust design. Other aspects, such as deformation, thermal expansion, wear, etc. need to be integrated in tolerance analysis [Scholz 1995, Chase 1991]. However, existing approaches only consider the impact of these additional effects. So the authors claim that a holistic robust tolerance design essentially requires the consideration of both the impact as well as the cause of these deviations. These causes can be both technical (such as forces, friction) and non-technical (the company’s choice on the place of production, quality philosophy, qualification of workers, etc.). This is even the more serious, since traditionally product developers hardly take into account non-technical causes during product development and tolerance analyses, particularly.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.robust
Keywords: robust design; tolerance analysis; worldwide manufacturing; climate effects

Sampling-based tolerance analysis: the key to establish tolerance-cost optimization in the product development process - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2021)
Tolerance allocation during detail design aims to identify a combination of tolerances which are tight enough to ensure total product functionality but also as wide as possible to minimize the resultant manufacturing costs. Optimization techniques automatize and thus significantly accelerate the complex search for suitable tolerance values taking both the design and manufacturing perspective into account. While sampling techniques became well-established for tolerance analysis, statistical approximative approaches, e.g. the root sum square method, are still commonly used for tolerance-cost optimization. However, this leads to a limited applicability and validity of the optimization which currently prevents its successful implementation in industry. Thus, the article discusses the direct and indirect effects of sampling methods on the definition and solution of the optimization problem and reveals the benefits and drawbacks of sampling-based tolerance-cost optimization in terms of effectiveness and efficiency using an illustrative case study. In addition, guidelines as well as recommendations for its proper application in research and industry are given. In doing so, this article shows that the use of sampling-based techniques can significantly contribute to a shift of tolerance-cost optimization from an expert tool for tolerance specialists with in-depth knowledge in statistics, optimization and programming, to a user-friendly engineering design tool with an enhanced usability, which enables solving problems of industrial complexity.<br
Keywords: Tolerance-cost optimization; Sampling techniques; Statistical tolerance analysis; Least cost tolerance allocation

Sampling-based Tolerance-Cost Optimization of Systems with Interrelated Key Characteristics - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2020)
Robustness is a key factor contributing to a high functionality of technical systems under uncertainty. In this context, existing methodologies, such as Axiomatic Design and Quality Function Deployment, can help to identify coupled functional requirements which significantly affect the robustness of a system. However, it is often not possible to decouple all in the final product design. As a consequence, multiple interrelated tolerance chains have to be considered in the subsequent tolerance design leading to multi-constrained or multi-objective optimization problems. Despite their significant influence on the optimization process and its results, interrelated tolerance chains have not been studied in detail yet, especially in the context of sampling-based tolerance-cost optimization. Moreover, a holistic framework for the tolerance-cost optimization of systems with multiple key characteristics is missing so far. In order to close that gap, this paper presents a framework to consider multiple key characteristics in both least-cost and best-quality tolerance-cost optimization using sampling techniques for tolerance analysis. Therefore, interrelated tolerance chains and their effects on the optimization process in terms of the definition and handling of multiple constraints and objectives are discussed in detail. The proposed research aims to bring all important aspects together in one common framework. Thus, it is supposed to help researchers and practitioners to properly define and solve the tolerance optimization problem. In order to show its benefits and applicability, it is applied to an illustrative case study. The novelty of this paper is to present a comprehensive method to support the tolerance engineer in creating a robust and optimal tolerance design of products with multiple interrelated key characteristics.<br
Keywords: Tolerance-cost optimization; Optimal tolerance allocation; Interrelated key characteristics; Multi-objective optimization

Sampling-basierte Toleranz-Kosten-Optimierung - Eine optimierungsbasierte Methode zur Vergabe kostenminimaler Toleranzen - Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (WiGeP News, 2020)

Scenario analysis and potential identification to structure of the roadmap to autonomous design - Dworschak, Fabian; Schleich, Benjamin; Wartzack, Sandro (11th Graz Symposium VIRTUAL VEHICLE, 2018)
In the long term, the cooperation between the central department for IT services of the AUDI AG and the institute of engineering design of the Friedrich-Alexander University aims for integration autonomous design in the deployment of virtual vehicles. To structure this task, a roadmap showing and arranging the upcoming steps is necessary similar to the roadmap towards autonomous driving. However, integration and deployment of data-driven solutions into the development processes differs widely to driving. First, the grade of automation is not homogenous across the development processes. Second, identifying useful solutions to a given task in the design process is difficult. This paper aims to answer the question how to bridge the gap between theoretical models for data-driven solutions and the deployment of these models in t
Keywords: Continuous integration and deployment of data and models; Model-based systems engineering; AI in vehicle development; testing; and operation

Schadens- und Ausfallmechanismen bei Wälzlagern unter Schwenkbewegungen - Halmos, Fabian; Bartz, Marcel; Wartzack, Sandro (15. VDI-Fachtagung „Gleit- und Wälzlagerungen 2023", 2023)

Schadens- und Ausfallmechanismen bei Wälzlagern unter Schwenkbewegungen - Halmos, Fabian; Bartz, Marcel; Wartzack, Sandro (Gleit- und Wälzlagerungen 2023, 2023)
Rolling bearings under oscillating motion are used in a wide range of applications. However, there are no validated calculation methods for calculating the rating life for this application. Instead, the oscillating motions are usually converted into continuous revolutions and then designed according to DIN ISO 281 or DIN 26281. Alternatively, one of the existing, but not validated, calculation approaches for non-continuous revolutions can be used. However, especially for small oscillations, it is unclear to what extent these calculation approaches are valid at all, since wear can occur here as a failure mechanism instead of fatigue. The aim of this paper is therefore to provide an understanding of possible failure mechanisms in oil-lubricated rolling bearings under small oscillating motions. For this purpose, several life tests are carried out and evaluated with a new type of rolling bearing oscillation test rig. Based on the damage that occurs, a statement can be made about the failure mechanisms under
CRIS-Team Scopus Importer:2023-12-08

Segmentation of musculotendinous structures of the hip from 3d imaging for patient-specific individualization of biomechanical simulations - Fleischmann, Christopher; Scherb, David; Leher, Irina; Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro; Sesselmann, Stefan (Advances in Intelligent Systems and Computing, 2021)
Due to a steady increase of total hip arthroplasty, biomechanical multibody simulations are moving more and more into focus. These simulations allow to calculate forces, moments and muscle activities in the human body and, thus, can help to improve surgery planning and outcomes. However, generic human body models based on anthropometric data are mostly used for these simulations. Since these models are not customized to patients, there is a need to adapt the models to the individual patient. Therefore, 3D models of bones are created by segmentation of CT and MRI scans and assigned different landmarks. This allows to define both, the shape and size of bones, in this case the femur, which leads to patient-specific adjustments of muscle attachment points. Also muscles can be segmented to determine important parameters such as muscle volume, allowing the definition of important simulation parameters, like the maximum isometric force or the tendon slack length of individual patients leading to customized models.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Biomechanics; Multibody simulation; Muscle function; Muscle segmentation; Orthopaedics; Subject-specific modeling and simulation; Surgery planning; Total hip arthroplasty

Semantic Support for Engineering Design Processes - Breitsprecher, Thilo; Codescu, Silvestru Mihai; Schröder, Lutz; Wartzack, Sandro; jucovschi, Constantin; Kohlhase, Michael (In Proc. 13th International Design Conference, DESIGN 2014, 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.profes_1.semant
Keywords: design knowledge; ontology; semantics in product development

Sensitivitätsanalyse der tribologischen Eigenschaften gefräster Oberflächenstrukturen bei der Blechmassivumformung - Breitsprecher, Thilo; Hense, Rouven; Beyer, Florian; Biermann, Dirk; Wartzack, Sandro; Willner, Kai (Tagungsband zum 2. Erlanger Workshop Blechmassivumformung 2013, 2013)
Reibeigenschaften von Oberflächen für Umformwerkzeuge gezielt einzustellen (Tailored Friction) nimmt bei der Entwicklung moderner Umformprozesse in technischer und ökonomischer Hinsicht eine zentrale Rolle ein. Dies betrifft insbesondere die Blechmassivumformung, die im Rahmen des SFB Transregio 73 erforscht wird. Ein neues Verfahren, das im SFB entwickelt wird, ist die Strukturierung durch regenerative Werkzeugschwingungen beim Fräsen. Ziel dabei ist es, einen separaten Prozessschritt, in dem nur strukturiert wird, einzusparen. Beim Fräsen mit Werkzeugschwingungen ist aufgrund der hohen Komplexität eine simulationsgestützte Auslegung unentbehrlich. Realitätsnahe Ergebnisse können dabei nur durch eine hinreichend gute Parametrisierung der Simulation erzielt werden, was im Besonderen für die Zerspankraftparameter gilt. In diesem Artikel wird die Sensitivität von tribologisch relevanten Kenngrößen auf die Zerspankraftparameter mit dem Ziel diskutiert, eine Aussage über die notwendige Güte zu treffen, mit der diese ermittelt werden müssen, um die Reibeigenschaften gefräster Oberflächen zuverlässig vorhersagen zu können. Um aus den simulierten gefrästen Oberflächen tribologische Kennwerte zu ermitteln, die für die Blechmassivumformung mit ihren hohen Flächenpressungen realitätsnah sind, findet ein Halbraummodell Anwendung.
Keywords: Tailored Friction; Sensitivitätsanalyse; Knowledge Discovery in Databases

Sensitivity Analysis of features in tolerancing based on constraint function level sets - Ziegler, Philipp; Wartzack, Sandro (Reliability Engineering & System Safety, 2015)
Usually, the geometry of the manufactured product inherently varies from the nominal geometry. This may negatively affect the product functions and properties (such as quality and reliability), as well as the assemblability of the single components. In order to avoid this, the geometric variation of these component surfaces and associated geometry elements (like hole axes) are restricted by tolerances. Since tighter tolerances lead to significant higher manufacturing costs, tolerances should be specified carefully. Therefore, the impact of deviating component surfaces on functions, properties and assemblability of the product has to be analyzed. As physical experiments are expensive, methods of statistical tolerance analysis tools are widely used in engineering design. Current tolerance simulation tools lack of an appropriate indicator for the impact of deviating component surfaces. In the adoption of Sensitivity Analysis methods, there are several challenges, which arise from the specific framework in tolerancing. This paper presents an approach to adopt Sensitivity Analysis methods on current tolerance simulations with an interface module, which bases on level sets of constraint functions for parameters of the simulation model. The paper is an extension and generalization of Ziegler and Wartzack [1]. Mathematical properties of the constraint functions (convexity, homogeneity), which are important for the computational costs of the Sensitivity Analysis, are shown. The practical use of the method is illustrated in a case study of a plain bearing.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.sensit
Keywords: Computer-aided tolerancing; Design features; Deviation Domain; Sensitivity Analysis

Sensor selection and integration for Cyber-Physical Systems in context of Digital Twins – A systematic review of requirements - Fett, Michel; Wilking, Fabian; Götz, Stefan; Kirchner, Eckhard; Wartzack, Sandro (2023 18th Annual System of Systems Engineering Conference (SoSe), 2023)
Digital Twins process real-time data collected from a Physical Twin. This real-time data is often measurement by sensors, which must be selected and integrated during the development or modification of the physical twin. In this paper, a systematic literature review on sensors for Digital Twins and Cyber-Physical Systems is conducted. The results are mapped into a framework for selection and integration. From this, the special requirements for the sensors that arise from the use of Digital Twins can be identified.<br

Shaping the digital twin for design and production engineering - Schleich, Benjamin; Anwer, Nabil; Mathieu, Luc; Wartzack, Sandro (CIRP Annals - Manufacturing Technology, 2017)
The digitalization of manufacturing fuels the application of sophisticated virtual product models, which are referred to as digital twins, throughout all stages of product realization. Particularly, more realistic virtual models of manufactured products are essential to bridge the gap between design and manufacturing and to mirror the real and virtual worlds. In this paper, we propose a comprehensive reference model based on the concept of Skin Model Shapes, which serves as a digital twin of the physical product in design and manufacturing. In this regard, model conceptualization, representation, and implementation as well as applications along the product life-cycle are addressed.
Keywords: Design; Tolerancing; Digital twin

Simplified integrative simulation of short fibre reinforced polymers under varying thermal conditions - Witzgall, Christian; Wartzack, Sandro (10th European LS-DYNA Conference - Book of Abstracts, 2015)
The use of injection moulded, short fibre reinforced structural parts in vehicle design is increasing due to their low density and outstanding mechanical properties. As the distribution and orientation of fibres within the components are heavily dependent on the moulding process, product developers do well to take process simulations into consideration before performing anisotropic structural analyses. To enable the use of these integrative simulations within early design stages, a simplified approach has been developed by Schöpfer [2] and extended by Gruber/Wartzack [1]. It considers the material's anisotropy by using the fibre orientation data gained from the injection moulding simulation. By reducing the complexity of the orientation condition and the material representation, a simulation approach suitable for early design stages was created. However, within the so-called IS4ED approach by Gruber the influence of high or low temperatures on the material behaviour is not considered. As the thermoplastic materials are sensitive to even minor changes in temperature, the IS4ED approach has to be enhanced. The decrease of stiffness and maximum stress levels and the increase of maximum strain at elevated temperatures have to be added to the approach. Nevertheless, the reduced complexity and suitability for early design steps, which are the main advantages, shall remain untouched. The material behaviour within the enhanced IS4ED approach will still be modelled by overlapping different material descriptions. In addition to the layers covering the anisotropic and strain-rate dependent behaviour, the definition of new layers to describe temperature dependency will be introduced in this paper. This will enable to predict the structural behaviour in a wide temperature range.
Keywords: Simulation; SFRP

Simplified simulation of aluminum-CFRP adhesive joints - Wartzack, Sandro; Witzgall, Christian; Kellermeyer, Markus; Most, Thomas (RDO-Journal, 2016)

Simplifying Computer Aided Ergonomics: A User-Product Interaction-Modeling Framework in CAD Based on a Taxonomy of Elementary Affordances - Wolf, Alexander; Wagner, Yvonne; Oßwald, Marius; Miehling, Jörg; Wartzack, Sandro (IISE Transactions on Occupational Ergonomics and Human Factors, 2021)
OCCUPATIONAL APPLICATIONS
CRIS-Team WoS Importer:2021-07-09

Simplifying Ergonomic Assessment for Designers: A User-Product Interaction-Modelling Framework in CAD - Wolf, Alexander; Wagner, Yvonne; Oßwald, Marius; Miehling, Jörg; Wartzack, Sandro; Wolf, Alexander; Wagner, Yvonne; Oßwald, Marius; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 21st Congress of the International Ergonomics Association (IEA 2021), 2021)
Digital human models have not yet reached their full potential for proactive virtual assessment of ergonomics in engineering and industrial design. Especially the modelling of interaction between user and product often is time demanding, cumbersome, unstandardized and embedded insufficiently in the computer-aided engineering environment. On the one hand, the interaction modelling needs to be applicable for a majority of products and shall contain as much a-priori knowledge regarding human behavior as possible. On the other hand, the method needs to be appropriate for designers, without special ergonomic expertise or human behavior training. In this contribution, we present an interaction-modelling framework based on the concept of affordances, which ought to resolve these partly contradictable demands. Hence, 31 elementary affordances, describing fundamental physical interaction possibilities between human end effectors and rudimental (product) geometries, were deduced using a classification method. The elementary affordances shall serve as a medium for interaction modeling. For this purpose, we introduce an interaction modelling routine, implemented in a CAD system, which makes use of the identified elementary affordances in terms of CAD-features. Those enable designers to apply interaction possibilities directly to a CAD-model in order to define the constraints for a DHM simulatio
CRIS-Team Scopus Importer:2021-08-13
Keywords: User product interaction; Digital human models; Affordance; CAD; Interaction modelling

Simulation-based development of Pareto-optimized tailored blanks for the use within sheet-bulk metal forming - Küstner, Christof; Beyer, Florian; Kumor, Dustin; Loderer, Andreas; Wartzack, Sandro; Willner, Kai; Blum, Heribert; Rademacher, Andreas; Hausotte, Tino (DS 84: Proceedings of the DESIGN 2016 14th International Design Conference, 2016)
In the context of lightweight design, the so-called tailored blanks are more frequently used to improve sheet-bulk metal forming process results. In order to meet the requirements of tailored blank designs for subsequent sheet-bulk metal forming process steps, design engineers can influence many process or geometry parameters. A crucial task for design engineers is to find the optimal process and geometry parameter setting that is an optimal design with respect to multiple design requirements. A simulation-based approach to face this challenge is presented in this pape
Keywords: pareto-optimized design; simulation study; friction law

Simulation based generation of an initial design taking into account geometric deviations and deformations - Walter, Michael; Breitsprecher, Thilo; Gruber, Georg; Wartzack, Sandro (Proceedings of the 18th International Conference on Engineering Design 2011 (ICED11), 2011)
The success of a product's development is essentially affected by its functionality. So the product developer has to ensure the functionality as early as possible. Since this usually can't be achieved with the first design several iterations are needed to modify the design. The product's functionality depends largely on the interaction of its components and their geometries. So geometric deviations of these components need to be taken into account. These deviations can result e.g. from manufacturing discrepancies or being operation-depending like deformations. This paper presents an approach which enables the product developer to determine an initial design proposal that fulfils its function. So no time- and money-consuming iterations are needed. Therefore the approach uses methods and tools like tolerance allocation, topology optimization and parameter optimization at an early stage. The tolerance allocation is needed to define the functional requirement of the non-ideal components. The optimization tools are used to create the initial design proposal fulfilling the functional requirement. A case study of a non-ideal scissor-type lift table illustrates the approach.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.simula
Keywords: Early functional validation; Initial design proposal; Non-ideal parts; Topology optimization

Simulation elastohydrodynamischer Wälz-/Gleit-Kontakte mit Oberflächenstrukturen durch kommerzielle FE-Programme - Weschta, Martin; Tremmel, Stephan; Wartzack, Sandro (Wissenschaftliches Kolloquium Wälzlager, 2015)

Simulation in Human-Centered Design - Past, Present and Tomorrow - Miehling, Jörg; Krüger, Daniel; Wartzack, Sandro (Smart Product Engineering - Proceedings of the 23rd CIRP Design Conference, 2013)
Due to the ever rising significance of the products’ usability the consideration of the user in the product development process becomes more and more important to stay competitive. This paper firstly outlines the historical evolution of how user-product relationships have been investigated and considered in product design in the past. A literature research has been conducted to acquire information about the state of the art in the multidisciplinary field of human-centered design as well as to derive which challenges towards a virtual assessment of human-related product properties exist. Finally the most recent research activities aiming to solve the identified issues as well as future prospects in simulating human-product interactions are presented.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.simula
Keywords: human-centered design; ergonomics; simulation; virtual product development; digital human modeling; biomechanics; hybrid mock-up

Simulation of Microstructured Rolling-Sliding Contacts - Weschta, Martin; Tremmel, Stephan; Wartzack, Sandro (Proceedings of the 2014 COMSOL Conference in Boston, 2014)
To reduce friction in lubricated tribological contacts, the surfaces of the contacting bodies can be microstructured to improve lubricating conditions. For lower loaded contacts this approach has already reached industrial applications, e.g. the piston-liner contact. For higher loaded contacts the effects are currently in basic research. Elastic deformation in the contact area plays an important role in those cases. This paper presents an approach to compute microstructured elastohydrodynamic contacts using COMSOL Multiphysics® software and compares results with those attained on a test bench.
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.simula

Simulation of Microtextured Surfaces in Starved EHL Contacts Using Commercial FE Software - Marian, Max; Weschta, Martin; Tremmel, Stephan; Wartzack, Sandro (Materials Performance and Characterization, 2017)
In order to improve the lubricating conditions and thus realize a reduction of friction and wear, the surfaces of contacting bodies in lubricated tribological contacts can be microtextured. Although this approach has already reached industrial applications for lower loaded contacts, it is still in basic research for higher loaded contacts, where elastic deformation plays a significant role. In the past, it was common in theoretical studies to assume a fully flooded condition for the inlet to the contact. However, in reality a lubricant contact may suffer from starvation due to high speeds, highly viscous lubricants, or limited lubricant supply. This article presents an efficient straightforward approach to compute starved microtextured elastohydrodynamic contacts based on a full-system approach and using commercial FE software. The numerical study on starvation is realized by shifting the position of the inlet meniscus toward the contact zone combined with the use of an appropriate cavitation model. Therefore, negative pressures are penalized by reducing the lubricant’s density, respectively its volume or mass fraction, with a penalty term. First, the implementation for the steady-state smooth-surface problem as well as the impact of decreasing lubricant supply on the film thickness are discussed as a reference case. Special is paid to proving suitability and validity of the used cavitation model for starvation problems. Subsequently, the influence of different degrees of starvation on film thickness and pressure distribution for a microtextured time-dependent demonstrator case is illustrate
Keywords: tribology; lubrication; microtextured surfaces; elastohydrodynamics; finite-element-method; penalty-variable-density; cavitation model; mass conservation; starvation

Simulationsbasierte Generierung von Präparationsrichtlinien für Zahn-Inlays im kaubelasteten Seitenzahnbereich - Klein, Daniel; Grimme, Tobias; Tremmel, Stephan; Petschelt, Anselm; Lohbauer, Ulrich; Wartzack, Sandro (ANSYS Conference & CADFEM User's Meeting 2012, 2012)
Caries is the major dental disease and the main reason for tooth extractions as clinical investigations show. Fortunately in many cases the carious lesion can be removed without extracting the whole tooth and replaced by a restoration, e.g. inlays. However, the lifetime of inlays is limited. Besides the inlay material the geomtery of the inlay can have a significant impact on the durability of an inlay. The aim of this paper is to show how the impact of the inlay geometry on the durability can be observed with the help of simulation and some common guidelines for dental restaurations are monitored.
Keywords: Simulation; Medizintechnik

Simulations-DNA: Datengetriebener Ansatz zur automatischen Plausibilitätsprüfung strukturmechanischer FE-Simulationen mittels Deep Learning - Sprügel, Tobias; Schleich, Benjamin; Wartzack, Sandro (VDI Bereichte 2333: SIMVEC - Simulation und Erprobung in der Fahrzeugentwicklung 2018, 2018)
In der modernen virtuellen Produktentwicklung ist der Einsatz von Simulationswerkzeuge zur Beurteilung der Auswirkungen von Konstruktionsänderungen auf das beabsichtigte Produktverhalten unerlässlich. Die Erstellung valider Simulationen erfordert jedoch Expertenwissen. Konstrukteure, die selten Finite-Elemente-Analysen (FEA) durchführen, müssen unterstützt und ihre FEA-Ergebnisse auf Plausibilität überprüft werden. Eine automatische Plausibilitätsprüfung für Finite Elemente (FE) Simulationen in der linearen Strukturmechanik kann nicht plausible Simulationen identifizieren und den Anwender warnen, die Ergebnisse vorsichtig zu interpretieren oder Rücksprache mit Simulationsexperten zu halten. Eine nicht plausible Simulation enthält Fehler, die von einem erfahrenen Simulationsingenieur schnell erkannt werden, während eine plausible Simulation solche Fehler nicht enthält. Die Menge der verfügbaren Simulationsdaten in der Industrie nimmt zu, daher ist eine datengetriebene Simulationsprüfung ein naheliegender nächster Schritt. Dennoch stellt sich die Frage, wie Simulationsdaten sehr unterschiedlicher Bauteile und Simulationen in ein einziges Softwaretool übertragen werden können, wie dieses Tool die relevanten Regeln hinter plausiblen Simulationen erlernen kann und wie es auf neue Simulationen angewendet werden kann. In diesem Beitrag wird ein Ansatz zur Umwandlung verschiedener FE-Netze, entsprechender FE-Ergebnisse und Randbedingungen in eine numerische Matrix fester Größe für sehr unterschiedliche strukturmechanische FE-Simulationen vorgestellt. Der neuartige Ansatz nutzt sphärische Detektorflächen, um dreidimensionale Informationen auf die Oberfläche zu projizieren. Es ermöglicht die Erzeugung der sogenannten Simulations-DNA; Klassifikationsalgorithmen wie z. B. Convolutional Neural Networks können diese Informationen klassifizieren. Die gesamte Methodik reduziert die Dimension einer 3D-Finite-Elemente-Simulation auf eine 2D-Matrix fixer Größe, bestehend aus numerischen Werten. Im Beitrag wird jeder einzelne Schritt der neuartigen Methodik zur Plausibilitätsprüfung von strukturmechanischen Simulationen für vereinfachte Bauteile und entsprechende Simulationen detailliert dargestellt und erläuter
Keywords: Deep Learning; Plausibilitätsprüfung; FE-Simulation; Sphärische Detektorfläche

Simulationsstrategie als Basis für Industrie 4.0 - Wartzack, Sandro (CADFEM Journal, 2015)
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.simula

Simulationsstrategie zur Abbildung des abweichungsbehafteten Herstellungsprozesses von Faser-Kunststoff-Verbund-Baugruppen - Freitag, Stephan; Götz, Stefan; Wartzack, Sandro (Tagungsband der 5. Summer School Toleranzmanagement 2023, 2023)

Simulative Parameterstudien an Wellblech-Sandwichstrukturen - Gruber, Georg; Wartzack, Sandro (ANSYS Conference & 29th CADFEM Users' Meeting, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.simula_6

SIMULTANEOUS DEFINITION OF KEY CHARACTERISTICS IN ORDER TO FACILITATE ROBUST DESIGN IN EARLY PRODUCT DEVELOPMENT STAGES - Götz, Stefan; Horber, Dennis; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2021)
The success of complex product development projects strongly depends on the clear definition of target factors that allow a reliable statement about the fulfilment of the product requirements. In the context of tolerancing and robust design, Key Characteristics (KCs) have been established for this purpose and form the basis for all downstream activities. In order to integrate the activities related to the KC definition into product development as early as possible, the often vaguely formulated requirements must be translated into quantifiable KCs. However, this is primarily a manual process, so the results strongly depend on the experience of the design engineer. In order to overcome this problem, a novel computer-aided approach is presented, which automatically derives associated functions and KCs already during the definition of product requirements. The approach uses natural language processing and formalized design knowledge to extract and provide implicit information from the requirements. This leads to a clear definition of the requirements and KCs and thus creates a founded basis for robustness evaluation at the beginning of the concept design stage. The approach is exemplarily applied to a window lifter.
Keywords: Robust design; Conceptual design; Requirements; Early design phases

Simultaneous Development of a Self-learning Engineering Assistance System - Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Sheet Bulk Metal Forming. Research Results of the TCRC73, 2020)
In order to support the design of sheet-bulk metal formed parts, a self-learning engineering assistance system (SLASSY) was developed during the course of the project. SLASSY can help in product development of sheet-bulk metal forming (SBMF) mainly in two ways. On the one hand, it facilitates the knowledge transfer from manufacturing experts back to product developers and on the other hand, it enables product developers to optimize their part designs based on the metamodels created from simulation and experimental parameter studies. The key scientific findings are the generalized workflow for creating these metamodels, which allows the creation of knowledge very soon during the development of a new manufacturing technology like SBMF. Based on this, metamodels allow the automatic generation of design alternatives, which are also valuable and manufacturable. Potential applications for this self-learning engineering assistance system can be found in every manufacturing-related industry, since it enables product developers to keep up with the development of a new or newly introduced manufacturing technology in their respective field. The methods developed can be applied to all fields, where simulations and experimental studies are applied to find new knowledge in a given manufacturing domai
Keywords: data driven design; engineering workbench; machine learning

Skin Model Based Simulation of Contact and Mobility for Mechanical Assemblies - Schleich, Benjamin; Anwer, Nabil; Zhang, Wei; Mathieu, Luc; Wartzack, Sandro (Proceedings of the 13th CIRP Conference on Computer Aided Tolerancing, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.skinmo_8

Skin Model Shapes: A new paradigm shift for geometric variations modelling in mechanical engineering - Schleich, Benjamin; Anwer, Nabil; Mathieu, Luc; Wartzack, Sandro (Computer-Aided Design, 2014)
Geometric deviations are inevitably observable on manufactured workpieces and have huge influences on the quality and function of mechanical products. Therefore, many activities in geometric variations management have to be performed to ensure the product function despite the presence of these deviations. Dimensional and Geometrical Product Specification and Verification (GPS) are standards for the description of workpieces. Their lately revision grounds on GeoSpelling, which is a univocal language for geometric product specification and verification and aims at providing a common understanding of geometric specifications in design, manufacturing, and inspection. The Skin Model concept is a basic concept within GeoSpelling and is an abstract model of the physical interface between a workpiece and its environment. In contrast to this understanding, established models for computer-aided modelling and engineering simulations make severe assumptions about the workpiece surface. Therefore, this paper deals with operationalizing the Skin Model concept in discrete geometry for the use in geometric variations management. For this purpose, Skin Model Shapes, which are particular Skin Model representatives from a simulation perspective, are generated. In this regard, a Skin Model Shape is a specific outcome of the conceptual Skin Model and comprises deviations from manufacturing and assembly. The process for generating Skin Model Shapes is split into a prediction and an observation stage with respect to the available information and knowledge about expected geometric deviations. Moreover, applications for these Skin Model Shapes in the context of mechanical engineering are given.
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.skinmo
Keywords: Geometric variations management; Computer aided tolerancing; Geometric product specification; Skin Model; Shape modelling; Shape representation

Skin Model Shapes: ein neuer Ansatz zur Toleranzsimulation auf Basis von Punktwolken und Oberflächennetzen - Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2017)
Die Toleranzsimulation ist ein essentielles Werkzeug zur frühzeitigen Analyse der Auswirkungen von Bauteil- abweichungen auf funktions- und qualitätskritische Baugruppenmaße. Dieser Beitrag stellt einen neuen Ansatz zur Toleranzsimulation auf Basis von Punktwolken und Ober-flächennetzen unter Berücksichtigung von Formabweichungen und in Übereinstimmung mit Toleranznormen vor und erläutert das, diesem Ansatz zugrundeliegende, Konzept der Skin Model Shapes.

Skin Model Shapes: Offering New Potentials for Modelling Product Shape Variability - Schleich, Benjamin; Wartzack, Sandro; Anwer, Nabil; Mathieu, Luc (ASME 2015 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, Volume 1A: 35th Computers and Information in Engineering Conference, 2015)
The modelling of nominal product geometry by computer-aided design tools has gained immense attention in industry during the last decades and is nowadays an integral part of the virtual product development process. However, the established geometry representation schemes for CAD imply severe drawbacks regarding the modelling of geometric part deviations, which are inevitably observed on every manufactured artefact. As a response, the concept of Skin Model Shapes, which stems from international standards for geometric product specification and verification, has been developed as a novel approach for the consideration of product shape variability. It employs discrete geometry methods and computational techniques, such as point clouds, surface meshes and geometric processing, to model shape variability and to facilitate the communication of geometric product information throughout the product design, manufacturing, and inspection processes. This paper highlights the foundations of this concept, demonstrates its potentials for the representation of product geometry considering geometric variations along the product lifecycle, and illustrates main applications in the context of computer aided product and process development. In this regard, a focus is laid upon recent results and contributions, such as contact modelling, tolerance analysis, and motion tolerancing based on Skin Model Shapes. Furthermore, challenges for future research, such as the application to complex shapes and compliant parts, as well as the consideration of novel manufacturing processes, are discussed.
Keywords: Computer-Aided Tolerancing; Tolerance Modelling; Skin Model Shapes

SLASSY—An Assistance System for Performing Design for Manufacturing in Sheet-Bulk Metal Forming: Architecture and Self-Learning Aspects - Sauer, Christopher; Breitsprecher, Thilo; Küstner, Christof; Schleich, Benjamin; Wartzack, Sandro (AI, 2021)
Substantial efforts have been made to integrate manufacturing- and design-relevant knowledge into product development processes. A common approach is to provide the relevant knowledge to the design engineers using a knowledge-based system (KBS) that, in turn, becomes the engineering assistance system. Keeping the knowledge up to date is a critical issue, making knowledge acquisition a bottleneck of developing and maintaining KBS. This article presents a robust metamodel optimization and performance estimation architecture for developing and maintaining a KBS useful for design-for-manufacturing from the context of sheet-bulk metal forming. It is shown that the presented KBS or engineering assistance system helps achieve performing design-for-manufacturing, integrating both design and manufacturing knowledge. Using the presented approach helps overcome the bottleneck of knowledge acquisition and knowledge update through its self-learning component based on data mining and knowledge discovery.<br
Keywords: engineering assistance system; knowledge discovery in database; sheet-bulk metal forming

So eng wie nötig, so breit wie möglich - Wartzack, Sandro; Walter, Michael; Schleich, Benjamin (Konstruktionspraxis, 2013)
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.soengw

Sonderforschungsbereich/Transregio "Blechmassivumformung" angelaufen - Wartzack, Sandro; Hetzner, Harald; Röhner, Sebastian (Konstruktion, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KLMEFK.sonder

Spider web inspired composite structures - a new concept for load introduction in fiber-reinforced-plastics sandwich structures - Franz, Michael; Völkl, Harald; Wartzack, Sandro (DS 119: Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
Sandwich structures represent a lightweight design method which leads to very light and at the same time stiff components through the combination of stiff outer skins and light core material. A major challenge in the design of sandwich structures is load introduction. In order to realize improved load introduction in sandwich structures and to leverage further possible lightweight design potential, the following paper presents a new concept using spider web inspired structures made of fiber reinforced plastic materials. In order to investigate the potential of the spider web concept, simulative comparative studies between the spider web structures and conventional load introductions are carried out<br

Statistical tolerance analysis—a survey on awareness, use and need in german industry - Walter, Michael S.J.; Klein, Christina; Heling, Björn; Wartzack, Sandro (Applied Sciences, 2021)
The importance of geometric deviations of components for the aesthetic and functional quality of products has been undisputed for decades. So, it is not surprising that not only have numerous researchers devoted themselves to this field, but also commercial software tools for the analysis and optimization of tolerance specifications (currently already fully integrated in 3D-CAD systems) have been available for around 30 years. However, it is even more surprising that the well-founded specification of tolerances and their analysis using a so-called statistical tolerance analysis are only established in a few companies. There is thus a contradiction between the proclaimed relevance of tolerances and their actual consideration in everyday business life. Thus, the question of the significance of geometric deviations and tolerances as well as the use of statistical tolerance analysis arises. Therefore, a survey among 102 German companies was carried out. The results are presented and discussed in this paper.
CRIS-Team Scopus Importer:2021-04-09
Keywords: GD&T; German industry; Survey; Tolerance analysis; Tolerance engineering

Statistical Tolerance Analysis of 3D-Printed Non-Assembly Mechanisms in Motion Using Empirical Predictive Models - Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Applied Sciences, 2021)
Fused Deposition Modelling (FDM) enables the fabrication of entire non-assembly mechanisms within a single process step, making previously required assembly steps dispensable. Besides the advantages of FDM, the manufacturing of these mechanisms implies some shortcomings such as comparatively large joint clearances and geometric deviations depending on machine-specific process parameters. The current state-of-the-art concerning statistical tolerance analysis lacks in providing suitable methods for the consideration of these shortcomings, especially for 3D-printed mechanisms. Therefore, this contribution presents a novel methodology for ensuring the functionality of fully functional non-assembly mechanisms in motion by means of a statistical tolerance analysis considering geometric deviations and joint clearance. The process parameters and hence the geometric deviations are considered in terms of empirical predictive models using machine learning (ML) algorithms, which are implemented in the tolerance analysis for an early estimation of tolerances and resulting joint clearances. Missing information concerning the motion behaviour of the clearance affected joints are derived by a multi-body-simulation (MBS). The exemplarily application of the methodology to a planar 8-bar mechanism shows its applicability and benefits. The presented methodology allows evaluation of the design and the chosen process parameters of 3D-printed non-assembly mechanisms through a process-oriented tolerance analysis to fully exploit the potential of Additive Manufacturing (AM) in this field along with its ambition: ‘Print first time right’<br
Keywords: additive manufacturing; fused deposition modelling; statistical tolerance analysis; non-assembly mechanisms; empirical predictive models; geometric deviations

Statistical Tolerance Analysis of Mechanisms with Interactions between Deviations - A Methodology with 10 easy Steps - Walter, Michael; Wartzack, Sandro (Proceedings of the 19th International Conference on Engineering Design, 2013)
The time-dependent motion behavior of a mechanism is essentially affected by different kinds of deviations. Consequently, the product developer has to analyze the mechanism and its kinematic behavior as early as possible to ensure the product's functional capabilities. However, possible interactions between the deviations and their effects on the system's motion, and thus the functionality are not considered yet. This paper presents a methodology, consisting of 10 easy steps, which enables the product developer to perform a statistical tolerance analysis of a system in motion, which underlies different kinds of deviations as well as several interactions among them. Therefore, the identification as well as the determination (statistically) of the interactions is required, which can be done using numerical simulations like multi-body-dynamics or manufacturing process simulations. An appropriate mathematical representation of the interactions is done using meta-models (like Artificial Neural Networks). These can be easily integrated into the tolerance analysis' functional relation. A case study of a non-ideal cross-arm window regulator illustrates the methodology's practical use. statistical tolerance analysis, artificial neural networks, robust design, simulation, design methods.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.statis_2

Statistical Tolerance-Cost-Optimization of Systems in Motion Taking into Account Different Kinds of Deviations - Walter, Michael; Wartzack, Sandro (Smart Product Engineering - Proceedings of the 23rd CIRP Design Conference, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.statis

Statistische Toleranzanalyse additiv gefertigter montagefreier Mechanismen unter Berücksichtigung von Gelenkspiel - Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 4. Summer School - September 2020, 2020)

Statistische Toleranzanalyse verknüpfter Schließmaße - Heling, Björn; Aschenbrenner, Alexander; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 2. Summer School - September 2015, 2015)

Status and Prospects of Skin Model Shapes for Geometric Variations Management - Schleich, Benjamin; Anwer, Nabil; Mathieu, Luc; Wartzack, Sandro (Procedia CIRP, Volume 43, 2016)
Geometric part deviations, which are inevitably observed on every manufactured workpiece, have distinct effects on the assemblability as well as on the function and quality of physical artefacts. As a consequence, geometric variations management is an important issue for manufacturing companies. However, assessing the effects of form deviations already in virtual product realization remains an important challenge. This paper illustrates and summarizes the current status and development trends of the Skin Model Shape paradigm, which provides an operationalization and a digital representation of the Skin Model concept for modelling product shape variability and hence may serve as a comprehensive model for computer-aided variations management.
Keywords: Computer-Aided Tolerancing; Skin Model Shapes; Geometric Variations Management; Virtual Product Realization

Steigerung der Bauteilqualität durch Erhöhung der Anlagensteifigkeit eines FDM-Druckers - Hallmann, Martin; Sprügel, Tobias; Kelber, Vincent; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2018)
Die Qualität 3D-gedruckter Bauteile ist von einer Vielzahl an Einflussparametern abhängig. Nach Identifikation der Haupteinflussparameter auf die relevante Zielgröße, wie z. B. Maß- und Formhaltigkeit, mechanischen Eigenschaften oder Optik, können geeignete Maßnahmen dabei helfen, die Anforderungen an das 3D-gedruckte Bauteil zu erfüllen. Der nachfolgende Beitrag zeigt am Beispiel des Bausatz-Druckers Anet A8, dass neben den Prozessparametern der mechanische Aufbau des Druckers einen erheblichen Einfluss auf die Bauteilqualität hat.

Strength Analysis of Structurally Optimized Aluminium-Composite Tubular Lap Joints - Jäger, Michael; Wartzack, Sandro (Proceedings of the Design Society, 2022)
Truss structures are a stiff, economical, and efficient lightweight design, the limiting factor of these structures are usually the load transfer elements. This paper presents an analytical design method for optimized adhesive tubular lap joints between CFRP tubes and aluminium inserts. The analytically optimized design agrees very well with the numerical simulations and experimental results. Although the experiments show a highly non-linear behaviour, where a linear elastic correlation is expected, the total load capacity is only reached when the adhesive is fully plasticised.<br
Keywords: lightweight design; design optimisation; tubular lap joint; experimentation; composites

Strength Mapping Algorithm (SMA) for Biomechanical Human Modelling using Empirical Population Data - Miehling, Jörg; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15), Vol. 10: Design Information and Knowledge Management, 2015)
Despite the increasing level of detail in biomechanical simulation, human models are not yet valid to represent specific individuals or populations. Therefore, the generic models need adaptation to depict the varying competencies of the respective person or user group aimed to investigate. There have been achievements in scaling single modelling domains (e.g. anthropometry). However, a comprehensive approach is still lacking. This paper extends available methods by introducing a Strength Mapping Algorithm (SMA) for the adaption of individual maximum isometric forces to match empirical strength data. This procedure involves static optimization simulation of predefined body postures to reveal the dependencies between muscle forces and joint torques of a generic model specifying the skeletal and muscular geometry. Based on this information, we determine a set of muscle scaling factors for a given age, gender and strength percentile. As a result, the SMA enables the quick generation of a large number of individuals in order to implement a design for populations paradigm. This leads one step closer to gain deeper insight on how health relevant products and processes are to be developed.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.streng
Keywords: User centred design; Human factors engineering; Simulation; Virtual engineering (VE); Strength percentiles

Structural Mechanics Analysis Using an FE-Mesh Adaption to Real, 3D Surface Detected Geometry Data - Katona, Sebastian; Sprügel, Tobias; Koch, Michael; Wartzack, Sandro (Journal of Mechanics Engineering and Automation, 2015)
Within today’s product development process, various FE-simulations (finite element) for the functional validation of the desired characteristics are made to avoid expensive testing with real components. Those simulations are performed with great effort for discretization, use of simulations conditions, like taking different non-linearities (i.e., material behavior, etc.) into account, to create meaningful results. Despite knowing the effects of deformations occurring during the production processes, always the non-deformed design model of a CAD-system (computer aided design) is used for the FE-simulations. It seems rather doubtful that further refinement of simulation methods makes sense, if the real manufactured geometry of the component is not considered for in the simulation. For an efficient exploit of the potential of simulation methods, an approach has been developed which offers a geometry model for simulation based on the existing CAD-model but with integrated production deviations as soon as a first prototype is at hand by adapting the FE-mesh to the real, 3D surface detected geometry.
Keywords: FEA (finite element analysis); preprocessing; simulation; 3D surface detection; RE (reverse engineering)

Structured ergonomic guidance in early design phases by analysing the user-product interaction - Schröppel, Tina; Endreß, Felix; Köpken, Ina; Miehling, Jörg; Wartzack, Sandro (Ergonomics, 2021)
Gathering information for an early, proactive integration of ergonomic user requirements is challenging due to the unstructured character of available knowledge. Knowledge acquisition and processing is therefore costly and time-consuming. This contribution presents and evaluates InProCo, an approach for structured ergonomic guidance that aims to improve accessibility and clarity of ergonomic requirements in early design phases by providing interaction-based ergonomic properties. InProCo reduces the complexity of gathering knowledge and provide a novel way to describe interactions. Within a three-stage evaluation process, a survey assessed standard interactions for completeness, the output given by the graphical user interface of the approach (GUI) was evaluated for correctness and the knowledge base was validated by comparing the approaches output with properties identified by participants within a one-day workshop. The results showed that there are enough predefined standard interactions, the output of the GUI is valid and the knowledge base contains high quality data
Keywords: User-product interaction; early design stages; ergonomic requirements; knowledge base; ergonomics methods in design

Strukturmechanische Simulation additiv im FFF-Verfahren gefertigter Bauteile - Völkl, Harald; Mayer, Johannes; Wartzack, Sandro (Konstruktion für die Additive Fertigung 2019, 2020)
Additive Fertigung ist zum etablierten Prozess geworden. Durch schichtweisen Aufbau werden nicht mehr nur Prototypen gefertigt, sondern auch Bauteile mit hohen Steifigkeits- und Festigkeitsanforderungen. Im Fused Filament Fabrication (FFF)-Verfahren gefertigte Bauteile werden schichtweise durch Extrusionspfade aufgebaut und besitzen in Pfadrichtung üblicherweise bessere mechanische Eigenschaften als quer dazu. Unterschiedliche Extrusionspfade, insbesondere im Bauteilinneren („Infills”) besitzen daher einen hohen Einfluss auf die mechanischen Bauteileigenschaften. Um diese bereits vor der eigentlichen Fertigung abschätzen zu können, wurde ein Simulationsansatz entwickelt, der ausgehend von Fertigungsinformation (G-code) ein Simulationsmodell aufbaut, welches die lokal unterschiedlichen Materialorientierungen berücksichtigt. Dieser Ansatz soll detailliert vorgestellt und anhand eines Demonstratorbauteils mit unterschiedlichen Infill-Mustern angewandt werde
Keywords: Leichtbau; Additive Fertigung; Simulation; Fused Filament Fabrication

Subject-specific tribo-contact conditions in total knee replacements: a simulation framework across scales - Rothammer, Benedict; Wolf, Alexander; Winkler, Andreas; Schulte-Hubbert, Felix; Bartz, Marcel; Wartzack, Sandro; Miehling, Jörg; Marian, Max (Biomechanics and Modeling in Mechanobiology, 2023)
Fundamental knowledge about in vivo kinematics and contact conditions at the articulating interfaces of total knee replacements are essential for predicting and optimizing their behavior and durability. However, the prevailing motions and contact stresses in total knee replacements cannot be precisely determined using conventional in vivo measurement methods. In silico modeling, in turn, allows for a prediction of the loads, velocities, deformations, stress, and lubrication conditions across the scales during gait. Within the scope of this paper, we therefore combine musculoskeletal modeling with tribo-contact modeling. In the first step, we compute contact forces and sliding velocities by means of inverse dynamics approach and force-dependent kinematic solver based upon experimental gait data, revealing contact forces during healthy/physiological gait of young subjects. In a second step, the derived data are employed as input data for an elastohydrodynamic model based upon the finite element method full-system approach taking into account elastic deformation, the synovial fluid’s hydrodynamics as well as mixed lubrication to predict and discuss the subject-specific pressure and lubrication condition
Keywords: Total knee replacement; Biomechanics; Biotribology; Multiscale simulation; In silico modeling

Subjektive Adaptionsfähigkeit im Kontext der alternssensiblen Produktentwicklung - Kamin, Stefan; Luft, Thomas; Miehling, Jörg; Williger, Bettina; Lang, Frieder; Wartzack, Sandro (Proceedings of the 25th Symposium Design for X, 2014)
Successful user involvement in user-centered product development should consider the motivational differences of older adults. We explored the influence of motivation when evaluating new technological products. We report findings based on the Subjective Technology Adaptivity Inventory – a measure of inter-individual differences in the motivation to use technology. Older adults participated in focus groups over a period of one year. Sessions involved the subjective evaluation of different technological products. Findings suggest that subjective technology adaptivity was associated with higher perceived usefulness of products. This association was stronger with increasing age. We discuss the findings with regard to the development of technological products for older adult
Keywords: User-centered product development; user involvement; aging; subjective technology adaptivity inventory

Surface modifications for adaption of tribological conditions in sheet-bulk metal forming processes - Löffler, Maria; Andreas, Kolja; Engel, Ulf; Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro; Stangier, Dominic; Tillmann, Wolfgang; Merklein, Marion (Proceedings THE "A" Coatings, 2016)
Keywords: Sheet-bulk metal forming; Coatings; Friction

Symbolic Parametric Representation of the Area and the Second Moments of Area of Periodic B-Spline Cross-Sections - Denk, Martin; Jäger, Michael; Wartzack, Sandro (Applied Mechanics, 2023)
The calculation of moments of area is one of the most fundamental aspects of engineering mechanics for calculating the properties of beams or for the determination of invariants in different kind of geometries. While a variety of shapes, such as circles, rectangles, ellipses, or their combinations, can be described symbolically, such symbolic expressions are missing for freeform cross-sections. In particular, periodic B-spline cross-sections are suitable for an alternative beam cross-section, e.g., for the representation of topology optimization results. In this work, therefore, a symbolic description of the moments of area of various parametric representations of such B-splines is computed. The expressions found are then compared with alternative computational methods and checked for validity. The resulting equations show a simple method that can be used for the fast conceptual computation of such moments of area of periodic B-splines.
Keywords: B-spline; cross-section; beam; moments of area; parametric; symbolic; moments; area

Symposium „Design for X“ und Summer School Toleranzmanagement - Wartzack, Sandro; Schleich, Benjamin (WiGeP News, 2020)

Synthesis of passive lightweight orthoses considering humanmachine interaction - Steck, Patrick; Scherb, David; Miehling, Jörg; Völkl, Harald; Wartzack, Sandro (DS 119: Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
With increasing age, the probability of neurological diseases such as strokes, cancers, meningitis and Parkinson’s also increase. A stroke, for instance, often leads to damage to the central nervous system and therefore subsequent problems within the musculoskeletal system occur. Such movement restrictions are currently treated with the help of orthoses. However, commercial passive orthoses have the disadvantage that not all functions are covered, e. g. supporting all phases of the gait cycle. Full functionality can only be ensured with heavier active orthoses. The aim of this contribution is to develop a new hybrid user-centered/lightweight-design approach with which fully functional, passive lightweight orthoses can be designed and developed effectively in the future. Therefore, the methodology according to PAHL/BEITZ is expanded by including user-specific functions and attributes. The developed approach is applied on an ankle-foot-orthosi

Sysml 4 Digital Twins – Utilization of System Models for the Design and Operation of Digital Twins - Wilking, Fabian; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
The implementation of Digital Twins has become a common task for many industrial companies to ensure a sufficient digitization of their products and maintain competitiveness. This results in the question of how to compensate additional effort caused by designing Digital Twins. With this paper, an approach for this compensation is presented by creating Digital Twin behaviour through utilizing SysML diagrams and directly derivate usable code from them for a further implementation. This offers a part solution of lowering the threshold for using MBSE and increasing its benefits.<br
Keywords: model-based systems engineering (MBSE); cyber-physical systems; systems engineering (SE); digital design; complex systems

Systematic development of load-path dependent FLM-FRP lightweight structures - Völkl, Harald; Wartzack, Sandro (Design Science, 2021)
Additive manufacturing offers a high degree of design freedom. When Design for Additive Manufacturing is conducted properly, lightweight potential can be exploited. This contribution introduces a novel design approach for the widespread fused layer modelling (FLM) technology when using orthotropic Fibre Reinforced Polymer filament. Its objective is to obtain stiff and strong load-path optimized FLM structures in a structured and algorithmic way. The approach therefore encompasses (1) build orientation optimization to consider weaker bonding between layers than intralayer; (2) topology optimization with orthotropic material properties to obtain favourable overall geometry and inner structure; (3) direct build path generation from optimized material orientation and alternatives to the direct generation and (4) simulation. The approach is demonstrated using a lift arm under multiple load cases and further demonstrator parts to show its general applicability. Lightweight potential of individual optimization steps and the influence of modifications contrasting general non-FLM-specific optimization are studied and discusse
Keywords: Lightweight Design; Additive Manufacturing; Fibre-Reinforced Plastics; Fused Layer Modelling; Structural Optimisation

Szenario-Analyse zur Digitalisierung und Automatisierung des Produktentwicklungsprozesses - Dworschak, Fabian; Küstner, Christof; Schleich, Benjamin; Wartzack, Sandro (Tagungsband 16. Gemeinsames Kolloquium Konstruktionstechnik, 2018)
The Federal Ministries of Economic Affairs and Energy, Transport and Digital Infrastructure and the Federal Ministry of the Interior presented the Digital Agenda 2014 - 2017 in August 2014. The catalogue of measures presented describes digital work with the help of modern IT technologies such as data mining (DM) and new development methods such as model-based systems engineering (MBSE). Until 2018, these technologies made their way into several large corporations and specialized IT companies. However, their distribution in small and medium-sized enterprises (SMEs) is still very low. This can be a major economic disadvantage for them, as the technologies are based on holistic approaches, such as systems-of-systems models and networking between customers and suppliers. The technology transfer project "Optimization-based design methodology in early phase of mechatronic product development (OptMePro)" of the European Regional Development Fund (EFRE) aims at developing methods and models for the integration of modern development methods and IT technologies for SMEs. In particular, this article presents a process model for a scenario analysis that enables SMEs to analyze their own product development process (PDP) regarding the current grade of digitization and automation. This process model characterizes the PDP, reveals automation potentials and finally suggests suitable measures for improvement. The process model is universally applicable, so that it meets the needs of as many SMEs as possible. In addition, the intermediate results of the procedure are clearly and comprehensibly visualized in order to guarantee their application in SMEs. Moreover, it ensures the individual identification of fields of action for machine learning processes, facilitates the integration of data-driven tools into modern product development processes and thus forms the basis for iterative digitization and automation of the PDP in SME
Keywords: Model-Based Engineering; Traceability; Digital Engineering

Tailored Coatings – Zur Auslegung beschichteter Bauteile - Tremmel, Stephan; Wartzack, Sandro; Meerkamm, Harald (Konstruktion, 2009)
Im Fahrzeug- und im Maschinenbau werden Komponenten zunehmend höher beansprucht. Dies gilt sowohl für die Bauteile selbst als auch für ihre Oberflächen. Sich kontaktierende Oberflächen stellen oft bestimmende Wirkflächenpaare dar (Zahnflanken, Nocke/Tassenstößel). Es ist daher konsequent, gezielt die Leistungsfähigkeit der Oberflächen zu steigern, um Wirkungsgrad oder Lebensdauer technischer Systeme zu erhöhen. Seit einigen Jahren kommen tribologische PVD-/PACVD-Schichten, v. a. DLC-Schichten, zum Einsatz. Diese erlauben die gezielte Adaption der Oberfläche auf die Anwendung. Man kann also von maßgeschneiderten Beschichtungen (Tailored Coatings) reden.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-KLMEFK.tailor
Keywords: DLC; Auslegung; Kontaktspannungen; Mehrachsigkeit

Taking into account the change of geometry in system simulation processes. - Mauser, Kristian; Breitsprecher, Thilo; Wartzack, Sandro; Hasse, Alexander (DS 80-6 Proceedings of the 20th International Conference on Engineering Design (ICED 15) Vol 6: Design Methods and Tools-Part 2 Milan, Italy, 27-30.07.15, 2015)
In product development process of dynamic systems more than one technical field (i.e. mechanical, electrical or combustion technologies) affects the product. It is of particular importance to ensure the functionality of such multi-domain products especially after changing one of the domain-specific sub-process (i.e. CAD-data in mechanical design). This is possible by simulating the system behaviour of the overall product in a multi-domain system simulation. The consideration of the detailed information of each technical domain in the system simulation is not possible at moment. Therefore the relevant information in each sub-process have to be identified and insert into the system simulation. In this contribution focus is set on mechanical sub-process. An application is developed that identifies all changed information of a product design in the CAD-environment and provides this information to the system simulation. A proof of the functionality of the developed procedure in shown in a use case. The piston of a single-cylinder combustion engine model is changed by the designer. After that the developed application is executed and the changed simulation results are discussed.
Keywords: Systems Engineering (SE); Design Engineering; Design Process

Teilprojekt 1: Virtuelle und experimentelle Toleranzuntersuchungen abweichungsbehafteter Baugruppen - Bode, Christoph; Schleich, Benjamin; Wartzack, Sandro (Abschlussbericht DFG-Forschungsgruppe FOR 2271, 2. Phase. Prozessorientiertes Toleranzmanagement mit virtuellen Absicherungsmethoden, 2023)

Temperature Behavior of Rolling Bearings Exposed to Centripetal Acceleration - Hochrein, David; Tremmel, Stephan; Wartzack, Sandro (Bearing World International Bearing Conference The Expert Forum for Bearings - Rolling and Plain Bearings!, 2018)
Rolling bearings which are operating under the influence of high centripetal accelerations are often subjected to enormous requirements. Beside the nominal lifetime and the arising frictional moment, the bearing temperature – an important factor for the achievable operating life of such bearings – is also a crucial aspect for the feasibility of rolling element bearings in the context of great accelerations. For this purpose the bearing temperatures in and outside of the load zone were measured during several tests in the acceleration field. The evaluation of the measurement results shows, among further findings, that the bearing load does not necessarily have a big influence on the temperature with bearings under the influence of centripetal acceleration
Keywords: rolling element bearings; centripetal acceleration; temperature behavior

The Balance Between a Usable and Emotional Product Design - A Concept for Prioritising Relevant Influencing Factors - van Remmen, Judith Sophie; Horber, Dennis; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)
Usability and emotionality represent fundamental aspects of user experience. Yet designing an equally usable and emotionally appealing product remains a challenge for product developers, not least due to conflicting goals. Product developers need a deep understanding of what is important to users in different situations of use to make a user-oriented decision between a more usable or emotionally appealing product design. To support product developers in conflicting decision-making situations, the presented systematic approach for the selection and prioritization of context-relevant influencing factors can contribute. By mapping influencing factors and the prioritization using decision theory methods, the importance of the influencing factors in different usage scenarios can be identifie
Keywords: Usability; emotional design; user experience; user-centred design; decision making

The challenge of handling material information from different sources - Krehmer, Hartmut; Wartzack, Sandro; et al. (Proceedings of the 18th International Conference on Engineering 2011 (ICED 11), 2011)
Nowadays there are a lot of different kinds of material information needed in the product development process. This article will analyze the challenge of handling material information from different sources and different phases in the development process of the automotive industry. The needs for various kinds of material information are analyzed by different subjects (legislative regulations, construction design, strategically requirements). The information sources are examined in order to understand the differences and the reasons for the difficulties that occur when integrating the material information into the systems and sources. As a result the main problem will be identified, which is the different semantics or naming of the materials. Two possible solutions to overcome the difficulties and to make the available information accessible are evaluated and compared. These approaches are a data warehouse and an intelligent search engine. On the basis of the evaluation the search engine approach will be identified as the preferred one. While a more sufficient solution to solve the problem of the many sources is presented, this article also provides a solution to overcome the problem of the different semantics. Copyright © 2002-2012 The Design Society. All rights reserved.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.thecha
Keywords: Heterogeneous systems; Integrating material information; Material information; Semantic problems

The Determination of Assistance-as-Needed Support by an Ankle–Foot Orthosis for Patients with Foot Drop - Scherb, David; Steck, Patrick; Wechsler, Iris; Wartzack, Sandro; Miehling, Jörg (International Journal of Environmental Research and Public Health, 2023)
Patients who suffer from foot drop have impaired gait pattern functions and a higher risk of stumbling and falling. Therefore, they are usually treated with an assistive device, a so-called ankle–foot orthosis. The support of the orthosis should be in accordance with the motor requirements of the patient and should only be provided when needed, which is referred to as assistance-as-needed. Thus, in this publication, an approach is presented to determine the assistance-as-needed support using musculoskeletal human models. Based on motion capture recordings of multiple subjects performing gaits at different speeds, a parameter study varying the optimal force of a reserve actuator representing the ankle–foot orthosis added in the musculoskeletal simulation is conducted. The results show the dependency of the simulation results on the selected optimal force of the reserve actuator but with a possible identification of the assistance-as-needed support required from the ankle–foot orthosis. The required increase in support due to the increasing severity of foot drop is especially demonstrated with the approach. With this approach, information for the required support of individual subjects can be gathered, which can further be used to derive the design of an ankle–foot orthosis that optimally assists the subjects.<br
Keywords: ankle–foot orthosis; digital human models; gait assistance; musculoskeletal simulation; foot drop; muscle weakness; design for medical devices

The evolution of knowledge-based engineering from a design research perspective: Literature review 2012–2021 - Kügler, Patricia; Dworschak, Fabian; Schleich, Benjamin; Wartzack, Sandro (Advanced Engineering Informatics, 2023)
Knowledge-based engineering (KBE) is a research field, which evolved in the 1980s within the context of artificial intelligence (AI), computer aided design (CAD) and computer programming. KBE is often referred to methods, processes and tools for knowledge reuse and design automation promising time and cost benefits in engineering design and originally especially in aerospace and automotive industry. Despite the long period of existence, theoretical foundations of KBE are weak and scientific literature is quite dispersed. About a decade ago, a review by Verhagen et al. collected the state of research and identified future research challenges, which has gained impact within the KBE research community. Therefore, within our review we aim at analysing the evolution of those research challenges in KBE literature during the last decade and further provide an overview of current shortcomings from a design research perspective. The analysis comprises 160 publications from the period of 2012 to 2021. Key findings from the review show, that the challenges from 2012 remain unsolved. We further derived that reuse and adoption of KBE approaches from literature is impeded by (1) a missing conceptualization of KBE research, (2) insufficient links from knowledge source to automation and (3) a tendency of insufficient distinction of the application area.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Design automation; Engineering design; KBE; Knowledge engineering; Knowledge-based engineering; Review

The Implications of the Skin Model Concept for Computer Aided Tolerancing - Schleich, Benjamin; Wartzack, Sandro (Smart Product Engineering, 2013)
During product origination many deviations occur which manifest in unreliable functional behaviour and reduced product quality. Thus, the observable geometric deviations have to be limited by geometric tolerances of function-relevant part features. In this context the standards for Geometrical Product Specification and Verification (GPS) provide helpful tools for geometric tolerancing. A basic concept within these standards is the skin model concept which can be understood as a model of the physical interface between the workpiece and its environment. Recent research tries to translate this concept into discrete geometry and focuses upon the technical aspects related to generating skin model shapes, whereas the implications of this concept and emerging simulation possibilities for the geometric variations management process stay disregarded. Therefore, this paper highlights the consequences of the skin model concept and modern simulation tools for the computer aided tolerancing process and the management of geometric deviations during product development.
Keywords: Skin Model; Geometric Variations Management; Tolerance Management; Computer Aided Tolerancing

The influence of speed and load spectra on the friction of rolling bearings - Stahl, Thomas; Tremmel, Stephan; Meerkamm, Harald; Wartzack, Sandro (65th STLE Annual Meeting & Exhibition 2010, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.theinf

The Influence of the Centripetal Acceleration on the Temperature Behavior of Rolling Bearings - Hochrein, David; Tremmel, Stephan; Wartzack, Sandro (Bearing World Journal, 2018)
The bearing temperature is one of the essential variables in order to describe a bearing system. Especially under extreme conditions such as external accelerations, an unsuitable temperature development at the bearing position can cause significant damage. This work examines the temperature behavior under the influence of high centripetal accelerations up to 1 000- times gravity. Therefore, the factors centripetal acceleration, relative speed of the specimen and the oil flow rate were varied systematically. Contrary to our expectations, the temperature does not rise with an increase of the centripetal acceleration. This behavior can essentially be explained by the impact of the acceleration to the supplied oil flow rate. Therefore the increased injection speed of the lubricating and cooling oil leads to a better cooling of the roller bearings and the bearing temperature nearly remains constant. If the relative speed of the specimen increases, the bearing temperature behaves as with bearings, which are not exposed to the influence of high accelerations. E.g. the temperature rises, even if only moderate. The temperature behavior was analyzed and evaluated in the context of the present frictional moment. In order to achieve a sufficient cooling effect by the lubricating oil flow an appropriate amount of lubricant is necessary. The present investigation showed that with roller bearings exposed to centripetal accelerations the necessary amount of oil is about ten times higher than under normal circumstances. Appropriate flow rates depending on the requirements were identified by the variation of the oil flow rate. A look at the overall context shows that the bearing temperature is not an exclusion criterion for the use of roller bearings exposed to high accelerations. With an appropriate design of the oil supply also a self-regulation effect of the oil flow rate can be achieved by the present accelerations.<br
Keywords: roller bearings; centripetal acceleration; temperature behaviour; appropriate oil supply quantity

The Interplay of Subjective Quality Evaluation, Prototyping Technologies and the User's Technology Acceptance - Buker, Tina; Endreß, Felix; Miehling, Jörg; Wartzack, Sandro (Proceedings of the Design Society, 2022)
Subjective product quality is a fundamental aspect to maintain a high level of user acceptance and to provide a good user experience. Prototypes can be used to evaluate subjective product quality in early design phases. We conducted an empirical study to examine the influence of different (re)presentations of prototypes determined by the chosen technology (2D image, VR, AR, 3D print) and the user's technology acceptance. Based on the results we recommend 2D images as most reliable for evaluating subjective product quality.<br
Keywords: empirical studies; emotional engineering; prototyping; subjective quality; technology acceptance

The Load-Scanning Test Evaluation of a Universal Tribological Model Test in View of Sheet Bulk Metal Forming - Hetzner, Harald; Tremmel, Stephan; Wartzack, Sandro (Key Engineering Materials, 2012)
Combining the loading conditions of two different classes of forming operations, in sheet bulk metal forming processes, contact pressures ranging from a few hundred MPa up to loads exceeding 2,500 MPa are experienced. With the additional need for an enhanced control of the material flow, which is best implemented by locally adapted frictional properties of the contact tool/workpiece, sheet bulk metal forming represents a challenge to tribology. As a consequence, the evaluation of the friction and wear properties of different surface modifications and lubricants within a variety of loading conditions is required. The load-scanning test is a universal tribological model test. Its most distinctive feature is the ability to assess the friction and wear behaviour of a tribological pairing within a whole range of contact loads in a single test run. The simple and quick test method also allows the investigation of plastic contacts. Due to these features, the load-scanning test is of particular interest with regard to the quantitative and qualitative evaluation of the application potentials and limits of use of tribological measures intended for sheet bulk metal forming. Like any model test, the load-scanning test has also specific drawbacks. In some test setups, the stress distribution in the contact area may be non-uniform. Further, the maximum realizable contact pressure may be limited by low yield strengths of the tested materials in combination with the insufficient flow restriction of the contact geometry and/or the moderate machine force. By comparison to other test methods and by giving examples of its application in different scenarios, the present paper discusses the potentials and limitations of the load-scanning test against the background of sheet bulk metal forming.© (2012) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.theloa
Keywords: Forming tool tribology; Load-scanning test; Sheet bulk metal forming; Tribological model test

The realization of an engineering assistance system for the development of noise-reduced rotating machines - Küstner, Christof; Wartzack, Sandro (DS 80-4 Proceedings of the 20th International Conference on Engineering Design (ICED 15), 2015)
Today, product developer face the challenge taking not only the requirements for mechanical properties of a product into account, but also other requirements like the acoustical properties, for instance. If undesired acoustical product properties are identified product developer ask experts for counter-measures. They usually can find solutions for these acoustical issues by detailed analysis of data like sound emission measurements, noise and vibration measurements or validated multi-body simulation results. By aid of an engineering assistance system the knowledge of the expert can be provided to product developer in order to reapply these findings for new products or product variants already in early design phases of the product development process. This will help the product developer to guarantee the specified acoustical product properties already in the earlier phases. This contribution will give an insight in the realization of the engineering assistance system ALARM for the development of noise-reduced machines.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.therea
Keywords: Knowledge management; Early design phases; Product modelling; models; Design for X (DfX)

The role of product development in the battle against product-related stigma – a literature review - Schröppel, Tina; Miehling, Jörg; Wartzack, Sandro (Journal of Engineering Design, 2021)
Stigma may be the Achilles’ heel of Inclusive Design, having a variety of negative effects on the user, e.g. anxiety or depression. From a product development (PD) perspective, such negative user stigmatisation can lead to the rejection of a product. PD cannot defeat stigma itself, but it can make a valuable contribution by reducing product-related stigma. Joining the battle, this contribution analyses the role of PD and identifies supports that help to reduce stigma in the respective context using an initial and a systematic literature review. The role of PD is split into four categories addressing the need to fulfil specific demands (reduce stigma and improve personal well-being), exploit potentials (see design as a tool, use the power of product semantics and design for our future selves), solve current problems (lack of knowledge and not taking the user seriously) and manage boundary conditions (complexity of stigma and the stigma-sensitivity of products). Individual, process, educational solutions or general strategies are supports that help meeting those expectations. Due to different challenges, there is still a need for action to improve those supports to deliver specific design recommendations and reduce the lack of knowledg
Keywords: Inclusive Design; stigma; support; product design; systematic literature review

The Value of Information in Clustering Dense Matrices: When and How to Make Use of Information - Endreß, Felix; Kipouros, T.; Buker, Tina; Wartzack, Sandro; Clarkson, P. J. (Proceedings of the Design Society, 2022)
Characterising a socio-technical system by its underlying structure is often achieved by cluster analyses and bears potentials for engineering design management. Yet, highly connected systems lack clarity when systematically searching for structures. At two stages in a clustering procedure (pre-processing and post-processing) modelled and external information were used to reduce ambiguity and uncertainty of clustering results. A holistic decision making on 1) which information, 2) when, and 3) how to use is discussed and considered inevitable to reliably cluster highly connected systems.<br
Keywords: cluster analysis; design structure matrix (DSM); socio-technical systems; dense matrices; design models

Ti3C2Tx Solid Lubricant Coatings in Rolling Bearings with Remarkable Performance beyond State-of-the-Art Materials - Marian, Max; Feile, Klara; Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro; Seynstahl, Armin; Tremmel, Stephan; Krauß, Sebastian; Merle, Benoit; Boehm, Thomas; Wang, Bo; Wyatt, Brian C.; et al. (Applied Materials Today, 2021)
Two-dimensional (2D) transition metal carbides, nitrides, and carbonitrides, known as MXenes, are a growing class of 2D materials, which offer great solid lubrication ability for low friction applications due to their weakly bonded multi-layer structure and tribo-layer formation with self-lubricating characteristics. To date, most studies have assessed their tribological response in basic laboratory tests. However, these tests do not adequately reflect the complex geometries, kinematics, and stresses present in machine components. Here, we aim at bridging this gap through assessment of the friction and wear performance of multi-layer Ti3C2Tx MXene solid lubricant coatings used in rolling bearings. MXenes’ tribological response is compared with state-of-the art solid lubricant coatings, which include molybdenum disulfide (MoS2), tungsten-doped hydrogenated amorphous carbon (a‑C:H:W), and hydrogen-free, more graphite-like amorphous carbon (a‑C). Multi-layer Ti3C2Tx MXene coatings reduce wear on the bearing washers by up to 94 %, which can be attributed to the transfer of the lubricious MXene nano-sheets to secondary tribo-contacts of the bearing. While the frictional torque of all solid lubricant coatings is similar during steady-operation, the MXene-coated bearings extend the service life by 30 % and 55 % compared to MoS2 and DLC, respectively. This contribution demonstrates the ability of MXene solid lubricant coatings to outperform state-of-the-art solid lubricants in dry-running machine components such as rolling bearing
Keywords: 2D materials; MXenes; MoS2; DLC; solid lubrication; rolling bearings

Time vs. Space: Comparing gait cycle normalization methods and their effect on foot placement control - Fleischmann, Sophie; Shanbhag, Julian; Miehling, Jörg; Wartzack, Sandro; Leyendecker, Sigrid; Koelewijn, Anne; Eskofier, Björn (28th Congress of the European Society of Biomechanics, 2023)

Tolerance Analysis of Additively Manufactured Non-assembly Mechanisms considering Joint Clearance - Schächtl, Paul; Hallmann, Martin; Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2020)
Besides numerous advantages, Additive Manufacturing enables the manufacturing of entire non-assembly mechanisms within one single process step. However, this requires comparatively large joint clearances that significantly influence their functionality. Existing tolerance analysis methods completely neglect or simplify these clearances and thus cannot adequately represent a realistic motion behavior. With the aim to overcome this drawback, this contribution presents a novel method for the statistical tolerance analysis of additively manufactured mechanisms. The integration of results from multi-body simulation enables a realistic representation of the movements within the joints. Finally, the exemplary application to a planar non-assembly mechanism shows, that the process-related large joint clearances have more significant influence than the part deviations.<br
Keywords: Additive ManufacturingTolerance AnalysisNon-assemblyJoint ClearanceMulti-body Simulation

Tolerance analysis of mechanism taking into account the interactions between deviations using meta-models - Walter, Michael; Sprügel, Tobias; Wartzack, Sandro (Proceedings of the 9th Norddesign, 2012)
A product’s functionality depends largely on the interaction of its components and their geometries. Hence, tolerance analyses are used to determine the effects of deviations on a functional key characteristic – also for mechanism. However, possible interactions between the different deviations and the resulting effects among themselves as well as on the functional key characteristics are not considered yet. This paper considers the extension of an existing “integrated tolerance analysis of systems in motion” approach in detail: The integration of meta-models, which represent the interactions, into the system’s functional relationship. Therefore different meta-modeling techniques as well as validation techniques are used. Consequently a recommendation can be derived, how the product developer can achieve a high prediction quality of the meta-models and therefore a reliable tolerance analysis of mechanism taking into account the appearing interactions.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.tolera
Keywords: tolerance analysis; mechanism; meta-modeling; data-mining; cross-validation

Tolerance Analysis of Rotating Mechanism Based on Skin Model Shapes in Discrete Geometry - Schleich, Benjamin; Wartzack, Sandro (Procedia CIRP, 2015)
Geometric deviations are inevitably observable on every manufactured workpiece. These deviations affect the function and quality of mechanical products and have therefore to be controlled by geometric tolerances. Computer-aided tolerancing aims at supporting design, manufacturing, and inspection by determining and quantifying these effects of geometric deviations on the product quality and the functional behaviour. However, most established tolerance representation schemes imply abstractions of geometric deviations and are not conform with the standards for geometric dimensioning and tolerancing. These limitations led to the development of a Skin Model inspired framework for the tolerance analysis, which is based on a representation of non-ideal workpieces employing discrete geometry representation schemes, such as point clouds and surface meshes. In this contribution, this Skin Model inspired framework for computer aided tolerancing is extended to systems in motion and applied to the tolerance analysis of rotating mechanism with higher kinematic pairs. For this purpose, the generation of non-ideal part representatives, as well as their processing with algorithms for registration and computational geometry are highlighted. Finally, the results are visualized and interpreted. The procedure as well as the simulation model itself are shown in a case study of a disk cam mechanism.
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.tolera
Keywords: Skin Model; Tolerance Analysis; Rotating Mechanism; Discrete Geometry; Computational Geometry

Tolerance analysis of systems in motion taking into account interactions between deviations - Walter, Michael; Sprügel, Tobias; Wartzack, Sandro (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2013)
A product's functionality depends largely on the interaction of its components and their geometries. Hence, tolerance analyses are used to determine the effects of deviations on functional key characteristics of mechanisms. However, possible interactions between the different deviations and the resulting effects on themselves as well as on the functional key characteristics have not yet been considered. This article considers the extension of the existing "integrated tolerance analysis of systems in motion" approach. By means of the methodology, the interactions between appearing deviations can be identified and integrated into a tolerance analysis functional relation. Therefore, the appearing interactions are represented by meta-models that can be easily integrated into the functional relation. Consequently, the product developer is able to gain information about the effects of deviations on functional key characteristics, as well as the effects of the deviations among themselves. In order to show the methodology's practical use, the interactions between deviations of a nonideal crank mechanism inside a four-stroke combustion engine are considered. For this purpose, two different meta-modeling techniques are used: response surface methodology and artificial neural networks. © IMechE 2012.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-KLMEFK.tolera
Keywords: Artificial neural networks; Interactions; Meta-modeling; Systems in motion; Tolerance analysis

Tolerance-Cost-Optimization of Systems with time-variant Deviations - Walter, Michael; Sprügel, Tobias; Wartzack, Sandro (Proceedings of the 13th CIRP Conference on Computer Aided Tolerancing, 2014)
This paper presents a methodology for the statistical tolerance-cost-optimization of systems with time-variant deviations, such as deformation, thermal expansion, mobility of parts and wear. By means of the approach, the product developer can identify the system’s optimal tolerance design against the backdrop of the diverging requirements: wide tolerances to reduce costs vs. narrow tolerances to ensure functionality. Therefore, Particle Swarm Optimization – a global statistical optimization technique – is applied to the time-variant tolerance-optimization problem to determine the tolerance range as well as a certain mean shift for each non-ideal dimension. The practical use of the methodology is illustrated for a modified tolerance stack-up problem. We provide a comprehensive walkthrough of the methodology’s application to the stack-up problem. Therefore, the essential mathematical background, the required functional dependencies and the considered parameters are detailed in a step-by-step procedure. So, we aim to establish the application of the statistical tolerance-cost-optimization in academia and industry and to motivate students and young graduates to apply this methodology by themselves.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.tolera
Keywords: tolerance synthesis; time-dependent mechanisms; deformation; thermal expansion; particle swarm optimization

Tolerance management during the design of composite structures considering variations in design parameters - Franz, Michael; Schleich, Benjamin; Wartzack, Sandro (International Journal of Advanced Manufacturing Technology, 2021)
Composite structures play an important role in realising resource-efficient products. Their high lightweight potential and improved manufacturing technologies lead to an increased use in high-volume products. However, especially during the design and development of high-volume products, the consideration of uncertainties is essential to guarantee the final product quality. In this context, the use of modern lightweight materials, such as fibre reinforced plastics (FRP), leads to new challenges. This is due to their high number of design parameters, which are subject to deviations from their nominal values. Deviating parameters, e.g. ply angles and thicknesses, influence the manufacturing process as well as the structural behaviour of a composite part. To consider the deviating design parameters during the design process, a new tolerance optimisation approach is presented, defining tolerance values for laminate design parameters, while ensuring the functionality of the composite structure. To reduce the computational effort, metamodels are used during this optimisation to replace finite element simulations. The proposed approach is applied to a use case with different key functions to show its applicability and benefit
Keywords: Composite structures; Tolerance optimisation; Metamodel; Endless fibre reinforced plastics

Tolerance Optimization of Patch Parameters for Locally Reinforced Composite Structures - Franz, Michael; Wartzack, Sandro (Applied Composite Materials, 2022)
A rising number of applications and increasing volume of composite structures production lead to a high relevance of variation management during their design. Structural optimization for lightweight purposes often results in designs consisting of a base laminate with local reinforcement patches. Nominally, these optimized designs offer a thorough exploitation of lightweight potential. Yet, they suffer from variations of the reinforcements resulting in a worsened manufacturing behavior and reduced structural performance. To ensure the quality, tolerances should be allocated for the parameters of the local reinforcement patches. Therefore, in the current contribution a tolerance optimization method is presented identifying optimal tolerance values for the design parameters of the reinforcements with respect to the structural behavior. This includes the discussion of challenges regarding the suitable parametrization and modeling of local reinforcement patches for variation simulation based on Finite Element Analysis (FEA), the usage of surrogate modeling to reduce the computational effort of structural analyses, as well as an approach to penalize tight tolerances of different parameter types. The proposed tolerance optimization is applied to a use case. Tolerances for the patch parameters are optimized, meeting the structural quality constraints of the composite structure.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Composite structures; Local reinforcement; Surrogate modeling; Tolerance optimization

Toleranz-Kosten-Optimierung abweichungsbehafteter Systeme - Wartzack, Sandro; Walter, Michael (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2014)
UnivIS-Import:2015-03-09:Pub.2014.tech.FT.FT-KLMEFK.tolera_1

Toleranz-Kosten-Optimierung bewegter Systeme mittels Partikelschwarm-Optimierung - Walter, Michael; Sprügel, Tobias; Weikert, Tim; Mann, Vincent; Romeis, Marcus; Wartzack, Sandro (Design for X. Beiträge zum 25. DfX-Symposium, 2014)
Both random and systematic deviations of manufactured parts as well as variation in manufacturing processes may have significant effects on the kinematic behavior of a mechanism. Hence, the product developer has to define both appropriate tolerances of the single parts and appropriate precision requirements of the manufacturing processes to ensure the mechanism’s functionality while causing low manufacturing costs. This paper presents an approach on the statistical tolerance-cost-optimization of a time-dependent system taking into account random and systematic deviations as well as the imprecision of corresponding manufacturing processes. The practical use of the approach is shown in a case study of a non-ideal cross-arm window regulator.
Keywords: tolerance optimization; mechanism; tolerance-cost-relations; particle swarm optimization

Toleranzmanagement 4.0: Chancen und Herausforderungen der zunehmenden Digitalisierung in der Fertigung für das Toleranzmanagement - Schleich, Benjamin; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 3. Summer School - September 2017, 2017)

Toleranzmanagement am KTmfk - Wartzack, Sandro; Schleich, Benjamin; Walter, Michael; Ziegler, Philipp (Summer School Toleranzmanagement: Beiträge zur 1. Summer School, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.tolera_9

Toleranzmanagement am Lehrstuhl für Konstruktionstechnik - Wartzack, Sandro; Schleich, Benjamin; Heling, Björn; Aschenbrenner, Alexander; Götz, Stefan (Summer School Toleranzmanagement - Beiträge zur 3. Summer School - September 2017, 2017)

Toleranzmanagement im Kontext von Industrie 4.0 - Wartzack, Sandro; Schleich, Benjamin; Aschenbrenner, Alexander; Heling, Björn (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2017)
Das Toleranzmanagement umfasst alle Tätigkeiten zur Steuerung geometrischer Bauteilabweichungen entlang des Produktlebenszyklus und ist daher von großer Bedeutung für produzierende Unternehmen. Gewohnte Wertschöpfungsketten befinden sich jedoch angesichts der vierten industriellen Revolution im Umbruch. Der Beitrag gibt daher einen Überblick über die Chancen und Herausforderungen für das Toleranzmanagement im Kontext von Industrie 4.0 und stellt mögliche Lösungsansätze vor.

Toleranzmanagement in Konzept- und früher Entwurfsphase: Erste Ansätze und Potentiale - Götz, Stefan; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
Accompanied by the frontloading efforts in product development, tolerancing becomes more and more important in early design stages. Motivated by the lack of methods for early phases of the design process, three approaches for considering tolerances in conceptual and preliminary design stages are presented in this paper. The first allows assessing the robustness of concepts with the help of a tolerance-specific FMEA. A subsequent method enables a tolerance specification and analysis based on a graphical visualization of the product structure. Furthermore, a sensitivity analysis for skeleton models is presented. By using these methods the design and tolerancing process runs simultaneously. Hence, a robust design and reliable tolerances already exist at the beginning of the detail design.
Keywords: Conceptual Design; Preliminary Design; Robust Design; Tolerance Analysis

Tolerierung bei der Auslegung endlosfaserverstärkter Faserverbundbauteile - Franz, Michael; Wartzack, Sandro (WiGeP News, 2021)

Topologieoptimierung mit transversal isotropem Materialmodell – Produktentwickler auf der Suche nach der optimalen Geometrie für Faser-Kunststoff-Verbunde - Völkl, Harald; Franz, Michael; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
Fiber-reinforced plastics bear a huge potential for lightweight design, especially due to their high strength-to-weight ratio and anisotropic behavior. Within topology optimization, due to the high number of dependent variables, specific solutions for transversely isotropic materials rarely exist – and existing ones require considerable computational effort. Yet, to fully exploit the lightweight potential, taking anisotropy into account is indispensable. A new bionic topology optimization approach is presented to facilitate efficient and effective optimization of such materials.
Keywords: Topology Optimization; FEA; Bionics; Fiber-reinforced plastic

Toward cost-efficient tolerancing of 3D-printed parts: a novel methodology for the development of tolerance-cost models for fused layer modeling - Roth, Martin; Schächtl, Paul; Giesert, Andreas; Schleich, Benjamin; Wartzack, Sandro (International Journal of Advanced Manufacturing Technology, 2022)
Tolerance allocation methods significantly contribute to the qualification of Additive Manufacturing (AM) for (small-)series production ensuring high performance and efficiency. However, their usage prerequisites the availability of quantitative, reliable information on the impact of the assigned tolerances on the resulting manufacturing costs. The given article proposes a novel methodology for the systematic development of tolerance-cost curves for a cost-efficient tolerancing of 3D-printed parts. The proposed structured workflow aims at serving as a general guideline for both researchers and practitioners, while the exemplarily chosen perspective from Fused Layer Modeling (FLM) illustrates its adaption to a specific AM technology. The indirect, non-apparent interrelations between tolerances and resulting costs are modelled with the aid of an activity-based cost model, whereas the individual costs elements are mapped as function of the values for the machine-specific process parameters for AM, e.g., layer height or printing speed, which are required to achieve the assigned design tolerances. The total procedure covers all relevant steps, viz. the identification and quantification of the single cost items, the design of benchmark artifacts, adapted to given manufacturing and measuring techniques, the empirical determination of data on cost and geometrical accuracy by design of experiments and tolerance-cost curves. Its exemplary application to an academic use case shows its general applicability and benefits, but also its current limitations.
Keywords: Tolerance-cost function; Geometrical accuracy; Additive Manufacturing; Least cost tolerance allocation; Tolerance-cost optimization; Fused Layer Modeling

Towards a more comprehensive understanding of Tolerance Engineering research importance - Krogstie, Lars; Walter, Michael; Wartzack, Sandro; Martinsen, Kristian (Proceedings of the 13th CIRP Conference on Computer Aided Tolerancing, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.toward

Towards Biomechanical Digital Human Modeling of Elderly People for Simulations in Virtual Product Development - Miehling, Jörg; Geißler, Bastian; Wartzack, Sandro (Proceedings of the Human Factors and Ergonomics Society 2013 International Annual Meeting, 2013)
This contribution illustrates a methodology to customize biomechanical digital human models to resemble people of different age and ability groups for the use in simulations to support user-centered design. Especially the conception of man models of elderly people holds potential for analyzing and optimizing products to yield more universal designs, due to the high heterogeneity of needs, wants and capabilities in this specific age group. The present approach considers age-related performance restrictions, but is also extendable to disease-related limitations. The conception process itself includes the scaling of anthropometry, muscle forces, range of motion as well as motion speed based on data from literature or manual measurements. The parameters are either selected by percentiles or the specific values itself.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.toward

Towards CAD integrated simulation of use under ergonomic aspects - Krüger, Daniel; Wartzack, Sandro (Proceedings of the DESIGN 2014 13th International Design Conference, 2014)
In this paper biomechanical human models are proposed as a possibility to simulate ergonomic aspects of user-product interaction already in the early stages of the development process. Hereby designers are enabled to quantify the relationship between design parameters and the level of biomechanical stress prevalent during product use within the user.
Keywords: ergonomics; virtual product development; design for use

Towards Customized Digital Engineering: Herausforderungen und Potentiale bei der Anpassung von Digital Engineering Methoden für den Produktentwicklungsprozess - Gerschütz, Benjamin; Sauer, Christopher; Wallisch, Anne; Mehlstäubl, Jan; Kormann, Andreas; Schleich, Benjamin; Alber-Laukant, Bettina; Paetzold, Kristin; Rieg, Frank; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung SSP 2021, 2021)
Mit dem Ziel, nationale und internationale Fachleute unterschiedlicher Disziplinen der Produktentwicklung aus Industrie und Wissenschaft in den Dialog zu bringen, organisiert der Verein zur Förderung produktionstechnischer Forschung e.V. und das Fraunhofer IAO gemeinsam mit dem Institut für Konstruktionstechnik und Technisches Design IKTD, dem Institut für Maschinenelemente IMA und dem Institut für Arbeitswissenschaft und Technologiemanagement IAT der Universität Stuttgart das Stuttgarter Symposium für Produktentwicklung SSP. Am 20. Mai 2021 findet das SSP zum sechsten Mal statt, diesmal als digitale wissenschaftliche Konferenz. Die Konferenz bietet Wissenschaftlern eine Plattform zur Präsentation und Diskussion ihrer neuesten Forschungsergebnisse im Bereich der Produktentwicklung und fördert so den interdisziplinären Wissenstransfer. Aufgerufen waren in der SSP 2021 Beiträge aus folgenden Kategorien: • Adaptive Bedienung für automatisiertes Fahren • Advanced Systems Engineering / Model-Based Systems Engineering • Agile Produktentwicklung • Design-Technik-Konvergenz • Digital Engineering • Innovations- und Technologiemanagement • Konstruktionsmethodiken • Leichtbau in der Produktentwicklung • Nachhaltige Produktentwicklung • Nutzerzentriertes Design • Wissensmanagement in der Produktentwicklung • Zuverlässige Produktentwicklung Im Plenum und vier Tracks mit jeweils drei Sessions werden 46 Beiträge präsentiert. Der Abstract der Keynote sowie die 45 Volltexte mit deutschen und englischen Abstracts sind in diesem Band zusammengefass
CRIS-Team Scopus Importer:2021-12-24
Keywords: Digital engineering; Industry 4.0; Product development

Towards individualized biomechanical models in multiple domains - Wechsler, Iris; Koelewijn, Anne; Wartzack, Sandro; Miehling, Jörg (28th Congress of the European Society of Biomechanics, 2023)

Towards Ontological Support for Principle Solutions in Mechanical Engineering - Breitsprecher, Thilo; Codesci, Mihai; Jucovaschi, Constantin; Kohlhase, Michael; Schröder, Lutz; Wartzack, Sandro (8th International Conference on Formal Ontology in Information Systems, 2014)
Among the standard stages of the engineering design process, the principle solution can be regarded as an analogue of the design specification, fixing the way the final product works. It is usually constructed as an abstract sketch where the functional parts of the product are identified, and geometric and topological constraints are formulated. Here, we outline a semantic approach where the principle solution is annotated with ontological assertions, thus making the intended requirements explicit and available for further machine processing; this includes the automated detection of design errors in the final CAD model, making additional use of a background ontology of engineering knowledg
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.toward_5
Keywords: document-oriented processes; Knowledge-based engineering

Towards postural control simulation using a sensorimotor enhanced musculoskeletal human model - Shanbhag, Julian; Fleischmann, Sophie; Eskofier, Björn; Koelewijn, Anne; Wartzack, Sandro; Miehling, Jörg (ISPGR World Congress 2023, 2023)

Towards the Understanding of Lubrication Mechanisms in Total Knee Replacements – Part I: Experimental Investigations - Nečas, David; Vrbka, Martin; Marian, Max; Rothammer, Benedict; Tremmel, Stephan; Wartzack, Sandro; Galandáková, Adéla; Gallo, Jiří; Wimmer, Markus A; Křupka, Ivan; Hartl, Martin (Tribology International, 2021)
This contribution is aimed at the detailed understanding of lubrication mechanisms within total knee replacement. While Part I is focused on the experimental investigation, Part II deals with the development of a predictive numerical model. Here, a knee simulator was used for direct optical observation of the contacts between a metal femoral and a transparent polymer components. Transient dynamic conditions were applied. Mimicked synovial fluids with fluorescently labelled constituents were used as the test lubricants. The results showed that γ-globulin forms thin boundary lubricating film, being reinforced by the interaction of phospholipids and hyaluronic acid. Further development of lubricating film is attributed to albumin layering. Based on the results, a novel lubrication model of the knee implant is propose
Keywords: Total knee replacement; Knee simulator; Fluorescent microscopy; Lubrication; Experiment

Towards the Understanding of Lubrication Mechanisms in Total Knee Replacements – Part II: Numerical Modeling - Marian, Max; Orgeldinger, Christian; Rothammer, Benedict; Nečas, David; Vrbka, Martin; Křupka, Ivan; Hartl, Martin; Wimmer, Markus A; Tremmel, Stephan; Wartzack, Sandro (Tribology International, 2021)
Total knee replacements are an effective surgical treatment to restore the function of the knee. For an adequate design, knowledge about stresses and lubrication conditions is vital. Part II proposes a fully-coupled transient 3D model for the soft elastohydrodynamically lubricated contact based upon the generalized Reynolds equation and Finite Element Method while Part I of this study focused on experimental observations. Within the scope of this contribution, a numerical model is presented and validated with experimental data. Good agreement between model predictions and experimental data was found. A strong influence of fluid and geometry assumptions and transient effects were found. Besides, it was demonstrated that the rheological synovial fluid properties have a decisive role in the tribological behavio

Towards Virtual Assessment of Human Factors: A Concept for Data-Driven Prediction and Analysis of Physical User-product Interactions - Wolf, Alexander; Binder, Nicole; Miehling, Jörg; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
The early consideration of human factors in product development hugely favours the development of products, which excel with a positive user experience. The virtual environment of product development however, still has significant gaps in the virtual assessment and simulation of human factors, especially for user-product interactions composed of human movements. This motivates us to introduce a concept for data-driven prediction and analysis of user-product interactions. Heart of the concept is a predictive component that models the interaction between the user, represented by a musculoskeletal model, and the product, represented by product characteristics. We describe the implementation of this concept based on a pilot study for a lifting task. Motion capturing was performed to build a database and compare the results of our novel approach. The resulting kinematic and dynamic quantities show similar curve profiles with a small constant offset to the measured data. This indicates that the concept enables the virtual comparison of different designs or concepts regarding human factor
Keywords: User centred design; Simulation; Early design phases; User-product interaction; Data-driven movement prediction

tribAIn – An ontology for knowledge representation in the domain of tribology - Kügler, Patricia; Marian, Max; Schleich, Benjamin; Tremmel, Stephan; Wartzack, Sandro (60. Tribologie-Fachtagung 2019. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen, 2020)
The tribAIn ontology aims to formalize knowledge obtained from tribological experiments, for supporting knowledge access and reuse. Due to the isolated and heterogeneous data sources, knowledge management with semantic technologies provide tremendous opportunities over classical databases. Especially the focus on meaning of data instead of the structure of data is suited for knowledge-intensive domains, like tribology. This meaning is formally and explicitly represented by the tribAIn ontology, which provides concepts and definitions for annotating and linking data gained from different sources, like measurement series as tabular data or results interpretation in natural language. From the perspective of an ontology-based application the tribAIn ontology forms the global scheme for querying and accessing the underlying data sources, which are linked by mapping schemes to the ontology. Compared to data warehousing, this makes semantic approaches much more flexible with respect to updating and extension of knowledge bases.<br
Keywords: ontology; tribological testing; knowledge reuse; semantic integration

tribAIn - Towards an Explicit Specification of Shared Tribological Understanding - Kügler, Patricia; Marian, Max; Schleich, Benjamin; Tremmel, Stephan; Wartzack, Sandro (Applied Sciences, 2020)
Within the domain of tribology, the science and technology for understanding and controlling friction, lubrication, and wear of relatively moving interacting surfaces, countless experiments are carried out and their results are published worldwide. Due to the variety of test procedures and a lack of consistency in the terminology as well as the practice of publishing results in the natural language, accessing and reusing tribological knowledge is time-consuming and experiments are hardly comparable. However, for the selection of potential tribological pairings according to given requirements and to enable comparative evaluations of the behavior of different tribological systems or testing conditions, a shared understanding is essential. Therefore, we present a novel ontology tribAIn (derived from the ancient Greek word “tribein” (= rubbing) and the acronym “AI” (= artificial intelligence)), designed to provide a formal and explicit specification of knowledge in the domain of tribology to enable semantic annotation and the search of experimental setups and results. For generalization, tribAIn is linked to the intermediate-level ontology EXPO (ontology of scientific experiments), supplemented with subject-specific concepts meeting the needs of the domain of tribology. The formalization of tribAIn is expressed in the W3C standard OWL DL. Demonstrating the ability of tribAIn covering tribological experience from experiments, it is applied to a use case with heterogeneous data sources containing natural language texts and tabular dat
Keywords: ontology; tribology; tribological testing; formalization; knowledge reuse; knowledge representation

Tribocatalytic Mo-X-N Coating System for Higher Efficiency of Engine Components - Dobrenizki, Ladislaus; Brugnara, Ricardo; Tremmel, Stephan; Wartzack, Sandro (MTZ Motortechnische Zeitschrift, 2020)
Surface coating is one of the most effective measures for reducing friction losses in combustion engines. High potential exists, for example, in the tribological contact between the tappet and the camshaft in the valve train. In this article, Schaeffler presents a nanostructured tribocatalytic PVD coating system made of molybdenum that forms protective tribofilms on the stressed surface. <br
Keywords: PVD Coatings; Friction reduction; Combustion Engine

Tribological adjustment of tungsten-modified hydrogenated amorphous carbon coatings by adaption of the deposition parameters - Hetzner, Harald; Zhao, Rong; Tremmel, Stephan; Wartzack, Sandro (Proceedings - 10th International Conference THE "A" Coatings, 2013)
In comparison to pure hydrogenated amorphous carbon coatings (a-C:H), the metal-modified variants (a-C:H:Me) are known to have better adhesion to the substrate due to lower residual stresses and brittleness. For this reason, particularly in higher loaded applications, like metal forming tools, a-C:H:Me is usually preferred over a-C:H, even though hardness and hence abrasion protection tends to be lower. Another interesting feature of a-C:H:Me is that, depending on the deposition parameters, the coating properties can be varied over wide ranges: From carbide-like to amorphous-carbon-like. In the present study, tungsten-modified hydrogenated amorphous carbon coatings (a-C:H:W) were deposited on tool steel by reactive magnetron sputtering of a tungsten-carbide target in argon-ethine atmosphere. From batch to batch, the four most relevant deposition parameters were varied according to a factorial design. The coatings were characterised in terms of their structural, mechanical and tribological properties. Using a statistics software, the deposition parameters significantly influencing the respective properties could be identified.
Keywords: reactive sputtering; amorphous carbon; tailored friction; factorial design

Tribological aspects in manufacturing processes of microstructured components and their tribological behavior in operation - Schrader, Tobias; Weschta, Martin; Merklein, Marion; Tremmel, Stephan; Engel, Ulf; Wartzack, Sandro (Proc. 6th International Conference on Tribology in Manufacturing Processes and Joining by Plastic Deformation, 2014)
An ever increasing mobility and a shortage of resources lead to restrictive politically driven limits for fuel consumption as well as an increasing demand of customers for efficient vehicles. Though electrification of cars proceeds, combustion engines will play an important role for conventional and hybrid concepts within next decades. Thus, for a contribution to increasing energy efficiency of vehicles it is vital to trace sources of friction losses and to identify possibilities for friction reduction in combustion engines. Therefore, the follower as a main contributor to friction losses in valve trains was chosen as a demonstrator for friction reduction effects by microstructured components. However, the realization of theoretically advantageous microstructures with filigree geometries is challenging for manufacturing technologies. The present study focuses on the elaboration of a technological basis for a repeatable production of components with microstructured surfaces by a combined cup backward extrusion micro coining process, coping with the demands of large-lot production. For realization of a high accuracy the influence of friction on geometry of microstructured components was investigated. In addition, running-in of components is decisive for final geometry and tribological behavior of microstructured surfaces and hence considered as well.
Keywords: Accuracy; Microstructures; Tribology

Tribological behavior of amorphous carbon coatings on Ti6Al4V alloy and UHMWPE for total knee replacement using a pin-on-disk tribometer - Rothammer, Benedict; Bartz, Marcel; Wartzack, Sandro (DKOU 2022, 2022)
Objectives: The aim of the endoprosthetic replacement of joints is to restore functionality and to provide patients with a painless life. Total knee replacements (TKR) usually consist of a Co28Cr6Mo (CoCr) femoral component that rubs against UHMWPE (PE) inlay. The wear particles removed from TKR are largely responsible for early prosthetic failure, primarily due to aseptic loosening. This study focused on the characterization and tribological testing of wear-reducing amorphous carbon coatings with good adhesion to Ti6Al4V (Ti64) and PE and to analyze wear mechanisms and influencing factors. Methods: Due to promising tribologically effective behavior, a tungsten-doped hydrogen-containing amorphous carbon coating (a-C:H:W) was applied to the Ti64 (Ti64:W) pins and an a-C:H coating to the UHMWPE (PE:H) disks by physical vapor deposition (PVD). A thin adhesive layer of titanium and an intermediate layer of tungsten carbide were used to achieve a good coating-substrate adhesion. In contrast, the a-C:H coating was applied to the PE substrate by reactive PVD without intermediate layers. The coating samples were characterized regarding coating thickness and adhesion to substrate using crater-grinding method [1] and scratch testing [2], respectively. Hardness was measured by instrumented indentation test [3]. The tribological behavior of the coated material pairings in comparison to the uncoated pairings was investigated utilizing a climate-controlled pin-on-disk tribometer. Efforts were made to reproduce the boundary conditions in the peri-implant environment, whereby the diluted bovine serum used was tempered to 37°C in fully flooded lubrication. The wear rates were determined using light and laser scanning microscopy. Results and conclusion: With an indentation hardness of about 16GPa, a-C:H:W coating (thickness of < 1 µm) was significantly harder than CoCr or Ti64 The coating systems deposited on Ti64 endured loads of about 8N in scratch tests without spalling. The a-C:H coating had a thickness of about 1.5µm and an indentation hardness of about 1.5GPa, which represented a forty-fold increase compared to substrate hardness while maintaining high adhesion. Thus, no coating applied to PE showed any damage in the form of chipping in the scratch tests. The wear rates of uncoated and coated disks as well as uncoated and coated pins are compared in figure 1. It was found that a coated sliding combination reduces wear on PE disks by about 41% and on pins by 77%. The a-C:H coating was suitable for preventing wear on PE due to its inert character and its favorable HIT/EIT ratio. A similar behavior was observed for the a-C:H:W coated Ti64 pins compared to the uncoated Ti64 and CoCr pins. Despite the pin having permanently been in contact, the magnitude of the wear rate differed between PE and metal substrates by a factor of 10. This could be attributed to the stiffer and harder character of metals, which could be supplemented by an additional coating with a-C:H:W to achieve tribologically favorable behavior. References German Institute for Standardization (DIN). DIN EN ISO 26423. 2016. German Institute for Standardization (DIN). DIN EN ISO 20502. 2016. German Institute for Standardization (DIN). DIN EN ISO 14577-1. 2015.

Tribological behavior of ceramic disks for application in mixer taps under different lubrication conditions - Ziegler, Marlene; Rothammer, Benedict; Marian, Max; Henzler, Stephan; Beau, Patrick; Bartz, Marcel; Wartzack, Sandro (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)
There are many tribological systems where technical ceramics are used because of their hardness and high wear resistance. Even in a mixer tap two ceramic disks are integrated in the cartridge. A common problem is the change of the haptic properties during usage, because of changes in the tribological system. Within this work the possibility of reproducing effects relvant for application in model tests is studied. Therefore, a ball-disk-tribometer in oscillating sliding mode was used to test ceramic-ceramic-pairings with varying lubricants. The tests ran without lubricant and with three lubricants of different qualities. Through the addition of any of the lubricants a reduction of the coefficient of friction in comparison to the test runs without lubricant was monitored. To consult the influence of higher temperature due to hot water inflow, all tests were performed at room temperature and at 65 °C. This variation of parameter had no big influence on the test results of tests without lubricant. In the tests with lubricants the coefficient of friction showed a clear dependency on change of temperature. To make a statement with respect to the original system, three mixer taps with different haptically characteristics were used as references

Tribological behavior of coated tungsten composites in sliding contact conditions with steel counter bodies - Sander, Thomas; Tremmel, Stephan; Wartzack, Sandro (Proceedings of the 15th Nordic Symposium on Tribology NORDTRIB 2012, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.tribol

Tribological behavior of different doped ta-C coatings for slip-rolling contacts with high hertzian contact pressure - Polzer, Markus; Bartz, Marcel; Rothammer, Benedict; Schulz, Edgar; Wartzack, Sandro (Industrial Lubrication and Tribology, 2023)
Purpose The curved and tribologically highly stressed surfaces of bearing components pose a major challenge for steel alloys or tribological resistant coatings like tetrahedral amorphous carbon (ta-C) coatings which in particular have an increased risk of delamination due to the significantly increased residual stresses. A possibility to prevent coating failure is the use of dopants while maintaining or even increasing tribological properties. This study aims to compare the tribological behavior of several doped diamond-like-carbon coatings with an undoped ta-C coating under varying slip conditions and Hertzian pressure up to 1800 MPa. Design/methodology/approach For this purpose, the tribological behavior was studied using of a ball-on-disc tribometer and a two-disc test rig under mixed/boundary conditions. The tests were conducted with coated specimens against uncoated 100Cr6 steel. Additionally, the influence of lubrication additives was studied due to the use of two fully formulated PAO-based oils, one without and one with molybdenum containing additives. The friction was measured in situ, and the wear was analyzed trough laser scanning microscopy and tactile measurement. Findings It was shown that the use of doped ta-C coatings exhibited a tendency for a more favorable tribological behavior compared to undoped ta-C coatings, with no general dependence on the lubricants used. The use of the most suitable coatings reduced the wear of the steel counter-body considerably. Originality/value To the best of the authors’ knowledge, this is the first approach of testing the tribological behavior of these doped ta-C coatings, developed for friction efficiency, in dependency on lubrication additives under the given load collective. The approach is relevant to determine whether the friction reduction and the wear inhibition of these coatings are suitable for higher contact pressures and load cycles.<br
Keywords: Tribology; DLC; ta-C coating; Friction; Wear; Slip-rolling; 2-Disc-tribometer

Tribological behaviour of amorphous carbon coatings for total knee arthroplasty - Rothammer, Benedict; Neusser, Kevin; Tremmel, Stephan; Bartz, Marcel; Wartzack, Sandro (5th International Conference on BioTribology, 2021)
Endoprosthetic replacement of the joint intends to restore the functionality and to provide the patient with a pain-free and more mobile life. However, aseptic loosening of the total knee arthroplasty (TKA) is a major cause of early prosthesis failure and is multifactorial in etiology with wear debris removed from the implant materials being largely responsible. For this reason, a great effort is made to reduce polymeric inlay wear by applying tribologically effective surface modifications. Thus, this study concentrated on the deposition of wear-reducing amorphous carbon coating systems with good adhesion to the materials Co28Cr6Mo and PE-UHMW used for medical technology applications by means of physical vapour deposition (PVD) and plasma-enhanced chemical vapour deposition (PECVD). The tribological effectiveness of the carbon coating systems can be particularly be enhanced by a good adhesion to the substrate. Therefore, specific attention was also paid to the investigation of adhesion. The tribological behaviour of the coated material pairings in comparison to the uncoated pairings was investigated utilizing a clima-controlled pin-on-disc tribometer in rotational sliding mode. The tribological behaviour was studied under mixed friction conditions for a total number of 200 000 sliding cycles. A bovine serum, tempered to 37 °C, was used as a substitute synovial fluid. The wear rates were determined using light and laser scanning microscopy every 20 000 cycles. Thereby, various wear mechanisms were detected, which in turn affected the coefficient of friction. The strong wear traces on PE-UHMW indicated abrasive and adhesive wear. Consequently, the present study showed the applicability of well-adhering coatings to the considered materials used for applications in medical technology and the potential for wear reduction. Furthermore, the tribometric characteristics obtained serve as a basis for further development of the coating systems.
Keywords: Tribology; Amorphous carbon coatings; Wear; Total knee arthroplasty

Tribological behaviour of MoS2 in hydrogen environment - Schneider, Thomas; Gradt, Thomas; Vierneusel, Bernd; Tremmel, Stephan; Wartzack, Sandro (Proceedings of the 5th World Tribology Congress WTC 2013, 2014)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.tribol_7

Tribological behaviour of tungsten doped hydrogenated amorphous carbon coatings deposited under various bias voltages and argon flows - Zhao, Rong; Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro (Proceeding 11th Coatings Science International COSI 2015, 2015)
In this paper, variants of tungsten doped hydrogenated amorphous carbon coatings (a-C:H:W) were deposited on high speed steel by reactive magnetron sputtering. During the deposition process the bias voltage and argon flow were varied according to a 3x3 grid line experimental design. The coatings were investigated in terms of their topological, mechanical and tribological properties with different interfacial mediums. Raman spectroscopy was used to identify phase composition of the coatings.

Tribological comparison of different doped DLC coatings under rolling-sliding conditions - Polzer, Markus; Bartz, Marcel; Wartzack, Sandro (5th YOUNG TRIBOLOGICAL RESEARCHER SYMPOSIUM, 2022)

Tribological measures for controlling material flow in sheet-bulk metal forming - Löffler, Maria; Andreas, Kolja; Engel, Ulf; Schulte, Robert Karl; Gröbel, Daniel; Krebs, Eugen; Freiburg, Dennis; Biermann, Dirk; Stangier, Dominic; Tillmann, Wolfgang; Weikert, Tim; Wartzack, Sandro; et al. (Production Engineering, 2016)
Sheet-bulk metal forming (SBMF) is characterized by successive and/or simultaneous occurrence of quite different load conditions regarding stress and strain states. These conditions significantly influence the material flow and thus the geometrical accuracy of the components. To improve the product quality a control of the material flow is required. An appropriate approach is given by locally adapted tribological conditions due to surface modifications of tool and workpiece, so-called tailored surfaces. Within the present study different methods to adapt the surfaces are presented and investigated with respect to their tribological effectiveness in SBMF. In a first step, requirements regarding necessary adaptions of the friction values for two SBMF processes are numerically defined. Based on the requirements different tailored surfaces are presented and analyzed regarding their tribological influence. Finally, the potential of surface modifications to improve SBMF processes is shown.
Keywords: Tribology; Surface modification; Sheet-bulk metal forming

Tribologisches Verhalten amorpher Kohlenstoffschichten auf Metallen für die Implantologie im Zustand der Grenzreibung - Rothammer, Benedict; Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro (59. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen. Band 2, 2018)
Der häufigste Grund für einen Implantatausfall stellt Verschleiß dar, da dieser vor allem zu einer aseptischen Lockerung des Implantats führt. Deshalb sollen in dieser Studie die polymeren Verschleißpartikel des Inlays durch den Einsatz tribologisch wirksamer Kohlenstoffschichten (DLC, diamond-like carbon) auf Implantatoberflächen reduziert und dadurch der Abrasivverschleiß minimiert werden. Daher wurden amorphe Kohlenstoffschichten auf Ti6Al4V (3.7165; 39 ± 2 HRC) und CoNi35Cr20Mo10 (2.4999; 47 ± 1 HRC) abgeschieden. Bei den abgeschiedenen Schichten handelt es sich um je eine reine (a-C:H), siliziumoxid- (a-C:H:SiO) und titandotierte (a-C:H:Ti) wasserstoffhaltige amorphe Kohlenstoffschicht. Der Fokus dieses Beitrags liegt auf einem Screening der Schichten bezüglich der Verschleißerscheinungsformen. Darauf aufbauend sollen mittelfristig wirkende Verschleißmechanismen identifiziert werden, um anschließend verschleißreduzierende Schichtsysteme ableiten zu können. Die tribologische Wirksamkeit der Kohlenstoffschichtsysteme lässt sich insbesondere durch eine hohe Haftung auf dem Grundwerkstoff begünstigen, sodass ein weiteres Augenmerk auf der mechanischen Untersuchung der Schichthaftung liegt. Die un- und beschichteten Proben wurden gegenüber medizinischem PE-UHMW (1401; HB = 33 N/mm2) in einem Ring-Scheibe-Versuch getestet. Als Schmierstoff kam fetales Rinderserum (FBS) zum Einsatz. In den Versuchen wurden unterschiedliche dominierende Verschleißmechanismen beobachtet, die wiederum die Reibungszahlen stark beeinflussen. Die deutlich sichtbaren Verschleißspuren auf dem PE-UHMW deuten auf Abrasiv- und Adhäsivverschleiß hin. Die Verschleißpartikel sind meist faser- oder partikelförmig ausgeprägt und liegen mit einer Größe von mindestens 33,8 µm deutlich über dem von BANKSTON et al. für kritisch befunden Wert von 0,1 µm, ab welchem das Osteolysenrisiko durch erhöhte makrozytäre Reaktionen begünstigt wird.
Keywords: Diamantähnlicher amorpher Kohlenstoff (DLC); Implantologie; Ring-Scheibe-Versuch

Tribologisches Verhalten amorpher Kohlenstoffschichten auf Metallen für die Knie-Totalendoprothetik - Rothammer, Benedict; Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2019)
Der häufigste Grund für einen Implantatausfall stellt Verschleiß dar, da dieser vor allem zu einer aseptischen Lockerung des Implantats führt. Deshalb sollen in dieser Studie die polymeren Verschleißpartikel des Inlays durch den Einsatz tribologisch wirksamer Kohlenstoffschichten (DLC, diamond-like carbon) auf Implantatoberflächen reduziert und dadurch der Abrasivverschleiß minimiert werden. Daher wurden amorphe Kohlenstoffschichten auf Ti6Al4V (3.7165; 39 ± 2 HRC) und CoNi35Cr20Mo10 (2.4999; 47 ± 1 HRC) abgeschieden. Bei den abgeschiedenen Schichten handelt es sich um je eine reine (a-C:H), siliziumoxid- (a-C:H:SiO) und titandotierte (a-C:H:Ti) wasserstoffhaltige amorphe Kohlenstoffschicht. Der Fokus dieses Beitrags liegt auf einem Screening der Schichten bezüglich der Verschleißerscheinungsformen. Darauf aufbauend sollen mittelfristig wirkende Verschleißmechanismen identifiziert werden, um anschließend verschleißreduzierende Schichtsysteme ableiten zu können. Die tribologische Wirksamkeit der Kohlenstoffschichtsysteme lässt sich insbesondere durch eine hohe Haftung auf dem Grundwerkstoff begünstigen, sodass ein weiteres Augenmerk auf der mechanischen Untersuchung der Schichthaftung liegt. Die un- und beschichteten Proben wurden gegenüber medizinischem Polyethylen-Ultra High Molecular Weight (PE-UHMW, 1401; HB = 33 N/mm2) in einem Ring Scheibe-Versuch getestet. Als Schmierstoff kam fetales Rinderserum (FBS) zum Einsatz. Die Verschleißpartikel sind in der Regel faser- oder partikelförmig ausgeprägt und weisen mindestens eine Größe von 33,8 μm auf. Dieser Wert ist oberhalb des kritischen Werts von 0,1 μm, unterhalb dessen bereits bei kleinem Abriebvolumen erhöhte makrozytäre Reaktionen ausgelöst werden. Dadurch wird das Risiko einer Osteolyse und ferner einer aseptischen Lockerung begünstigt. Ein Grund für die Abweichung der Partikelgrößen liegt in den unterschiedlichen in-vitro Versuchsaufbauten (Tribometer, Kniesimulator) und dem in-vivo eingesetzten Gelenkersatzes begründet. Generell sollte das Verschleißvolumen für Partikel in einer Größenordnung von 0,2…0,6 μm gering gehalten werden.
Keywords: Diamantähnlicher amorpher Kohlenstoff (DLC); Knie-Totalendoprothese; Ring-Scheibe-Versuch; Verschleiß

Tribologische Wechselwirkungen zwischen amorphen Kohlenstoffschichten und Schmierölen am Beispiel hoch beanspruchter Ventililtriebskomponenten - Schulz, Edgar; Musayev, Yashar; Tremmel, Stephan; Hosenfeldt, Tim; Wartzack, Sandro; Meerkamm, Harald (DIAMOND BUSINESS, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.FT.FT-KLMEFK.tribol

Umsetzung der Digitalisierung in der Produktentwicklung - Gerschütz, Benjamin; Götz, Stefan; Wartzack, Sandro (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2023)
Product development is undergoing a transformation. The paradigm of virtual product development is increasingly moving towards digital engineering. However, Small and Medium Enterprises (SMEs) face problems in optimising their processes by integrating data-driven methods due to a lack of approaches for focused process analysis and method identification. The proposed approach provides a structured process to support the integration of data-driven methods in product development. The focus is on finding use cases in existing and established processes and on selecting suitable methods.<br
Keywords: Digitalization; Process Transformation; Digital Engineering; Product Development Process; SME

Uncertainty considerations by context factors for the monitoring of the degree of product maturity - Luft, Thomas; Reitmeier, Jochen; Paetzold, Kristin; Wartzack, Sandro (Proceedings of the DESIGN 2014 13th International Design Conference, 2014)
As the product development process is a knowledge and information handling process, information acquisition, processing and sharing is very important. However, information is often subject to uncertainty and influenced by the context. Therefore, this paper presents a novel approach for uncertainty considerations with contextual factors by using a matrix-based product description. This will be used to facilitate the situation-specific planning of virtual validations, an efficient monitoring of the degree of product maturity and the management of goal-oriented iteration cycles.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.uncert
Keywords: uncertainty; design structure matrix; property validation; maturity management; early design; decision making

Universal Design—An Old-Fashioned Paradigm? - Kett, Susan; Wartzack, Sandro (Emotional Engineering, 2017)
Universal Design is a strategy that intends to consider the heterogene-ous needs of users in our societies. Initially appearing during the civil rights movements in the 1950s, it focused firstly on physical accessibility and equality. Nowadays, subjective values addressing social inclusion or self-actualization are becoming more and more important. Stigmatization especially plays a major role in Universal Design’s acceptance, which is mainly emotion-driven. Therefore, modern Universal Design must aim for both the objective and the subjective well-being of users. In product design aspects of quality of life as a concept of success-ful user centring can help in considering various aspects of product quality, in-cluding subjectivity in particular. In this context an approach is provided to inte-grate attitudinal differences in users’ perception. Its impact on the modern Universal Design strategy is further considered by introducing a hierarchical product structure.
Keywords: Emotional Engineering; Universal Design; User centered Design; Quality of Life Technology

Unterstützung der Auslegung von Wälzlagern durch elastohydrodynamische Simulation - Wirsching, Sven; Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (WiGeP News, 2022)

Unterstützung des Variantenmanagements von Elektromotoren durch wissensbasierte Systeme - Tüchsen, Johann; Dorsch, Julian; Obendorfer, Moritz; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 30. DfX-Symposium 2019, 2019)
The automotive industry electrifies a huge variety of previously mechanically-actuated car functions. While sharing the same function. the used electric motors often differ in customer related geometries and interfaces. The suppliers have to cope with this huge external variance using an appropriate variant management. With this paper. the support of the variant management of electric drives by knowledge-based systems is proposed. Therefore. a combination of two systems containing the knowledge of the configuration and design of motors are used. The concept is applied and evaluated on the example of the shaft rotor lamination connection. As a result. the amount of internal variants can be reduced and controlled as well as the designer can be supported during the development process.<br
Keywords: Variant Management; Knowledge-based Systems; KBS; Electric Drives

Untersuchung des Reibungsverhaltens von Wälzlagern unter dem Einfluss von Zentripetalbeschleunigungen zur energieeffizienten Gestaltung von Lagerungen - Hochrein, David; Tremmel, Stephan; Graf-Goller, Oliver; Wartzack, Sandro (VDI - Berichte 2308, 2017)
Wälzlagerungen unter Zentripetalbeschleunigung haben wesentlichen Anteil an der Reibungsentstehung in Verbrennungsmotoren und Planetenradlagerungen. Aufgrund der komplexen Lastsituation sind Analysen bezüglich der Ursachen für die Reibungsentwicklung allerdings schwierig. Aus diesem Grund wurde ein Prüfstand entwickelt, mit dem einzelne Wälzlager unter dem Einfluss von bis zu 3000 g hinsichtlich Reibung anwendungsunabhängig untersucht werden können. Die Auswertung des dynamischen Ergebnissignals im Zeitbereich ist ohne Kenntnis der einzelnen Signalelemente nicht möglich. Daher ist es sinnvoll vom Zeitbereich in den Frequenzbereich zu wechseln. Dies geschieht durch Anwendung der Fast Fourier Transformation. Im Frequenzbereich werden die Signalkomponenten, sowie deren Einflussintensität sichtbar. Anhand dieses neuen Analyseansatzes lassen sich Einflussparameter auf die Wälzlagerreibung besser beurteilen.

Untersuchung des tribologischen Verhaltens wolframmodifizierter amorpher Kohlenstoffschichten (a-C:H:W) bei systematischer Variation der Biasspannung und des Argonflusses während des Beschichtungsprozesses - Zhao, Rong; Weikert, Tim; Tremmel, Stephan; Wartzack, Sandro (55. Tribologie-Fachtagung: Reibung, Schmierung und Verschleiß, 2014)
Metallmodifizierte wasserstoffhaltige amorphe Kohlenstoffschichten (DLC) werden als vielversprechende Kandidaten für die Beschichtung von Umformwerkzeugen angesehen. Sie zeichnen sich nicht nur durch geringe Eigenspannungen und gute Schichthaftung zum Substrat aus, sondern es ist auch möglich, ihre mechanischen Eigenschaften durch den Metallanteil in der amorphen Kohlenstoffmatrix einzustellen. Entsprechend dem aktuellen Stand der Forschung haben die Beschichtungsprozessparameter starken Einfluss auf die Struktur, die mechanischen Eigenschaften sowie das tribologische Verhalten der Schichten. In dieser Arbeit wurden wolframmodifizierte wasserstoffhaltige amorphe Kohlenstoffschichten (a‑C:H:W) auf Schnellarbeitsstahl (1.3343) durch reaktives Magnetronsputtern eines Wolframkarbidtargets in Ethin-Argon-Atmosphäre hergestellt. Hierbei wurden systematisch die Biasspannung und der Argonfluss jeweils in drei Stufen variiert. Anschließend fand eine mechanische und tribologische Charakterisierung der Schichtvarianten statt. Ihr Verschleißverhalten wurde unter trockenen und ölgeschmierten (mit und ohne Additivierung) Bedingungen untersucht. Dabei konnte ein jeweils unterschiedliches Verschleißverhalten beobachtet werden. Dieses ist insbesondere auf bestimmte tribochemische Reaktionen zwischen den abgeschiedenen Kohlenstoffschichten und den Additivkomponenten des Schmieröls zurückzuführen.
Keywords: Diamantähnlicher amorpher Kohlenstoff; Biasspannung; Stift-Scheibe-Versuch

Untersuchung des tribologisch-mechanischen Verhaltens amorpher Kohlenstoffschichten mittels Load Scanner - Wartzack, Sandro; Pejic, Goran; Durst, Karsten; Schaufler, Jens; Hetzner, Harald; Tremmel, Stephan (2012)
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.unters

Untersuchungen an a-C:H:Me-beschichteten Rillenkugellagern unter Trockenlaufbedingungen - Kröner, Julia; Tremmel, Stephan; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2019)
Under extreme environmental conditions or due to restrictions oil- or grease-lubricated standard rolling bearings can only be used to a limited extent or not at all. Existing solutions are expensive due to the special materials or lubricants used or have only a very limited service life. The alternative approach presented here involves the use of cost-effective standard rolling bearings, which have been modified with a friction and wear-reducing coating on individual components of the rolling bearing. Radial deep groove ball bearings of type 6206 are tested in operating life tests on a four bearing test rig. All investigated coating systems are described in the literature as basically usable under dry running conditions and normal atmosphere: Graphite, titanated molybdenum disulfide (MoS2:Ti), a modified (a-C:H:X) and a metal-containing hydrogen-containing amorphous carbon coating (a-C:H:Me). The different coating systems were applied to the raceways of the rolling bearing using PVD or PACVD processes and tested with both steel and ceramic balls. The results of these experiments in terms of operating life, tribological behaviour and, in particular, the repeatability of the results will be presented in this paper.<br
Keywords: Trockenlauf; Rillenkugellager; PVD-Beschichtung; Amorphe Kohlenstoffschicht; Bauteiltest; Vier-Lager- Prüfstand; Gebrauchsdauer

Untersuchungen an a-C:H:Me-beschichteten Rillenkugellagern unter Trockenlaufbedingungen - Kröner, Julia; Tremmel, Stephan; Wartzack, Sandro (60. Tribologie-Fachtagung 2019. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen., 2019)
Unter extremen Umgebungsbedingungen, wie sehr hohen oder niedrigen Temperaturen, Strahlung und Vakuum oder bedingt durch Restriktionen beispielsweise im Bereich von Reinräumen, in der Lebensmittel- und Papierindustrie können öl- oder fettgeschmierte Standardwälzlager nur beschränkt oder nicht eingesetzt werden. Bisherige Lösungen sind durch die eingesetzten Sonderwerkstoffe oder -schmierstoffe kostspielig oder besitzen durch die Reduzierung oder Vermeidung des mineralölbasierten Schmierstoffs nur eine sehr eingeschränkte Gebrauchsdauer. Letzteres ist bedingt durch den Wegfall der positiven Eigenschaften des Schmierstoffs, wie Wärmetransport sowie Reibungsreduzierung oder Verschleißminderung durch weitgehende Trennung der Oberflächen. Der hier vorgestellte, alternative Ansatz sieht die Verwendung kostengünstiger Standardwälzlager vor, welche mit einer reibungs- und verschleißmindernden Schicht auf einzelnen Komponenten des Wälzlagers modifiziert wurden. Die im Rahmen dieses Beitrags beschriebenen Untersuchungen fokussieren sich auf Anwendungen unter Normalatmosphäre bei Raumtemperaturen. Geprüft werden Radial-Rillenkugellager des Typs 6206 in Gebrauchsdauerversuchen auf einem Vier-Lager-Prüfstand. Alle untersuchten Schichtsysteme werden in der Literatur für Anwendung unter Trockenlaufbedingungen und Normalatmosphäre als grundsätzlich geeignet beschrieben: Graphit, titandotiertes Molybdändisulfid (MoS2:Ti), eine modifizierte (a-C:H:X) sowie eine metallhaltige wasserstoffhaltige amorphe Kohlenstoffschicht (a-C:H:Me). In umfangreichen Screening-Versuchen hat sich die a-C:H:Me-Schicht in Bezug auf die Gebrauchsdauer als beste Alternative herausgestellt. Dabei wurden die unterschiedlichen Schichtsysteme auf den Laufbahnen des Wälzlagers mittels PVD- oder PACVD-Prozessen appliziert und sowohl mit Stahl- (100Cr6) als auch Keramikkugeln (Siliziumnitrid – Si3N4) als Gegenkörper getestet. Die Kombination mit Keramikkugeln wurde anschließend weiterverfolgt, sowie zusätzliche Paarungen, bei denen die Stahlkugeln ebenfalls mit einer a-C:H:Me-Schicht versehen wurden. Die Ergebnisse dieser Versuche in Bezug auf Gebrauchsdauer, tribologisches Verhalten sowie insbesondere die Wiederholbarkeit der Ergebnisse sollen in diesem Beitrag vorgestellt werden.<br
Keywords: Trockenlauf; Rillenkugellager; PVD-Beschichtung; amorphe Kohlenstoffschicht; Bauteiltest; Vier-Lager-Prüfstand; Gebrauchsdauer

USE CASES FOR A HYBRID AUGMENTED REALITY COMPUTER WORKSTATION IN CAD WORKFLOWS - Harlan, Jakob; Götz, Stefan; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Many immersive approaches for design activities show a great potential for their specific use cases, but still overall usage of extended reality technology in product developers day-to-day work is little. The user's workflow between classical desktop work environment and its immersive counterpart is interrupted by both a data gap and an interface gap. The three-dimensional product data usually needs preparation and the user has to physically change the interface in use. The hybrid augmented reality computer workstation aims to close these gaps. A hologram of the current model is visualized next to the screen in reach of the user for intuitive inspection and spatial interactions. In this paper we present use cases for this novel immersive workstation in the CAD workflow. An explorative user study of the typical product designer`s workflow reveals the most common activities. Guided by those, eight uses cases are formulated and classified into fundamental, drafting, and modelling CAD tasks. These cases include novel hybrid augmented reality interactions derived from literature, which are assessed with respect to their applicability.<br
Keywords: Computer Aided Design (CAD); Virtual reality; Workspaces for design; Augmeted Reality; Natural User Interfaces

Use of Printed Sensors to Measure Strain in Rolling Bearings under Isolated Boundary Conditions - Bartz, Marcel; Häußler, Felix; Halmos, Fabian; Ankenbrand, Markus; Jüttner, Michael; Roudenko, Jewgeni; Wirsching, Sven; Reichenberger, Marcus; Franke, Jörg; Wartzack, Sandro (Lubricants, 2023)
The knowledge of the operating conditions in rolling bearings in technical applications offers many advantages, for example, to ensure a safe operation and to save resources and costs with the help of condition monitoring and predictive maintenance procedures. In many cases, it is difficult to implement sensors to measure the operating conditions of the rolling bearing, for reasons such as inaccessibility of the mounting position or non-compliance with installation space neutrality, which influences the sensor on the measuring point. Printed sensors using a digital deposition process, which can be used in very narrow design spaces, offer advantages in this respect. So far, these sensors have not been established in rolling bearings, so there is potential for technical application. This paper discusses the fundamental advantages and disadvantages as well as the challenges of the application, and it demonstrates the feasibility under isolated boundary conditions by applying a printed strain gauge sensor to the outer ring of a cylindrical roller bearing NU210 in an experimental setup to measure the strain under load. In this setup, the outer ring is deformed by 2 mm under an increasing radial load using a hydraulic press, and the strain is measured. Both a commercial reference sensor and a FE-simulation are used to validate the measurement. The results show that an implementation using printed sensors as a strain gauge works successfully. The resulting challenges, such as measuring strain gradients and printing on curved surfaces, are finally evaluated, and an outlook for further work is given.<br
Keywords: rolling bearings; sensor-integrated machine elements; strain measurement; printed strain gauges; printed sensors

Using Machine Learning Methods for Predicting Cage Performance Criteria in an Angular Contact Ball Bearing - Schwarz, Sebastian; Grillenberger, Hannes; Graf-Goller, Oliver; Bartz, Marcel; Tremmel, Stephan; Wartzack, Sandro (Lubricants, 2022)
Rolling bearings have to meet the highest requirements in terms of guidance accuracy, energy efficiency, and dynamics. An important factor influencing these performance criteria is the cage, which has different effects on the bearing dynamics depending on the cage’s geometry and bearing load. Dynamics simulations can be used to calculate cage dynamics, which exhibit high agreement with the real cage motion, but are time-consuming and complex. In this paper, machine learning algorithms were used for the first time to predict physical cage related performance criteria in an angular contact ball bearing. The time-efficient prediction of the machine learning algorithms enables an estimation of the dynamic behavior of a cage for a given load condition of the bearing within a short time. To create a database for machine learning, a simulation study consisting of 2000 calculations was performed to calculate the dynamics of different cages in a ball bearing for several load conditions. Performance criteria for assessing the cage dynamics and frictional behavior of the bearing were derived from the calculation results. These performance criteria were predicted by machine learning algorithms considering bearing load and cage geometry. The predictions for a total of 10 target variables reached a coefficient of determination of R2≈0.94" role="presentation">R2≈0.94 for the randomly selected test data sets, demonstrating high accuracy of the models.
Keywords: Wälzlager; Maschinelles Lernen; Käfiginstabilität; Künstliche neuronale Netze; Random Forest; Gradient Boosting; Evolutionäre Algorithmen

Using machine learning to increase efficiency in design of experiments for cyclic characterization of fibre-reinforced plastics - Gadinger, Marc; Witzgall, Christian; Hufnagel, Thomas; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)
Efficient characterization of fatigue behavior plays a crucial role in engineering design as it reduces the financial costs associated with expensive experimental tests. Existing methods for characterizing the fatigue behavior of fibre-reinforced plastics have proven inefficient due to the oversight of important design parameters, such as fibre orientations. To address this challenge, we propose an innovative approach based on Gaussian process regression. Our approach integrates previously unaccounted design parameters into the decision-making process, ensuring that optimal design points are selected for testing. By doing so, we maximize the gain of knowledge within the model, resulting in improved efficiency and accurate characterization of fatigue behavio
Keywords: fatigue behavior; machine learning; gaussian processes; fibre-reinforced plastics

Utilization of system models in model-based systems engineering: definition, classes and research directions based on a systematic literature review - Wilking, Fabian; Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Design Science, 2024)
The use of system models within model-based systems engineering (MBSE) is essential for improved communication or system documentation. Previous publications have investi- gated further reuse of these system models, for example, transforming them directly into discipline-specific models for reuse. The authors refer to this as the term “Utilization” of system models. It aims the compensation of modelling efforts and a further integration of linked models within MBSE. Motivated by a lack of common understanding of this term, a systematic literature review of the state of the art is presented. With this systematic overview, a definition and classification system for different use cases and system life cycle stages are created. These are key results to support engineers and researchers in adopting existing or discovering new utilization approaches. This supports the mission of advanced systems engineering and aims the identification of new research directions coming along with SysML v2 and the advanced systems engineering methods.
Keywords: Model-based systems engineering; MBSE; Systems engineering; System models; SysML

Utilizing the Embodiment Function Relation and Tolerance Model for Robust Concept Design - Li, Jiahang; Horber, Dennis; Keller, Christoph; Grauberger, Patric; Götz, Stefan; Wartzack, Sandro; Matthiesen, Sven (Proceedings of the Design Society, 2023)
The early use of Robust Design (RD) supports the development of product concepts with low sensitivity to variation, which offers advantages for reducing the risk of costly iterations. Due to the lack of approaches for early evaluation of product robustness, the embodiment-function-relation and tolerance (EFRT-) model was developed, which combines the contact and channel approach and tolerance graphs. The information exchange of both approaches offers a high potential for reliable robustness evaluation results. However, that potential currently relies unused, since the link between applicable robustness criteria and the extended information is missing. To solve this problem, four research steps were determined: (1) understanding of robustness, (2) collection of RD principles, (3) identification of EFRT-model information and (4) mapping of RD principles and information. The results show nine adapted RD principles, the identified model information for the robustness evaluation, the evaluation criteria as well as their mapping. Utilizing the mapping and the proposed criteria in this contribution, a more comprehensive robustness evaluation in early stages is enable
Keywords: Robust Design; Conceptual Design; Product Modelling / Models; Variation Management; Contact and Channel Approach

Validierung eines Ansatzes zur Simulation kurzfaserverstärkter Thermoplaste in frühen Entwurfsphasen - Witzgall, Christian; Wartzack, Sandro (Design for X. Beiträge zum 26. DfX-Symposium, 2015)
A simplified approach towards a simplified integrative simulation for short fibre reinforced polymers (SFRP) has been proposed by Gruber and Wartzack. It uses orientation information from injection moulding simulation directly inside a structural or crash simulation. For describing the complex material behavior of SFRP, a layerwise stacking of simple material models is used. Thus, only standard material models which can be computed efficiently have to be used. Within the present paper, the simulative approach is to be verified and validated, i.e. the physical plausibility and the usability for loadcases with elevated strain rates are examined.

Validierung von prozessgerecht strukturoptimierten Bauteilentwürfen mittels integrierter FEM-Realgeometrieanalyse - Hautsch, Stefan; Katona, Sebastian; Sprügel, Tobias; Koch, Michael; Rieg, Frank; Wartzack, Sandro (Design for X. Beiträge zum 26. DfX-Symposium, 2015)
The structural optimization as a tool of the virtual product development process (PDP) provides broad possibilities to scoop leightweight design and improvement potentialities when developing new products. To promote the further dissemination of structural optimization, the focus of the developments lies on a process-ready structural optimization, which does not only aim at design, safeguarding and later alteration through process restrictions , but at a straightforward generation of a process- and production-ready part by using computer-aided optimization tools. This efficient approach in product development helps to reduce iterations in the PDP, but also brings along the need for a validation of the newly created procedure because manufacturing processes like forming often cause deviations in the physical part which were not regarded in the dimensioning of the desired part. Hence the established simulation of the desired component design (based on 3D CAD data) should be supplemented with a simulation of the physical part geometry (based on the 3D scan of a prototype). The overvalue of the current development is a efficiency increase of the product development process through a reduction of iteration loops and effective generation of process-, production- and utilization-ready part designs with the aid of structural optimization tools and a knowledge database, illustrated exemplarily by the forming process. The finite element (FE) analysis of the desired geometry is joined by a validation of the adapted product development process by geometry analysis and FE-simulation of the physical geometry provided by a 3D scanner. Consequently, the deviations made by the manufacturing process can be analyzed for their relevance for the part's performance and the design can be safeguarded.
Keywords: validation; finite element analysis; structural optimization; 3D scan

Variant Value Management to Optimize Compexity and Value of Product Families - Luft, Thomas; Schmied, Christian; Schöberl, Maximilian; Wartzack, Sandro; Zimmermann, Markus; Mörtl, Markus (23rd INTERNATIONAL DEPENDENCY AND STRUCTURE MODELING CONFERENCE, DSM 2021, 2021)

Variation Analysis of Design Parameters of Fibre-Reinforced Plastic Parts - Franz, Michael; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
Lightweight Design as an engineering domain is becoming more and more important in terms of sustainable mobility. Therefore, a large number of researchers is developing methods for utilisation of modern, but as well more complex materials with high lightweight potential. One subgroup of these materials are fibre-reinforced plastics (FRP). A lot of work is done supporting the design engineer in exploiting the structural and mechanical behaviour as good as possible. Whereas variations of laminate parameters, resulting from production, are poorly studied. Their impact especially on defined measures under load is of high importance, e.g. having a look on clearances in automotive industry. Because of the high complexity of FRP-parts, resulting from many laminate parameters, tolerancing is not an intuitive process. This is reflected in the fact that there is no defined procedure for tolerancing of FRP-parts. To support the design engineer the authors perform sensitivity analysis for simple loadcases to identify layers with a high importance on a defined measure. The results then are generalised to provide general guidelines to the design enginee

Verbesserungspotentiale in der Entwicklung und Validierung hoch dynamisch belasteter Leichtbaukomponenten im Umfeld der Zulieferindustrie - Gruber, Georg; Walter, Michael; Wartzack, Sandro (Design for X. Beiträge zum 21. DfX-Symposium, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-KLMEFK.verbes

Vereinfachte Simulation von Klebeverbindungen an Hybridstrukturen durch Einsatz von Metamodellen - Witzgall, Christian; Merklein, Annette; Resch, Thomas; Starost, Stephan; Kellermeyer, Markus; Vogt, Jürgen; Most, Thomas; Will, Johannes; Wartzack, Sandro (Simulation und Erprobung in der Fahrzeugentwicklung 2016, 2016)

Vergleichende Studie der Topologie-Optimierungsalgorithmen CONLIN und SUMT - Gruber, Georg; Stockinger, Andreas; Tremmel, Stephan; Wartzack, Sandro (Tagungsband zum 5. Landshuter Leichtbau-Colloquium, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-KLMEFK.vergle

Verification of a passive ankle-foot orthosis design method by using truss models - Scherb, David; Steck, Patrick; Wartzack, Sandro; Miehling, Jörg (28th Congress of the European Society of Biomechanics, 2023)
Passive ankle-foot orthoses (AFOs) are the most common treatment option for people suffering from foot drop. By holding the foot in a neutral position and thereby preventing its drop, a significant improvement of the patients’ gait pattern and comfortable gait speed can be realised [1]. However, the effect is limited and a discrepancy remains compared to the gait of healthy people [2]. Thus, active AFOs driven by motorsand external power supply were developed, which allow for adjustability of the required ankle position. Their disadvantages, as high weight or difficult power supply, have inhibited their use in daily life so far [3]. Therefore, we develop a novel passive AFO that is equipped with supporting structures providing an adjustable assistance for patients. The main requirement for the new design is to provide an appropriate assistance for the patients’ needs, i.e. to match the support required by the patient and transfer this support through the product to the patient. A popular tool for investigating the effects of orthoses and similar devices (referred to as wearable assistive devices) are digital human models, allowing to study the biomechanical outcomes of the assistance [4]. In this way, a conceptual method was developed that enables the design of the passive AFO’s supporting structures in accordance with the pathological situation of the patients. This contribution aims to verify the method by using truss models of the passive AFO for different patients’ conditions. The elaborated method enables the integration of finite element models in musculoskeletal human models (MHMs) to design the passive AFO. To save computing time, the design of an AFO was discretized for each patient with beam elements and subsequently the number of beams was minimized by means of topology optimization (see Figure 1). The musculoskeletal human models are created from motion capture recordings of subjects in a gait laboratory. By biomechanical analysis of the gait records, the kinematics and externally applied loads at the truss models during the gait cycle are determined. The resulting stresses and deformations are calculated with these boundary conditions in the truss models and the resulting reaction forces are then applied as external forces to the MHM Thereby, the biomechanical effects of the assistance with a truss model of the AFO can be simulated. By comparing the results, the verification of the method is realized. Therefore, the relation between the provided support to previously determined assistance-as-needed calcu-lations [5] are examined. The results of the truss support show an activation of the plantarflexor muscles from 20 - 60 % of the gait cycle, referred to as the stance phase and no activation after 60 % of the gait cycle, the swing phase (see Figure 1). The supporting forces and torque depict the majority of provided assistance in the stance phase of the gait cycle and a minor part in the swing phase of gait cycle. The good agreement of resulting biomechanical effects of the truss AFO model simulations (muscle activations and provided support torque) compared to data from previous assistance-as-needed calculations (Figure 1) verify the developed passive AFO design method. Thus, the functionality of the method for providing design suggestions and the possibility to depict the interaction between MHM and AFO is proven. In the next validation step, model order reduced finite element models of the AFO will be used to incorporate a more realistic behaviour of the AFO design in the simulation.<br

Versagensprognose bei der Crashsimulation von Kunststoff Türsystemen zur Erschließung des Leichtbaupotenzials in Fahrzeugen - Wartzack, Sandro (VDI-Bericht, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.FT.FT-KLMEFK.versag

Verschiedene Rollen im Wissensmanagement – eine bibliografische Studie - Luft, Thomas; Wartzack, Sandro (Wissensmanagement - Magazin für Führungskräfte, 2014)
• Schon die Tatsache, dass Wissen subjektiv – also personengebunden – ist, zeigt wie untrennbar Wissensmanagement vom Menschen bzw. Mitarbeiter ist. [18, 19] • Nicht nur aus empirischer bzw. industrieller Sicht sondern auch aus bibliographischer bzw. wissenschaftlicher Sicht lässt sich eine Vielzahl unterschiedlicher Rollenbeschreibungen für das Wissensmanagement finden. • In einer bibliographischen Studie wurden verschiedene Rollenbeschreibungen im Wissensmanagement erarbeitet und sowohl hinsichtlich ihrer Bezeichnungen und Zuständigkeiten als auch im Hinblick auf ihre jeweiligen Aufgabenbereiche und damit einhergehend auch Kompetenzen und Verantwortlichkeiten beleuchtet.
Keywords: Wissensmanagement; Wissensmanager; Wissensingenieur; Rollen; bibliografische Studie

Verschleißmodellierung mischreibungsbehafteter Maschinenelemente am Beispiel eines Axial-Zylinderrollenlagers - Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (VDI-Berichte 2378, 2021)
Keywords: Verschleißsimulation; Mischreibung; Wälzlager

Verschleißsimulation grenz- und mischreibungsbehafteter Wälzkontakte - Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2021)
Im Rahmen dieses Beitrags wird ein Vorgehensmodell zur numerischen Verschleißberechnung von Wälzkontakten vorgestellt. Das FEM-basierte Verschleißsimulationsmodell von Winkler [1] wird um die Möglichkeit erweitert, neben mischreibungsbehafteten Kontakten auch grenzreibungsbehaftete Kontakte zu berücksichtigen. Am Beispiel eines Axial-Zylinderrollenlagers und zweier Lastfälle werden Ergebnisse einer Verschleißmodellierung sowohl im Mischreibungsgebiet als auch im Grenzreibungsgebiet präsentier
Keywords: Verschleißmodellierung; Kontaktmechanik; Elastohydrodynamik (EHD); Mischreibung; Grenzreibung; Wälzlager

Verschleißsimulation grenz- und mischreibungsbehafteter Wälzkontakte - Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (62. Tribologie-Fachtagung 2021, 2021)
Keywords: Verschleißsimulation; Mischreibung; Grenzreibung; Wälzlager

Virtual Assessment of Product Use Based on Biomechanical Human Models - Wartzack, Sandro; Krüger, Daniel; Miehling, Jörg (Anais do 19. Seminário International de Alta Tecnologia, 2014)

Virtual Validation Of Functional Automotive Door Assembly Properties By Means Os Superosed CAT And FEM Analysis - Ehlert, Matthias; Heling, Björn; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED 15) Vol 4: Design for X, Design to X, 2015)
As with all industrially manufactured goods, it is generally necessary to ensure costumer requirements are met. Therefore, it is important to ensure that functional as well as optical specifications of a product are fulfilled for large quantities in series production. The following piece of work demonstrates the effect that the elasticity of an assembly has on specific functional criteria in order to meet the aim of a robust design. For this purpose an automotive door assembly is examined, where tightness is one of the most relevant attributes from the customer’s perspective. In the present case, the effect of the elastic sealing system on the development of the limiting positions of the observed assembly that result from a corresponding tolerance analysis will be examined in greater detail which, in turn, has an impact on tightness. The term ‘limiting position’ generally describes the largest deviation from the nominal dimension that can occur with a high level of statistical probability. To that end, a simulation-based integrated process is introduced that covers CAT as well as FEM methods and in this way respects the elasticity of the system with its corresponding deformation.
Keywords: Computer aided design (CAD); Robust design; Virtual engineering (VE); Computer aided tolerancing (CAT)

Virtuelles Planen und Bewerten menschlicher Arbeit - Wolf, Alexander; Miehling, Jörg; Quadrat, Eric; Nolte, Alexander; Fritzsche, Lars; Bauer, Sebastian; Spitzhirn, Michael; Peters, Markus; Leidholdt, Wolfgang; Wischniewski, Sascha; Wartzack, Sandro (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
Die ergonomische Gestaltung von Arbeitsplätzen ist eine Grundvoraussetzung zur Vorbeugung von Erkrankungen des Muskel-Skelett-Systems durch körperliche Arbeit. In diesem Beitrag wird das Forschungs- und Entwicklungsprojekt „ema2AnyBody“ vorgestellt, in dem ein Softwaretool zur virtuellen Planung und Bewertung menschlicher Arbeit entwickelt wird. Das Besondere dabei: Die Bewertung kann anhand biomechanischer Beanspruchungsgrößen erfolgen, die mithilfe einer automatisierten biomechanischen Simulation erhoben werde

Virtuelle Toleranzbeurteilung abweichungsbehafteter Bauteile - Schleich, Benjamin; Wartzack, Sandro (Design for X - Beiträge zum 23. DfX-Symposium - Oktober 2012, 2012)
Geometric deviations are observable on every manufactured part and can have huge influences on the functional behaviour of technical products. Therefore, allowable limits for these imperfections have to be specified and set during product development. However, this task is quite difficult since geometric deviations affect the product behaviour in various ways. Thus, current approaches try to incorporate the whole workpiece geometry in tolerance activities instead of reducing the functional behaviour by expressing it as vector chains. In this context, the virtual assessment of geometric deviations is an important step in geometry-based computer aided tolerancing. This contribution illustrates the methodology as well as some applications of virtual tolerance assessment and highlights the possibilities and advantages of geometry-based tolerancing.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KLMEFK.virtue

Virtuelle und experimentelle Toleranzuntersuchungen abweichungsbehafteter Baugruppen - Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (Industriekolloquium der Forschergruppe FOR 2271, 2019)

Vision Toleranzmanagement 4.0 - Wartzack, Sandro (Konstruktion, 2017)

Visualisation of biomechanical stress quantities within CAD environments - Krüger, Daniel; Wartzack, Sandro (Proceedings of the 20th International Conference on Engineering Design (ICED15) Vol.10, 2015)
The demographic development in many industrialised societies and markets with a growing power of the customers augments the importance of user-centred design approaches. In this regard it is crucial for design engineers to understand how the use of a product is affecting the prospective user physically and emotionally. In this contribution an attempt is made to quantify physical effects on the human body during the interaction with technical systems. We present an approach to visualise biomechanical stress quantities obtained from simulations with musculoskeletal human models within CAD engineering environments. The objective is to enable designers to intuitively estimate how their solutions will influence the physical state of the user. The topic is relevant for the design of technical artefacts that are characterised by a close interaction with people. This comprises ergonomic questions in product design but also the planning of manufacturing processes as well as the development of medical devices for training and rehabilitation
UnivIS-Import:2015-10-26:Pub.2015.tech.FT.FT-KLMEFK.visual
Keywords: CAD; visualisation; biomechanics; ergonomics

Visuelle Unterstützung der Toleranzanalyse in der industriellen Anwendung - Striegel, Serena; Schleich, Benjamin; Ehlert, Matthias; Zielinski, Daniel; Wartzack, Sandro (Summer School Toleranzmanagement - Beiträge zur 3. Summer School - September 2017, 2017)

Vom Ideal- zum Realmodell: Bauteile mit Fertigungsabweichungen durch automatische FE-Netzadaption simulieren - Katona, Sebastian; Kestel, Philipp; Koch, Michael; Wartzack, Sandro (Entwerfen Entwickeln Erleben – Beiträge zu virtuellen Produktentwicklung und Konstruktionstechnik, 2014)

Vom schließmaßbasierten Toleranzmanagement zum eigenschaftsbasierten Robust Design - Ziegler, Philipp; Wartzack, Sandro (Design for X. Beiträge zum 24. DfX-Symposium, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-KLMEFK.vomsch

Voraussetzungen für den Einsatz datengetriebener Methoden in der Produktentwicklung - Mehlstäubl, Jan; Nicklas, Simon; Gerschütz, Benjamin; Sprogies, Nicolai; Schleich, Benjamin; Lohner, Thomas; Wartzack, Sandro; Stahl, Karsten; Paetzold, Kristin (Proceedings of the 32nd Symposium Design for X (DFX2021), 2021)
Data mining and machine learning are successfully applied in many business areas such as marketing or production. Due to the increasing complexity in data and information flows and the large amount of data, data-driven solutions have also great potential in product development. Nevertheless, many companies are not able to integrate data-driven methods into their product development process. In order to support the application of data-driven methods, this paper identifies necessary prerequisites for their integration in product development. Based on a data analysis process, the prerequisites are elaborated and, subsequently, levers for their design are derive
Keywords: Data-driven Methods; Product Development; Data Mining; Machine Learning

Vorgehensweisen zur Vorhersage menschlicher Bewegung durch muskuloskelettale Simulation - Wolf, Alexander; Miehling, Jörg; Wartzack, Sandro (Design for X. Beiträge zum 28. DfX-Symposium, 2017)
Musculoskeletal simulations are holding the capability to quantify man-machine interactions of systems which are not build yet. Thus, they have the capability to be an important CAE-tool in product development. The most common approach of musculoskeletal simulations is the inverse dynamic analysis. Unfortunately this approach has view disadvantages, which are the main reason why musculoskeletal simulations are not in broad application yet. The main disadvantage is that measurements have to take place for every simulation. To overcome the measurements for inverse dynamics, movement and external forces have to be predicted. We present two approaches for motion prediction and describe which of them is more suitable to match the needs of product development.
Keywords: musculoskeletal simulation; posture- and movement-prediction; human centered design; man–machine interaction

Vorgehen zur Validierung von Toleranzanalyseverfahren von Mechanismen - Heling, Björn; Schleich, Benjamin; Wartzack, Sandro (Konstruktion, 2021)
Das Toleranzmanagement bietet die Möglichkeit, die Folgen von unweigerlich auftretenden geometrischen Abweichungen prädiktiv bei der Produktentwicklung zu berücksichtigen und gezielt zu steuern. Dazu werden Toleranzanalyseverfahren eingesetzt, die eine Überlagerung der geometrischen Bauteil- und Prozessabweichungen und deren Folgen für die Produktqualität virtuell abbilden. Der vorliegende Beitrag zeigt erstmalig eine Möglichkeit auf, wie diese Toleranzanalyseverfahren validiert werden können.<br

Vorstellung der Forschergruppe "Prozessorientiertes Toleranzmanagement mit virtuellen Absicherungsmethoden“ - Wartzack, Sandro; Heling, Björn; Schleich, Benjamin (Industriekolloquium der Forschergruppe FOR 2271, 2019)

Vorstellung einer neuen Prüfstandsgruppe zur Untersuchung des Fliehkrafteinflusses auf das Reibungsmoment von Wälzlagern - Hochrein, David; Graf-Goller, Oliver; Tremmel, Stephan; Wartzack, Sandro (Tribologie und Schmierungstechnik, 2017)
Anwendungen in denen Wälzlager Fliehkraftbelastung erfahren sind beispielsweise Planetenradlagerungen oder Pleuellagerungen im Verbrennungsmotor. Im Bereich der Getriebetechnik sind die Anforderungen an Planetenradlagerungen vor allem in den letzten Jahren aufgrund von Wirkungsgradoptimierungen stark angestiegen und die zu ertragenden Beschleunigungen werden in wenigen Jahren Werte bis zum 8 000‑fachen der Erdbeschleunigung erreichen. Dies entspricht in etwa einer Verdoppelung der aktuellen Belastung. Im Gegensatz hierzu sind die Anforderungen für Pleuellagerungen schon seit Beginn der Entwicklung von Verbrennungsmotoren sehr komplex. Im Bereich der Kraftfahrzeugmotoren haben sich daher in den vergangenen Jahrzenten überwiegend Gleitlager etabliert, obwohl zu Beginn der Motorenentwicklung diese Anwendung eine Domäne der Wälzlager war. In beiden Anwendungen sind fliehkraftbelastete Wälzlager ein wesentlicher Beitragsleister für das Gesamtreibungsmoment des Aggregats und weisen somit ein vielversprechendes Energieeinsparpotential auf. Aufgrund der extremen und komplizierten Belastungen sind die Vorgänge in solchen Lagern bisher allerdings nur wenig erforscht. Aus diesem Grund ist eine Prüfstandsgruppe entwickelt und gebaut worden, die eine intensive experimentelle Untersuchung dieser Thematik erlaubt.
Keywords: Wälzlager; Reibung; Fliehkraftfeld

Vorstellung einer neuen Prüfstandsgruppe zur Untersuchung des Fliehkrafteinflusses auf das Reibungsmoment von Wälzlagern - Hochrein, David; Graf-Goller, Oliver; Tremmel, Stephan; Wartzack, Sandro (57. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen, 2016)
Anwendungen in denen Wälzlager Fliehkraftbelastung erfahren sind beispielsweise Planetenradlagerungen oder Pleuellagerungen im Verbrennungsmotor. Im Bereich der Getriebetechnik sind die Anforderungen an Planetenradlagerungen vor allem in den letzten Jahren aufgrund von Wirkungsgradoptimierungen stark angestiegen und die zu ertragenden Beschleunigungen werden in wenigen Jahren Werte bis zum 8 000‑fachen der Erdbeschleunigung erreichen. Dies entspricht in etwa einer Verdoppelung der aktuellen Belastung. Im Gegensatz hierzu sind die Anforderungen für Pleuellagerungen schon seit Beginn der Entwicklung von Verbrennungsmotoren sehr komplex. Im Bereich der Kraftfahrzeugmotoren haben sich daher in den vergangenen Jahrzenten überwiegend Gleitlager etabliert, obwohl zu Beginn der Motorenentwicklung diese Anwendung eine Domäne der Wälzlager war. In beiden Anwendungen sind fliehkraftbelastete Wälzlager ein wesentlicher Beitragsleister für das Gesamtreibungsmoment des Aggregats und weisen somit ein vielversprechendes Energieeinsparpotential auf. Aufgrund der extremen und komplizierten Belastungen sind die Vorgänge in solchen Lagern bisher allerdings nur wenig erforscht. Aus diesem Grund ist eine Prüfstandsgruppe entwickelt und gebaut worden, die eine intensive experimentelle Untersuchung dieser Thematik erlaubt.
Keywords: Wälzlager; Reibung; Fliehkraftfeld

Was macht ein Wissensingenieur? - Luft, Thomas; Wartzack, Sandro (Wissensmanagement - Magazin für Führungskräfte, 2015)
• Das bewusste und effiziente Managen des Wettbewerbsfaktors „Wissen“ ist eine immer wichtiger werdende sozio-kulturelle und organisatorische Managementaufgabe. [2, 9, 11] • In einer empirischen Studie wurden verschiedene Rollenbeschreibungen im Wissensmanagement erhoben und sowohl hinsichtlich ihrer Bezeichnungen und Zuständigkeiten als auch im Hinblick auf ihre jeweiligen Aufgabenbereiche und damit einhergehend auch Kompetenzen und Verantwortlichkeiten analysiert. • Im Fokus des vorliegenden Beitrags stehen insbesondere die Aufgaben der Rolle des  Wissensingenieurs und die an diese Rolle gestellten Anforderungen.
Keywords: Wissensingenieur; Wissensarbeiter; Wissensmanagement; Berufsbild

Wear Mechanism of Superhard Tetrahedral Amorphous Carbon (ta-C) Coatings for Biomedical Applications - Rothammer, Benedict; Schwendner, Michael; Bartz, Marcel; Wartzack, Sandro; Böhm, Thomas; Krauß, Sebastian; Merle, Benoit; Schroeder, Stefan; Uhler, Maximilian; Kretzer, J. P.; Weihnacht, Volker; Marian, Max (Advanced Materials Interfaces, 2023)
Tetrahedral amorphous carbon (ta-C) coatings have the potential to protect biomedical implants from wear and increase their service life. This study elucidates the biocompatibility, mechanical properties, adhesion, and wear resistance of ta-C coatings fabricated by physical vapor deposition on cobalt-chromium-molybdenum (CoCr) and titanium (Ti64) alloys as well as ultrahigh molecular weight polyethylene (UHMWPE). Satisfactory cytocompatibility is verified using contact angle and surface tension measurements as well as indirect and direct cell testing. Scratch testing demonstrates excellent adhesion to the substrates and as confirmed by nanoindentation, the coatings represent an up to 13-fold and 182-fold increase in hardness on the hard and soft materials. In metal pin-on-UHMWPE disk sliding experiments under simulated body fluid lubrication, the wear rates of the disk are reduced by 48% (against CoCr) and 73% (against Ti64) while the pin wear rates are reduced by factors of 20 (CoCr) and 116 (Ti64) compared to uncoated pairings. From optical and laser scanning microscopy, Raman measurements, and particle analyses, it is shown that the underlying substrates remain well protected. Nonetheless, focused ion beam scanning electron microscopy revealed coating process-related and thermally driven subductions as well as tribologically induced near-surface fatigue, which can potentially constitute critical wear mechanism
Keywords: biotribology; diamond-like carbon; physical vapor deposition coatings; synovial joint; total knee replacements; wear-resistance

Wear Modeling of non-conformal Rolling Contacts subjected to Boundary and Mixed Lubrication - Winkler, Andreas; Bartz, Marcel; Wartzack, Sandro (23rd International Colloquium Tribology 2022, 2022)
Keywords: Verschleißsimulation; Mischreibung; Grenzreibung; Wälzlager

Web-Based Assessment of CAD Data in Undergraduate Design Education - Krüger, Daniel; Wartzack, Sandro (ASME 2014 12th Biennial Conference on Engineering Systems Design and Analysis Volume 1: Applied Mechanics; Automotive Systems; Biomedical Biotechnology Engineering; Computational Mechanics; Design; Digital Manufacturing; Education; Marine and Aerospace Applications, 2014)
In this contribution a web-based assessment framework for CAD data is proposed which has been developed based on the experience the authors made giving undergraduate courses at a German university. The framework is the backbone of a hybrid teaching concept combining conventional classroom lessons with e-learning elements. In-between the classroom lessons the students receive instructions on a particular modeling task via a web-interface. The same interface is used to hand in solutions in form of CAD files. Teachers who need to assess these solutions are supported by a semi-automated analysis of the CAD geometry. An algorithm compares each solution with a reference solution in order to reveal typical modeling mistakes. After the assessment is completed the students receive a feedback on their work. A case study on the application of the teaching concept in a course with 691 participants held during summer term 2013 reveals the positive experience the authors made using the system and points to some issues that need to be improved in the future.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.webbas
Keywords: Computer-aided design; Design education; E-assessment; Elearning; Virtual product development

Weight and cost reduction of the thermal management for traction batteries by using the DSM methodology - Luft, Thomas; Klein, Florian; Wartzack, Sandro (Proceedings of the DESIGN 2014, 2014)
This paper provides a methodology to reduce weight and costs of thermal management systems for traction batteries in vehicles by using value engineering approaches and a matrix-based product description. This allows product developers to analyze and to improve the complex dependencies and relationships between all requirements, functions, properties and characteristics of the product as well as the respective associated costs and weights. This methodology is used and validated in the contribution for a simplified sealing plate of one cell module.
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.FT-KLMEFK.weight
Keywords: design optimization; matrix-based product description; DSM; lightweight design; cost reduction; decision making

Welches Wissensmanagement-System passt zum Unternehmen? - Luft, Thomas; Frey, Dennis; Wartzack, Sandro (Wissensmanagement - Magazin für Führungskräfte, 2014)
• Die Software für einen effizienten Umgang mit Wissen muss auf die Organisation zugeschnitten sein. • Ein Evaluationsprozess zur Auswahl eines geeigneten Wissensmanagementsystems (WMS) erleichtert die Entscheidungsfindung. • Ein WMS muss gewisse funktionale Anforderungen erfüllen, um organisatorisches Lernen und organisatorische Effektivität zu gewährleisten.
Keywords: IT-Systeme; IT-Tools; Software-Auswahl

What does Design for Production mean? – From Design Guidelines to Self-learning Engineering Workbenches - Wartzack, Sandro; Sauer, Christopher; Küstner, Christof (Proceedings of the 11th International Workshop on Integrated Design Engineering, 2017)
Today, product developers are highly interested in designing and assembling lightweight parts, which subsequently leads to the development of new manufacturing technologies. In order to evaluate their designs, product developers depend on manufacturing knowledge. In the last decades the manufacturing knowledge has been shared as design guidelines. But, there are no guidelines for new manufacturing technologies. To face this challenge, we started with a mathematical description of the product’s properties (metamodels) by means of data mining methods. The data has been acquired by scientists for manufacturing technologies in experimental and numerical parameter studies. We utilized the metamodels in a knowledge-based design synthesis, which is based on evolutionary multi-objective optimization. Finally, we present an answer to the question of what “Design for Production” in context of new manufacturing technologies really means.
Keywords: design for X; self-learning; data mining; Pareto-optimal design

What’s more important for product design – usability or emotionality? An examination of influencing factors - Buker, Tina; Schmitt, Teresa; Miehling, Jörg; Wartzack, Sandro (Journal of Engineering Design, 2022)
Usability and emotionality are fundamental aspects of user experience. However, the actual creation of an equally usable and emotionally appealing product design is still challenging for product developers, not least because of competing objectives during such equal consideration of both aspects. In order to make a user-oriented decision between a more usable or more emotional product design, product developers need a profound understanding of what matters to the user in different usage situations. By conducting 22 semistructured interviews, we contribute to this aim by identifying and examining factors that influence a user’s perceived importance of usability and emotionality in product design. In total, 29 influencing factors were identified with the purpose of use, the type of product and other people’s attitudes towards a product being most relevant or both emotionality and usability. Nine influencing factors from the literature were additionally examined in terms of their strength and direction in which they influence the importance of emotionality and usability. Hereby, considerable differences within individual expressions of the influencing factors were revealed. Furthermore, the perceived importance of emotionality varied much more than that of usability.<br
Keywords: Usability; emotional design; user experience; user-centred design; interview

What the Statistics Tell Us—How to Use Empiric Data in Design for Emotional Impressions - Kett, Susan; Schmitt, Benedikt; Wartzack, Sandro (Research into Design for Communities, Volume 2, 2017)
Looking at technical consumer products like communication devices or pc accessory, we state high saturated markets in developed societies. This leads to a broad range of market offers not only in performance or financial aspects. The users seek for more individual products that differentiate on a subsequent, more qualitative level. User centered design approaches have been developed to handle the resulting high product variety and to keep them economically efficient. E.g., Universal Design supports the development of products for as many persons as possible, also including those with physiological or cognitive deficits. But to really raise the quality of life we also need to take other needs into account. Maslow’s hierarchy of needs states that with the fulfilment of physical needs the level shifts to psychological demands like emotional or attitudinal satisfaction. We will shortly introduce a framework that supports an emotional design optimization based on interdisciplinary findings (e.g. psychology, market research or Kansei Engineering) and statistical data analysis. For a valid forecasting, robust and transparent mathematical treatment of this data is required. To this, we give a first overview of possible approaches and their potential to ensure robust and transparent mathematical data treatment in design for emotional impressions.
Keywords: Emotional engineering; Kansei engineering; User segmentation

Wissensbasierte Navigation für die lärmreduzierte Auslegung rotierender Maschinen in der Produktentwicklung - Küstner, Christof; Wartzack, Sandro (Design for X - Beiträge zum 25. DfX-Symposium, 2014)
Today, product developer face the challenge taking not only the requirements for mechanical properties of a product into account, but also other requirements like the acoustical properties, for instance. The problem is that important product properties like the acoustical properties are only revealed in the later development phases. Normally product developers elicit knowledge from experts to fulfil these additional requirements. In this contribution, an approach for a knowledge-based navigation for the development of noise-reduced machines is presented. Therefore the knowledge identification, acquisition, formalization and the implementation in an assistant system are described. This approach contributes to the improvement of knowledge transfer from expert to product developer vice versa.
UnivIS-Import:2015-10-26:Pub.2014.tech.FT.FT-KLMEFK.wissen
Keywords: knowledge-based navigation; assistant system; noise-reduced development; activities and decisions

Wissensbasierter Aufbau konstruktionsbegleitender Finite-Elemente-Analysen durch ein FEA-Assistenzsystem - Kestel, Philipp; Wartzack, Sandro (Entwerfen Entwickeln Erleben – Beiträge zu virtuellen Produktentwicklung und Konstruktionstechnik, 2016)
Finite-Elemente-Analyse (FEA) gewinnen in der Produktentwicklung zunehmend an Bedeutung.Für eine effiziente Nutzung der FEA muss diese jedoch frühzeitig in der Produktentwicklung angewendet werden. Darüber hinaus wird für einen erfolgreichen Einsatz umfangreiches Expertenwissen vorausgesetzt. Dieses Wissen konzentriert sich in den Unternehmen hauptsächlich auf erfahrene Berechnungsingenieure, die aufgrund zeitlicher Engpässe Simulationen meist nur zur Nachrechnung bereits ausdetaillierter Produktmodelle durchführen.Konstruktionsbegleitende Simulationen werden hingegen zu selten eingesetzt oder sind nicht aussagekräftig genug, wenn diese nicht von Berechnungsexperten erstellt werden. Vor diesem Hintergrund wir ein FEA-Assistenzsystem entwickelt, durch das weniger erfahrener Simulationsanwender, wie Konstruktionsingenieure, unterstützt und die Erstellung aussagekräftiger, strukturmechanischer Simulationen automatisiert wird.

Wissensbasierte und berechnungsunterstützte Konzeptabsicherung in den frühen Phasen der Produktentwicklung am Beispiel des Elektromotors - Tüchsen, Johann; Richter, Michael; Heydenreich, Johannes; Koch, Matthias; Schleich, Benjamin; Wartzack, Sandro (2018)
In order to prevent costs and unneeded effort in product development, design verifications in early development phases are used to identify non-suitable designs and errors. Therefore, this contribution proposes a concept for a completely automated design check based on simplified one-dimensional calculations including knowledge-based correction factors optimized for electric drives. Using knowledge-based systems (KBS) structure in combination with compiled template computer scripts, a very fast and multidisciplinary solution is given to evaluate the suitability of the created solution regarding the requirements. Additionally this concept is expandable for additional modules or motors and easy to maintai
Keywords: Konzeptabsicherung; Knowledge-based Systems; KBS; analytische Modelle

Zur Notwendigkeit eines konstruktionsmethodischen Ansatzes für die zeitfeste Auslegung endlosfaserverstärkter Kunststoffbauteile - Hartwich, Tobias S.; Völkl, Harald; Franz, Michael; Witzgall, Christian; Krause, Dieter; Wartzack, Sandro (Design for X - Beiträge zum 30. DfX-Symposium, 2019)
Efficient and systematic design methods are indispensable aids on the way to effective lightweight solutions. In this article, the necessity of providing the product developer with a design method for the design of endless fibre-rein-forced plastic (FRP) components to fulfil fatigue requirements is highlighted. Existing damage models and test methods could be used and extended within such approaches. A suitable method should take into account particularly the variety of requirements for FRP components and consider other influences, e.g. from multi-layer composite design or load introduction, preferably sup-ported by CAE tools. The simple applicability of an effective approach should be demonstrated both on test specimens and on demonstrator components.<br
Keywords: Lightweight Design; Fibre-reinforced plastics; Fatigue; Design methods

Zustandsdiagnose von Maschinen im Kontext von Industrie 4.0 unter Einsatz von Data-Mining Methoden - Küstner, Christof; Mitsch, Jürgen; Hegwein, Matthias; Meintker, Nico; Mönks, Konrad; Fröhlich, Moritz; Wartzack, Sandro (Design for X - Beiträge zum 27. DfX-Symposium, 2016)
Today, the machine industry offers a range of After-Sales-Services, including the installation and commissioning of the purchased products, the provision of spare parts, inspections or comprehensive maintenance contracts. Studies prove that After-Sales-Services often generate revenues that are several times higher than the original purchase price, which is why these services significantly contribute to a company's balance sheet. Worldwide operation of machines could lead to long machine downtimes before service technicians reach the operating site. Therefore, companies are interested in machine prognostics and predictive maintenance techniques. To accomplish this, an approach for condition-based maintenance in context of the internet of things and the use of data mining is presented in this contribution.
Keywords: condition-based maintenance; machine prognostics; internet of things; data mining

転がり軸受部品における圧縮残留応力とその寿命に及ぼす影響の計算と実験的研究 (Deutsch: Rechnerische und experimentelle Untersuchung des Einflusses von Druckeigenspannungen in Wälzlagerkomponenten und deren Auswirkung auf die Lebensdauer) - Pabst, Alexander; Tremmel, Stephan; Wartzack, Sandro (Machine design, 2018)
Reibungsreduzierung und Leistungsverdichtung im Antriebsstrang von Fahrzeugen stellen einen aktiven beitrag zur CO2-Reduzierung dar. In der konsequenten Optimierung und Verwendung von reibungsarmen Wälzlagern im Antriebsstrang besteht ein großes Potential zur Effizienzsteigerung. Eine weitere Möglichkeit stellt das Downsizing von Wälzlagern dar. Aus dem Einsatz von kleineren und leichteren Wälzlagern resultieren im Anwendungsfall geringere Verlustleistungen. Es ist jedoch zu berücksichtigen, dass gleichzeitig die Tragfähigkeit des Lagers reduziert wird. Aus diesem Grund ist für eine reibungsreduzierte Ausführung die Steigerung der Ermüdungslebensdauer durch zusätzliche Werkstoff-, Wärmebehandlungs- oder Bearbeitungsmaßnahmen notwendig. Basierend auf diesem Ansatz setzt sich dieser Beitrag mit gezielt eingebrachten Druckeigenspannungen im wälzbeanspruchten Werkstoffbereich von Wälzlagerkomponenten zur Lebensdauersteigerung, am Beispiel von Planetenbolzen, auseinander. Es werden Ergebnisse aus Wälzlagerlebensdauerversuchen unter dem Einfluss von Druckeigenspannungen und den damit verbundenen Lebensdauersteigerungen präsentiert. Begleitend dazu werden die herstellseitig eingebrachten Druckeigenspannungen mit Hilfe einer Variante der Schubspannungsintensitätshypothese und durch Lebensdauermodelle rechnerisch bewertet. Das Ziel ist die Berücksichtigung solcher Eigenspannungen bei der Auslegung von Wälzlagern für unterschiedliche Anwendungsfälle
Keywords: Wälzlager; Druckeigenspannung; Verfestigung; Lebensdauer; Ermüdung